2D analysis of polydisperse core-shell nanoparticles using analytical ultracentrifugation - Walter, Johannes; Gorbet, Gary; Akdas, Tugce; Segets, Doris; Demeler, Borries; Peukert, Wolfgang (Analyst, 2017)
Accurate knowledge of the size, density and composition of nanoparticles (NPs) is of major importance for their applications. In this work the hydrodynamic characterization of polydisperse core-shell NPs by means of analytical ultracentrifugation (AUC) is addressed. AUC is one of the most accurate techniques for the characterization of NPs in the liquid phase because it can resolve particle size distributions (PSDs) with unrivaled resolution and detail. Small NPs have to be considered as core-shell systems when dispersed in a liquid since a solvation layer and a stabilizer shell will significantly contribute to the particle's hydrodynamic diameter and effective density. AUC measures the sedimentation and diffusion transport of the analytes, which are affected by the core-shell compositional properties. This work demonstrates that polydisperse and thus widely distributed NPs pose significant challenges for current state-of-the-art data evaluation methods. The existing methods either have insufficient resolution or do not correctly reproduce the core-shell properties. First, we investigate the performance of different data evaluation models by means of simulated data. Then, we propose a new methodology to address the core-shell properties of NPs. This method is based on the parametrically constrained spectrum analysis and offers complete access to the size and effective density of polydisperse NPs. Our study is complemented using experimental data derived for ZnO and CuInS NPs, which do not have a monodisperse PSD. For the first time, the size and effective density of such structures could be resolved with high resolution by means of a two-dimensional AUC analysis approac
Keywords: nanoparticles; centrifugation; resolution; core-shell; ZnO; analysis

2-photon fluorescence of quantum dots for investigations of nanoparticle formation and growth - Dinkel, Rebecca; Braunschweig, Björn; Peukert, Wolfgang (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2016)

A biphasic batch and continuous flow synthesis of hydrophobic gold and silver nanoparticles - Distaso, Monica; Peukert, Wolfgang (Reaction Chemistry & Engineering, 2023)
Plasmonic nanoparticles functionalized with hydrophobic ligands are required for several applications in flexible electronic, sensors and memory devices for their dispersability in polymeric matrices. In the current paper, we report a method for the batch and continuous synthesis of gold and silver nanoparticles (NPs) functionalized with oleylamine and oleic acid following a modified Brust-Schiffrin method. The role of key components of the reaction mixture in the phase transfer step is unravelled via(1)H and C-13 nuclear magnetic resonance (H-1 and C-13 NMR) spectroscopy. Gold and silver nanoparticles are characterized by Transmission and Scanning Electron Microscopy (TEM, SEM), Scanning TEM in High Angle Annular Dark Field mode (STEM-HAADF) coupled with X-ray Spectroscopy (STEM-EDX) analysis and UV-vis spectroscopy. Based on the findings for the synthesis in batch mode, we demonstrate the feasibility of the continuous flow synthesis for both gold and silver systems.
CRIS-Team WoS Importer:2023-06-02

Abrasion-Induced Acceleration of Melt Crystallisation of Wet Comminuted Polybutylene Terephthalate (PBT) - Tischer, Florentin; Düsenberg, Björn; Gräser, Timo; Kaschta, Joachim; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2022)
Within this contribution, the effect of grinding media wear on the melt crystallisation of polybutylene terephthalate (PBT) is addressed. PBT was wet ground in a stirred media mill in ethanol using different grinding media beads (silica, chrome steel, cerium-stabilised and yttrium-stabilised zirconia) at comparable stress energies with the intention to use the obtained particles as feed materials for the production of feedstocks for laser powder bed fusion additive manufacturing (PBF-AM). In PBF‑AM, the feedstock’s optical, rheological and especially thermal properties—including melt crystallisation kinetics—strongly influence the processability and properties of the manufactured parts. The influence of process parameters and used grinding media during wet comminution on the optical properties, crystal structure, molar mass distribution, inorganic content (wear) and thermal properties of the obtained powders is discussed. A grinding media-dependent acceleration of the melt crystallisation could be attributed to wear particles serving as nuclei for heterogeneous crystallisation. Yttrium-stabilised zirconia grinding beads proved to be the most suitable for the production of polymer powders for the PBF process in terms of (fast) comminution kinetics, unchanged optical properties and the least accelerated crystallisation kinetics.<br
Keywords: wet comminution; stirred media mills; abrasion; polymer; additive manufacturing; powder bed fusion; thermal properties; isothermal DSC

Accelerated grain refinement during accumulative roll bonding by nanoparticle reinforcement - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Scripta Materialia, 2011)
Ceramic nanoparticles produced by comminution are introduced homogeneously during accumulative roll bonding (ARB) in aluminium AA1050A by airgun spraying from a stabilized aqueous suspension. In the so-produced nanoparticle-reinforced ultrafine-grained material, acceleration of microstructural evolution during the early ARB cycles as well as reduced grain sizes at higher cycles are observed, both caused by additional local straining around the embedded nanoparticles and accompanied by further strengthening. The presented method of nanoparticle application allows homogeneous as well as graded particle distributio

A Combined SAXS/SANS Study for the in Situ Characterization of Ligand Shells on Small Nanoparticles: The Case of ZnO - Schindler, Torben; Schmiele, Martin; Schmutzler, Tilo; Kassar, Thaer; Segets, Doris; Peukert, Wolfgang; Radulescu, Aurel; Kriele, Armin; Gilles, Ralph; Unruh, Tobias (Langmuir, 2015)
ZnO nanoparticles (NPs) have great potential for their use in, e.g., thin film solar cells due to their electro-optical properties adjustable on the nanoscale. Therefore, the production of well-defined NPs is of major interest. For a targeted production process, the knowledge of the stabilization layer of the NPs during and after their formation is of particular importance. For the study of the stabilizer layer of ZnO NPs prepared in a wet chemical synthesis from zinc acetate, only ex situ studies have been performed so far. An acetate layer bound to the surface of the dried NPs was found; however, an in situ study which addresses the stabilizing layer surrounding the NPs in a native dispersion was missing. By the combination of small angle scattering with neutrons and X-rays (SANS and SAXS) for the same sample, we are now able to observe the acetate shell in situ for the first time. In addition, the changes of this shell could be followed during the ripening process for different temperatures. With increasing size of the ZnO core (dcore) the surrounding shell (dshell) becomes larger, and the acetate concentration within the shell is reduced. For all samples, the shell thickness was found to be larger than the maximum extension of an acetate molecule with acetate concentrations within the shell below 50 vol %. Thus, there is not a monolayer of acetate molecules that covers the NPs but rather a swollen shell of acetate ions. This shell is assumed to hinder the growth of the NPs to larger macrostructures. In addition, we found that the partition coefficient μ between acetate in the shell surrounding the NPs and the total amount of acetate in the solution is about 10% which is in good agreement with ex situ data determined by thermogravimetric analysis.
Keywords: nanoparticle; solar; cell; electroptical; property

A Comprehensive Brownian Dynamics Approach for the Determination of Non-ideality Parameters from Analytical Ultracentrifugation - Uttinger, Maximilian; Wawra, Simon; Guckeisen, Tobias; Walter, Johannes; Bear, Andreas; Thajudeen, Thaseem; Sherwood, Peter J.; Smith, Ana-Suncana; Wagemans, Anja M.; Stafford, Walter F.; Peukert, Wolfgang (Langmuir, 2019)
Brownian dynamics (BD) has been applied as a comprehensive tool to model sedimentation and diffusion of nanoparticles in analytical ultracentrifugation (AUC) experiments. In this article, we extend the BD algorithm by considering space-dependent diffusion and solvent compressibility. With this, the changes in the sedimentation and diffusion coefficient from altered solvent properties at increased pressures are accurately taken into account. Moreover, it is demonstrated how the concept of space-dependent diffusion is employed to describe concentration-dependent sedimentation and diffusion coefficients, in particular, through the Gralen coefficient and the second virial coefficient. The influence of thermodynamic nonideality on diffusional properties can be accurately simulated and agree with well-known evaluation tools. BD simulations for sedimentation equilibrium and sedimentation velocity (SV) AUC experiments including effects of hydrodynamic and thermodynamic nonideality are validated by global evaluation in SEDANAL. The interplay of solvent compressibility and retrieved nonideality parameters can be studied utilizing BD. Finally, the second virial coefficient is determined for lysozyme from SV AUC experiments and BD simulations and compared to membrane osmometry. These results are in line with DLVO theory. In summary, BD simulations are established for the validation of nonideal sedimentation in AUC providing a sound basis for the evaluation of complex interactions even in polydisperse systems.
CRIS-Team Scopus Importer:2019-09-17

A Comprehensive Brownian Dynamics-Based Forward Model for Analytical (Ultra)Centrifugation - Thajudeen, Thaseem; Walter, Johannes; Uttinger, Maximilian; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2017)
In this study, it is demonstrated how Brownian dynamics (BD) simulations can be used as a comprehensive forward model for analytical ultracentrifugation (AUC) and analytical centrifugation experiments. BD simulations are a versatile alternative to the numerical solution of Lamm's equation. Time dependent concentration profiles can be accurately predicted by means of the BD simulations even for colloidal systems with multiple species. It is shown that in combination with Mie's theory for light scattering, BD simulations can be extended to generate data mimicking a multiwavelength detector for AUC. The forward model can be utilized as a comprehensive tool for developing and testing sophisticated data analyzing tools that can enhance the capabilities of using centrifugation-based techniques for characterizing nanoparticles. The model is validated using common analysis tools developed for the evaluation of sedimentation velocity data generated by a single wavelength extinction detector. The accuracy of the code is also proved using the recently developed and highly versatile High Dynamic Range-MULTIwavelength FITting tool for accurately predicting particle size distributions via gravitational sweep experiments performed in AUCs equipped with multiwavelength detectors.
Keywords: Brownian dynamics; analytical ultracentrifugation; Mie scattering; extinction coefficient; multiwavelength detectors

A comprehensive methodology to study double emulsion stability - Leister, Nico; Götz, Vanessa; Bachmann, Stephan Jan; Nachtigall, Stephanie; Hosseinpour, Saman; Peukert, Wolfgang; Karbstein, Heike (Journal of Colloid and Interface Science, 2022)
The stability of emulsions requires the fast formation of viscoelastic interfaces between water and oil phases. In double emulsions, two surfactant types (hydrophilic and lipophilic) are present and two interfacial films are involved. Understanding cooperative adsorption of these surfactants and its implication on properties of water/oil/water interfacial films will enable replacing the empirical methodologies used in designing double emulsion systems with a knowledge-based approach. The distribution of surfactants between the water/oil interfaces was investigated using single droplet diffusion experiments and simulation of equilibrium surfactant density profiles. The stability of the interfaces against coalescence was characterized by dye transport in a leach cell and coalescence time of single droplets in a model experiment. The conformation of the surfactants at an interface was then examined via surface rheology, sum frequency generation spectroscopy, and dissipative particle dynamics simulation. Two selected hydrophilic surfactants combined with a lipophilic surfactant induce very different properties at water/oil interfaces and different dye release behaviour from their corresponding double emulsions. Competitive adsorption of sodium dodecyl sulfate and lipophilic surfactant results in the improvement of encapsulation efficiency, elasticity of the interface, and resistance against coalescence due to the intercalation of surfactant alkyl chains into the oil chains.
Keywords: Coalescence; Diffusion; Double emulsions; Stability; Surfactants

A comprehensive study on the mechanism behind formation and depletion of Cu2ZnSnS4 (CZTS) phases - Ahmad, Rameez; Brandl, Marco; Distaso, Monica; Herre, Patrick; Spiecker, Erdmann; Hock, Rainer; Peukert, Wolfgang (Crystengcomm, 2015)
High efficiency kesterite based solar cells have vigorously raised the research interests in this material. The challenge lies in understanding the formation and co-existence of more than 10 possible by-products during and after the synthesis of Cu2ZnSnS4 (CZTS) and their various different structural and electronic defects. The present contribution shows an in-depth study on the stages of formation and depletion of nanoparticulate CZTS. Employing a hot injection synthesis method, we give direct experimental evidence of the co-existence of cubic, tetragonal and defected CZTS structures and different by-products as a function of time and temperature. SEM, (HR) TEM, XRD, EDX, ICP-OES, Raman spectroscopy and UV-Vis-NIR spectroscopy have been used in order to better evaluate and interpret data for crystal structures and compositions. The obtained understanding on the formation of different phases suggests 250 degrees C as the most favourable synthesis temperature. Based on our study, general strategies can be developed for controlling the amount of formed phases, the by-products and the defects in kesterite and other similar multicomponent nanoparticles as well as in bulk systems.

Adhesion forces of spherical alumina particles on ceramic substrates - Peukert, Wolfgang; Götzinger, Martin (Journal of Adhesion, 2004)
Adhesion forces of spherical alumina particles on ceramic substrates were studied. Results of direct force measurements using an atomic force microscope (AFM) were compared with theoretical results of a new rod model and with molecular dynamic computer simulation. Spherical alumina particles were produced by a flame process. The particles were glued to cantilevers, and interaction forces were measured by the AFM. A significant reduction of adhesion forces due to adsorbed layers was observed. The interaction volumes were determined by AFM scanning using a soft cantilever. The measured interaction forces were compared with calculated forces using the Hamaker concept including an adsorbed surface layer and the determined interaction volume (rod model). It turned out that calculated adhesion forces, neglecting deformation, are smaller than measured ones. This problem can be overcome if deformation according to Hertz is included in the rod model. Even for such a hard material as alumina, deformation occurs in the contact zone, which was also observed in a molecular dynamic computer simulatio
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.adhesi
Keywords: Alumina; Molecular dynamics; Particle adhesion; Roughness

Adhesive force distribution of rough adhesive systems for the example of a ball-plate system - Peukert, Wolfgang; Götzinger, Martin (Chemie Ingenieur Technik, 2003)

Adipogenic, chondrogenic, osteogenic, and antimicrobial features of glass ceramic material supplemented with manganese - Rau, Julietta V.; De Stefanis, Adriana; Barbaro, Katia; Fosca, Marco; Yankova, Viktoriya G.; Matassa, Roberto; Nottola, Stefania Annarita; Nawaz, Qaisar; Ali, Muhammad Saad; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Non-Crystalline Solids, 2021)
Innovative Mn-containing glass ceramic (Na2O[2.00]-K2O[0.09]-MgO[3.10]-MnO[2.07]-CaO[38.78]-CaF2[2.25]-P2O5[9.66]-SiO2[41.71] [wt%]) was obtained by sol-gel. It was investigated by High Resolution Field Emission Scanning Electron Microscopy, Energy Dispersive X-Ray Spectroscopy, X-Ray fluorescence, X-Ray Diffraction, and Fourier Transform Infrared Spectroscopy. Ion release characteristics of the glass ceramic powder were quantified via Inductively Coupled Plasma Optical Emission Spectroscopy. Biological tests were performed using equine adipose tissue mesenchymal stem cells (AMSCs). MTT assay demonstrated the cytocompatibility of the prepared material. AMSCs differentiation test showed that the glass ceramic favored the stem cell differentiation in adipogenic, chondrogenic, and osteogenic lineages, the last one being qualitatively more pronounced. The antimicrobial properties were evaluated against Escherichia coli, Enterococcus faecalis, Pseudomonas aeruginosa, Salmonella typhi, and Staphylococcus aureus bacteria strains and Candida albicans fungus. The inhibition of Gram-negative bacteria (S. tiphy, E. coli), Gram-positive (E. faecalis) and fungus (C. albicans) was detected, while the inhibition of P. aeruginosa and S. aureus was not significant.
CRIS-Team Scopus Importer:2021-02-19
Keywords: antimicrobial; bioactive glass; glass ceramic; manganese; osteogenic

Adsorption isotherms and irreversible binding of proteins on commercially available hydrophobic adsorbents - Millitzer, Marcus; Wenzig, Edda; Peukert, Wolfgang (Chemical Engineering & Technology, 2005)
Quantitative data about the behavior of proteins in different downstream processing unit operations are needed. Adsorption isotherms that are usually used to design such process steps may not be sufficient as for protein binding there is to distinguish between an adsorbing and a desorbing branch of the isotherm, leading to different apparent adsorption coefcients for adsorption and desorption, respectively. It is demonstrated that two different proteins show simultaneously reversible as well as irreversible ”adsorption” in hydrophobic interaction protein chromatography and that the reversible and the irreversible part of the apparent ”adsorption” isotherm can be separated.
Keywords: Adsorption isotherm; Protein

Adsorption of CTAB on Sapphire- c at High pH: Surface and Zeta Potential Measurements Combined with Sum-Frequency and Second-Harmonic Generation. - Abdelmonem, Ahmed; Zhang, Yingchun; Braunschweig, Björn; Glikman, Dana; Rumpel, Armin; Peukert, Wolfgang; Begovic, Tajana; Liu, Xiandong; Lützenkirchen, Johannes (Langmuir, 2022)
The adsorption of cetyltrimethylammonium bromide (CTA+Br-) on sapphire-c surfaces was studied at pH 10 below the surfactants' critical micelle concentration. The evolution of interfacial potentials as a function of CTAB concentration was characterized by surface and zeta potential measurements and complemented by molecular dynamic (MD) simulations as well as by second-harmonic (SHG) and vibrational sum-frequency generation (SFG) spectroscopy. The changes in interfacial potentials suggest that the negative interfacial charge due to deprotonated surface aluminols groups is neutralized and can be even overcompensated by the presence of CTA+ cations at the interface. However, SFG intensities from strongly hydrogen-bonded interfacial water molecules as well as SHG intensities decrease with both increasing CTAB concentration and the magnitude of the surface potential. They do not suggest a charge reversal at the interface, while the change in zeta potential is actually consistent with an apparent charge inversion. This can be qualitatively explained by results from MD simulation, which reveal adsorbed CTA+ cations outside a first strongly bound hydration layer of water molecules, where they can locally distort the structural order and replace some of the interfacial water molecules adjacent to the first layer. This is proposed to be the origin for the significant loss in SFG and SHG intensities with increasing CTAB concentration. Moreover, we propose that CTA+ can act as a counterion and enhance the occurrence of deprotonated surface aluminols that is consistent with the decrease in surface potential.

Advanced Multiwavelength Detection in Analytical Ultracentrifugation - Pearson, Joseph; Walter, Johannes; Peukert, Wolfgang; Coelfen, Helmut (Analytical Chemistry, 2018)

Advanced processes for better materials-tape casting from nanoparticles - Peukert, Wolfgang; Knieke, Catharina; Vozdecky, Pavel; Roosen, Andreas (Chemie Ingenieur Technik, 2011)
It is shown by the example of a ceramic tape casting process, how advances in the field of process engineering lead to improved material properties. One great advance is the possibility of producing nanoparticles in stirred media mills. The nano-sized particle suspensions can be directly processed to ceramic tapes. The processing of nanoparticles requires specifically adjusted process conditions, but leads to a drastic improvement of the final product properties. Hence, dense and crack-free ceramic tapes with a higher mechanical strength, a lower surface roughness and a translucent character compared to tapes from micro-sized powders can be obtained. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Ceramic tapes; Nano-milling; Stirred media mill

Aerosol synthesis of germanium nanoparticles supported by external seeding: Theoretical and experimental analysis - Wergen, Lukas; Domaschke, Maximilian; Herre, Patrick; Wu, Mingjian; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Aerosol Science, 2019)

Aerosol synthesis of silicon nanoparticles with narrow size distribution-Part 1: Experimental investigations - Körmer, Richard; Jank, Michael; Ryssel, Heiner; Schmid, Hans-Joachim; Peukert, Wolfgang (Journal of Aerosol Science, 2010)
A study on the feasibility of aerosol processing of nearly monodisperse silicon nanoparticles via pyrolysis of monosilane in a hot wall reactor is presented. For optimal conditions silicon nanoparticles with a geometric standard deviation of 1.06 were synthesized at a production rate of 0.7 g/h. The size of the particles could be precisely controlled in the range of 20–40 nm, whilst maintaining a geometric standard deviation in the range of 1.06–1.08, by proper choice of the governing parameters temperature, residence time and precursor concentration. The results show that narrow particle size distributions can only be obtained in the temperature range between 900 and 1100 °C, as long as both the initial silane concentration (1 mbar silane partial pressure) and the reactor total pressure are low (25 mbar). This regime for the production of narrow particle size distributions has not been identified in prior work on the thermal decomposition of silane. Narrowly distributed particles can be obtained under conditions where nucleation and particle growth are separated and the agglomeration rates are negligible.

Aerosol synthesis of silicon nanoparticles with narrow size distribution-Part 2: Theoretical analysis of the formation mechanism - Körmer, Richard; Schmid, Hans-Joachim; Peukert, Wolfgang (Journal of Aerosol Science, 2010)
This work investigates the mechanisms which lead to the formation of silicon nanoparticles with narrow size distributions by means of population balance modeling. The model accounts for the full aerosol process, including chemical reaction, nucleation from supersaturated vapor, growth and agglomeration. The results are in good agreement with experimental data. The effects of the process parameters temperature, silane concentration and reactor total pressure are systematically investigated. The simulation allows an in-depth insight into the particle formation mechanism and reveals the key requirements which are necessary for the generation of narrow particle size distributions. In this mechanism, only a short nucleation burst occurs, while surface growth plays the dominant role in silane precursor consumption. A key role is attributed to condensation, because the numerical calculations can only reflect the experimental observations, if the condensation mechanism is included in the model.

Ageing mechanism of gold and silver nanorods in aqueous solution - Segets, Doris; Damm, Cornelia; Vieweg, Benito; Yang, Guang; Spiecker, Erdmann; Peukert, Wolfgang (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites - 2010 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2010, 2010)
The current work addresses the understanding of the shape transformation of silver and gold nanorods towards more spherical nanostructures in aqueous suspension at ambient temperature. The shape transformation process was characterised using UV/Vis absorption spectroscopy, scanning electron microscopy (SEM), anodic stripping voltammetry and high resolution transmission electron microscopy (HRTEM). The increase in the particle number density during ageing indicates that the rods break spontaneously in smaller particles by surface defect induced ripening.
Keywords: Ageing; Gold nanorods; Optical characterization; Shape stability; Silver nanorods

A general approach for the characterization of fragmentation problems - Peukert, Wolfgang; Toneva, Petya Ivanova (Advanced Powder Technology, 2006)
A general approach for the quantitative and systematic characterization of fragmentation problems, which is based on the Weibull statistics, is presented. A model, initially developed for materials stressed under impact with respect to their breakage probability, has been successfully applied to the characterization of compressive comminution, fragmentation of nanoparticle agglomerates and destroying of adhesive bonds. The experimental results from the slow compression comminution and from the comminution by falling weight match for various materials and particle sizes exactly to the master curve deduced for impact comminution. However the material parameters determined for compression comminution are not identical for one and the same material to that determined by impact comminution. This indicates that the two model parameters are not pure material characteristics as assumed from the impact experiments but depend on the stress mechanism. The dependence of the fragmentation degree on the particle size and the energy input observed when impacting particles in the micrometer to millimetre range has been proven also for nanoparticle agglomerates. Furthermore a model analogical to that for breakage has been deduced for the quantification of the failure of adhesive bonds.
Keywords: Adhesion; Breakage probability; Fragmentation; Fragmentation degree; Modelling; Weibull statistics

A General Approach To Study the Thermodynamics of Ligand Adsorption to Colloidal Surfaces Demonstrated by Means of Catechols Binding to Zinc Oxide Quantum Dots - Lin, Wei; Walter, Johannes; Burger, Alexandra; Maid, Harald; Hirsch, Andreas; Peukert, Wolfgang; Segets, Doris (Chemistry of Materials, 2015)
A general strategy to study the thermodynamics of ligand adsorption to colloidal surfaces was established. The versatility of our approach is demonstrated by means of catechols binding to ZnO quantum dots (QDs). First, isothermal titration calorimetry (ITC) was used to extract all relevant thermodynamic parameters, namely association constant, enthalpy, entropy, and free energy of ligand binding. Noteworthy, the determined ΔG of −20.3 ± 0.4 kJ mol–1 indicates a strong, reproducible, and exothermic interaction between the catechol anchor group and the oxide particle surface. To confirm the characterization of ligand binding by measuring the heat of adsorption, the free energy was cross-validated by mass-based adsorption isotherms. A combination of inductively coupled plasma optical emission spectroscopy (ICP-OES) and UV/vis spectroscopy was developed to quantitatively determine the mass of bound catechols with respect to the available particle surface. The association constant K was determined by a Langmuir fit to be 2618 M–1 which leads to ΔG = −19.50 kJ mol–1 according to ΔG = −RTln K. To close the mass balance, analytical ultracentrifugation (AUC) was applied to detect the amount of the free, unbound catechol in solution. Finally, Raman spectroscopy and nuclear magnetic resonance spectroscopy (NMR) were performed to quantify the amount of remaining acetate from particle synthesis and to distinguish bound (chemisorbed) and unbound (physisorbed) catechol. Our results reveal that approximately 65 wt % of acetate is replaced, and physisorbed catechol will not affect the amount of remaining acetate on the ZnO surface. Moreover, no pronounced chemical shift peak as it would be expected for free catechol is observed by NMR at all. This indicates a highly dynamic adsorption–desorption equilibrium between the free and the physisorbed state of catechol on the particle surface. Our concept of combined analytics is seen to be a generally applicable strategy for particle-ligand interfacial studies. It gives detailed insight into thermodynamics, binding states, and ligand composition and is thus considered as an important step toward tailored colloidal surface properties.

Agglomeration and breakage of nanoparticles in stirred media mills - A comparison of different methods and models - Peukert, Wolfgang; Sommer, Marc; Stenger, Frank; Wagner, Norman (Chemical Engineering Science, 2006)
The increasing industrial demand for nanoparticles challenges the application of stirred media mills to grind in the sub-micron size range. It was shown recently [Mende et al., 2003. Mechanical production and stabilization of submicron particles in stirred media mills. Powder Technology 132, 64-73] that the grinding behavior of particles in the sub-micron size range in stirred media mills and the minimum achievable particle size is strongly influenced by the suspension stability and thus the agglomeration behavior of the suspension. Therefore, an appropriate modeling of the process must include a superposition of the two opposing processes in the mill i.e., breakage and agglomeration which can be done by means of population balance models. Modeling must now include the influence of colloidal surface forces and hydrodynamic forces on particle aggregation and breakup. The superposition of the population balance models for agglomeration and grinding with the appropriate kernels leads to a system of partial differential equations, which can be solved in various ways numerically. Here a modified h-p Galerkin algorithm which is implemented in the commercially available software package PARSIVAL developed by CiT (CiT GmbH, Rastede, Germany) and the moment methodology according to [Diemer and Olsen, 2002a. A moment methodology for coagulation and breakage problems: Part I - analytical solution of the steady-state population balance. Chemical Engineering Science 57 (12), 2193-2209; Diemer and Olsen, 2002b. A moment methodology for coagulation and breakage problems: Part II - moment models and distribution reconstruction. Chemical Engineering Science 57 (12), 2211-2288] are used and compared to explicit data on alumina. This includes a comparison of the derived particle size distributions, moments and its accuracy depending on the starting particle size distribution and the used agglomeration and breakage kernels. Finally, the computational effort of both methods in comparison to the prior mentioned parameters is evaluated in terms of practical application. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Agglomeration; Breakage; Modeling; Population balance model; Stirred media mill; Suspensions

A model-based precipitation study of copper-based catalysts - Peukert, Wolfgang; Hartig, Martin Andreas Johannes; Jacobsen, Nikolas; Leuthold, Alexander (AIChE Journal, 2015)
Numerical methods of particle technology are used to model the formation of catalyst precursors with the purpose to control disperse properties. A multicomponent and multiphase population balance model is applied to the precipitation of catalyst precursors in a T-mixer. Copper precursors are chosen to be investigated in detail as a basis for catalysts with a broad range of applications such as in methanol synthesis, water-gas shift and hydrogenation reactions. The simulations results could be validated by ex situ measurements such as the pH of the suspension, the solid dry weight of the precipitate, and the yield. Simulations show that dissociation reactions of copper and carbonate species in water control significantly the formation of Georgeite. Consumption of the copper component by solid formation can be controlled in a range of 20-100% by the adjustment of the pH of the copper nitrate reactant solution.
Keywords: Catalyst preparation; Methanol synthesis; Mixing; Population balance; Precursor chemistry

A model for the particle mass yield in the aerosol synthesis of ultrafine monometallic nanoparticles by spark ablation - Domaschke, Maximilian; Schmidt, Melanie; Peukert, Wolfgang (Journal of Aerosol Science, 2018)
Keywords: Nanoparticles; Scanning mobility particle sizer; Aerosol synthesis; Dimensional analysis; Spark ablation

A model for the particle mass yield in the aerosol synthesis of ultrafine monometallic nanoparticles by spark ablation - Domaschke, Maximilian; Schmidt, Melanie; Peukert, Wolfgang (Journal of Aerosol Science, 2018)
Keywords: Nanoparticles; Scanning mobility particle sizer; Aerosol synthesis; Dimensional analysis; Spark ablation

Amphiphilic invertible polyesters as reducing and stabilizing agents in the formation of metal nanoparticles - Kohut, Ananiy; Voronov, Andriy; Samaryk, Volodymyr; Peukert, Wolfgang (Macromolecular Rapid Communications, 2007)
Metal nanoparticles of various size and shape are prepared by the reduction of metal precursors in polymer micellar architectures (nanoreactors). The nanoreactors are developed from the amphiphilic invertible polyesters solved over a wide concentration range in solvents that strongly differ in polarity. In a non-polar medium, the micelle core contains hydrophilic [poly(ethylene oxide)] fragments, which acts as a reducing agent of metal ions. Nanoparticle stabilization occurs because of the presence of hydrophobic (polymethylene) fragments outside of the micelle structure. The size and shape of the nanoreactors may be altered by the polyester composition and molecular weight as well as by the solvent polarity and concentration of the amphiphilic polyester.
Keywords: amphiphilic polymers; invertibility; metals; nanoparticles; nanoreactors; synthesis

A multiwavelength emission detector for analytical ultracentrifugation - Wawra, Simon; Onishchukov, Georgy; Maranska, Maria; Eigler, Siegfried; Walter, Johannes; Peukert, Wolfgang (Nanoscale Advances, 2019)

An additive-free silicon anode in nanotube morphology as a model lithium ion battery material - Zhuo, Ying; Sun, Hong; Uddin, Md. Helal; Barr, Maissa; Wisser, Dorothea; Roßmann, Philip Kazys; Esper, Julian Duane; Tymek, Sarah; Döhler, Dirk; Peukert, Wolfgang; Hartmann, Martin; Bachmann, Julien (Electrochimica Acta, 2021)
Ordered arrays of parallel, cylindrical silicon nanotubes are obtained by aluminothermic reduction of SiO2 nanotubes generated by atomic layer deposition (ALD) on nanoporous aluminum oxide templates. The reduction to amorphous Si (a-Si) is characterized by a combination of X-ray diffraction (XRD), solid-state cross-polarization magic-angle spinning nuclear magnetic resonance (29Si CP-MAS NMR), ultraviolet-visible spectroscopy, attenuated total reflectance infrared spectroscopy (ATR-IR), and X-ray photoelectron spectroscopy (XPS). These a-Si nanotube arrays are electrochemically active in a lithium-ion battery environment when prepared on Cu current collectors without any additives. The absence of the traditional additive carbon black, which is an electrochemically inert conductor, increases the proportion of capacity associated with faradaic reactions (Li incorporation) with respect to the capacitive component. Electrochemical impedance spectroscopy (EIS) and charge-discharge tests demonstrate that the nanotube morphology yields an improved tolerance to fast cycling.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Aluminothermic reduction; Anode material; Atomic layer deposition; Lithium ion battery; Si nanotube

Analysis of bulk solids attrition in pneumatic conveying by distinguishing between process and material parameters - Peukert, Wolfgang; Frye, Lars (BHR Group Limited, 2004)
For the investigation of attrition, it is distinguished between process and material parameters. Therefore, attrition is regarded as a result of a process function determining the stress conditions the particles are subjected to and a material function summarizing the material specific response to these. The process function was determined by employing computational fluid dynamics (CFD) and by analyzing experimental results as well as discrete element simulations (DEM) carried out at Glasgow Caledonian University. The material function was determined by carrying out attrition experiments on varying scales and by measuring thermo-mechanical material properties with dynamic mechanical analysis (DMA).
Keywords: attrition; material; parameter; process; simulation

Analysis of optical absorbance spectra for the determination of ZnO nanoparticle size distribution, solubility, and surface energy - Segets, Doris; Gradl, Johannes; Klupp Taylor, Robin; Vassilev, Vassil; Peukert, Wolfgang (Acs Nano, 2009)
We present a model to calculate particle size distributions (PSDs) of colloidal ZnO nanoparticles from their absorbance spectra. Using literature values for the optical properties of bulk ZnO and correlating the measurement wavelengths in the UV−visible regime with distinct particle sizes by a tight binding model (TBM), an algorithm deconvolutes the absorbance spectra into contributions from size fractions. We find an excellent agreement between size distributions determined from TEM images and the calculated PSDs. For further validation, bimodal PSDs have been investigated and an approach to determine not only particle size but also solid concentration is introduced. We will show the applicability of our model by the determination of temperature-dependent ripening rates, which enables the calculation of solubilities, surface tensions, and the activation enthalpy of ripening. In principle, our methodology is applicable to different semiconductor nanoparticles in various solvents as long as their bulk properties are known and scattering is negligible.

Analysis of tribo-charging during powder spreading in selective laser sintering: Assessment of polyamide 12 powder ageing effects on charging behavior - Hesse, Nicolas; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lübbert, Christian; Roth, Stephan; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2019)
Powder flowability is key to achieving high process stability and part quality by application of smooth and dense layers in selective laser sintering (SLS). This study sheds light on the rarely investigated effect of tribo-electric charge build-up during powder delivery in the SLS process. This is achieved by a novel approach to quantify electrostatic potentials during doctor blading. The presented model setup is used in combination with charge spectrometry and impedance spectroscopy to investigate the alterations in tribo-electric charging behavior for the most commonly used laser sintering material polyamide 12 in its virgin and aged, c.f. reused, states. We show that the electrostatic charge build-up is significantly enhanced for aged polymer powder material, likely contributing to altered performance in SLS processing.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Additive manufacturing; Charge distribution; Electrostatics; Polyamide 12; Polymer ageing; Powder layer formation; Selective laser sintering; Surface potential; Tribo-charging

Analysis of ultrafine metal oxide particles in aerosols using mobility-resolved time-of-flight mass spectrometry - Domaschke, Maximilian; Lübbert, Christian; Peukert, Wolfgang (Journal of Aerosol Science, 2019)
In this work we present a powerful method to gain insight into the formation of inorganic nanoparticles from the gas phase by combining a high-resolution differential mobility analyzer with a time-of-flight mass spectrometer. Exemplary particles are generated by glowing-wire evaporation from tungsten, tantalum, rhenium, niobium and molybdenum and transferred via a new custom-made interface to the mobility classifier that is directly attached to the mass spectrometer. With only minor fragmentation occurring, clusters that represent early stages of particle formation from the gas phase can be detected. Regardless of the inert experimental conditions, only oxides were found for all tested precursor metals. Comparing the recorded mass-mobility data with theoretical predictions from a modified Mason-Schamp equation shows that produced materials possess densities smaller than those of the respective bulk materials. The maximum observed particle sizes were about 2 nm.
CRIS-Team Scopus Importer:2019-08-27
Keywords: Differential mobility analyzer; Glowing-wire evaporation; Multidimensional characterization; Nanoparticles; Time-of-flight mass spectrometry

An effective dialysis method for surface funtionalization of nanoparticles in liquid phase - Sample: Porphyrine derivatives @ ZnO-Nanorods - Klaumünzer, Martin; Münzel, C.; Burger, Alexandra; Mackovic, Mirza; Voigt, Michael; Spiecker, Erdmann; Hirsch, Andreas; Peukert, Wolfgang (Nanotechnology 2013: Advanced Materials, CNTs, Particles, Films and Composites - 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
In order to optimize electron transfer and optoelectronic properties in nanoparticulate thin films for electronics we show the surface functionalization of ZnO nanorods by exchanging the stabilizing 2-[2-(2-Mefhoxyefhoxy)-ethoxy] acetic acid at the ZnO surface with redoxactive organic molecules. Surface functionalization is undertaken by an efficient dialysis method. Emission- and absorption-spectroscopy indicate an effective electronic interaction between the ZnO nanorods and the pophyrine derivatives. In addition, we discuss on the binding mechanism and the ligand exchange kinetics of the porphyrine molecules. Our experiments suggest a better and faster binding to the ZnO nanorod surface for porphyrine A than for porphyrine B. This can be explained by steric effects. Moreover we claim a fourfold anchored binding for porphyrine A and we shed light on entropic effects during ligand exchange.

An effective way to stabilize colloidal particles dispersed in polar and nonpolar media - Peukert, Wolfgang; Kohut, Ananiy; Voronov, Andriy (Langmuir, 2006)
This article offers a new approach to building up self-adjustable invertible polymer coatings at solid surfaces. The approach is based on a two-step process. In the first step, the surface of dispersed TiO has been functionalized with the aid of toluene diisocyanate (TDI) as a coupling agent. In the second step, the chains of amphiphilic oligoester have been covalently grafted to the titanium dioxide surface functionalized with isocyanate groups. It is shown that the titania modified in this way can form stable suspensions in both polar (water) and nonpolar (toluene) media. Multiple redispersion cycles show the ability of the modified titanium dioxide particles, after their removal from one type of dispersion and consequent drying, to be redispersed in dispersing media strongly differing by polarity from the previous. © 2007 American Chemical Society.
Keywords: polymer; particle; coating; self-adjustible; functional

A new approach for the stabilization of amorphous drug nanoparticles during continuous antisolvent precipitation - Trzenschiok, Holger; Distaso, Monica; Peukert, Wolfgang (Chemical Engineering Journal, 2019)
In this study a stabilization approach for the bottom-up production of drug nanoparticles was established and demonstrated for four commonly used drugs. The nanoparticles were produced by liquid antisolvent precipitation utilizing in-house build static mixers. The influence of the mixing conditions on the final particle size distributions was studied by variation of the energy input during precipitation. Multivalent cations of a non-toxic metal can be used to achieve superior electrostatic stabilization of the precipitated nanoparticles. For zirconium salts used as stabilizers in particular, the dependency of the resulting particle size on the pH and the salt concentration in the antisolvent was investigated. Remarkably, our approach allows the continuous production of drug nanoparticles down to a few 10 nm in diameter. A simple method to analyze the particle composition based on FTIR spectra is proposed and verified by thermogravimetric analysis. The amorphous character of the obtained particles was verified using X-ray diffraction and differential scanning calorimetry. To further demonstrate the broad applicability of our approach the solvent was varied and the stabilization applied to a different formation mechanism.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Amorphous nanoparticles; Antisolvent precipitation; Ibuprofen; Micromixer; Poorly soluble drug; Stabilization

An experimental study of ultrafiltration for sub-10nm quantum dots and sub-150 nm nanoparticles through PTFE membrane and Nuclepore filters - Peukert, Wolfgang; Segets, Doris; Chen, Sheng-Chieh; Ling, Tsz-Yan; Pui, David (Journal of Membrane Science, 2016)
Ultrafiltration techniques (pore size of membrane below 100nm) are widely used in chemical engineering, semiconductor, pharmaceutical, food and beverage industries. However, for small particles, which are more and more attracting interests, the pore size often does not correlate well with sieving characteristics of the ultra-membranes. This may cause serious issues during modeling and prediction of retention efficiencies. Herein, a series of liquid filtration experiments with unfavorable conditions were performed. PTFE membranes (50, 100nm) and Nuclepore filters (50, 400nm) were challenged with 1.7nm manganese doped ZnS and 6.6 nm ZnO quantum dots (QDs), 12.4, 34.4 and 50 nm Au and 150 nm SiO nanoparticles. For larger and medium sized particles, sieving and eventually pore blockage phenomena were observed. In comparison, for small QDs, a high initial retention efficiency (>0.4) in both filters was monitored, followed by a reduced efficiency with ongoing particle loading. This high initial retention of small nanoparticles was attributed to diffusion deposition rather than to sieving since the ratio of pore size to particle size was significantly high (up to 58). Our experimental results allow a basic understanding of the deposition mechanism of small nanoparticles (diffusion vs. sieving) in different filter structures.
Keywords: Diffusion deposition; Loading effect; Quantum dot; Surface interactions; Ultrafiltration

Angle-resolved second-harmonic light scattering of colloidal interfaces - Peukert, Wolfgang; Braunschweig, Björn; Sauerbeck, Christian (Proceedings of a meeting held 3-8 November 2013, San Francisco, California, USA. Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)

An improved generalized AMBER force field (GAFF) for urea - Özpinar, Gül; Peukert, Wolfgang; Clark, Timothy (Journal of Molecular Modeling, 2010)
We describe an improved force field parameter set for the generalized AMBER force field (GAFF) for urea. Quantum chemical computations were used to obtain geometrical and energetic parameters of urea dimers and larger oligomers using AM1 semiempirical MO theory, density functional theory at the B3LYP/6-31G(d,p) level, MP2 and CCSD ab initio calculations with the 6-311++G (d,p), aug-cc-pVDZ, aug-cc-pVTZ, and aug-cc-pVQZ basis sets, and with the CBS-QB3 and CBS-APNO complete basis set methods. Seven different urea dimer structures were optimized at the MP2/aug-cc-pVDZ level to obtain accurate interaction energies. Atomic partial charges were calculated at the MP2/aug-cc-pVDZ level with the restrained electrostatic potential (RESP) fitting approach. The interaction energies computed with these new RESP charges in the force field are consistent with those obtained from CCSD and MP2 calculations. The linear dimer structure calculated using the force field with modified geometrical parameters and the new RESP charge set agrees well with available experimental data.

An in situ study to shed light on the formation of goethite spindles by pseudomorphic transformation of intermediate phases - Michaud, Mark; Peukert, Wolfgang; Distaso, Monica (Powder Technology, 2023)
Size and shape control of nanoparticles is fundamental to tune their material properties and to identify structure property functions. Herein, the shape of goethite (α-FeOOH) particles is varied from needle to spindle upon sodium carbonate modulation. Our in-depth study sheds light on the formation path of goethite particles by in situ monitoring the pH, the dissolved oxygen concentration and Raman spectroscopy in the presence and in the absence of sodium carbonate. The pH evolution indicates two distinct plateaus, at 7–6.5, and 6–6.3, respectively: the time when the dissolved oxygen concentration vanishes is correlated with the time required to oxidize Fe(II) to Fe(III). Raman spectroscopy enabled the identification of the intermediate phases green rust at 500 cm−1 and siderite at 1080 cm−1. Their formation and depletion was correlated with the kinetics of goethite formation. The evolution of the olation reaction is monitored through the bending vibration of water at 1640 cm−1. Finally, goethite particles are characterized ex situ via X-ray diffraction to assess the crystalline phase, scanning electron microscopy (SEM) for evaluating the size and shape of particles and transmission electron microscopy (TEM) for the analysis of the three-dimensional arrangement of self-assembled layers. The evaluation of reflectance spectra with CIELAB color metrics show that goethite spindles have enhanced color properties in comparison to the needle-shaped particles.
CRIS-Team Scopus Importer:2023-06-23
Keywords: Nanoparticles; Precipitation; Raman spectroscopy; Shape-control; Structure property relationship

Anisometric engineering of particle interfaces: Multidimensional characterization and gram‐scale production - Klupp Taylor, Robin; Meincke, Thomas; Sadafi, Fabrizio-Zagros; Walter, Johannes; Pflug, Lukas; Watanabe, Shun; Peukert, Wolfgang; Stingl, Michael (Chemie Ingenieur Technik (Special Issue: ProcessNet‐Jahrestagung und 33. DECHEMA‐Jahrestagung der Biotechnologen 2018), 2018)
A simple continuous-flow liquid-phase approach for the partial coating of nanoscale particles with metal was established [1]. Unique to this is the surface conformal and morphology-tailored growth of the metal. Due to their anisotropic surface character, the resulting materials are potentially relevant as particulate surfactants or for the assembly of novel photonic, catalytic or theranostic materials. In this contribution, three significant challenges are described that have recently been tackled. Firstly, it is shown how the use of a KM type micromixer with very short characteristic mixing times facilitates the understanding of the metal coating growth process. Secondly, the application of multiwavelength analytical ultracentrifugation for the determination of yield, coating thickness, and coverage distribution of the metal patches is considered. The validity of the measurements through microscopy and spectroscopy is confirmed and it is demonstrated how this characterization method can be employed to support process design. Finally, it is illustrated how the continuous flow approach can be developed in order to produce anisotropic metal-coated particles on the gram scale, and a first analysis of the novel optical properties of the powders is provided. [1] T. Meincke, H. Bao, L. Pflug, M. Stingl, R. N. Klupp Taylor, Chem. Eng. J. 2016, 308, 89. DOI: https://doi.org/10.1016/j.cej.2016.09.0

Anodic Titanium Dioxide Nanotubes for Magnetically Guided Therapeutic Delivery - Hasanzadeh Kafshgari, Morteza; Kah, Delf-Thorge Eric; Mazare, Anca Valentina; Nguyen, Nhat Truong; Distaso, Monica; Peukert, Wolfgang; Goldmann, Wolfgang; Schmuki, Patrik; Fabry, Ben (Scientific Reports, 2019)
Hollow titanium dioxide (TiO2) nanotubes offer substantially higher drug loading capacity and slower drug release kinetics compared to solid drug nanocarriers of comparable size. In this report, we load TiO2 nanotubes with iron oxide nanoparticles to facilitate site-specific magnetic guidance and drug delivery. We generate magnetic TiO2 nanotubes (TiO2NTs) by incorporating a ferrofluid containing Ø ≈ 10 nm iron oxide nanoparticles in planar sheets of weakly connected TiO2 nanotubes. After thermal annealing, the magnetic tubular arrays are loaded with therapeutic drugs and then sonicated to separate the nanotubes. We demonstrate that magnetic TiO2NTs are non-toxic for HeLa cells at therapeutic concentrations (≤200 µg/mL). Adhesion and endocytosis of magnetic nanotubes to a layer of HeLa cells are increased in the presence of a magnetic gradient field. As a proof-of-concept, we load the nanotubes with the topoisomerase inhibitor camptothecin and achieve a 90% killing efficiency. We also load the nanotubes with oligonucleotides for cell transfection and achieve 100% cellular uptake efficiency. Our results demonstrate the potential of magnetic TiO2NTs for a wide range of biomedical applications, including site-specific delivery of therapeutic drugs.
CRIS-Team Scopus Importer:2019-09-27

A novel apparatus for in situ compression of submicron structures and particles in a high resolution SEM - Romeis, Stefan; Paul, Jonas; Ziener, Marc; Peukert, Wolfgang (Review of Scientific Instruments, 2012)
We report on the development and characterization of a novel in situ manipulation device to perform stressing experiments on the submicron scale inside a high resolution field emission scanning electron microscope. The instrument comprises two main assembly groups: an upper part for positioning and moving a mounted probe and a force sensor as well as a specimen support as lower part. The upper part consists of a closed loop tripod piezoelectric scanner mounted on a self-locking coarse positioning stage. Two interlocked steel springs and a linear variable differential transformer measuring the springs’ deflections compose the lower part of the instrument. This arrangement acts as force-sensor and sample support. In comparison to already well-established concepts a wide measuring range is covered by adjusting the spring constant between 30 N/m and 50000 N/m. Moreover, the new device offers striking advantages with respect to force calibration and sample deformation measurements. Force calibration is performed using the eigenfrequency of the force detection system directly inside the SEM. Deformation data are obtained with high accuracy by simultaneously recording displacements above and below the specimen. The detrimental apparatus compliance is determined, and the influence on measured data subsequently minimized: an easy to validate two-springs-in-series model is used for data correction. A force resolution in normal direction of 100 nN accompanied by a sample deformation resolution of 5 nm can be achieved with the instrument using an appropriate load cell stiffness. The capabilities and versatility of this instrument are exemplified by compression experiments performed on submicron amorphous silica particles.

A novel approach for preparation and in situ tensile testing of silica glass membranes in the TEM - Mackovic, Mirza; Przybilla, Thomas; Dieker, Christel; Herre, Patrick; Romeis, Stefan; Stara, Hana; Schrenker, Nadine; Peukert, Wolfgang; Spiecker, Erdmann (Frontiers in Materials, 2017)
The mechanical behavior of glasses in the micro- and/or nanometer regime increasingly gains importance in nowadays modern technology. However, suitable small scale preparation and mechanical testing approaches for a reliable assessment of the mechanical properties of glasses still remain a big challenge. In the present work, a novel approach for site-specific preparation and quantitative in situ tensile testing of thin silica glass membranes in the transmission electron microscope is presented. Thereby, advanced focused ion beam techniques are used for the preparation of nanoscale dog bone shaped silica glass specimens suitable for in situ tensile testing. Small amounts of gallium are detected on the surface of the membranes resulting from redeposition effects during the focused ion beam preparation procedure. Possible structural changes of silica glass upon irradiation with electrons and gallium ions are investigated by controlled irradiation experiments, followed by a structural analysis using Raman spectroscopy. While moderate electron beam irradiation does not alter the structure of silica glass, ion beam irradiation results in minor densification of the silica glass membranes. In situ tensile testing of membranes under electron beam irradiation results in distinctive elongations without fracture confirming the phenomenon of superplasticity. In contrast, in situ tensile testing in the absence of the electron beam reveals an elastic/plastic deformation behavior, and finally leads to fracture of the membranes. The Young’s moduli of the glass membranes pulled at beam off conditions in the TEM are comparable with values known for bulk fused silica, while the tensile strength is in the range of values reported for silica glass fibers with comparable dimensions. The impact of electron beam irradiation on the mechanical properties of silica glass membranes is further discussed. The results of the present work open new avenues for dedicated preparation and nanomechanical characterization of silica glasses, and further contribute to a fundamental understanding of the mechanical behavior of such glasses when being scaled down to the nanometer regim
Keywords: Silica glass; in situ TEM; in situ nanomechanical testing; Mechanical Properties; Electron beam irradiation; superplasticity; FIB; Raman spectroscopy

A novel process chain for the production of spherical sls polymer powders with good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of the 7th World Congress on Particle Technology, WCPT 2014, 2015)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) applying polymer powder systems is promising. In the case of SLS basically only polyamide is available as an optimized powder material showing satisfying behavior during processing. Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. Within this account we present a novel process route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the process chain is demonstrated for polystyrene (PS) and poly butylene terephthalate (PBT) and the increase of powder flowability after the consecutive process steps has been monitored using a tensile strength tester. The influence of particle habitus and surface functionalization on powder flowability and its properties is discussed. In a first step polymer microparticles are produced by a wet grinding method at reduced temperatures. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns and adapted to specific needs. The dependencies of mean product particle size, particle size distribution and grinding kinetics on stressing conditions, system composition and especially process temperature (increase of the brittleness of the polymer vs. increase of dampening of grinding bead motion with decreasing temperature) will be extensively discussed for the polymers PS, PBT, poly oxo methylene (POM) and Poly ether ether ketone (PEEK). The comminution products obtained typically consist of microparticles of irregular shape and poor powder flowability, i.e. these intermediate products are cohesive and thus will show poor SLS processability. An improvement of flowability of the ground polymer particles is achieved in a second step by changing their shape. The irregular particles are rounded using a heated downer reactor. It will be demonstrated that the 'degree' of rounding can be controlled by changing the temperature profile or the residence time. To further improve the flowability of the cohesive spherical polymer microparticles nanoparticles are adhered to the microparticles' surface in a third step. The improvement of powder flowability after the consecutive process steps is remarkable: rounded and dry-coated PS powders exhibit a strongly reduced tensile strength (by a factor 5) in comparison to the tensile strength of the edged PS comminution product. The improved flowability and packing behavior of the polymer powders open new options in SLS processing including the usage of much smaller polymer bead
Keywords: downer reactor; dry particle coating; polymers; selective laser sintering; wet grinding

A novel process for production of spherical PBT powders and their processing behavior during laser beam melting - Schmidt, Jochen; Sachs, Marius; Zhao, Meng; Fanselow, Stephanie; Wudy, Katrin; Drexler, Maximilian; Drummer, Dietmar; Wirth, Karl-Ernst; Peukert, Wolfgang (31st International Conference of the POLYMER PROCESSING SOCIETY, 2016)
Additive manufacturing processes like laser beam melting of polymers are established for production of prototypes and individualized parts. The transfer to other areas of application and to serial production is currently hindered by the limited availability of polymer powders with good processability. Within this contribution a novel process route for the production of spherical polymer micron-sized particles of good flowability has been established and applied to produce polybutylene terephthalate (PBT) powders. Moreover, the applicability of the PBT powders in selective laser beam melting and the dependencies of process parameters on device properties will be outlined. First, polymer micro particles are produced by a novel wet grinding method. To improve the flowability the produced particles the particle shape is optimized by rounding in a heated downer reactor. A further improvement of flowability of the cohesive spherical PBT particles is realized by dry coating. An improvement of flowability by a factor of about 5 is achieved by subsequent rounding of the comminution product and dry-coating as proven by tensile strength measurements of the powders. The produced PBT powders were characterized with respect to their processability. Therefore thermal, rheological, optical and bulk properties were analyzed. Based on these investigations a range of processing parameters was derived. Parameter studies on thin layers, produced in a selective laser melting system, were conducted. Hence appropriate parameters for processing the PBT powders by laser beam melting, like building chamber temperature, scan speed and laser power have been identified.
Keywords: downer reactor; dry coating; polybutylene terephthalate (PBT); selective laser beam melting of polymers; wet grinding

A novel process route for the production of spherical LBM polymer powders with small size and good flowability - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Powder Technology, 2014)
Rapid prototyping has been applied so far in the production of special parts at low piece numbers. Currently, 'rapid prototyping' gradually is transferred to additive manufacturing opening new applications. At present basically only polyamide (PA) is available as an optimized powder material showing satisfying behavior during processing in laser beam melting (LBM). Other types of polymer powders produced by cryogenic grinding show poor powder flowability as well as an unfavorable particle habitus resulting in poor device quality. In fact, it is challenging to produce laser sintering powders with small particle size, good flowability and processability. We present a novel process chain for the production of spherical polymer micron-sized particles of good flowability that can be applied to a large variety of polymers: in a first step polymer particles are produced by a wet grinding method that are rounded in a second step using a heated downer reactor. To increase the flowability of the cohesive spherical polymer particles further nanoparticles are adhered to the particle surface in the third step. We demonstrate an increase of powder flowability by a factor of 5. The influence of particle habitus and nanoparticle functionalization on powder flowability is discussed in detail. © 2014 Elsevier B.V.
Keywords: Downer reactor; Dry particle coating; Flowability; Laser beam melting (LBM); Polymers; Wet grinding

A novel process route for the production of spherical SLS polymer powders - Schmidt, Jochen; Sachs, Marius; Blümel, Christina; Winzer, Bettina; Toni, Franziska; Wirth, Karl-Ernst; Peukert, Wolfgang (Proceedings of PPS-30 : the 30th International Conference of the Polymer Processing Society : conference papers : 6-12 June 2014, Cleveland, Ohio, USA, 2015)
Currently, rapid prototyping gradually is transferred to additive manufacturing opening new applications. Especially selective laser sintering (SLS) is promising. One drawback is the limited choice of polymer materials available as optimized powders. Powders produced by cryogenic grinding show poor powder flowability resulting in poor device quality. Within this account we present a novel proceb route for the production of spherical polymer micron-sized particles of good flowability. The feasibility of the proceb chain is demonstrated for polystyrene e. In a first step polymer microparticles are produced by a wet grinding method. By this approach the mean particle size and the particle size distribution can be tuned between a few microns and several 10 microns. The applicability of this method will be discubed for different polymers and the dependencies of product particle size distribution on strebing conditions and proceb temperature will be outlined. The comminution products consist of microparticles of irregular shape and poor powder flowability. An improvement of flowability of the ground particles is achieved by changing their shape: they are rounded using a heated downer reactor. The influence of temperature profile and residence time on the product properties will be addrebed applying a viscous-flow sintering model. To further improve the flowability of the cohesive spherical polymer particles nanoparticles are adhered onto the microparticles' surface. The improvement of flowability is remarkable: rounded and dry-coated powders exhibit a strongly reduced tensile strength as compared to the comminution product. The improved polymer powders obtained by the proceb route proposed open new pobibilities in SLS procebing including the usage of much smaller polymer bead
Keywords: Downer reactor; Poly butylene terephthalate (PBT); Poly oxo methylene (POM); Polystyrene (PS); Rounding; Selective laser sintering (SLS); Wet grinding; rounding

A population balance model of quantum dot formation: Oriented growth and ripening of ZnO - Segets, Doris; Hartig, Martin Andreas Johannes; Gradl, Johannes; Peukert, Wolfgang (Chemical Engineering Science, 2012)
The precipitation of zinc oxide (ZnO) semiconductor quantum dots was investigated throughout the whole particle formation process, namely reaction, nucleation, growth and ripening and described by means of population balance equations (PBE). Regarding nucleation, the simulation revealed that the mechanism for the solid formation is by orders of magnitude lower than predicted by classical homogeneous nucleation theory. Thus, the earliest stages of particle formation were described by a combination of reaction kinetics determined by experiments for the formation of preformed clusters and subsequent oriented cluster aggregation. Finally, slow Ostwald ripening, i.e. the growth of larger structures at the expense of smaller particles, was modeled in good agreement with the already experimentally determined particle sizes for ripening temperatures between 10 and 50 °C.

Application of Printable ITO/PEDOT Nanocomposites as Transparent Electrodes in Optoelectronic Devices - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Conference on Lasers and Electro-Optics, 2012)
Printable transparent hybrid composites consisting of indium tin oxide (ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene: polystyrene sulfonic acid (PEDOT:PSS)) as matrix material were developed and used as transparent electrodes in all-printed flexible electroluminescent lamps and electrochromic display
Keywords: optical devices; electro-optical devices; thin films; transparent conductive coatings

A review of models for single particle compression and their application to silica microspheres - Paul, Jonas; Romeis, Stefan; Tomas, Jürgen; Peukert, Wolfgang (Advanced Powder Technology, 2014)
We report on the deformation behavior of single silica microspheres. For the first time a detailed discussion on the quantitative evaluation of force–deformation data in the elastic and plastic regime is given. The microspheres are compressed between two flat plates of a custom built manipulation device supported by a scanning electron microscope. The device allows a high sample throughput enabling full statistical evaluation of force–deformation data of single microspheres. Existing theories describing the deformation behavior of single spheres are discussed and applied to the elastic and plastic deformation regime of silica microspheres. The results obtained from the theories are compared between each other and values reported in literature. The silica microspheres exhibit a significantly different deformation behavior than expected from bulk fused silica, i.e. a distinct plastic deformation behavior. Furthermore, a significant decrease in Young’s modulus and hardness was observed caused by high porosity and reduced crosslinking of silicon atoms, respectively, that is inherent to silica produced by Stöber synthesis. However, the calculated contact pressures exceed the compressive strength of bulk fused silica by at least a factor of two as an effect of a reduced amount of material flaws in microstructures.

Assessing stress conditions and impact velocities in fluidized bed opposed jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Schott, Florian; Wirth, Karl Ernst; Peukert, Wolfgang (Particuology, 2020)
Fluidized bed opposed jet mills are capable of meeting the continuously growing demand for contamination-free fine particles. In this type of jet mill, the solid material is entrained and accelerated by expanding gas jets that are focused onto a focal point inside a fluidized bed. The resulting particle collisions induce breakage. The process is affected by the relative particle velocities and the number of particle–particle collisions. Clearly, both quantities are distributed. However, to date, neither relative particle velocities nor collision frequencies in such units have been determined. The present work introduces an innovative method to assess the stressing conditions in jet mills experimentally. To this end, mixtures of glass and ductile metal microspheres were used, with the latter employed in small amounts. Inter-particle collisions between the aluminum and glass spheres lead to the formation of dents on the microparticles. The size and number of these dents are associated with the individual collision velocities and overall collision frequencies. The correlation between dent size and collision velocity was obtained from finite element calculations based on empirical data. The proposed approach was validated using particle image velocimetry during secondary gas injection into a fluidized bed reactor. In this case the effect of the distance between two opposed nozzles was examined. For a lab-scaled fluidized bed opposed jet mill the effects of gas pressure and hold-up were investigated. Relative particle velocities were found to be significantly lower than the gas velocities, while the number of contacts per particle was determined to be extremely high.
CRIS-Team Scopus Importer:2020-07-03
Keywords: Finite element modeling; Fluidized bed opposed jet mill; Relative velocity distribution; Single particle probes; Stress number distribution

Assessing the influence of viscosity and milling bead size on the stressing conditions in a stirred media mill by single particle probes - Strobel, Alexander; Schwenger, Jan; Wittpahl, Sandra; Schmidt, Jochen; Romeis, Stefan; Peukert, Wolfgang (Chemical Engineering Research & Design, 2018)
Keywords: Fluid viscosity; Grinding media size; Stress number and energy distribution; Single particle probes; Stirred media milling

Assigning Electronic States in Carbon Nanodots - Strauß, Volker; Kahnt, Axel; Zolnhofer, Eva; Meyer, Karsten; Maid, Harald; Placht, Christian; Bauer, Walter; Nacken, Thomas; Peukert, Wolfgang; Etschel, Sebastian; Halik, Marcus; Guldi, Dirk Michael (Advanced Functional Materials, 2016)
Luminescent carbon nanodots exhibit enormous potential to be used as functional building blocks in energy conversion devices. Their intrinsic heterogeneity, however, hinders a thorough characterization and subsequently their applicability. In this work, the spectroscopic and electrochemical properties of prototype carbon nanodots were thoroughly studied in solution. Spectro-electrochemical experiments revealed information on the spectral features of several oxidized and reduced species of our carbon nanodots. Therefore, these experiments were complemented with pulse radiolysis where the spectral signature of the one-electron oxidized and reduced forms were identified. Both, electrochemically and radiolytically reduced and oxidized products show high reactivity in solution which correlates with an open-shell character, detected by paramagnetic resonance spectroscopy. The herein presented studies help to understand the complex nature of carbon nanodots and serve to overcome difficulties in device fabrication.

A study of adhesion forces of oxide particles by molecular modeling and AFM-measurements - Peukert, Wolfgang; Götzinger, Martin (Proceedings 26th Annual Meeting of The Adhesion Society, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.astudy
Keywords: adhesion; surface; afm

A test of improved force field parameters for urea: molecular-dynamics simulations of urea crystals - Ozpinar, Gul Altinbas; Beierlein, Frank; Peukert, Wolfgang; Zahn, Dirk; Clark, Timothy (Journal of Molecular Modeling, 2012)
Molecular-dynamics (MD) simulations of urea crystals of different shapes (cubic, rectangular prismatic, and sheet) have been performed using our previously published force field for urea. This force field has been validated by calculating values for the cohesive energy, sublimation temperature, and melting point from the MD data. The cohesive energies computed from simulations of cubic and rectangular prismatic urea crystals in vacuo at 300 K agreed very well with the experimental sublimation enthalpies reported at 298 K. We also found very good agreement between the melting points as observed experimentally and from simulations. Annealing the crystals just below the melting point leads to reconstruction to form crystal faces that are consistent with experimental observations. The simulations reveal a melting mechanism that involves surface (corner/edge) melting well below the melting point, and rotational disordering of the urea molecules in the corner/edge regions of the crystal, which then facilitates the translational motion of these molecules.

Attractive particle interaction forces and packing density of fine glass powders - Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Blümel, Christina; Wirth, Karl-Ernst; Peukert, Wolfgang; Pöschel, Thorsten (Scientific Reports, 2014)
We study the packing of fine glass powders of mean particle diameter in the range (4-52)μm both experimentally and by numerical DEM simulations. We obtain quantitative agreement between the experimental and numerical results, if both types of attractive forces of particle interaction, adhesion and non-bonded van der Waals forces are taken into account. Our results suggest that considering only viscoelastic and adhesive forces in DEM simulations may lead to incorrect numerical predictions of the behavior of fine powders. Based on the results from simulations and experiments, we propose a mathematical expression to estimate the packing fraction of fine polydisperse powders as a function of the average particle size.

Attrition of polymeric bulk materials in pneumatic conveying: mechanisms and material properties - Peukert, Wolfgang; Frye, Lars (Pneumatic and hydraulic conveying systems III, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.attrit
Keywords: transport; conveyer

Attrition of polymeric bulk materials in pneumatic conveying: mechanisms and material properties - Peukert, Wolfgang; Frye, Lars (Particulate Science and Technology, 2003)
In the approach presented, attrition of bulk solids in pneumatic conveying is regarded as a result of a process function (stress conditions) and a material function (influence of material properties). The paper focuses on dilute phase conveying (homogeneous flow) and in the first part describes the determination of the process function by employing computational fluid dynamics (CFD). In the second part, experimental results for the determination of the material function by means of simulating the previously identified stress modes of impact and friction under well-defined stress conditions are presented. Contrary to what was expected initially, the numerical simulations as well as experimental results indicate that sliding friction is apparently of importance in dilute phase conveying. This conclusion can be drawn from the low calculated impact angles in a pipe bend (r B /D=5; D=80 mm), which lie between 10 and 35°. Consequently, the tangential impact velocity components ranging from 32 to 40 m/s are considerably higher than the normal ones (5 to 22 m/s). These results are confirmed by observations made in experiments to determine the material function. The relative attrition behavior of four different polypropylenes under pure sliding friction conditions closely resembles that observed in attrition experiments carried out in a pipe bend of the above geometry, while differences are observed for normal impact condition
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.attrit_5
Keywords: Attrition; Pneumatic Conveying; Polymers; Process Function; Material Function; Computational Fluid Dynamics (CFD)

Attrition of polymeric bulk solids in pneumatic conveying: determination of process and material function - Peukert, Wolfgang; Frye, Lars (4th International Conference on Bulk Solids Handling, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.attrit
Keywords: polymer; process; function

Automated synthesis of quantum dot nanocrystals by hot injection: Mixing induced self-focusing - Salaheldin, Ahmed M.; Walter, Johannes; Herre, Patrick; Levchuk, Ievgen; Jabbari, Yasaman; Kolle, Joel; Brabec, Christoph; Peukert, Wolfgang; Segets, Doris (Chemical Engineering Journal, 2017)
The hot injection technique for the synthesis of quantum dots (QDs) is a well-established and widely used method in the lab. However, scale-up rules do not exist. One reason is that in particular the role of process parameters like mixing on particle formation is largely unknown, as systematic examination of the latter is impossible for the laborious and complex manual synthesis. Herein we studied the mixing induced self-focusing of particle size distributions (PSDs) of CdSe QDs using automation in combination with a defined stirrer geometry. Basis for our study is a platform that allows parallelization with inline temperature monitoring, defined injection rate, accurate sampling times as well as controlled stirring. Reproducibility in terms of optical product properties was analyzed by absorption and emission whereas reproducibility in terms of the PSD was verified by deconvolution of UV/Vis absorbance spectra and especially by analytical ultracentrifugation (AUC) complemented by transmission electron microscopy (TEM). In line with previous results, AUC confirmed that even QDs made by hot injection in an automated setup are polydisperse with multimodal size distributions. Finally, reproducibility in combination with early stage sampling and controlled mixing allowed us for the first time to analyze the influence of stirring on focusing and defocusing of PSDs, that has been expressed in terms of the evolution of the relative standard deviation (RSD). Our work paves the way to gain in-depth understanding of often forgotten process-structure relationships of colloidal nanoparticles which eventually is a first step in the direction of the development of scalable synthesis and reliable application of high-quality QDs in technical application

A widely applicable method to stabilize nanoparticles comprising oxygen-rich functional groups - Distaso, Monica; Lautenbach, Vanessa; Uttinger, Maximilian; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Peukert, Wolfgang (Powder Technology, 2022)
Colloidal stability of nanoparticle suspensions is fundamental to apply nanomaterials in functional devices and to develop new methodologies in nanoscience. Herein, a versatile method is described to disperse and stabilize various solids with technological applications in pharmaceutical industry, batteries and fuel cells, dye sensitized solar cells, pigments and coatings. The method is based on the use of Zr(IV) hydroxo-complexes that interact with carboxylic- and hydroxo- functional groups at the solid-liquid interfaces of active pharmaceutical ingredients (API), carbon black (CB) and Pt-CB, metal oxide and metal oxy-hydroxide nanoparticles. The colloidal stability is assessed via sedimentation analysis, electrophoretic measurements, ultraviolet-visible spectroscopy (UV–Vis), attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) and isothermal titration calorimetry (ITC). The effect of the anion and pH are studied in depth. Finally, the current work enables liquid phase length and diameter characterization of rod-like goethite (α-FeOOH) particles without relying on tedius counting the particles from electron micrographs.
CRIS-Team Scopus Importer:2022-07-08
Keywords: Functional devices; Nanoparticles; Nanoparticulate inks; Stability; Surface

A widely applicable tool for modeling precipitation processes - Haderlein, Michael; Güldenpfennig, Andreas; Segets, Doris; Peukert, Wolfgang (Computers & Chemical Engineering, 2017)
This work presents a generalized tool for modeling precipitation processes for the parallel formation of multiple solid phases. A symmetric mixing model for T-mixers is presented which mimics the mixing process in a numerically highly efficient way. This model can easily be extended to other reactor types such as stirred tank reactors following the implementation given in this work. Modelling ion activities and ion complexation is strongly accelerated by the analytical formulation of the Jacobian of the corresponding system of equations. Solid formation processes are described via the numerically efficient Direct Quadrature Method of Moments (DQMOM) which is parallelized for treating multiple solid phases simultaneously. Expressions for agglomeration of multiple solid phases and for particle transfer between different mixer zones are given. Both the models of the individual processes and the entire precipitation tool are validated and tested in multiple scenarios proving the flexibility of the tool.
Keywords: Ion complexation; Mixing; Multi-phase; Population Balance Equation; Precipitation; T-Mixer

Binary Indium-Zinc Oxide Photoanodes for Efficient Dye-Sensitized Solar Cells - Peukert, Wolfgang; Stanzel, Melanie; Kunzmann, Andreas; Guldi, Dirk Michael; Costa Riquelme, Rubén Dario (Advanced Energy Materials, 2016)
The benefits of incorporating binary metal-oxide electrodes en route toward efficient dye-sensitized solar cells (DSSCs) have recently emerged. The current work aims at realizing efficient indium-doped zinc oxide based DSSCs by means of enhancing charge transport processes and reducing recombination rates. Electrochemical impedance spectroscopic assays corroborate that low amounts of indium reduce charge transport resistances and increase electron recombination resistances. The latter are in concert with a remarkable enhancement of the charge collection efficiency from 33% to 83% for devices with ZnO and InZnO photoanodes, respectively. Going beyond 15 mol% of indium, an effective electron trapping increases the charge transport resistance and, in turn, dramatically reduces charge collection efficiency. Upon implementing InZnO into an electron cascade photoanode architecture featuring an InZnO bottom layer and a ZnO top layer, a device efficiency of 5.77% and a significantly high current density of 20.4 mA cm in binary ZnO DSSCs are achieved.
Keywords: binary oxides; charge collection efficiency; flame spray pyrolysis; indium-zinc oxide photoanodes; n-type DSSCs

Bioactive Glass Flakes as Innovative Fillers in Chitosan Membranes for Guided Bone Regeneration - Zhang, Huijun; Wu, Jingjing; Wan, Ying; Romeis, Stefan; Esper, Julian Duane; Peukert, Wolfgang; Zheng, Kai; Boccaccini, Aldo R. (Advanced Engineering Materials, 2021)
Herein, novel bioactive glass flakes (BGFs) (45S5 composition), obtained by compression in the liquid phase in a stirred media mill, are combined with chitosan (CS) to develop composite membranes using solvent casting for guided bone regeneration (GBR). The incorporation of BGFs endows CS membranes with superior bioactivity as evidenced by rapid hydroxyapatite formation after 3 days of immersion in simulated body fluid (SBF). Moreover, the addition of BGFs reduces the swelling ratio of CS membranes, beneficial for GBR applications. The swelling behavior can also be modulated by tuning the added amount of BGFs. In vitro cell studies indicate the noncytotoxicity of composite membranes toward osteoblast cell line MC3T3-E1, although the presence of BGFs slightly reduces the cell viability compared to pure CS membranes. The incorporation of BGFs also improves the osteogenic differentiation of MC3T3-E1 cells as indicated by the enhanced alkaline phosphatase activity. The results show the feasibility of BGFs as anisotropic bioactive fillers in polymeric matrices. In conclusion, the developed CS-BGF composite membranes show promising potential as a novel material for GBR.
CRIS-Team Scopus Importer:2021-10-08
Keywords: bioactive fillers; bioactive glass flakes; chitosan; composites; guided bone regeneration

Biocompatibility of submicron Bioglass® powders obtained by a top-down approach - Dörfler, Anja; Detsch, Rainer; Romeis, Stefan; Schmidt, Jochen; Eisermann, Claudia; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part B: Applied Biomaterials, 2014)
In this study in vitro bioactivity and biocompatibility of two submicron 45S5 Bioglass powders obtained by top-down processing have been evaluated and are compared to the as-received powder. Both submicron powders exhibited flake-like morphologies with lateral extensions of only a few microns; the flake thickness accounted for a few tens of nanometers. Enhanced in vitro bioactivity was found for the comminuted powders upon immersion in simulated body fluid. In vitro biocompatibility was evaluated by incubation of MG-63 osteoblast-like cells with various amounts (0-200 μg/mL) of the glass powders. Neither LDH-activity nor mitochondrial activity (WST-8) tests indicated cell toxicity. Increased mitochondrial activity was found for the submicron powders: incubation with high amounts revealed up to a threefold increase of osteoblast activity (ALP-activity). An overgrowth of the formed mineralized phase with phenotypical MG-63 cells was found by staining only for the submicron glasses. A distance ring is formed for the as-received powder. Superior bioactivity markers are found for shorter process times, that is, lower mass specific surface areas. This is attributed to the formation of carbonates during the comminution process. © 2013 Wiley Periodicals, Inc.
Keywords: in vitro bioactivity and biocompatibility; MG-63 cells; sub-micron particles; top-down production

Biodegradabiliy of spherical mesoporous silica particles (MCM-41) in simulated body fluid (SBF) - Boccardi, Elena; Philippart, Anahi; Beltran, Ana M.; Schmidt, Jochen; Liverani, Liliana; Peukert, Wolfgang; Boccaccini, Aldo R. (American Mineralogist, 2018)
Keywords: Mesoporous silica particles; Simulated body fluid; Bone tissue engineering; Drug carriers; Biomaterials - Mineralogy Meets Medicine; Biodegradability

Breakage behaviour of different materials - construction of master curve for the breakage probability - Peukert, Wolfgang; Vogel, Lutz (Powder Technology, 2003)
An approach to quantify the grinding behaviour of different materials is presented. Based on a dimensional analysis and on fracture mechanical considerations, two material parameters, fMat. and Wm,min, are derived theoretically. fMat. characterises the resistance of particulate material against fracture in impact comminution. fMat. comprises the effect of particle size on fracture and the resistance against the external load which is quantified by the specific impact energy. Wm,min characterises the specific energy which a particle can take up without fracture. Values for fMat. and Wm,min which determine the grindability of different materials are given. Both the dimensional analysis and the fracture mechanical considerations lead to the same influence of initial particle size, mass-specific impact energy and newly derived material parameters on the comminution result. Experimentally, the material parameters are determined by single-particle impact tests. Together with the initial particle size and the impact energy, they allow for a quantitative description of the breakage probability of different materials in the form of a mastercurve and can also be applied for the qualitative description of the breakage function. The results for five polymers, limestone and glass spheres of different sizes are shown.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.breaka
Keywords: Breakage probability; Breakage function; Single-particle tests; Grinding; Comminution; Material properties; Mastercurve

Brownian dynamics simulations of analytical ultracentrifugation experiments exhibiting hydrodynamic and thermodynamic non-ideality - Uttinger, Maximilian; Walter, Johannes; Thajudeen, Thaseem; Wawra, Simon; Peukert, Wolfgang (Nanoscale, 2017)

Can spray freeze-drying improve the re-dispersion of crystalline nanoparticles of pure naproxen? - Braig, Veronika; Konnerth, Christoph-Günther; Peukert, Wolfgang; Lee, Geoffrey (International Journal of Pharmaceutics, 2019)
Spray freeze drying (SFD) was used to prepare re-dispersible powders of crystalline, pure-drug nanodispersions of naproxen in lactose and stabilized with hydroxypropyl cellulose. The particle size of the rehydrated powders was determined using static light scattering/Mie analysis. The nanoparticles present in the SFD powders were aggregated but could be dispersed on re-dispersion with water and stirring either with or without additional ultrasonic treatment. The disaggregation of the SFD nanoparticles was superior to that reported in the literature for spray dried nanoparticles of the same composition. It appears that the moderately-rapid freezing of the large spray droplets in LN2 during SFD produces less aggregation than does evaporative drying of the much smaller droplets during spray drying. Re-dispersion was also found to depend strongly on the pH of the original nanodispersion. The solubility of this weak acid is greater at higher pH which resulted in formation of a dissolved fraction of drug in the nanodispersions during media milling. After SFD, the dissolved naproxen fraction formed an amorphous solid which re-dissolves on re-hydration whereas the crystalline nanoparticles disaggregate.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Nanoparticles; Particle size; Poorly soluble drug; Re-dispersion; Spray freeze drying

Carbon Nanodots: Toward a Comprehensive Understanding of Their Photoluminescence - Strauß, Volker; Margraf, Johannes; Dolle, Christian; Butz, Benjamin; Nacken, Thomas; Walter, Johannes; Bauer, Walter; Peukert, Wolfgang; Spiecker, Erdmann; Clark, Timothy; Guldi, Dirk Michael (Journal of the American Chemical Society, 2014)
We report the characterization of carbon nanodots (CNDs) synthesized under mild and controlled conditions, that is, in a microwave reactor. The CNDs thus synthesized exhibit homogeneous and narrowly dispersed optical properties. They are thus well suited as a testbed for studies of the photophysics of carbon-based nanoscopic emitters. In addition to steady-state investigations, time-correlated single-photon counting, fluorescence up-conversion, and transient pump probe absorption spectroscopy were used to elucidate the excited-state dynamics. Moreover, quenching the CND-based emission with electron donors or acceptors helped shed light on the nature of individual states. Density functional theory and semiempirical configuration-interaction calculations on model systems helped understand the fundamental structure-property relationships for this novel type of material.

Carbon nano-onions: Individualization and enhanced water dispersibility - Lucherelli, Matteo Andrea; Stiegler, Lisa; Steiger, Florian; Åhlgren, E. Harriet; Requena-Ramírez, Julia; Castro, Edison; Echegoyen, Luis; Hirsch, Andreas; Peukert, Wolfgang; Kotakoski, Jani; Walter, Johannes; Perez-Ojeda Rodriguez, Maria Eugenia; et al. (Carbon, 2024)
Carbon nano-onions (CNOs) are a unique class of carbon nanomaterials, with a concentric fullerene-like structure and sp2-hybridized carbon atoms. Onions present high mechanical strength, good conductivity, the capability to intercalate alkali metals, showing promising applications in diverse fields, such as tribology, energy storage, and nanomedicine. Their production has been developed by several techniques, with the most interesting being the thermal annealing of carbon nanodiamonds because of the easy scalability (gram-scale) and morphologic control (size and shape form perfectly spherical to polygonal). However, this synthesis is commonly affected by the formation of strong aggregates larger than 100 nm, attributed to carbon soot formation or strong van der Waals interactions, hindering the work with small and individual particles, leading to an altered yield of functionalization. In this study we propose a method for CNO individualization based on strong acid treatment, yielding highly water dispersible nanoparticles. Analytical ultracentrifugation (AUC) analysis is employed as a technique to investigate the particle dimensions directly in dispersion, permitting an ensemble analysis free from further sample preparation bias. Moreover, we also provide a comprehensive evaluation of the common post-synthetic treatment methods, and their effects. By means of scanning transmission electron microscopy with medium angle annular dark field detector and electron energy loss spectroscopy (STEM-MAADF and EELS) we have shown images of individual CNOs. Their successful separation achieved in this study is significant for future research and applications in nanomedicine, electrochemistry, and materials composites, where sample homogeneity is critical.<br
CRIS-Team Scopus Importer:2024-01-12
Keywords: Analytical ultracentrifugation; Carbon materials; Carbon nano-onions; Exfoliation; Materials chemistry

Carboxylate Ion Pairing with Alkali-Metal Ions for β-Lactoglobulin and Its Role on Aggregation and Interfacial Adsorption - Beierlein, Frank; Clark, Timothy; Braunschweig, Björn; Engelhardt, Kathrin; Glas, Lena; Peukert, Wolfgang (Journal of Physical Chemistry B, 2015)
We report a combined experimental and computational study of the whey protein extgreekb-lactoglobulin (BLG) in different electrolyte solutions. Vibrational sum-frequency generation (SFG) and ellipsometry were used to investigate the molecular structure of BLG modified air-water interfaces as a function of LiCl, NaCl, and KCl concentrations. Molecular dynamics (MD) simulations and thermodynamic integration provided details of the ion pairing of protein surface residues with alkali-metal cations. Our results at pH 6.2 indicate that BLG at the air-water interface forms mono- and bilayers preferably at low and high ionic strength, respectively. Results from SFG spectroscopy and ellipsometry are consistent with intimate ion pairing of alkali-metal cations with aspartate and glutamate carboxylates, which is shown to be more effective for smaller cations (Li(+) and Na(+)). MD simulations show not only carboxylate-alkali-metal ion pairs but also ion multiplets with the alkali-metal ion in a bridging position between two or more carboxylates. Consequently, alkali-metal cations can bridge carboxylates not only within a monomer but also between monomers, thus providing an important dimerization mechanism between hydrophilic surface patches.
EAM Import::2019-03-13
Keywords: electrolyte; solution; molecular; dynamics; surface

Centrifugation | Analytical Ultracentrifugation - Peukert, Wolfgang; Walter, Johannes (Encyclopedia of Analytical Science, 2019)
Analytical ultracentrifugation is a highly accurate, reproducible and versatile technique to characterize the molecular weight, size, shape anisotropy, density and association of macromolecules and nanoparticles in solution. As a well-accepted analytical method, it has been applied widely in biology, biochemistry and polymer science to characterize (bio-)macromolecules and gains increasing interest in particle technology due to recent hard- and software developments. Multiwavelength detection providing access to spectral properties is one of the most important developments of the recent years. Experiments in the analytical ultracentrifuge are performed in sector shaped cells to measure the spatial and temporal concentration gradients using extinction, interference or fluorescence detectors. A moving boundary forms in sedimentation velocity experiments where high centrifugal forces are present. The rate of movement and shape of the boundary are determined by sedimentation and diffusion properties, respectively. The sedimentation depends on the analyte’s mass and frictional properties whereas diffusion is solely determined by frictional effects. Equilibrium studies are performed at lower rotor speeds where the mass transport due to sedimentation and diffusion balances, thus providing access to molecular weight distributions and interaction parameters. A variety of data analysis algorithms have been developed. Recently, multidimensional analysis has been established.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Analytical ultracentrifugation; Association; Centrifugation; Density; Diffusion; Interactions; Lamm equation; Macromolecule; Mass; Multidimensional properties; Nanoparticle; Sedimentation; Shape; Size; Spectrum

Changes within the stabilizing layer of ZnO nanoparticles upon washing - Schindler, Torben; Schmutzler, Tilo; Schmiele, Martin; Lin, Wei; Segets, Doris; Peukert, Wolfgang; Appavou, Marie-Sousia; Kriele, Armin; Gilles, Ralph; Unruh, Tobias (Journal of Colloid and Interface Science, 2017)
In detail, it was observed that the diffuse acetate shell shrinks to the size of a monolayer upon washing but the acetate content of this monolayer is higher than within the diffuse shell of the particles of the native dispersion. A second washing cycle reduces the acetate concentration within the stabilizing shell and the stability of the dispersion drops accordingly. After another (third) washing cycle strong agglomeration was observed for all investigated samples. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Small angle scattering; Stabilization; Quantum dots; Purification; Stabilizing shell

Chapter 13 Enabling Nanomilling through Control of Particulate Interfaces - Peukert, Wolfgang; Sommer, Marc (Elsevier B.V., 2007)
The postulated grinding limit at around half a micron that has existed for decades does not exist. Particle sizes down to 10 nm can be obtained. Nanomilling in aqueous and non-aqueous media becomes possible when the particulate interfaces are carefully controlled to prevent agglomeration of the broken fragments. Particle stability ensures also low suspension rheology. Any influence of the type of mill is not pronounced, if it exists at all. Important features are small milling beads, a high energy density in the mill, i.e. stirrer speeds in the range of 6-12 m/s and inhibition of agglomeration. Stabilization must be faster than the breakage kinetics. The latter can be estimated from population balance models. Ionic stabilization is preferable wherever it works because this mechanism is rather simple and can be detected on-line during milling by means of electro-acoustic spectroscopy. Even though stabilization can be achieved by the steric mechanism more research is necessary to understand details of the stabilization process. Nanomilling is a neat example which shows that real breakthroughs become possible even in very old and traditional technologies by fundamental studies of the underlying mechanisms. Nanomilling became, thus, an option for those who look for simple and versatile processes to nanoparticles. © 2007.
Keywords: nano; particle; milling; interface; interaction; energy

Chapter 20 Modelling of Mills and Milling Circuits - Peukert, Wolfgang; Toneva, Petya Ivanova (2007)
This chapter provides an overview of the existing mathematical models for the simulation of grinding and classification in mill–classifier circuits not only for ball mills but also for other mill types. Examples of the simulation of closed circuits are divided according to the mill type and the level of sophistication introduced into the models. Milling circuits are used in various industrial sectors to achieve desired product size distributions and product properties. The optimization and control of milling circuits is of high technological importance. Various models of mills and milling circuits are published in the literature with different precision and degree of sophistication. Mostly the grinding and classification are investigated separately and then both unit operations are connected into a mathematical model by the recirculation feed. To provide cost and time savings as well improvement of productivity through optimization of a grinding circuit a mathematical simulation of the process can be applied.
Keywords: milling; modeling; mathematical; grinding; classification; ball; mill; optimization

Characterisation of grinding-relevant particle properties by inverting of a population balance model - Vogel, Lutz; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2002)
An approach for the quantitative characterisation of feed materials in impact grinding is presented. With the help of dimensional reasoning and a fracture mechanic model two material parameters can be derived which describe the breakage probability quantitatively. The influence of stress intensity (impact energy), stress number, initial particle size and material are separated clearly. The two derived material parameters can be determined by single particle impact experiments with narrow size fractions of the feed material. A single mastercurve for the selection function of five different polymers, limestone and glass describes the breakage behaviour for two decades of initial particle size. The procedure using narrow feed size fractions can be simplified by using feed material with a broad particle size distribution. Then the appropriate population balance has to be inverted in order to determine the particle properties. Both, the population balance and the inversion are presented and validated with experimental results.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.charac_6
Keywords: Breakage probability; Comminution; Mastercurve; Population balance

Characterization of a downer reactor for particle rounding - Sachs, Marius; Friedle, Maximilian; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2016)
The gradual shift of rapid prototyping towards additive manufacturing (AM) implies higher demands on the available material. So far, most of the processes as laser beam melting (LBM) rely on polyamide as PA12. To overcome limitations and to address this lack of suitable polymer material with a fine particle size, Schmidt et al. [1] have established a wet-grinding process which allows the production of very fine polymer particles. Since the ground product shows a rather bad flowability, further treatment is necessary to enable the use of this material in AM. A rounding of the chiseled particles can improve the flowability [2]. This treatment changes the morphology of the particles by surface tension forces in the molten state [3]. To accomplish rounding of the polymer powder, a downer reactor in semi-industrial scale has been established and will be characterized in this article. Main topics are the powder dispersion, the inlet geometry and its influence on the gas flow behavior inside the downer. This was achieved by combining basic simulation and experimental data. Furthermore, the heat distribution and agglomeration in the gas phase were investigated as important parameters of the process. Finally, a proof of concept by rounding wet ground PBT material was successfully conducted. The product was investigated to obtain data about a change in particle size and polymeric structure.
Keywords: CFD; Downer reactors; Laser beam melting; Particle rounding; Polymers

Characterization of complex particle properties by mobility-classified mass spectrometry – A case study for glutathione capped gold nanoclusters - Lübbert, Christian; Peukert, Wolfgang (Journal of Aerosol Science, 2024)
CRIS-Team Scopus Importer:2024-03-29

Characterization of Electrospray Drop Size Distributions by Mobility-Classified Mass Spectrometry: Implications for Ion Clustering in Solution and Ion Formation Pathways - Lübbert, Christian; Peukert, Wolfgang (Analytical Chemistry, 2021)
One of the outcomes of electrospray ionization is the size distribution of the droplets, which determines, together with the solvent composition and the source gas temperature, the minimum distance from the sprayer tip to the mass spectrometer inlet and therefore the ion transfer efficiency. Even more importantly, the average number of analyte molecules and, if present, contaminant species per droplet depend on the drop size. Consequently, the drop size distribution is a key parameter in nonspecific ion clustering in solution and ion suppression. The finding that small droplet sizes improve the mass spectral quality led to the development of nanoelectrospray sources, which dispense liquid flow rates below 0.1 μL/min and can generate drops with diameters smaller than 100 nm. However, current discussions on the effect of drop size on ion formation pathways and efficiencies remain qualitative because the exact drop size distributions are unknown. Here, we show that ion mobility-classified mass spectrometry of raffinose cluster ions allows us to determine very precisely the drop size distribution generated by the electrospray source in positive- and negative-ion modes. Based on the derived drop size distributions, we can quantitatively predict nonspecific ion clustering and can extract accurate probabilities for emission of species from parent drops upon Coulomb fission.

Characterization of gas phase temperatures in dependence of particle presence in the flame spray pyrolysis process - Peukert, Wolfgang; Gao, Yi; Kögler, Andreas; Kilian, Daniel; Seeger, Thomas; Leipertz, Alfred; Engel, Sascha (CLEO: Applications and Technology, CLEO_AT 2012, 2012)
We introduce a novel strategy to acquire gas phase temperatures by O2 pure rotational CARS during flame spray pyrolysis (FSP) for silica production. RCARS benefits from a polarization filtering technique that is essential in particle and droplet environments. Particle containing regions were located by correlating laser-induced breakdown (LIB) in a particle-laden and a particle-free flame at different heights. Measured temperatures in the particle regime show significantly lower flame temperatures for particle-laden flames since energy is dissipated rapidly by radiation heat transfer in the presence of particles. ©2011 Optical Society of Americ
Keywords: gas; phase; flame; spray; pyrolysis; polarization; laser

Characterization of mixing in a T-mixer: A combined experimental and numerical study - Peukert, Wolfgang; Schwarzer, Hans-Christoph; Manhart, Michael (European Conference on Mixing, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.charac
Keywords: mixing; simulation

Characterization of particle surfaces - Peukert, Wolfgang; Götzinger, Martin (World Congress Particle Technology 4, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.charac_34
Keywords: particle; surface

Characterization of Polymer Powders for Selective Laser Sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Hesse, Nicolas; Bück, Andreas; Peukert, Wolfgang (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Characterization of stressing conditions in mills – A comprehensive research strategy based on well-characterized model particles - Strobel, Alexander; Romeis, Stefan; Wittpahl, Sandra; Herre, Patrick; Schmidt, Jochen; Peukert, Wolfgang (Powder Technology, 2017)
Despite the abundant industrial use of various wet mills a detailed understanding of the mechanisms involved is far from being complete. During comminution stress distributions are applied to the individual particles of a processed suspension. In fact, the type of stressing and the acting stress energies are distributed. The distributions of acting stress energy and number of stress events per product particle are governed by the used mill and its operational conditions. Mill functions link the stress energy and stress number distributions to the operating parameters and are so far unknown. We introduce a new methodology to directly characterize the effective stress energy and effective stress number distributions within stirred media mills: Mechanically fully characterized spherical particles are used as particulate probes. The underlying finite element model for the energetic behavior of the probes during uniaxial compression is supported by manipulation experiments on the single particle level. The deformation behavior of individual particles and the respective changes of the particles’ shapes are used to determine the stressing history of the particles and hence the stress energy and stress number distributions in the mill. Experimental limitations and prospects of the proposed methodology are outlined in detail. The new approach is comprehensively discussed for a lab-scale stirred media mill operated at exemplary process conditions. The transfer to other mills or unit operations, however, is straightforward.
Keywords: Finite element modelling; Single particle compression; Single particle probes; Stress energy distribution; Stress number distribution

Characterization of surface properties of carbon black and graphite - Peukert, Wolfgang; Götzinger, Martin (Annales Universitatis Mariae Curie-Sklodowska, Sectio AA Chemia, 2002)
Carbon black is used in several technical applications. Fillers in tires, black pigments in printing technology or synthetic cloth fibers are only a few examples. Because of the small particle size of carbon blacks, the surface properties have a great influence on the product property . We studied two different carbon black that show a large difference up to 20% in rolling drag when used as filler in tires. Different roughness or diverse polar groups on the surfaces are possible reasons for this. Morphology, surface structure and chemical surface composition of carbon black are not well defined. For such systems, TGA-MS and gas adsorption are powerful tools to analyze surface properties. We use adsorption equilibria in the Henry-region that reflect the interaction of molecules with the particle surfaces. From measured Henry-coefficients and known atomic surface structure, dispersive interaction parameters of the solid, e.g. a Hamaker-constant, can be determined by inversely solving the applied adsorption model. This method can be used to characterize carbon black if the interactions of different molecules with carbon atoms are calibrated on a defined surface like graphite. From known interaction potentials of various probe molecules, structural information like surface roughness of carbon black can be determined
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.charac

Characterization of the grinding behaviour in a single particle impact device: studies on pharmaceutical powders. - Peukert, Wolfgang; Meier, Matthias; John, Edgar; Wirth, Karl Ernst; Wieckhusen, Dierk (European Journal of Pharmaceutical Sciences, 2008)
The grinding behaviour of different materials can be described by the two material parameters fMat and Wm,min [Vogel, L., Peukert, W., 2003. Breakage behaviour of different materials-construction of a mastercurve for the breakage probability. Powder Technol. 129, 101-110]. fMat describes the resistance of particulate material against fracture in impact comminution, Wm,min characterizes the specific energy which a particle can take up without comminution. The material parameters are determined experimentally by single particle impact tests. This concept is also applicable to pharmaceutical powders, as will be shown in this work. A device is presented for the characterization of particles with sizes down to a few 10 microm. Particles are dispersed and accelerated in an air stream which is flowing against an impact plate. The impact velocity is controlled by the air flow. An LDA system enables the measurement of particle velocities. The results obtained with this jet mill are in accordance to those obtained from another single particle impact device used by Vogel and Peukert, in which the influence of fluid flow is completely avoided. Since the new device is especially designed for finer powders, it will allow a more detailed analysis of the material parameters at smaller particle sizes. Additionally, a new analysis method has been developed in order to determine the breakage probability not from sieve analysis but from laser light diffraction (LLD) data by using a population balance.
Keywords: grinding; comminution; particle

Characterizations of drug carrying magnetic nanoparticles for tumor therapy: Biological outcome and first immunological aspects - Dürr, Stephan; Tietze, Rainer; Lyer, Stefan; Janko, Christina; Schreiber, Eveline; Mann, Johannes; Turcu, R.; Gitter, K.; Odenbach, S.; Vasylyev, Serhiy; Herrmann, Martin; Peukert, Wolfgang; et al. (Magnetohydrodynamics, 2013)
Nanosized magnetic drug carriers offer a splendid prospect for directed drug application. The increased drug concentration in cancer tissue reached for this kind of application enables therapeutic effects on tumors that cannot be achieved using conventional chemotherapeutic treatment. Characterizing the drug targeting system and its behavior in vitro is necessary for understanding the biological outcome. In our studies, IRspectroscopy shows covalent binding of the biocompatible fatty acid layer. Although binding of mitoxantrone (MTO) to particles is hardly defined, considerable amounts of drug can be carried by nanoparticles. Furthermore, the nanosized drug carrier complex has to be investigated due to its biological outcome. Real-time cell analysis is useful to observe the therapeutic particles concerning their outcome in cell culture time-resolved up to several days. First experiments in concordance to a conventional assay show that the effectivity of nanoparticle bound MTO in cell culture is higher than treatment with pure MTO. A preliminary study demonstrates that the burden of the immune system is reduced by Magnetic Drug Targeting (MDT) vs. conventional chemotherapy. For a better understanding of MDT for cancer treatment, further studies have to be done to explain especially the binding behavior of superparamagnetic iron oxide nanoparticles to the respective chemotherapeutic agent.
Keywords: nano; magnetic; characterization; particle; agent

Choosing the right nanoparticle size-designing novel ZnO electrode architectures for efficient dye-sensitized solar cells - Pfau, Markus; Kunzmann, Andreas; Segets, Doris; Peukert, Wolfgang; Wallace, Gordon G.; Officer, David L.; Clark, Timothy; Costa, Ruben Dario; Guldi, Dirk Michael (Journal of Materials Chemistry A, 2017)
A novel concept for constructing optimized ZnO-based photoanodes as integrative components of dye-sensitized solar cells (DSSCs) is realized by deploying differently sized nanoparticles, ranging from 2 to 10 nm, together with commercially available 20 nm nanoparticles. The 2 nm nanoparticles were used to construct an efficient buffer layer for transparent electrodes based on 10 nm nanoparticles, resulting in a relative increase of device efficiency from 1.8 to 3.0% for devices without and with a buffer layer, respectively. A mixture of 10 and 20 nm nanoparticles was optimized to maximize the diffuse reflection and to minimize the charge transport resistance in a light-scattering layer. This optimization resulted in a homogenous layer of more than 15 mm that provided a device efficiency of 3.3%. The buffer layer, transparent electrode, and light-scattering electrode, were then combined to give an overall efficiency of around 5%. Thus, this work demonstrates that varying the electrode architecture with nanoparticles of different diameters is a powerful strategy for improving the overall efficiency of ZnO-based DSSCs.

Chromatographic property classification of narrowly distributed ZnS quantum dots - Süß, Sebastian; Bartsch, Katja; Wasmus, Christina; Damm, Cornelia; Segets, Doris; Peukert, Wolfgang (Nanoscale, 2020)
Although optimized synthesis methods for nanoparticles (NPs) on small scale can lead to narrow particle size distributions (PSDs) and thus defined optical properties, in particular during scale-up, an additional classification step must be applied to adjust the particle properties according to the needs of the later application. NP chromatography is a promising separation method, which can be potentially transferred to preparative and industrial scale. Herein, we demonstrate that remarkable classification of ZnS quantum dots (QDs) with respect to the fundamental band gap energy is achieved by chromatography although the PSD of the feed material is already very narrow (1.5-3.0 nm). We investigated the interactions of ZnS QDs with stationary and mobile phase materials in order to select a proper material couple so that irreversible NP adhesion, agglomeration, decomposition or dissolution of the ZnS QDs during the chromatographic experiments are avoided and highly reproducible chromatograms are obtained. Using a fraction collector, the already narrowly size distributed feed material was separated into coarse and fine fractions with distinct band gap energies. For characterization of the chromatographic fractionation, quantities known from particle technology, i.e. separation efficiency, cut size and yield, were adapted to the band gap energy distributions accessible from UV/Vis spectroscopy. The optimization of process conditions (flow rate, temperature, switching time of the fraction collector) allows fine-tuning of the property classification and therefore of the optical properties within the narrow distribution of the ZnS QDs. Our study shows the strength and high potential of chromatography for preparative and continuous separation of NPs even in case of narrow size-distributed sub-10 nm semiconductor QDs.
CRIS-Team Scopus Importer:2020-06-19

Classification and characterization of multimodal nanoparticle size distributions by size-exclusion chromatography - Gromotka, Lukas; Uttinger, Maximilian; Schlumberger, Carola; Thommes, Matthias; Peukert, Wolfgang (Nanoscale, 2022)
Size-exclusion chromatography (SEC) is a well-known, versatile and scalable technique for the separation of molecules according to their hydrodynamic size in solution as well as for the determination of molecular weight distributions of polymers. In this paper we demonstrate and generalize the applicability of SEC to the classification and characterization of multimodal distributions of nanoparticles over a broad size range. After calibration with gold standards from 5 nm to 80 nm, the calibration curve is used to determine the particle size distributions (PSDs) of the standards which are in agreement with comprehensive nanoparticle size analysis by analytical ultracentrifugation. Universal calibration curves independent of the core material and surface functionality can be constructed if the pore diameter of the stationary phase exceeds the particle diameter by a factor of 2-3. Mixtures of gold standards are separated by SEC and evaluated in terms of peak resolution and size-dependent separation curves depending on how well the individual peaks are resolved. Baseline separation of a multimodal mixture is observed and its PSD is determined. Mixtures can be fractionated into coarse and fine fractions with nm precision at different switching times of the fraction collector. Our study demonstrates the strength of SEC to classify multimodal PSDs as well as to accurately determine size distributions of complex nanoparticle dispersions over a broad size range.

Classification of Different Zones in a Flame Spray Pyrolysis Process - Münsterjohann, Bettina; Engel, Sascha; Kilian, Daniel; Will, Stefan; Peukert, Wolfgang (International Workshop Nucleation and Early Stages of Particle Formation, 2014)

Classification of Nanoparticles by Size-Selective Precipitation: The Role of Solubility Parameters - Süß, Sebastian; Sobisch, T.; Lerche, D.; Mori, Y.; Peukert, Wolfgang; Segets, Doris (Chemie Ingenieur Technik, 2016)

Classification of Zinc Sulfide Quantum Dots by Size: Insights into the Particle Surface–Solvent Interaction of Colloids - Peukert, Wolfgang; Lutz, Christian; Yamamoto, Kyoko; Komada, So; Süß, Sebastian; Mori, Yasushige; Segets, Doris (Journal of Physical Chemistry C, 2015)
We present a detailed study on the classification of ZnS quantum dots (QDs) by size selective precipitation (SSP). SSP allows the postsynthetic narrowing of a given feed distribution and is usually realized by titration of a poor solvent into a suspension of dispersed particles. Thereby preferred flocculation of larger structures is induced. Our results confirm that SSP is a highly robust process, following a law of mass action. That means a certain solvent composition always leads to the same ratio between coarse and fines particles with respect to a specific particle size xi. This ratio is independent of the particle size distribution (PSD) of the feed, the washing history of the particles, and the solid concentration of the particles. Regarding the illustration of our findings, we established a combined approach that takes Hansen solubility parameters (HSP) of solvent mixtures as well as changing van der Waals interactions into account. Relating both to each other, a size-dependent region of enhanced solubility is clearly identified. Our concept allows a differentiation between volume-related effects like van der Waals interactions and surface-related effects like the interaction of a ligand with a solvent mixture. A comprehensive interpretation of classification results obtained with different good solvents and poor solvents enables to deduce a general strategy for the demanding determination of HSP for small colloids. Our work makes an important contribution to the design of an appropriate colloidal postprocessing which is applicable to larger quantitie
Keywords: ZnS; quantum; dot; selctive; precipitation; flocculation; structure; hansen; solubitlity; size

Cobalt-Releasing 1393 Bioactive Glass-Derived Scaffolds for Bone Tissue Engineering Applications - Hoppe, Alexander; Jokic, Bojan; Janackovic, Djordje; Fey, Tobias; Greil, Peter; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang; Lao, Jonathan; Jallot, Edouard; Boccaccini, Aldo R. (ACS Applied Materials and Interfaces, 2014)
Loading biomaterials with angiogenic therapeutics has emerged as a promising approach for developing superior biomaterials for engineering bone constructs. In this context, cobalt-releasing materials are of interest as Co is a known angiogenic agent. In this study, we report on cobalt-releasing three-dimensional (3D) scaffolds based on a silicate bioactive glass. Novel melt-derived "1393" glass (53 wt % SiO2, 6 wt % Na2O, 12 wt % K2O, wt % MgO, 20 wt % CaO, and 4 wt % P2O5) with CoO substituted for CaO was fabricated and was used to produce a 3D porous scaffold by the foam replica technique. Glass structural and thermal properties as well as scaffold macrostructure, compressive strength, acellular bioactivity, and Co release in simulated body fluid (SBF) were investigated. In particular, detailed insights into the physicochemical reactions occurring at the scaffold-fluid interface were derived from advanced micro-particle-induced X-ray emission/Rutherford backscattering spectrometry analysis. CoO is shown to act in a concentration-dependent manner as both a network former and a network modifier. At a concentration of 5 wt % CoO, the glass transition point (T-g) of the glass was reduced because of the replacement of stronger Si-O bonds with Co-O bonds in the glass network. Compressive strengths of >2 MPa were measured for Co-containing 1393-derived scaffolds, which are comparable to values of human spongy bone. SBF studies showed that all glass scaffolds form a calcium phosphate (CaP) layer, and for 1393-1Co and 1393-5Co, CaP layers with incorporated traces of Co were observed. The highest Co concentrations of similar to 12 ppm were released in SBF after reaction for 21 days, which are known to be within therapeutic ranges reported for Co2+ ions.
Keywords: cobalt; hypoxia; bioglass; bioactive; scaffold; bone tissue engineering; angiogenesis

Colloid process engineering - Peukert, Wolfgang; Kind, Matthias; Rehage, Heinz; Schuchmann, Heike (Springer International Publishing, 2015)
This book deals with colloidal systems in technical processes and the influence of colloidal systems by technical processes. It explores how new measurement capabilities can offer the potential for a dynamic development of scientific and engineering, and examines the origin of colloidal systems and its use for new products. The future challenges to colloidal process engineering are the development of appropriate equipment and processes for the production and obtainment of multi-phase structures and energetic interactions in market-relevant quantities. The book explores the relevant processes and for controlled production and how they can be used across all scales.
Keywords: colloid; multi-phase; process

Coloration in Supraparticles Assembled from Polyhedral Metal-Organic Framework Particles - Wang, Junwei; Liu, Yang; Bleyer, Gudrun; Peukert, Wolfgang; Görlitzer, Eric; Englisch, Silvan; Przybilla, Thomas; Mbah Chrameh, Fru; Engel, Michael; Spiecker, Erdmann; Imaz, Inhar; Maspoch, Daniel; et al. (Angewandte Chemie International Edition, 2022)
Supraparticles are spherical colloidal crystals prepared by confined self-assembly processes. A particularly appealing property of these microscale structures is the structural color arising from interference of light with their building blocks. Here, we assemble supraparticles with high structural order that exhibit coloration from uniform, polyhedral metal–organic framework (MOF) particles. We analyse the structural coloration as a function of the size of these anisotropic building blocks and their internal structure. We attribute the angle-dependent coloration of the MOF supraparticles to the presence of ordered, onion-like layers at the outermost regions. Surprisingly, even though different shapes of the MOF particles have different propensities to form these onion layers, all supraparticle dispersions show well-visible macroscopic coloration, indicating that local ordering is sufficient to generate interference effects.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Emulsion; Metal–Organic Frameworks; Self-Assembly; Structural Color; Supraparticles

Combination of a dielectric continuum model with inverse gas chromatography for the characterization of solid surfaces - Peukert, Wolfgang; Mehler, Carsten; Thielmann, Frank (Adsorption Science & Technology, 2002)
The use of dielectric continuum model for the characterization of solid surfaces was combined for the first time with inverse gas chromatography. Extension of dielectric continuum models to adsorption from the gaseous phase allowed the distributed surface properties of solid surfaces to be determined. An inverse gas chromatograph was used for the measurement of adsorption equilibria as a quick alternative to time-consuming measurements by gravimetric or volumetric set-ups. Combination of the two techniques allowed the rapid determination of the distributed properties of solid surfaces to be effected and the results were interpreted in a fundamental physical sense. This led to a novel and promising way for the rapid and exact characterization of solid surfaces.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.combin
Keywords: dielectric; gas; chromatography; characterization; solid; surface

Combined continuous nanoparticle synthesis with chromatographic size classification - Gromotka, Lukas; Biegel, Markus; Damm, Cornelia; Traore, Nabi; Drobek, Dominik; Spiecker, Erdmann; Peukert, Wolfgang (Advanced Powder Technology, 2024)
In this paper, we report a combination of the continuous flow synthesis of gold nanoparticles (AuNPs) with subsequent purification and narrowing of the particle size distribution (PSD) by size-exclusion chromatography (SEC) by adapting the flow rates of synthesis and classification. First, we show scalability of chromatographic classification with respect to column dimension and the absence of irreversible nanoparticle adhesion on the column material. Two different syntheses lead to a large and widely distributed and a small and narrowly distributed AuNP dispersion, which are classified by a semipreparative column. The PSDs of individual fractions are characterized by analytical SEC. The broadly distributed AuNP dispersion was classified into three fractions with distinct PSDs. For the narrowly distributed AuNPs, the separation is almost independent of the mobile phase flow rate: coarse and fine fractions with almost identical PSDs and separation efficiency curves are observed irrespective of the flow rate. Even NP samples with narrow PSDs can be classified into multiple fractions with tailored PSDs while simultaneously removing dissolved impurities from the dispersion. With our study, we demonstrate the potential of a direct combination of continuous NP synthesis with chromatographic classification for the optimization of final PSDs and the simultaneous purification of nanoparticulate dispersions.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Continuous flow synthesis; Gold nanoparticles; Purification; Size classification; Size-exclusion chromatography

Combined experimental/numerical study on the precipitation of nanoparticles - Peukert, Wolfgang; et al. (Aiche Journal, 2004)
Nanoparticle precipitation in a T-mixer was investigated experimentally as well as through simulations based on the population balance equation coupled with a global mixing model using barium sulfate as the substance under investigation. A detailed predictive precipitation model is presented and the important model parameters are identified: the mixing kinetics, the interfacial energy, and the physicochemical calculation of supersaturation. Furthermore, the capability of the global mixing model was evaluated, achieving good agreement of the mean particle sizes between experimental and simulation results. Many insights into the kinetics and the relevant time scales of the competing steps such as micromixing (mixing at the molecular level), nucleation, growth, and aggregation are obtained. However, some discrepancies in the width of the particle size distributions remain that are attributed to spatial and temporal fluctuations in the flow field and, consequently, in the mixing kinetics that cannot be resolved by the applied global mixing model. © 2004 American Institute of Chemical Engineers.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.combin
Keywords: Barium sulfate; Interfacial energy; Micromixing; Nanoparticle; Population balance equation; Precipitation

Communication via electron and energy transfer between zinc oxide nanoparticles and organic adsorbates - Gnichwitz, Jan-Frederik; Hirsch, Andreas; Guldi, Dirk Michael; Peukert, Wolfgang; Werner, Fabian; Marczak, Renata (Journal of Physical Chemistry C, 2009)
Stable ZnO nanoparticles suitable for further surface functionalization were synthesized in the liquid phase from homogeneous ethanolic solutions of the precursors lithium hydroxide and zinc acetate. It was found that the growth of the particles was governed by temperature as well as the presence of the reaction byproduct lithium acetate during the aging process. In particular, the reaction could be almost completely arrested by removal of this byproduct. The washing consisted of repeated precipitation of the ZnO particles by addition of alkanes such as heptane, removal of the supernatant, and redispersion in ethanol. Furthermore, the surface of the colloidal ZnO nanoparticles was successfully modified by catechol-anchoring group containing dye molecules, i.e., 5-(N-(3,4-dihydroxyphenethyl)-2-phenoxyacetamide)-10,15,20-(p-tert- butyltriphenyl)porphyrinatozinc (DOPAZ) and 5-(3,4-dihydroxy-N-phenylbenzamide)- 10,15,20-tris(4-tert-butylphenyl)porphyrinatozinc (CAMIZ), for the study of photochemical properties. Thermogravimetric analysis proved the stability of the catechol anchor groups. Steady-state absorption spectroscopy as well as steady-state and time-resolved emission studies confirmed the electronic communication between the ZnO nanoparticles in their excited state and both of the porphyrins. More than 96% emission quenching of ZnO can be achieved by addition of the porphyrins, proving that the visible emission of the ZnO is caused by surface states, since only the surface of the particles was altered by the grafting experiments. Moreover, with increasing porphyrin concentrations the lifetimes changed from 46.0 to 15.3 ns. The shortened lifetimes prompt a new deactivation pathway, namely, through the electronic coupling of the porphyrins to the ZnO nanoparticle. Assuming that the decrease in lifetime is entirely due to electron transfer to the porphyrins, a rate constant of 0.35 × 10 s could be determined for this process. When testing the excited state of the porphyrin in comparative assays between ZnO and Al O , we conclude a similar electron transfer deactivation. © 2009 American Chemical Society.
Keywords: Nanoparticle; electron; functionalization

Conceptual stabilizer selection for nanomilling based on dispersibility parameters - Peppersack, C.; Flach, Frederik; Prziwara, P.; Damm, Cornelia; Breitung-Faes, S.; Peukert, Wolfgang; Kwade, A. (Advanced Powder Technology, 2023)
The choice of stabilizers to prevent particle agglomeration during nanomilling is an elaborate process which is often based on empirical rules and experience. Usually, extensive screening studies are required to find an appropriate stabilizing additive. The present study shows how the selection of polymeric stabilizers can be narrowed down to a couple of additives based on Hansen solubility parameters. The stabilizing capability was found to be a function of the difference between solubility parameters of additive and particulate species. Solubility parameters of different additives and two particle species were determined by inverse gas chromatography and the stabilization performance was evaluated by nanomilling experiments conducted with a stirred media mill. It is shown that a certain difference of solubility parameters between particle and additive is necessary in order to provide colloidal stability of small particles after milling. On the one hand, the additive needs a certain affinity to the particle surface, while on the other hand it also has to be compatible with the solvent. Based on experimental data, a solubility parameter difference in the range of 7.5–10 MPa0.5 was identified as a good measure for a proper stabilizer selection. The approach was proved for two organic particle species and represents a promising tool for a more efficient formulation development of drug nanosuspensions.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Colloidal stability; Hansen solubility parameter; Inverse gas chromatography; Nanomilling

Conduction Mechanisms and Environmental Sensitivity of Solution-Processed Silicon Nanoparticle Layers for Thin-Film Transistors - Weis, Sebastian; Körmer, Richard; Jank, Michael; Lemberger, Martin; Otto, Michael; Ryssel, Heiner; Peukert, Wolfgang; Frey, Lothar (Small, 2011)
Room-temperature, solution-processed, silicon nanoparticle thin films show significant gating with distinct hysteresis in their current–voltage characteristics. Device performance strongly depends on measurement environment and charge transport is determined by particle surfaces. Particle encapsulation with polymethyl methacrylate or Al2O3 reduces hysteresis and device sensitivity against environmental influences. Both Al2O3 coating and UV exposure during measurements alter current transport and enhance conductivity, providing evidence for surface-dominated transpor
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.LEB.conduc
Keywords: silicon; nanoparticle; thin; film

Conductivity in nonpolar media: Experimental and numerical studies on sodium AOT-hexadecane, lecithin-hexadecane and aluminum(III)-3,5-diisopropyl salicylate-hexadecane systems - Peschka, Dirk; Schmidt, Jochen; Wagner, Barbara; Bänsch, Eberhard; Münch, Andreas; Peukert, Wolfgang; Prignitz, Rodolphe (Journal of Colloid and Interface Science, 2012)
The conductivity behavior of doped hydrocarbon systems is studied by applying impedance spectroscopy. In the case of 3,5-diisopropyl salicylato aluminum (III) the charge carriers are formed by dissociation of the compound and their concentration is proportional to the square root of the solute concentration. In hydrocarbon systems that consist of micelle forming compounds (sodium AOT/lecithin) a linear dependence of charge carrier concentration on solute concentration is observed in the concentration regime where micelles are present. The conduction mechanisms are studied by numerical solution of a Poisson-Nernst-Planck system that describes the charge transport. We follow two different approaches to extract the degree of micelle dissociation from the impedance data. Firstly, by computing the response of a linear approximation of the Poisson-Nernst-Planck model, and secondly by computing the fully nonlinear response from direct numerical simulations using finite elements. For high and moderate frequencies both approaches agree very well with the experimental data. For small frequencies the response becomes nonlinear and the concept of impedance fails. Furthermore, the numerically computed values for the degree of dissociation are of the same order of magnitude as the values obtained with classical formulas, but still differ by a factor of about 1/3. The direct numerical simulation allows new insight into the conduction mechanisms for different frequency regimes. © 2012 Elsevier In
Keywords: Degree of dissociation; Direct numerical simulation; Electrochemical impedance spectroscopy; Finite element analysis; Poisson-Nernst-Planck model; Reverse micelles

Congratulations to Prof. Dr.-Ing. Otto Molerus on the occasion of his 70th birthday on June 18th 2004 - Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2005)
On behalf of the editors of this special issue of Powder Technology and of the colleagues who contributed to this issue, we congratulate Prof. Dr.-Ing. Otto Molerus on the occasion of his 70th birthday. Birthdays, particularly b round Q ones, invite one to sit back for a moment. We remember things from the past and look into the future. Dear Prof. Molerus, colleagues from all over the world have been motivated by your birthday to dedicate a paper to you. You are connected with many of the scientists here through numerous contacts, discussions and joint projects.
Keywords: Congratulation; birthday; molerus; particle; technology

Continuous synthesis of CuInS2 quantum dots - Akdas, Tugce; Haderlein, Michael; Walter, Johannes; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (RSC Advances, 2017)
In colloidal semiconductor nanocrystal synthesis, many activities have been focused on the control over the mean particle size of the product. However, for device applications additional requirements apply, e.g. the necessity for a narrow particle size distribution (PSD). In the present work, we investigate the impact of reactor characteristics on the synthesis of CuInS2 quantum dots (QDs). Therefore, the synthesis is carried out in three different reactors, namely in a fully scalable and continuous tubular reactor, in a commercial microreactor and in a batch three-neck round-bottom flask. All reaction products from the three reactor types have the same crystal structure and inorganic composition. Slight differences in optical properties are mainly ascribed to differences in the PSD, which is confirmed by sedimentation velocity experiments. Furthermore, the necessity for using different post-processing routines coupled with our findings by analytical ultracentrifugation (AUC) hint at changes in the organic matrix surrounding the CuInS2 QDs. Our study demonstrates the massive impact of heat transfer on the synthesis and the final PSD of CuInS2 QDs synthesized via heating-up and allows us to draw conclusions on their formation.

Control of aggregation in production and handling of nanoparticles - Peukert, Wolfgang; Schwarzer, Hans-Christoph; Stenger, Frank (4th International Conference on Bulk Solids Handling, 2003)
In product engineering of particulate systems, the property function relates the dispersity to the product properties, whereas the process function shows how to produce the required dispersity. These principles are applied to the production of nanoparticles. Nanoparticles are controlled by surface forces. Due to their high mobility nanoparticles are unstable and may coagulate rapidly if the particles are not stabilized. Stabilization is achieved by tailoring the particulate surfaces, e.g. through repulsive double layer forces. Macroscopic properties are thus controlled by microscopic control of the interfaces, i.e. we bridge the gap between the molecular level and material properties. These principles are generally valid and are thus applied to precipitation and to nanomilling in stirred ball mills. The mean particle size in precipitation can be controlled by either the mixing intensity or the surface charge density of the particles. In stirred media mills oxide particles as small as 10 nm can be achieved by stabilizing the particles appropriately.
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.contro
Keywords: nanoparticle; aggregation; handling

Control of coating properties by tailored particle interactions: relation between suspension rheology and film structure - Peukert, Wolfgang; Günther, Lydia (Colloids and Surfaces, 2003)
The microstructure of dip-coated particulate thin films is studied by varying the stability of an aqueous silica sol used as coating bath. Different stability conditions are adjusted by changing electrolyte concentration and pH-value. The sol is characterized by acoustic and electroacoustic spectroscopy to obtain particle size distribution (PSD) and ζ-potentials. Furthermore, photometric measurements supplement the studies of stability behavior giving clear evidence of a non-DLVO contribution that is attributed to hydration forces. The structure of coatings, defined as the order of particles within the layer, was found to vary with stability parameters. It is observed that the surface roughness scanned by atomic force microscope (AFM) increased with increasing electrolyte concentration. Moreover, the structural evolution of the particulate network as a function of solid concentration and stability parameters is studied. For these purposes the sol is accumulated by dialysis against polyethylenglycol (PEG) and evaluated in terms of the viscosity as a function of shear rate. Finally, the influence of coating structures on the UV-light transmission properties is determined. Especially in case of LaCl3 a strong dependency between sol stability and the optical transmission property of the thin film is observed. The results explicitly confirm a correlation between microscopic structure and macroscopic propert
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.struct
Keywords: Dip-coating; Particles; Stability; Rheology; Particle arrangement

Control of Crystallization of PBT-PC Blends by Anisotropic SiO2 and GeO2 Glass Flakes - Düsenberg, Björn; Esper, Julian Duane; Maussner, Felix; Mayerhofer, Magdalena; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Polymer composites and blend systems are of increasing importance, due to the combination of unique and different material properties. Blending polybutylene terephthalate (PBT) with polycarbonate (PC) has been the focus of attention for some time in order to combine thermo-chemical with mechanical resistance. The right compounding of the two polymers is a particular challenge, since phase boundaries between PBT and PC lead to coalescence during melting, and thus to unwanted segregation within the composite material. Amorphization of the semi-crystalline PBT would significantly improve the blending of the two polymers, which is why specific miscibility aids are needed for this purpose. Recent research has focused on the functionalization of polymers with shape-anisotropic glass particles. The advantage of those results from their two-dimensional shape, which not only improves the mechanical properties but are also suspected to act as miscibility aids, as they could catalyze transesterification or act as crystallization modifier. This work presents a process route for the production of PBT-PC blends via co-comminution and an in-situ additivation of the polymer blend particles with anisotropic glass flakes to adjust the crystallinity and therefore enhance the miscibility of the polymers.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anisotropic particles; co-comminution; crystallization modifiers; functional filler; glass flakes; polymer-blends

Control of particle interfaces - the critical issue in nanoparticle technology - Peukert, Wolfgang; Günther, Lydia; Götzinger, Martin; Schwarzer, Hans-Christoph; Stenger, Frank (Advanced Powder Technology, 2003)
In the field of particle technology, processes cannot yet be designed from a basic molecular understanding. Nanotechnology, however, begins to bridge this gap between molecules and particles, and may thus not only open new ways for the production and handling of particulate matter, but also for the engineered design of advanced material properties. The visions and applications in nanoparticle technology cover a broad range, e.g. quantum dots in information technology, refractory particles for advanced ceramics, highly active substances in pharmacy, catalysts and micro- and mesoporous adsorbents to name only a few applications. Starting from the concept of product engineering we investigate the basic preconditions for tailoring nanoparticulate properties, i.e. the control of the particle interactions. This concept is then applied to precipitation as an example for particle synthesis and to particulate thin film formation as an example for structure formation.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.contro_7
Keywords: Nanoparticles; Precipitation; Product engineering; Surface forces; Thin films

Correlation between product purity and process parameters for the synthesis of Cu2ZnSnS4 nanoparticles using microwave irradiation - Ahmad, Rameez; Nicholson, K. S.; Nawaz, Qaisar; Peukert, Wolfgang; Distaso, Monica (Journal of Nanoparticle Research, 2017)
Kesterites (CZT(S,Se)4) emerged as a favourable photovoltaic material, leading to solar cell efficiencies as high as 12.7%. The development of sustainable roll-to-roll printing processes that make use of Cu2ZnSnS4 (CZTS) nanoparticle inks requires the proper design of synthetic approaches and the understanding of the relation between process parameters and product purity. In the current paper, we developed this relationship by calculating a specific energy factor. A microwave-assisted synthetic method that operates at atmospheric pressure and makes use of eco-friendly solvents is established. Four solvents, i.e. ethylene glycol (EG), diethylene glycol (di-EG), triethylene glycol (tri-EG) and tetraethylene glycol (tet-EG) are compared and the temperature during the reaction is assessed by two different methods. In particular, two by-products have been identified, i.e. Cu2-x S and a hexagonal phase. We show that the variation of reaction parameters such as power irradiation, type of solvent and precursor concentration influences the nanoparticles' sizes (from 12 to 6 nm) and also the temperature-time profile of reaction which, in turn, can be related to phase purity of CZTS nanoparticles. The results suggest that the product purity scales with the specific energy factor providing a useful tool to a rational design of high-quality CZTS nanoparticles.
Keywords: Disordered CZTS; Energy conversion; Cubic CZTS; Photovoltaics; Solar cells; Green chemistry; Kesterite

Correlation between shape, evaporation mode and mobility of small water droplets on nanorough fibres - Funk, Christine; Winzer, Bettina; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2014)
The dynamic wetting behaviour and the mobility of droplets on fibres is a very important factor in coating processes, textile fabrication, in self-cleaning processes and in the filtration of fluids. In principal, filter regeneration depends on the mobility of the droplets on the fibre surface. Mobile droplets tend to coalesce which greatly simplifies their removal from the filter. In this contribution mobility analyses of water droplets on monofilaments in air are performed. Studies of droplet evaporation on pure PET fibres and on nanorough fibres coated with SiO2 nanoparticles of diameters between 6 nm and 50 nm in a hydrophilic binder system were done. We show that the mobility of water droplets correlates with the droplet conformation which in turn is determined by the droplet-fibre interface. We demonstrate that fibre coatings can be used to tailor the conformation and mobility of water droplets. The smaller the nanoparticle diameters in the coating are, the smaller are the contact angles between water droplets and fibre and the better is the mobility of the droplets on the fibre. Our results allow a fast optimization of the fibre surface properties which are directly influencing the contact angle, the mobility and the coalescence of water droplets and thus filter regeneration.
Keywords: Silica; Three phase contact line; Fibre surface energy; Nanoparticle coating; Wettability of fibres; Coalescing media; Droplet conformation; Contact angle; Evaporation mode; Droplet mobility

Correlation of Enhanced Strength and Internal Structure for Heat-Treated Submicron Stöber Silica Particles - Romeis, Stefan; Paul, Jonas; Hanisch, Mathias; Marthala, Venkata; Hartmann, Martin; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2014)
The Stöber–Fink–Bohn (SFB) method allows the synthesis of spherical silica particles over a wide size range. Owing to the complex formation mechanism, the internal structure and related mechanical properties are not well understood. Within this account, the internal structure of synthesized SFB particles is changed systematically by heat treatments. Characterization by colloid titration, infrared spectroscopy, and solid-state nuclear magnetic resonance spectroscopy and the assessment of mechanical properties for single particles by in situ micromanipulation shed light on structure–property relations. Over the course of heat treatment, SFB particles become denser and owing to condensation of internal hydroxyl groups, the cross-linking of the silica network is enhanced. The observed chemical and structural changes are reflected by the mechanical properties of the particles: starting from a low Young’s modulus and hardness, clearly below the bulk properties of fused silica, both values are increasing over the course of the thermal treatment. Hardness for fused silica is approached after a treatment at 800 °C and exceeded after a treatment at 1000 °C. Young’s modulus approaches the bulk value. Furthermore, a significant plasticity is found: the sustained deformations are extremely high, and thus silica spheres with enhanced strength have been obtained by the thermal treatment.

Crystal Shape Engineering of Silicon Nanoparticles in a Thermal Aerosol Reactor - Koermer, Richard; Butz, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Crystal Growth & Design, 2012)
In this work, the capability of gas phase synthesis for crystal shape engineering of silicon nanoparticles (SiNP) in a hot wall reactor is demonstrated. Therefore, the necessary boundary conditions for the formation of monodisperse spherical SiNP as well as octahedral shaped particles from silane pyrolysis are systematically deduced. The different shapes of the SiNP are ascribed to different growth regimes (reaction limitation, diffusion limitation) depending on the global process parameters. Single crystalline, defect-free, spherical particles with a mean diameter of 30 nm (geometric standard deviation below 1.1) and octahedra with a mean edge length of about 100 nm could be obtained solely by process parameter adjustment. Particle size and shape as well as crystallinity were characterized by scanning electron microscopy and X-ray diffraction. The inner structure and faceting of the particles was analyzed in detail by high resolution transmission electron microscopy. A model which elucidates the orientation relation between inner silicon structure and the particle shape is derived for the octahedra.

Deciphering the Role of Impurities in Methylammonium Iodide and Their Impact on the Performance of Perovskite Solar Cells - Levchuk, Ievgen; Hou, Yi; Gruber, Marco; Brandl, Marco; Herre, Patrick; Tang, Xiaofeng; Högl, Florian; Batentschuk, Miroslaw; Osvet, Andres; Hock, Rainer; Peukert, Wolfgang; Tykwinski, Rik; et al. (Advanced Materials Interfaces, 2016)
Solution-based perovskite solar cell fabrication typically involves rather complex processing sequences to yield highest performance. While most studies concentrate on the exploration of processing conditions, the purity levels of common perovskite precursor solutions have been investigated and a number of impurities that are critically important toward controlling the crystallization of perovskites are found. In this study, an in-depth chemical study of the possible impurities formed during CHNHI preparation is presented and their relevance on solar cell processing is revealed. A primary consideration is the chemical transformation of hypophosphorous acid, which plays the role of the stabilizer for HI. The detrimental role of the impurities is best demonstrated by comparing perovskite solar cell devices fabricated from impurity-free precursors versus precursors containing different concentrations of impurities. Most interestingly, it is revealed that a certain concentration of impurities is detrimental to the growth of large-grained crystals. PbHPO nanoparticles, which are formed after hypophosphorous acid transformation, actually cause crystal domain growth through serving as a nucleation center. This study gives valuable insight into the rate determining steps of perovskite crystal growth and further provides the basis for developing reliable and reproducible high-performance recipes for perovskite solar cell processing.
Keywords: Grain size; Impurities; Perovskites; Seed growth; Solar cells

Deformation behavior of micron-sized polycrystalline gold particles studied by in situ compression experiments and frictional finite element simulation - Paul, Jonas; Romeis, Stefan; Herre, Patrick; Peukert, Wolfgang (Powder Technology, 2015)
We present a combined experimental and finite element study on the deformation behavior of micron-sized polycrystalline gold particles. This study enables detailed insights into the underlying deformation mechanisms of the particles. Scanning electron microscope supported in situ uniaxial compression experiments of the single spherical polycrystalline gold particles were performed in the size range of 1. μm by using a custom built manipulation device. By testing a large number of particles stress-strain data and information on the particle morphology were obtained with statistical significance. The experimentally observed stress-strain behavior and the geometric shape of the stressed particles were found to be in excellent agreement with the elastic-perfectly plastic finite element model accounting for frictional effects at the contact interfaces. A significantly increased yield strength compared to bulk gold was found - grain size strengthening according to the Hall-Petch relation was identified as the main hardening mechanism. Hardness was found to vary with strain - an effect related to the altering geometric shape of the particles during compression. Comparison to a frictionless finite element model revealed the necessity of considering the effect of friction. These findings are not restricted to gold particles, but should be applicable to a wide range of elastic-perfectly plastic materials.
Keywords: FEM; Friction; Gold particles; In situ SEM; Mechanical properties

Deformation behavior of nanocrystalline titania particles accessed by complementary in situ electron microscopy techniques - Herre, Patrick; Romeis, Stefan; Mackovic, Mirza; Przybilla, Thomas; Paul, Jonas; Schwenger, Jan; Torun, Boray; Grundmeier, Guido; Spiecker, Erdmann; Peukert, Wolfgang (Journal of the American Ceramic Society, 2017)
Keywords: mechanical properties; titanium oxide; transmission electron microscopy; nanoparticles; scanning electron microscopy

Deformation behavior of nanocrystalline titania particles accessed by complementary in situ electron microscopy techniques - Herre, Patrick; Romeis, Stefan; Mackovic, Mirza; Przybilla, Thomas; Paul, Jonas; Schwenger, Jan; Torun, Boray; Grundmaier, Guido; Spiecker, Erdmann; Peukert, Wolfgang (Journal of the American Ceramic Society, 2017)
The mechanical behavior of nanostructured spherical submicrometer titania parti- cles was studied by in situ uniaxial compression experiments in the scanning and transmission electron microscope (SEM and TEM). Mesoporous and amorphous titania particles were prepared by a wet chemical sol-gel approach. To obtain nanocrystalline (nc) single-phase anatase and rutile particles the amorphous parti- cles were cryst allized by high-temperature annealing. For each sample the defor- mation behavior of at least 50 particles was investigated by in situ compression experiments in the SEM. In all cases an elastic – predominantly plastic deforma- tion behavior accompanied by crack initiation at exceptionally high engineering strain values of several percent were observed. Crack propagation presumably along grain boundaries and a Weibull distributed fracture stress was shown for all nc particles. Complementary in situ TEM experiment s and ex situ analysis of focused ion beam prepared particle cross-sections were carried out to identify the underlying deformati on mechanisms. Grain rotations and grain sliding are observed for nc anatase particles during in situ compr ession and are further identi- fied to be linked to a densification of the mesoporous particle structure. Our dedi- cated prepar ation and quanti tative in situ characterization methodology provides an excellent basis for a better understanding of the mechanical behavior of advanced ceramics.
Keywords: mechanical properties; nanoparticles; scanning electron microscopy; titanium oxide; transmission electron microscopy

Delamination and Dissolution of Titanate Nanowires: A Combined Structure and in Situ Second Harmonic Generation Study - Schürer, Benedikt; Elser, Michael J.; Sternig, Andreas; Peukert, Wolfgang; Diwald, Oliver (Journal of Physical Chemistry C, 2011)
Mechanistic insights into shape and structure transformation of metal oxide nanostructures are critical to our understanding of how synthesis parameters and chemical environment affect their properties. Na2Ti3O7 nanowires, which are composed of titanate nanosheets and which contain sodium ions in the interlayer region, are thermodynamically unstable in acid solutions. At room temperature nanosheet delamination along the nanowire length axis leads to coiled-up nanoscrolls. At 373 K, a dissolution and TiO2 recrystallization process gives rise to colloidal anatase nanoparticles. The impact of temperature on different reaction pathways is attributed to differences in the energy barriers associated with the two transformation channels. We comprehensively investigated these reactions with X-ray diffraction and electron microscopy and for the first time tracked processes at the solid–liquid interface such as nanosheet delamination by time-resolved second harmonic generation (SHG) measurements. The applicability of the SHG method for in situ studies which address the transformation of layered nanostructures in aqueous solution even at high electrolyte concentrations is demonstrated.

Delamination of graphite in a high pressure homogenizer - Nacken, Thomas; Damm, Cornelia; Walter, Johannes; Rüger, Andreas; Peukert, Wolfgang (RSC Advances, 2015)
A scalable industrial method for graphene and Few-Layer-Graphene (FLG) production by graphite delamination in N-methylpyrrolidone and water-surfactant mixtures using a high pressure homogenizer is presented. This paper is focused on processing conditions and extensive subsequent analysis of the delaminated products by a combination of analytical ultracentrifugation, UV/Vis and statistical Raman spectroscopies including co-localization with atomic force microscopy. In this way quantitative processing-structure-property correlations showing how suspension properties and processing parameters governing yield, quality and lateral dimension of the produced graphene are obtained. It is found that a high pressure homogenizer can be used to obtain sufficiently high concentrated FLG suspensions with low defect concentration.

Delamination of graphite sheets in stirred media mills - Knieke, Catharina; Peukert, Wolfgang (2008 AIChE Annual Meeting, AIChE 100, 2008)

Delamination of graphite sheets in stirred media mills - Knieke, Catharina; Peukert, Wolfgang (2008 AIChE Annual Meeting, AIChE 100, 2008)

Delamination of hexagonal boron nitride in a stirred media mill - Damm, Cornelia; Peukert, Wolfgang; Körner, Julia (Journal of Nanoparticle Research, 2013)
A scalable process for delamination of hexagonal boron nitride in an aqueous solution of the non-ionic surfactant TWEEN85 using a stirred media mill is presented. The size of the ZrO beads used as grinding media governs the dimensions of the ground boron nitride particles as atomic force microscopic investigations (AFM) reveal: the mean flakes thickness decreases from 3.5 to 1.5 nm and the ratio between mean flake area and mean flake thickness increases from 2,200 to 5,800 nm if the grinding media size is reduced from 0.8 to 0.1 mm. This result shows that a high number of stress events in combination with low stress energy (small grinding media) facilitate delamination of the layered material whereas at high stress energies in combination with a low number of stress events (large grinding media) breakage of the layers dominates over delamination. The results of particle height analyses by AFM show that few-layer structures have been formed by stirred media milling. This result is in agreement with the layer thickness dependence of the delamination energy for hexagonal boron nitride. The concentration of nanoparticles remaining dispersed after centrifugation of the ground suspension increases with grinding time and with decreasing grinding media size. After 5 h of grinding using 0.1 mm ZrO grinding media the yield of nanoparticle formation is about 5 wt%. The nanoparticles exhibit the typical Raman peak for hexagonal boron nitride at 1,366 cm showing that the in-plane order in the milled platelets is remained. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Delamination; Hexagonal boron nitride; Stirred media mill

Design and scale-up of a semi-industrial downer-reactor for the rounding of irregular polymer particles - Peukert, Wolfgang; Sachs, Marius; Schmidt, Jochen; Wirth, Karl-Ernst (AIP Conference Proceedings 1713, 2016)
The recent development of rapid prototyping technologies towards additive manufacturing reveals some major drawbacks of processes such as laser beam melting (LBM). This contribution focuses on the lack of suitable polymer material with a fine particle size and good flowability. Polymer particles obtained by a wet grinding process 1 are treated in a heated downer reactor. This treatment changes the particles' morphology from a chiselled state towards a spherical form by surface tension forces in a molten state 2 and leads to an improved flowability. To reach the required amount of rounded polymer powder, a downer reactor in semi-industrial scale has been established and will be characterized in this article. For the purpose of particle rounding it is necessary to avoid contact of molten particles with each other and with the hot reactor walls. Furthermore, the heat distribution has been investigated as one of the key parameters of the process. Finally, a proof of concept by rounding wet grinded PBT material was successfully conducted. The product was examined to obtain data about a change in particle size and flowability.
Keywords: additive manufacturing; downer reactor; particle rounding; polymers

Design of a new invertible polymer coating on a solid surface and its effect on dispersion colloidal stability - Peukert, Wolfgang; Kohut, Ananiy; Ranjan, Sodhi; Voronov, Andriy; Tokarev, Victor; Bednarska, O.; Gevus, O.; et al. (Langmuir, 2006)
This article presents a new approach to building up self-adjustable invertible polymer coatings at solid surfaces. The approach is based on a two-step process. In the first step, the surface of dispersed TiO or silicon wafers was functionalized with the aid of a reactive copolymer, viz., poly(styrene-alt-maleic anhydride) (PSM), to which, in the second step, the chains of amphiphilic oligoester have been tethered. The latter contains both hydrophilic poly(ethylene glycol) and hydrophobic aliphatic dibasic acid moieties being alternately distributed along the oligomer chains. It is shown that the titania modified in this way can form stable suspensions in both polar (water) and nonpolar (toluene) media. Moreover, multiple drying/redispersion cycles demonstrate the ability of the modified titania particles, after their removal from one type of dispersion and consequent drying, to be redispersed in dispersing media strongly differing by polarity from that of the previous medium. An environmentally induced switching of the surface properties has been observed via the measurement of the wetting contact angles and scanning force microscopy (SFM) of silicon wafers covered by PSM with tethered oligoester chains. These experiments give strong support for the predicted capability of such polymer coatings to switch their environmental appearance (i.e., to behave as a self-adjustable invertible interface because of the ability of the tethered amphiphilic oligoester chains to change their conformations in response to environmental changes in such a manner so as to adapt and enhance their compatibility with the surrounding media). © 2006 American Chemical Society.
Keywords: surfaces; polymer; titan; oxide; dispersion

Detailed Analysis of the Growth Kinetics of ZnO Nanorods in Methanol - Voigt, Michael; Klaumünzer, Martin; Thiem, Heiko; Peukert, Wolfgang (Journal of Physical Chemistry C, 2010)
The growth kinetics of ZnO nanorods in methanol is studied by a combination of scanning and high-resolution transmission electron microscopy and X-ray diffraction analysis. In the early stage of growth oriented attachment of 2−3 spheroidal crystallites to rod-like structures occurs. Later, rods of up to 90 nm in length with a hexagonal cross-section up to 18 nm in diameter form by ripening. Our main finding is that the growth follows a power law as a function of the ripening time with exponents of 0.32 to 0.39 for the length and 0.17 to 0.21 for the diameter. In contrast to previous studies on the growth of ZnO rods in alcohols our results indicate that the growth is dominated by anisotropic Ostwald ripening that is limited by volume diffusion.

Detailed investigations of ZnO photoelectrodes preparation for dye sensitized solar cells - Marczak, Renata; Werner, Fabian; Ahmad, Rameez; Lobaz, Volodymyr; Guldi, Dirk Michael; Peukert, Wolfgang (Langmuir, 2011)
Wurtzite ZnO hexagonal nanopyramids were successfully synthesized in the liquid phase from homogeneous methanolic solutions of zinc acetate and tetramethylammonium hydroxide at an excess of zinc ions. The formation and properties of the nanocrystals were examined as a function of synthesis conditions. No significant influence of the [Zn ]/[OH ] ratio was noticed on the final particle size, in spite of increased amounts of OH ions, which tend to accelerate the particle nucleation and growth. Nevertheless, the reactant concentration ratio influences the surface properties of the ZnO nanocrystals. Mesoporous ZnO films were prepared by doctor blading ethanolic pastes containing ZnO nanoparticles and ethyl cellulose onto FTO conductive glass substrate followed by calcination. Additionally, the influence of a plasticizer (triacetin)-used during the paste preparation-on the film quality was investigated. A higher content of ZnO nanoparticles and plasticizer in the pastes improved the film quality. Four different temperatures (i.e., 400, 425, 450, and 475 °C) were used for the film calcination and their influence on the structural properties of the films was characterized. In principle, increasing the calcination temperature goes hand in hand with an increase of particle size, as well as the pore diameter and reduction of the surface area. Suitable mesoporous films were employed as photoanodes in dye sensitized solar cells (DSSCs). In order to assess the effect of the varied parameters on complete DSSC devices-using cis-diisothiocyanato-bis(2,2′- bipyridyl-4,4′-dicarboxylato) ruthenium(II)bis(tetrabutylammonium (N719) as a sensitizer-incident photon to current efficiency (IPCE) and current voltage measurements were carried out. The IPCE measurements confirmed photoinduced electron injection from the dye, reaching IPCE values up to 76%. Furthermore, current-voltage characteristics of complete cells emphasized the importance of the proper preparation methods and temperatures. These features are important assets for the preparation of nanocrystalline ZnO based photoelectrodes and for improving the DSSC performance. © 2011 American Chemical Society.

Determination of 2D Particle Size Distributions in Plasmonic Nanoparticle Colloids via Analytical Ultracentrifugation: Application to Gold Bipyramids. - Frank, Uwe; Drobek, Dominik; Sánchez-Iglesias, Ana; Wawra, Simon; Nees, Nico; Walter, Johannes; Pflug, Lukas; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Liz-Marzan, Luis M.; Peukert, Wolfgang (ACS nano, 2023)
Multidimensional particle properties determine the product properties in numerous advanced applications. Accurate and statistically meaningful measurements of complex particles and their multidimensional distributions are highly challenging but strongly needed. 2D particle size distributions of plasmonic nanoparticles of complex regular shape can be obtained from analytical ultracentrifugation experiments via the optical back coupling method. A workflow for the calculation of frictional properties of arbitrarily shaped nanoparticles was developed based on bead shell models and applied to gold bipyramids with a pentagonal cross-section. The obtained 2D particle length-diameter distributions and the reduced cumulative 1D length and diameter distributions were compared to transmission electron microscopy measurements. While we find very good agreement for most measurements, the obtained length and diameter distributions were shifted by a few nanometers for some samples. Transmission electron microscopy, energy-dispersive X-ray spectroscopy, electron tomography, and finite element modeling indicate that the shift originated from a slight mismatch between the assumed shape of the simulated perfect bipyramids and the real particle shape and composition due to the presence of silver in the particles. This study demonstrates the feasibility of the applied techniques for complex shape analysis of nanoparticle ensembles with unmatched particle count numbers.
Keywords: analytical ultracentrifugation; bead modeling; electron tomography; extinction cross section; gold bipyramids; optical back coupling; particle shape distribution

Determination of Hansen parameters for particles: A standardized routine based on analytical centrifugation - Süß, Sebastian; Sobisch, Titus; Peukert, Wolfgang; Lerche, Dietmar; Segets, Doris (Advanced Powder Technology, 2018)
Keywords: Particle interactions; Formulation; Dispersibility; Nanoparticles; Hansen solubility parameter

Determination of Hansen parameters for particles: A standardized routine based on analytical centrifugation - Süß, Sebastian; Sobisch, Titus; Peukert, Wolfgang; Lerche, Dietmar; Segets, Doris (Advanced Powder Technology, 2018)
Keywords: Particle interactions; Formulation; Dispersibility; Nanoparticles; Hansen solubility parameter

Determination of material properties relevant to grinding by practicable labscale milling tests - Peukert, Wolfgang; Vogel, Lutz (European Congress on Comminution, 2002)
The breakage probability of different materials can be described well by a single mastercurve comprising the breakage performance of various materials. The function which is obtained when the Weibull statistics is applied to particle breakage depends on the mass-specific impact energy, a minimum energy required to cause any particle fracture at all, the initial particle size and a material parameter which describes the material-specific breakage behaviour. The material parameters are determined by single particle experiments. This procedure under well known stressing conditions gives reproducible results. A second approach to determine the material parameters from more practicable and less time consuming labscale milling tests is presented.
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.determ
Keywords: grinding; labscale milling tests; weibull statistics

Determination of quantitative structure-property and structure-process relationships for graphene production in water - Nacken, Thomas; Damm, Cornelia; Xing, Haichen; Rüger, Andreas; Peukert, Wolfgang (Nano Research, 2015)
A scalable method for graphene and few-layer graphene (FLG) production by graphite delamination in aqueous solutions of the nonionic surfactant TWEEN®80 (TW80) using stirred-media mills is presented. Delaminated product analysis using statistical Raman spectroscopy yielded extensive processing-structure-property relationships that revealed how stress intensity and specific energy input, i.e., the process parameters, govern the yield of graphene production and defect formation. The dispersed carbon concentration increased but the content and the quality of the FLG product decreased sharply with higher specific energy input. The FLG content of the product was up to 90%, especially for low specific energy input. Moreover, Raman analyses revealed that stress intensities greater than about 1 nJ were related to significant defect formation in the product particles. Another key parameter for graphene production is solvent viscosity. The FLG concentration in the product increased by a factor of 10 when the solvent’s viscosity was increased from 1 to 6 mPa·s because shear- and friction-induced delamination was enhanced and in-plane fracture was reduced due to dampening of bead motion. Based on the processing-structure-property relationships found, we propose that the delamination process can be designed in such way that the product consists, almost totally, of FLG and that single-layer graphene is produced. The scalability of graphene production by stirred-media delamination was demonstrated when an increase in the batch size from 0.2 to 2 L had no significant effect on product quality. [Figure not available: see fulltext.]
Keywords: few-layer graphene; graphene; graphite delamination; process parameters; statistical Raman spectroscopy; stirred-media mill

Determination of specific and non-specific protein-protein interactions for beta-lactoglobulin by analytical ultracentrifugation and membrane osmometry experiments - Uttinger, Maximilian; Hundschell, Christoph S.; Lautenbach, Vanessa; Pusara, Srdjan; Bather, Simon; Heyn, Timon R.; Keppler, Julia K.; Wenzel, Wolfgang; Walter, Johannes; Kozlowska, Magdalena; Wagemans, Anja M.; Peukert, Wolfgang (Soft Matter, 2022)
Protein-protein interactions are essential for the understanding of biological processes. Specific protein aggregation is an important aspect for many biological systems. In particular, electrostatic interactions play the key role for protein-protein interactions, as many amino acids have pH-dependent charge states. Moreover, protein dissociation is directly related to the solution pH, ionic strength, temperature and protein concentration. The subtle interplay between different specific and non-specific interactions is demonstrated for beta-lactoglobulin (BLG) with a focus on low salt concentrations, thus mimicking technically relevant processing conditions. BLG is a well-characterized model system, proven to attain its monomer-dimer equilibrium strongly dependent upon the pH of the solution. In this manuscript, we present a unique combination of analytical ultracentrifugation and membrane osmometry experiments, which quantifies specific and non-specific interactions, i.e. in terms of the dimer dissociation constants and the second osmotic virial coefficient, at pH 3 and 7 and sodium chloride concentrations of 10 mM and 100 mM. This provides direct insight to protein-protein interactions for a system with a concentration-dependent monomer-dimer equilibrium. Moreover, using a coarse-grained extended DLVO model in combination with molecular dynamics simulations, we quantify non-specific monomer-monomer, monomer-dimer and dimer-dimer interactions as well as the binding free energy of BLG dimerization from theoretical calculations. The experimentally determined interactions are shown to be mainly governed by electrostatic interactions and further agree with free energy calculations. Our experimental protocol aims to determine non-specific and specific interactions for a dynamically interacting system and provides an understanding of protein-protein interactions for BLG at low salt concentrations.
Keywords: 2nd virial-coefficient; molecular-dynamics; sedimentation-velocity; aqueous-solutions; salt; equilibrium; stability; systems; range; solubility

Determination of specific and non-specific protein-protein interactions for beta-lactoglobulin by analytical ultracentrifugation and membrane osmometry experiments - Uttinger, Maximilian; Hundschell, C. S.; Lautenbach, Vanessa; Pusara, Srdjan; Bather, S.; Heyn, T. R.; Keppler, J. K.; Wenzel, W.; Walter, Johannes; Kozlowska, Mariana; Wagemans, A. M.; Peukert, Wolfgang (Soft Matter, 2022)
Protein-protein interactions are essential for the understanding of biological processes. Specific protein aggregation is an important aspect for many biological systems. In particular, electrostatic interactions play the key role for protein-protein interactions, as many amino acids have pH-dependent charge states. Moreover, protein dissociation is directly related to the solution pH, ionic strength, temperature and protein concentration. The subtle interplay between different specific and non-specific interactions is demonstrated for beta-lactoglobulin (BLG) with a focus on low salt concentrations, thus mimicking technically relevant processing conditions. BLG is a well-characterized model system, proven to attain its monomer-dimer equilibrium strongly dependent upon the pH of the solution. In this manuscript, we present a unique combination of analytical ultracentrifugation and membrane osmometry experiments, which quantifies specific and non-specific interactions, i.e. in terms of the dimer dissociation constants and the second osmotic virial coefficient, at pH 3 and 7 and sodium chloride concentrations of 10 mM and 100 mM. This provides direct insight to protein-protein interactions for a system with a concentration-dependent monomer-dimer equilibrium. Moreover, using a coarse-grained extended DLVO model in combination with molecular dynamics simulations, we quantify non-specific monomer-monomer, monomer-dimer and dimer-dimer interactions as well as the binding free energy of BLG dimerization from theoretical calculations. The experimentally determined interactions are shown to be mainly governed by electrostatic interactions and further agree with free energy calculations. Our experimental protocol aims to determine non-specific and specific interactions for a dynamically interacting system and provides an understanding of protein-protein interactions for BLG at low salt concentrations.
CRIS-Team WoS Importer:2022-09-09

Determination of the Lateral Dimension of Graphene Oxide Nanosheets Using Analytical Ultracentrifugation - Walter, Johannes; Nacken, Thomas; Damm, Cornelia; Thajudeen, Thaseem; Eigler, Siegfried; Peukert, Wolfgang (Small, 2014)
In this paper, a method to determine the lateral dimensions of 2D nanosheets directly in suspension by analytical ultracentrifugation (AUC) is shown. The basis for this study is a well-characterized and stable dispersion of graphene oxide (GO) monolayers in water. A methodology is developed to correlate the sedimentation coefficient distribution measured by AUC with the lateral size distribution of the 2D GO nanosheets obtained from atomic force microscopy (AFM). A very high accuracy can be obtained by virtue of counting several thousand sheets, thereby minimizing any coating effects or statistical uncertainties. The AFM statistics are further used to fit the lateral size distribution obtained from the AUC to determine the unknown hydrodynamic sheet thickness or density. It is found that AUC can derive nanosheet diameter distributions with a relative error of the mean sheet diameter of just 0.25% as compared to the AFM analysis for 90 mass% of the particles in the distribution. The standard deviation of the size-dependent error for the total distribution is found to be 3.25%. Based on these considerations, an expression is given to calculate the cut size of 2D nanosheets in preparative centrifugation experiments.

Determination of the length and diameter of nanorods by a combination of analytical ultracentrifugation and scanning mobility particle sizer - Thajudeen, Thaseem; Walter, Johannes; Srikantharajah, Rubitha; Lübbert, Christian; Peukert, Wolfgang (Nanoscale Horizons, 2017)
A combination of orthogonal measurement techniques is utilized in this study to predict the average lengths and diameters of colloidal nanorods. Sedimentation coefficient distributions and electrical mobility distributions obtained from analytical ultracentrifugation and a scanning mobility particle sizer, respectively, are used for the hydrodynamic correlation. The method is validated theoretically and application to Au and ZnO nanorod samples is shown. The results demonstrate that the combination of both measurement techniques is an excellent method for the two-dimensional characterization of nanorods.

Determination of the quantum dot band gap dependence on particle size from optical absorbance and transmission electron microscopy measurements - Segets, Doris; Lukas, Matthew; Klupp Taylor, Robin; Scheele, Marcus; Zheng, Haimei; Alivisatos, Pa; Peukert, Wolfgang (Acs Nano, 2012)
This work addresses the determination of arbitrarily shaped particle size distributions (PSDs) from PbS and PbSe quantum dot (QD) optical absorbance spectra in order to arrive at a relationship between band gap energy and particle size over a large size range. Using a modified algorithm which was previously developed for ZnO, we take only bulk absorption data from the literature and match the PSDs derived from QD absorbance spectra with those from transmission electron microscopical (TEM) image analysis in order to arrive at the functional dependence of the band gap on particle size. Additional samples sized solely from their absorbance spectra with our algorithm show excellent agreement with TEM results. We investigate the influence of parameters of the TEM image analysis such as threshold value on the final result. The band gap versus size relationship developed from analysis of just two samples lies well within the bounds of a number of published data sets. We believe that our methodology provides an attractive shortcut for the study of various novel quantum-confined direct band gap semiconductor systems as it permits the band gap energies of a broad size range of QDs to be probed with relatively few synthetic experiments and without quantum mechanical simulations. © 2012 American Chemical Societ
Keywords: absorbance spectra; automated TEM image analysis; optical properties; particle size distribution; PbS(e); quantum dot

Determination of the two-dimensional distributions of gold nanorods by multiwavelength analytical ultracentrifugation - Wawra, Simon; Pflug, Lukas; Thajudeen, Thaseem; Kryschi, Carola; Stingl, Michael; Peukert, Wolfgang (Nature Communications, 2018)
Properties of nanoparticles are influenced by various parameters like size, shape or composition. Comprehensive high throughput characterization techniques are urgently needed to improve synthesis, scale up to production and make way for new applications of multidimensional particulate systems. In this study, we present a method for measuring two-dimensional size distributions of plasmonic nanorods in a single experiment. Analytical ultracentrifuge equipped with a multiwavelength extinction detector is used to record the optical and sedimentation properties of gold nanorods simultaneously. A combination of sedimentation and extinction properties, both depending on diameter and length of the dispersed nanorods, is used to measure two-dimensional distributions of gold nanorod samples. The length, diameter, aspect ratio, volume, surface and cross-sectional distributions can be readily obtained from these results. As the technique can be extended to other non-spherical plasmonic particles and can be used for determining relative amounts of particles of different shapes it provides complete and quantitative insights into particulate systems.
EAM Import::2019-03-13

Determination of the yield, mass and structure of silver patches on colloidal silica using multiwavelength analytical ultracentrifugation - Meincke, Thomas; Walter, Johannes; Pflug, Lukas; Thajudeen, Thaseem; Völkl, Andreas; Cardenas Lopez, Paola; Uttinger, Maximilian; Stingl, Michael; Watanabe, Satoshi; Peukert, Wolfgang; Klupp Taylor, Robin (Journal of Colloid and Interface Science, 2022)
Anisotropic nanoparticles offer considerable promise for applications but also present significant challenges in terms of their characterization. Recent developments in the electroless deposition of silver patches directly onto colloidal silica particles have opened up a simple and scalable synthesis method for patchy particles with tunable optical properties. Due to the reliance on patch nucleation and growth, however, the resulting coatings are distributed in coverage and thickness and some core particles remain uncoated. To support process optimization, new methods are required to rapidly determine patch yield, thickness and coverage. Here we present a novel approach based on multiwavelength analytical ultracentrifugation (MWL-AUC) which permits simultaneous hydrodynamic and spectroscopic characterization. The patchy particle colloids are produced in a continuous flow mixing process that makes use of a KM-type micromixer. By varying the process flow rate or metal precursor concentration we show how the silver to silica mass ratio distribution derived from the AUC-measured sedimentation coefficient distribution can be influenced. Moreover, through reasoned assumptions we arrive at an estimation of the patch yield that is close to that determined by arduous analysis of scanning electron microscopy (SEM) images. Finally, combining MWL-AUC, electrodynamic simulations and SEM image analysis we establish a procedure to estimate the patch thickness and coverag
Keywords: ultracentrifugation; localized surface plasmon resonance; patchy particles; continuous flow synthesis; multidimensional characterization

Determination of Translational and Rotational Diffusivities of Anisotropic Nanoparticles by Heterodyne Polarized and Depolarized Dynamic Light Scattering - Wu, Wenchang; Chittem, Pranay; Meißner, Frederik; Damm, Cornelia; Peukert, Wolfgang; Fröba, Andreas Paul (Journal of Physical Chemistry C, 2024)
This work presents the determination of translational diffusivities DT and rotational diffusivities DR of gold nanorods and silver nanocubes using polarized and depolarized dynamic light scattering. In combination with a heterodyne detection scheme, the signal-to-noise ratio of the analyzed correlation functions is significantly improved, which reduces the uncertainties in the determined mean lifetimes of the fluctuations studied and, thus, in the diffusivities. The heterodyne detection scheme also simplifies the data evaluation when homodyne conditions cannot be realized. For nanorods with aspect ratios ranging from 3.6 to 4.8, DT and DR were determined with average expanded uncertainties of (6 and 8) %. DT and DR increase with increasing temperature. In contrast, no concentration dependence of the diffusivities could be found for particle concentrations close to infinite dilution. Based on their values and a model in the literature, the length and width of the nanorods could be determined to be in agreement with the values from electron microscopy with deviations of (12 and 16) %. In this work, it was also demonstrated that dynamic light scattering is applicable for the determination of DT and DR for nanocubes with small anisotropy, with expanded uncertainties of (1.4 and 12) %. Due to the small anisotropic contribution to the scattered light, DR could only be obtained by depolarized dynamic light scattering. The experimental DR values are smaller than those calculated theoretically by the Stokes–Einstein–Debye relation, which, however, considers the nanocubes as equivalent sphere
Keywords: Colloids; Diffusion; Dynamic light scattering; Light; Nanoparticles

Development of an advanced multiwavelength emission detector for the analytical ultracentrifuge - Lautenbach, Vanessa; Onishchukov, Georgy; Wawra, Simon; Frank, Uwe; Hartmann, Lukas; Peukert, Wolfgang; Walter, Johannes (Nanoscale Advances, 2024)
An advanced design of the analytical ultracentrifuge with multiwavelength emission detection (MWE-AUC) is presented which offers outstanding performance concerning the spectral resolution and range flexibility as well as the quality of the data acquired. The excitation by a 520 nm laser is complemented with a 405 nm laser. An external spectrograph with three switchable tunable gratings permits optimisation of the spectral resolution in an order of magnitude range while keeping the spectral region broad. The new system design leads also to a significant reduction of systematic signal noise and allows the assessment and control of inner filter effects. Details regarding the very large signal dynamic range are presented, an important aspect when studying samples in a broad concentration range of up to five orders of magnitude. Our system is validated by complementary studies on two biological systems, fluorescent BSA and GFP, using the commercial Optima AUC with absorbance detection for comparison. Finally, we demonstrate the capabilities of our second generation MWE-AUC with respect to multiwavelength characterisation of gold nanoclusters, which exhibit specific fluorescence depending on their structure. Overall, this work depicts an important stepping stone for the concept of multiwavelength emission detection in AUC. The MWE-AUC developed, being to our knowledge the first and sole one of its kind, has reached the development level suitable for the future in-depth studies of size-, shape- and composition-dependent emission properties of colloids.
CRIS-Team Scopus Importer:2024-03-22

Development of poly(L-lactide) (PLLA) microspheres precipitated from triacetin for application in powder bed fusion of polymers - Dechet, Maximilian; Demina, Anna; Römling, Lea; Gomez Bonilla, Juan Sebastian; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2020)
In this work, the development and processing behavior of poly(L-lactide) (PLLA) particles for powder bed fusion (PBF) of polymers obtained via a green and sustainable process route are thoroughly studied. Liquid-liquid phase separation and precipitation from triacetin, a non-toxic solvent, are applied for the production of highly spherical PLLA particles of excellent flowability. Starting from the measured cloud-point diagram of the PLLA-triacetin system, appropriate temperature profiles for the precipitation process are derived. The effect of process parameters on the product properties is addressed in detail; the PLLA particles are characterized regarding their size distribution and morphology. Furthermore, material properties including thermal behavior (c.f. processing window for powder bed fusion (PBF)) and powder flowability are assessed. The spherical PLLA particles of narrow size distribution display a wide sintering window of 59 K and an excellent flowability due to the intrinsic surface roughness of the particles. Thus, tensile test bars and complex porous gyroid specimens were successfully manufactured via PBF without the need for any additional surface functionalization of the particles with flow agents. The high potential of the newly developed PLLA powders produced via an environmentally friendly approach omitting the use of halogenated or toxic solvents, as well as flowing aids, is demonstrated by mechanical testing of the printed specimen

Die in-situ Adsorption als neuer Weg zur schonenden Gewinnung von Proteinen - Peukert, Wolfgang; Millitzer, Marcus; Wenzig, Edda (Chemie Ingenieur Technik, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.dieins
Keywords: adsorption

Diffusion of gold nanoparticles in porous silica monoliths determined by dynamic light scattering - Wu, Wenchang; Cui, Junwei; Sultan, Umair; Gromotka, Lukas; Malgaretti, Paolo; Damm, Cornelia; Harting, Jens; Vogel, Nicolas; Peukert, Wolfgang; Inayat, Alexandra; Fröba, Andreas Paul (Journal of Colloid and Interface Science, 2023)
Hypothesis: The applicability of the dynamic light scattering method for the determination of particle diffusivity under confinement without applying refractive index matching was not adequately explored so far. The confinement effect on particle diffusion in a porous material which is relevant for particle chromatography has also not yet been fully characterized. Experiments: Dynamic light scattering experiments were performed for unimodal dispersions of 11-mercaptoundecanoic acid-capped gold nanoparticles. Diffusion coefficients of gold nanoparticles in porous silica monoliths were determined without limiting refractive index matching fluids. Comparative experiments were also performed with the same nanoparticles and porous silica monolith but applying refractive index matching. Findings: Two distinct diffusivities could be determined inside the porous silica monolith, both smaller than that in free media, showing a slowing-down of the diffusion processes of nanoparticles under confinement. While the larger diffusivity can be related to the slightly slowed-down diffusion of particles in the bulk of the pores and in the necks connecting individual pores, the smaller diffusivity might be related to the diffusion of particles near the pore walls. It shows that the dynamic light scattering method with a heterodyne detection scheme can be used as a reliable and competitive tool for determining particle diffusion under confinement.
CRIS-Team Scopus Importer:2023-03-29
Keywords: Confinement; Diffusion; Dynamic light scattering; Gold nanoparticles; Porous material

Direct numerical simulation of water–ethanol flows in a T-mixer - Schikarski, Tobias; Peukert, Wolfgang; Avila, Marc (Chemical Engineering Journal, 2017)
The efficient mixing of fluids is key in many applications, such as chemical reactions and nanoparticle precipitation. Detailed experimental measurements of the mixing dynamics are however difficult to obtain, and so predictive numerical tools are helpful in designing and optimizing many processes. If two different fluids are considered, the viscosity and density of the mixture depend often nonlinearly on the composition, which makes the modeling of the mixing process particularly challenging. Hence water-water mixtures in simple geometries such as T-mixers have been intensively investigated, but little is known about the dynamics of more complex mixtures, especially in the turbulent regime. We here present a numerical method allowing the accurate simulation of two-fluid mixtures. Using a high-performance implementation of this method we perform direct numerical simulations resolving the spatial and temporal dynamics of water-ethanol flows for Reynolds numbers from 100 to 2000. The flows states encountered during turbulence transition and their mixing properties are discussed in detail and compared to water-water mixtures.
Keywords: Mixing; T-mixer; Direct numerical simulation; Miscible fluids; Water–ethanol; Transition to turbulence; Turbulent flows

Direct Tape Casting of Nanosized Al2O3 Slurries Derived from Autogenous Nanomilling - Vozdecky, Pavel; Roosen, Andreas; Knieke, Catharina; Peukert, Wolfgang (Journal of the American Ceramic Society, 2010)
Nanoparticles offer many advantages in the manufacture of ceramic products concerning processing and final properties, but are still difficult to process, and not all ceramic powder compositions can be obtained commercially like, e.g., alpha-alumina. In this paper, the production of alpha-alumina nanosized particles with a median size < 60 nm by a wet grinding process in a highly concentrated suspension of up to 49 wt% solid content starting from a commercial microsized powder is presented. Furthermore, the subsequent direct processing of these suspensions to ceramic green tapes via tape casting is performed. The effect of nanosized alpha-Al2O3 powders on the viscosity of slurries, the casting process, binder burnout, and sintering behavior is characterized. Flat and crack-free sintered substrates with a density > 95%TD, a submicrometer microstructure, and a translucent appearance could be obtained. A decrease of the sintering temperature, an improvement of the mechanical strength, and a lower surface roughness were achieved through the use of nanoparticles compared with particles in the micrometer size range.

Disperse forces of particle - surface interactions: direct AFM measurements and modelling - Peukert, Wolfgang; Götzinger, Martin (Powder Technology, 2003)
Fundamentals of particle–particle interaction are of great interest in agglomeration processes. Particle adhesion depends on dispersive forces (van der Waals force), local chemical bindings, Coulomb force and capillary attractions. Additionally, surface properties like roughness, adsorption layers and surface chemistry strongly affect adhesion forces. van der Waals interactions are poorly understood because popular ab initio force calculations for molecules like density functional theory (DFT) often do not lead to proper results. van der Waals forces are difficult to measure directly. We present direct measurements of particle–particle and particle–surface interactions in the gas phase carried out with an atomic force microscope (AFM). Special emphasis is given to a proper statistical treatment of the data. For modelling of particle adhesion, we use computer-assisted empirical potential methods. Parameters like adsorbed water and surface roughness are considered. We extract parameters for weak interactions from the Lifshitz theory and gas adsorption data. Adsorbing molecules can be used as probes to measure dispersive forces. Studying surface and particle properties combined with computer-assisted modelling is a basic requisite to reach the aim of predicting particle–particle interactions in industrial processes.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.disper
Keywords: AFM measurements; van der Waals forces; Adhesion; Adsorption; Alumina

Dispersing and stabilizing silicon nanoparticles in a low-epsilon medium - Reindl, Armin; Voronov, Andriy; Gorle, Prem Kumar; Rauscher, Martin; Roosen, Andreas; Peukert, Wolfgang (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2008)
One possible approach to prevent the oxidation of silicon nanoparticles during a dispersing process is to use a dispersing medium, which does not contain any oxygen atoms in its structure, e.g. toluene. However, dispersing nanoparticles in such a non-polar organic medium is a major challenge, because the particles tend to aggregate very easily. The attempt of wet-grinding non-stabilized SiNP in toluene with a stirred media mill results in mu m-sized aggregates that precipitate rapidly. In order to achieve stable suspensions with regard to aggregation a suitable additive, added during the process of dispersion, is necessary. The stabilizing efficiency of several different additives, mostly oligo- and polymeric compounds, was evaluated by investigating the aggregate formation via dynamic light scattering, complemented by scanning electron micrographs. This work demonstrates that the stability of the particulate system and therefore the formation of aggregates can be adjusted selectively by the choice of the additive towards well-dispersed or densified particles. The attachment of the additives upon the surface of the SiNP was examined by diffuse reflectance infrared Fourier transform spectroscopy and the surface coverage was quantified by a combination of thermogravimetric analysis and gas sorption experiments. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: silicon nanoparticles; dispersing; steric stabilization; stirred media mill; additive

Dispersing nanoparticles in liquids - Müller, Frank; Peukert, Wolfgang; Polke, Reinhard F.; Stenger, Frank (International Journal of Mineral Processing, 2004)
Dispersing particles in liquids is a key requirement for a diversity of applications including pigments for coating applications, ceramic materials, fillers in polymers and tailored rheology of suspensions. Dispersing is especially demanding when the primary particle size is in the nanometer size range. In order to overcome the adhesion forces, high stress intensities are required. However, the high mobility of primary particles may lead to fast aggregation. which has to be prevented by adequate stabilisation of produced primary particles.The dispersion apparatuses and their influencing parameters are discussed. A special problem is the evaluation of the degree of defragmentation. The results of different purposes are presented and discussed. Unanswered questions should lend to further investigations including systematic fundamental studies on model systems, to understand the product behaviour better. (C) 2004 Elsevier B.V All rights reserved.
Keywords: dispersing; defragmentation; liquids

Dispersing nanoparticles in liquids - Peukert, Wolfgang; Müller, F.; Polke, R; Stenger, Frank (European Congress on Comminution, 2002)
Dispersing particles in liquids is a key requirement for a diversity of applications including pigments for coating applications, ceramic materials, fillers in polymers and tailored rheology of suspensions. Dispersing is especially demanding when the primary particle size is in the nanometer size range. In order to overcome the adhesion forces, high stress intensities are required. However, the high mobility of primary particles may lead to fast aggregation, which has to be prevented by adequate stabilisation of produced primary particles. The dispersion apparatuses and their influencing parameters are discussed. A special problem is the evaluation of the degree of defragmentation. The results of different purposes are presented and discussed. Unanswered questions should lead to further investigations including systematic fundamental studies on model systems, to understand the product behaviour better.
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.disper
Keywords: dispersing; defragmentation; liquids

Dispersing silicon nanoparticles in a stirred media mill - investigating the evolution of morphology, structure and oxide formation - Frank, Gerhard; Peukert, Wolfgang; Reindl, Armin; Altin, Ergün; Aldabergenova, Saule (physica status solidi (a), 2007)
Silicon nanoparticles were dispersed for 24 hours in 1-butanol using a stirred media mill. Via this process intrinsically stable suspensions (in regard to aggregation) of Si nanoparticles were produced after 6 hours of dispersing. The evolution of morphology, particle size and structure was investigated by dynamic light scattering, X-ray diffraction, Raman spectroscopy and high resolution transmission electron microscopy as a function of dispersing time. The average crystallite size decreased from about 18 nm down to about 10 nm within 24 hours of milling as determined by X-ray diffraction and Raman scattering measurements. In addition careful analysis of the Raman spectra revealed a decrease of the crystalline volume fraction from 75% down to 24% and a corresponding increase of the amorphous phase. The microstructural development with varying crystallite size and crystalline volume fraction was directly confirmed by transmission electron microscopy measurements. Elemental analysis showed an increase of oxygen content that was directly proportional to the increase in specific surface area of the silicon nanoparticles during the dispersing process. The surface chemistry of the Si nanoparticles was analyzed by diffuse reflectance infrared Fourier transform spectroscopy that indicated vibrational bands of HSi-Si 3-xO x, SiO x, and residual 1-butanol. The final product of the dispersing process seems to be a two-phase mixture of amorphous Si and Si nanocrystallites covered with SiO x on the surface. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.disper
Keywords: nano; particle; dispersion

Dispersing silicon nanoparticles with a stirred media mill and subsequent functionalization with phenyl acetylene - Reindl, Armin; Cimpean, Carla Ramona; Bauer, Walter; Peukert, Wolfgang; Kryschi, Carola; Comanici, Radu; Ebbers, André (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2007)
Silicon particles were dispersed in 1-butanol using a stirred media mill. Morphology, size and bulk structure of untreated, ground and styrenyl-functionalized silicon nanoparticles (SiNP) were examined using high-resolution transmission electron microscopy (HRTEM), dynamic light scattering (DLS) and X-ray diffraction (XRD). The amorphous oxide shell of the SiNP was removed by hydrofluoric acid (HF) etching. The resulting hydride (H)-terminated SiNP surfaces were functionalized with styrene via hydrosilylation of phenyl acetylene. Evidences for the styrenyl termination of the SiNP through Sisingle bondC bonds were obtained from diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), solid-state C nuclear magnetic resonance (NMR) and HRTEM. © 2007 Elsevier B.V. All rights reserved.
Keywords: Silicon nanoparticles; Stirred media mill; Hydrosilylation; Nuclear magnetic resonance

Dispersion of aggregates in shear flow - Peukert, Wolfgang; et al. (2007 AIChE Annual Meeting, 2007)

Dispersion of aggregates in shear flow - Peukert, Wolfgang; et al. (2007 AIChE Annual Meeting, 2007)

Drag Force Simulation of Particle Agglomerates with the Lattice Boltzmann Method - Thürey, Nils; Rüde, Ulrich; Peukert, Wolfgang; Feichtinger, Christian; Binder, Christian; Schmid, Hans-Joachim (18th Symposium Simulationstechnique ASIM 2005 Proceedings, 2005)
In this work we show, that the Lattice Boltzmann method is capable of calculating the drag force on spheres with a sufficient accuracy. The main Interest lies on laminar flows around nano particle agglomerates. To give an overview over the simulated force accuracy the results are compared with analytical solutions. Thereby the benefit from curved boundary treatments such as [YD03] and [PL03] is taken into account. Through the use of curved boundary treatments the lattice radius of the spheres can be reduced and thus smaller domain sizes can be used with the same force accuracy. Further more, results for complex agglomerates are presented and compared to solutions of the Stokesian Dynamics approach [AS01]
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.lsinfs.dragfo_7
Keywords: drag; stokkesian; simulation; lattice; boltzmann

Dry particle coating of polymer particles for tailor-made product properties - Blümel, Christina; Schmidt, Jochen; Dielesen, Andrea; Sachs, Marius; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (AIP Conference Proceedings 1593, 2014)
Disperse polymer powders with tailor-made particle properties are of increasing interest in industrial applications such as Selective Laser Beam Melting processes (SLM). This study focuses on dry particle coating processes to improve the conductivity of the insulating polymer powder in order to assemble conductive devices. Therefore PP particles were coated with Carbon Black nanoparticles in a dry particle coating process. This process was investigated in dependence of process time and mass fraction of Carbon Black. The conductivity of the functionalized powders was measured by impedance spectroscopy. It was found that there is a dependence of process time, respectively coating ratio and conductivity. The powder shows higher conductivities with increasing number of guest particles per host particle surface area, i.e. there is a correlation between surface functionalization density and conductivity. The assembled composite particles open new possibilities for processing distinct polymers such as PP in SLM process. The fundamentals of the dry particle coating process of PP host particles with Carbon Black guest particles as well as the influence on the electrical conductivity will be discussed.<br
Keywords: agglomeration; dry particle coating; conductivity; percolation; impedance spectroscopy

Dry powder coating in additive manufacturing - Schmidt, Jochen; Peukert, Wolfgang (Frontiers of Chemical Science and Engineering, 2022)
Dry powder coating is used in many industries to tailor the bulk solid characteristics of cohesive powders. Within this paper, the state of the art of dry coating of feedstock materials for powder based additive manufacturing (AM) processes will be reviewed. The focus is on feedstock materials for powder bed fusion AM processes, such as powder bed fusion of polymers with a laser beam and powder bed fusion of metals with lasers or an electron beam. Powders of several microns to several ten microns in size are used and the feedstock’s bulk solid properties, especially the flowability and packing density are of immanent importance in different process steps in particular for powder dosing and spreading of powder layers onto the building area. All these properties can be tuned by dry particle coating. Moreover, possibilities to improve AM processability and to manipulate the resulting microstructure (c.f. grain refinement, dispersion strengthening) by adhering nanoparticles on the powders will be discussed. The efect of dry coating on the obtained powder properties along the whole AM process chain and the resulting part properties is assessed. Moreover, appropriate characterization methods for bulk solid properties of dry-coated AM powders are critically discussed<br

Dynamic range multiwavelength particle characterization using analytical ultracentrifugation. - Peukert, Wolfgang; Walter, Johannes (Nanoscale, 2016)
We demonstrate how a sophisticated data analysis methodology enables us to perform multiwavelength evaluations of dynamic rotor speed gradient experiments obtained by analytical ultracentrifugation equipped with a multiwavelength detector. Our data evaluation tool HDR-MULTIFIT allows for the accurate analysis of sedimentation coefficient distributions which can be converted to particle size distributions. By means of multiwavelength evaluation, species dependent extinction spectra can be determined even for complex mixtures. Moreover, optical and hydrodynamic properties can be correlated for spherical particles of known optical properties applying multiwavelength evaluation and Mie's theory leading to a significant increase in the dynamic range of the experiment. We provide the theoretical background about the operation principle of our methodology and compare the performance of the multiwavelength analysis to the conventional single wavelength analysis as it is applied in turbidity analysis. We validate our technique using NIST traceable reference particles and show that our technique is universally applicable to materials of known and unknown optical properties, thus clearly extending the possibilities of particle analysis.
Keywords: muliwavelength; ultracentrifugation; sedimentation; particle

Dynamics of fine grinding in a fluidized bed opposed jet mill - Köninger, Benedikt; Hensler, Timo; Romeis, Stefan; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
Keywords: Fine dry comminution; First order kinetics; Fluidized bed opposed jet mill; Process dynamics

Early Stages of Oriented Attachment: Formation of Twin ZnO Nanorods under Microwave Irradiation - Distaso, Monica; Mackovic, Mirza; Spiecker, Erdmann; Peukert, Wolfgang (Chemistry - A European Journal, 2012)
Let’s become twins! Early stages of formation of twin ZnO nanorods under microwave irradiation have been studied. The coupling of facets with the same polarity was triggered by the rough surface and the defect-rich microstructure of the constituent ZnO building blocks. Oriented attachment was found to be the underlying mechanism of the twinning process (see scheme).

Early stages of particle formation by in-situ UV-vis and HRS - Peukert, Wolfgang; Segets, Doris; Schürer, Benedikt (technical proceedings of the 2010 NSTI Nanotechnology Conference and Expo, 2010)
We present a new approach for the study of early states of particle formation that can be applied for precipitation processes that occur on timescales from milliseconds to several minutes. A T-shaped micro-mixer is used to precipitate nanoparticles at steady state conditions. The nucleation and growth of the nanoparticles occurs along the path through a transparent quartz capillary. Hyper Rayleigh scattering (HRS) and UV/Vis absorbance spectra are recorded simultaneously. By changing the measurement position along the capillary, different reaction stages of the nanoparticle formation process can be studied in detail. As the precipitation is performed at steady state the integration time for recording signals is not limited by the kinetics of the precipitation process. The HRS intensities and the particle size information can be used to calculate the nucleation and growth rates of the particle formation process.
Keywords: Hyper Rayleigh Scattering; Nanoparticle; Precipitation; UV-Vis; ZnO

Easy Room Temperature Synthesis of High Surface Area Anatase Nanowires with Different Morphologies - Schneider, Christopher; Liu, Ning; Romeis, Stefan; Peukert, Wolfgang; Schmuki, Patrik (ChemistryOpen, 2019)
Anatase nanowires were synthesized in solution by using a simple mixing of titanium diisopropoxide bis(acetylacetonate), lactic acid and sodium hydroxide at room temperature. We discuss effects of reaction parameters and post treatment (annealing) on the nanowire morphology, surface area, and crystallinity, as well as the competing morphology directing effects of lactic acid and sodium hydroxide. Then the room temperature nanowires were directly grown onto fluoride doped tin oxide (FTO) glass to form photoanodes. Photoelectrochemical measurements of the different nanowires were performed and compared to conventional nanowires produced by high temperature synthesis. Clearly the nanowires introduced in this work show a significant increase in the maximum photocurrent, compared to classic hydrothermal nanowire layers.
CRIS-Team Scopus Importer:2019-05-02
Keywords: lactic acid; low temperature processes; nanowires; sodium hydroxide; titanium dioxide

Effective Ligand Engineering of the Cu2ZnSnS4 Nanocrystal Surface for Increasing Hole Transport Efficiency in Perovskite Solar Cells - Khanzada, Laraib Sarfraz; Levchuk, Ievgen; Hou, Yi; Azimi, Seyed Hamed; Osvet, Andres; Ahmad, Rameez; Brandl, Marco; Herre, Patrick; Distaso, Monica; Hock, Rainer; Peukert, Wolfgang; Batentschuk, Miroslaw; et al. (Advanced Functional Materials, 2016)
Effective engineering of surface ligands in semiconductor nanocrystals can facilitate the electronic interaction between the individual nanocrystals, making them promising for low-cost optoelectronic applications. Here, the use of high purity CuZnSnS (CZTS) nanocrystals as the photoactive layer and hole-transporting material is reported in low-temperature solution-processed solar cells. The high purity CZTS nanocrystals are prepared by engineering the surface ligands of CZTS nanocrystals, capped originally with the long-chain organic ligand oleylamine. After ligand removal, CZTS nanocrystals show substantial improvement in photoconductivity and mobility, displaying also an appreciable photoresponse in a simple heterojunction solar cell architecture. More notably, CZTS nanocrystals exhibit excellent hole-transporting properties as interface layer in perovskite solar cells, yielding power conversion efficiency (PCE) of 15.4% with excellent fill factor (FF) of 81%. These findings underscore the importance of removing undesired surface ligands in nanocrystalline optoelectronic devices, and demonstrate the great potential of CZTS nanocrystals as both active and passive material for the realization of low-cost efficient solar cells.
Keywords: CZTS solar cells; HTM; Inorganic nanocrystals; Ligand exchange; Perovskite

Effect of Fast Annealing on Structural Characteristics and Optical Properties of Cu2ZnSnS4 Absorber Films Deposited by Doctor-Blade Technique - Hassanien, A. E.; Abdelhaleem, Soraya; Ahmad, Rameez; Schuster, Matthias; Moustafa, S. H.; Distaso, Monica; Peukert, Wolfgang; Wellmann, Peter (Journal of Nanoelectronics and Optoelectronics, 2019)
Cu2ZnSnS4 of kesterite structure is a non-toxic, earth-abundant and low-cost alternative for Cu (In, Ga)Se-2 compound due to its direct band gap of similar to 1.5 eV and absorption coefficient higher than 10(4) cm(-1). The thin CZTS films were prepared by the Doctor-Blade technique as a cheap, simple and suitable process for large-scale production. The ink of CZTS nanoparticles was synthesized by a solvothermal method and dispersed in chloroform before deposition on glass substrates. The effect of annealing conditions (temperature and time) on the structural characteristics (phase formation and grain size) and optical properties (band gap) of CZTS thin films was investigated. The elemental composition of the CZTS films was investigated by energy dispersive X-ray spectroscopy. The films, before and after annealing, are rich in sulfur, which decreases with the increase of annealing temperature as a result of its evaporation at high temperature. X-ray diffraction analysis and Raman scattering measurements confirm the formation of the crystalline tetragonal phase of CZTS. Values of the optical band gap were estimated using Tauc equation and optical transmission data. The band gap decreases from 2.10 eV to 1.23 eV and the grain grows from 4.6 nm to 38.8 nm as the annealing temperature ascends. The dependence of band gap energy on the grain size is verified, thus, the size of the grain can be used as a factor tuning the band-gap energy.
CRIS-Team WoS Importer:2019-08-30

Effect of functionalization of colloidal gold on controlled flocculation by the ligand-receptor mechanism - Kogut, A.M.; Voronov, A.S.; Kislenko, V.N.; Peukert, Wolfgang (Russian Journal of Applied Chemistry, 2005)
Modification of colloidal gold particles with octadecanthiol and alkyl biotin, with the subsequent flocculation of these particles via introduction of a tetramer protein avidin, was studied.
Keywords: Gold; Biotin; Flocculation; Gold Particle; Colloidal Gold

Effect of grinding conditions on mechanochemical grafting of poly(1-vinyl-2-pyrrolidone) onto quartz particles - Damm, Cornelia; Mallembakam, Madhusudhan Rao; Peukert, Wolfgang (Advanced Powder Technology, 2010)
Grinding of quartz in an aqueous solution of 1-vinyl-2-pyrrolidone (VP) in a stirred media mill results in grafting of poly(1-vinyl-2-pyrrolidone) (PVP) onto the quartz particles as proven by FTIR-spectroscopy. The grinding kinetics, the particle size of the final product and the amount of PVP grafted onto the silica particles depend on grinding conditions like VP and quartz concentration, pH and size of grinding media. The grinding kinetics becomes slower in the presence of VP due to the damping effect of the forming PVP chains. The final particle size, however, is almost independent on VP concentration. The amount of PVP grafted onto the silica particles ground for 12 h increases with growing VP concentration because the amount of adsorbed VP and the polymerization rate increase with growing VP concentration. The primary particle size and the kinetics of particle breakage do not depend on the pH-value of the dispersing medium, whereas the degree of agglomeration of the particles decreases with increasing pH-value of the medium. Under alkaline conditions, however, less PVP is grafted onto the quartz particles than under neutral or strong acidic conditions. The reasons for these effects are pH-dependent interactions between the grafted PVP chains and the surface hydroxyl groups on the quartz particles. If the quartz concentration in the suspension decreases the grinding kinetics becomes much faster because the specific energy input increases with decreasing particle concentration if the other process parameters are kept constant. For a very low quartz concentration (1 wt.%), however, after 7 h of grinding the particle size measured by dynamic light scattering starts to increase with grinding time. SEM investigations reveal that grinding of 1 wt.% quartz in aqueous VP solution for longer than 7 h results in the formation of plate-like particles. © 2009 The Society of Powder Technology Japan.
Keywords: Mechanochemical polymerization; Quartz; Reactive grinding

Effect of manganese, zinc, and copper on the biological and osteogenic properties of mesoporous bioactive glass nanoparticles - Westhauser, Fabian; Wilkesmann, Sebastian; Nawaz, Qaisar; Hohenbild, Frederike; Rehder, Felix; Saur, Merve; Fellenberg, Jörg; Moghaddam, Arash; Ali, Muhammad Saad; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Biomedical Materials Research Part A, 2020)
Mesoporous bioactive glass nanoparticles (MBGNs) have demonstrated promising properties for the local delivery of therapeutically active ions with the aim to improve their osteogenic properties. Manganese (Mn), zinc (Zn), and copper (Cu) ions have already shown promising pro-osteogenic properties. Therefore, the concentration-dependent impact of MBGNs (composition in mol%: 70 SiO2, 30 CaO) and MBGNs containing 5 mol% of either Mn, Zn, or Cu (composition in mol%: 70 SiO2, 25 CaO, 5 MnO/ZnO/CuO) on the viability and osteogenic differentiation of human marrow-derived mesenchymal stromal cells (BMSCs) was assessed in this study. Mn-doped MBGNs (5Mn-MBGNs) showed a small “therapeutic window” with a dose-dependent negative impact on cell viability but increasing pro-osteogenic features alongside increasing Mn concentrations. Due to a constant release of Zn, 5Zn-MBGNs showed good cytocompatibility and upregulated the expression of genes encoding for relevant members of the osseous extracellular matrix during the later stages of cultivation. In contrast to all other groups, BMSC viability increased with increasing concentration of Cu-doped MBGNs (5Cu-MBGNs). Furthermore, 5Cu-MBGNs induced an increase in alkaline phosphatase activity. In conclusion, doping with Mn, Zn, or Cu can enhance the biological properties of MBGNs in different ways for their potential use in bone regeneration approaches.
CRIS-Team Scopus Importer:2020-12-25
Keywords: copper; manganese; mesoporous bioactive glass nanoparticles; osteogenic differentiation; zinc

Effect of particle presence on gas phase temperature in the flame spray pyrolysis - Peukert, Wolfgang; Engel, Sascha; Gao, Yi; Kögler, Andreas; Kilian, Daniel; Seeger, Thomas; Leipertz, Alfred (Nanotechnology 2012: Advanced Materials, CNTs, Particles, Films and composites (Volume 1), 2012)
For the production of manufactured nanoparticles at a commercial scale flame processes are most frequently used. An important basis for understanding the complexity of this process is the characterization of the combustion process in dependence of the operation conditions. As minor changes of process parameters have huge impact on the product, invasive classic methods would fail. Hence, there is a demand for non-invasive advanced optical measurement tools acquiring data regarding the flame and the particle formation without changing the product by the applied measuring technique. In this work, gas phase temperatures, significantly influencing product particle sizes, were acquired by O -based pure rotational CARS during flame spray pyrolysis (FSP) and were compared for a particle-free and a particle-laden flame. Furthermore, the influence of different precursor concentrations on the distribution of the liquid regime was investigated by Mie scattering.
Keywords: Flame spray pyrolysis; Nanoparticles; Rotational CARS; Spray combustion; Temperature measurement

Effect of particle rounding on the processability of polypropylene powder and the mechanical properties of selective laser sintering produced parts - Gomez Bonilla, Juan Sebastian; Kletcher, Robin; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
Common techniques for the production of polymer powders for selective laser sintering (SLS) involve the comminution of polymers. Comminution of polymers often results in powders made of irregular shaped particles with a low bulk density and a bad flow behavior. With the aim to improve the flowability of grinded powders and, thus, the SLS processability, a thermal process for particle shape modification was developed. This has been applied successfully for a broad variety of thermoplasts. In this contribution, a modified design of a rounding reactor with direct heating and optimized geometry is presented. The performance of the new design is assessed by the rounding of commercially available polypropylene powders. The influence of the rounding process on the packing density, flowability and particle size and shape distributions of the powders is investigated. Test specimens produced by SLS were tested to assess the effect of the rounding process on the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Comminution; Compressive strength; Laser heating; Particle size; Polypropylenes; Powders; Sintering; Modified designs; Optimized geometries; Packing density; Particle size and shape; Polymer powders; Selective laser sintering (SLS); Shaped particles; Thermal process

Effect of pH and urea on the proteins secondary structure at the water/air interface and in solution - Guckeisen, Tobias; Hosseinpour, Saman; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2021)
Hypothesis: The secondary structure of proteins affects their functionality and performance in physiological environments or industrial applications. Change of the solution pH or the presence of protein denaturants are the main chemical means that can alter the secondary structure of proteins or lead to protein denaturation. Since proteins in the bulk solution and those residing at the solution/air interface experience different local environments, their response to chemical denaturation can be different. Experiments: We utilize circular dichroism and chiral/achiral sum frequency generation spectroscopy to study the secondary structure of selected proteins as a function of the solution pH or in the presence of 8 M urea in the bulk solution and at the solution/air interface, respectively. Findings: The liquid/air interface can enhance or decrease protein conformation stability. The change in the secondary structure of the surface adsorbed proteins in alkaline solutions occurs at pH values lower than those denaturing the studied proteins in the bulk solution. In contrast, while 8 M urea completely denatures the studied proteins in the bulk solution, the liquid/air interface prevents the urea-induced denaturation of the surface adsorbed proteins by limiting the access of urea to the hydrophobic side chains of proteins protruding to air.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Circular dichroism (CD); Denaturation; Proteins secondary structure; Sum frequency generation (SFG) spectroscopy

Effect of polymer species and concentration on the production of mefenamic acid nanoparticles by media milling - Peukert, Wolfgang; Ito, A; Konnerth, Christoph-Günther; Schmidt, Jochen (European Journal of Pharmaceutics and Biopharmaceutics, 2016)
The effect of four structurally different polymer species (hydroxypropylcellulose, polyvinylpyrrolidone, vinylpyrrolidone-vinyl acetate copolymer and polyvinyl alcohol) on the production of mefenamic acid nanoparticles during media milling has been studied. It was found that product particle sizes are strongly determined by the type of polymeric stabiliser as well as by its concentration at constant process conditions. With respect to small product particle sizes an optimum excipient concentration was identified and adjusted for colloidal stability of the drug nanosuspensions. Furthermore, it was found that overdosing of excipients must be omitted to suppress ripening due to enhanced solubilisation phenomena. Hence, the smallest product particle sizes were obtained using a polymeric stabiliser which exhibits a high affinity to the model drug compound and a low solubilisation capacity. Affinities of each polymer species to mefenamic acid and corresponding surface concentrations were determined using straightforward and simple viscosity measurements of the supernatant. A relationship between polymer affinity, solubilisation capacity and limiting product particle size has been observed, which supports the hypothesis that final product particle sizes are rather determined by the solid-liquid equilibrium than by pure mechanical fracture.
Keywords: Active pharmaceutical ingredient; Formulation; Media milling; Mefenamic acid; Nanosuspension; Ripening; Solubilisation; Solubility; Surface concentration

Effect of process conditions on mechanical behavior of aluminium wrought alloy EN AW-2618 additively manufactured by Laser Beam Melting in powder bed - Karg, Michael; Ahuja, Bhrigu; Schaub, Adam; Schmidt, Jochen; Sachs, Marius; Mahr, Alexander; Wiesenmayer, Sebastian; Wigner, Leon; Wirth, Karl-Ernst; Peukert, Wolfgang; Merklein, Marion; Schmidt, Michael (Proceedings of Laser in Manfacturing Conference 2015, 2015)
Additive Manufacturing offers geometric freedom excellently suited for topology optimized light weight designs. Ideally these should be built from materials of high strength to weight ratio and high plastic formability- such as aluminium-copper wrought alloys. Al-Cu wrought alloys are considered much less suitable for welding without cracks, so processing them in Laser Beam Melting of Metals in powder bed (LBM) can be considered challenging. Today, the only class of aluminium alloys widely processed by LBM is that of aluminium-silicon cast alloys which are easily weldable. In this contribution, mechanical characteristics of LBM samples are presented and discussed. Tensile tests were conducted under variation of load direction relative to build-up direction and heat treatment. Pronounced anisotropy was observed. Remarkably, elongation at break of T6 heat treated samples pulled in build-up direction exceeds values from literature for conventionally manufactured EN AW-2618A. The chemical constitutions of both the powder and the LBM samples were analyzed and shown to be similar to the expected EN AW-2618A. For further interpretation, boundary conditions of sample production, metallographic microsections and fracture surfaces were considere
Keywords: Additive Manufacturing; high-strength Aluminium Copper Wrought Alloy EN AW-2618A; AlCuMgNi; 3.1924; Selective Laser Melting™; LaserCUSING™; Direct Metal-Laser-Sintering™

Effect of protein adsorption on the dissolution kinetics of silica nanoparticles - Ali, Muhammad Saad; Uttinger, Maximilian; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang (Colloids and Surfaces B-Biointerfaces, 2022)
Nanoparticulate systems in the presence of proteins are highly relevant for various biomedical applications such as photo-thermal therapy and targeted drug delivery. These involve a complex interplay between the charge state of nanoparticles and protein, the resulting protein conformation, adsorption equilibrium and adsorption kinetics, as well as particle dissolution. SiO2 is a common constituent of bioactive glasses used in biomedical applications. In this context, the dissolution behavior of silica particles in the presence of a model protein, bovine serum albumin (BSA), at physiologically relevant pH conditions was studied. Sedimentation analysis using an analytical ultracentrifuge showed that BSA in the supernatant solution is not affected by the presence of silica nanoparticles. However, zeta potential measurements revealed that the presence of the protein alters the particles' charge state. Adsorption and dissolution studies demonstrated that the presence of the protein significantly enhances the dissolution kinetics via interactions of positively charged amino acids in the protein with the negative silica surface and interaction of BSA with dissolved silicate species. Our study provides comprehensive insights into the complex interactions between proteins and oxide nanoparticles and establishes a reliable protocol paving the way for future investigations in more complex systems involving biological solutions as well as bioactive materials.

Effect of roughness on particle adhesion in aqueous solutions: A study of Saccharomyces cerevisiae and a silica particle - Götzinger, Martin; Weigl, Bernhard; Peukert, Wolfgang; Sommer, Karl (Colloids and Surfaces B: Biointerfaces, 2007)
An atomic force microscope (AFM) has been used to quantify the adhesion of living cells Saccharomyces cerevisiae on three different silica surfaces with defined roughness. The effects of support roughness on the adhesion forces of a smooth silica particle were studied in addition. A living single cell was immobilized at the apex of a tipless AFM cantilever using a key-lock mechanism. Adhesion was quantified from the force-distance data measured on a smooth silica substrate and two substrates coated with hydrophilic monodisperse silica particles with 110 and 240 nm in diameter to study the effect of roughness on particle adhesion. The AFM technique gives unique insight into the primary colonization event of biofilm formation. The new knowledge helps substantially to design surface coatings relevant for biotechnology, medicine and dentistry. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Saccharomyces cerevisiae; silica; adhesion; roughness; AFM

Effect of surfactants on the molecular structure of the buried oil/water interface - Hosseinpour, Saman; Götz, Vanessa; Peukert, Wolfgang (Angewandte Chemie International Edition, 2021)
The oil/water interface, for instance in emulsions, is often stabilized by surfactants. Hence, the co-existence of oil, water, and surfactant molecules at the buried oil/water interface determines macroscopic properties such as surface tension or emulsion stability. Utilizing an inherently surface sensitive spectroscopic method, sum frequency generation (SFG) spectroscopy, we show that adsorption of an anionic surfactant to the buried oil/water interface increases the magnitude of the interfacial electric field. Meanwhile, the degree of ordering of the interfacial oil molecules increases with the surfactant concentration due to the intercalation of aliphatic chains of interfacial oil and surfactant molecules. At sufficiently high surfactant concentrations, the interfacial charge reaches a maximum value and the interfacial oil molecules arrange in a fully ordered conformation, a state which coincides with the significant decrease in interfacial tension and increased emulsion stability.

Effect of the Counteranion on the Formation Pathway of Cu2ZnSnS4 (CZTS) Nanoparticles under Solvothermal Conditions - Ahmad, Rameez; Saddiqi, Naeem-ul-Hasan; Wu, Mingjian; Prato, Mirko; Spiecker, Erdmann; Peukert, Wolfgang; Distaso, Monica (Inorganic Chemistry, 2020)
Cu2ZnSnS4 and Cu2ZnSnSe4 (CZTS and CZTSe, respectively) and their mixed chalcogenide phase Cu2ZnSnSxSe4-x (CZTSS(e)) are benign and cheap photovoltaic absorber materials that represent a valuable alternative to the more expensive chalcogenide systems: i.e., Cu(In,Ga)SS(e)2 (CIGSS(e)). One of the main challenges related to the fabrication of CZTS(e) layers is the control over both the crystalline phase (tetragonal, cubic, or hexagonal) and the formation of binary (MS, M = Cu(II), Zn(II), Sn(II); M'2-xS, M'= Cu(I), x = 0, 0.2; M″S2, M″ = Sn(IV)) and ternary products (CTS phases, Cu2SnS3, Cu3SnS4) that hinder the performance of the corresponding devices. In the present work, we rationalize the formation pathway of the CZTS phase through binary and ternary products when salt precursors with chloride and acetate as counteranions, respectively, are employed. The results show that the counteranions have a remarkable influence on the formation pathway of CZTS nanoparticles. The use of chloride precursors leads to the predominant formation of CTSs ternary phases (Cu2SnS3, Cu3SnS4), whereas the formation of the CZTS phase is not observed even for higher temperature and longer reaction time (250 °C, 24 h). In the case of acetates the copresence of CZTS as the main product, together with binary and ternary phases, is observed in the early stages of the reaction even at lower temperature and shorter reaction time (200 °C, 2 h), while when the reaction time and temperature are increased, only the CZTS phase is observed. In addition to a careful microstructural characterization of the as-synthesized materials by Raman spectroscopy, X-ray diffraction (XRD), Energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), and high-resolution transmission electron microscopy (HRTEM), we shed light on the reactivity among the metal precursors, the organic ligand oleylamine, and the sulfur precursor carbon disulfide (CS2) by 13C nuclear magnetic resonance (13C NMR) and investigate in depth the effect on particle surfaces by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and XPS. A rationale for the formation pathway of CZTS nanoparticles is proposed and supported by experimental evidence.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Salts; Anions; Precursors; Nanoparticles; Organic compounds

Effects of an adhesive force of admixed particles on compressed packing fractions in a particle bed - Peukert, Wolfgang; Paul, Jonas; Koch, Thomas; Yoshida, Mikio; Sanagawa, Tomoya; Okano, Shun-ichiro; Oshitani, Jun; Yamamoto, Hiroaki; Gotoh, Kuniaki (Advanced Powder Technology, 2015)
One of the techniques for a reduction in particle cohesiveness is the admixing of nano-particles. However, the mechanism of cohesiveness reduction has not yet been clarified. In this study we focused on a compressed packing fraction as one of the values reflecting the cohesiveness and flowability in a compressed particle flow. In order to estimate the mechanism of the reduction, the effects of an adhesive force of admixed particles on the packing fraction were investigated experimentally. In the experiments, silica particles with 397 and 8 nm diameters were used as the main and the admixed particles, respectively. The surfaces of the admixed particles were modified chemically in order to vary their adhesive force with maintaining morphological and mechanical characteristics. At more than 2.0% mixing mass ratios, the decreasing rate with increasing the mass ratio in net difference value of packing fraction for modified admixed particles was smaller than that for the raw particles. A calculation of the packing fraction of the admixed particles in the voids of main particles revealed that difference of the decreasing rates could be attributed to the difference of cohesivenesses between raw and modified admixed particles. The maximum packing fraction achieved by the modified admixed particles was lower than that achieved by the raw admixed particles. However, when a mixture of main and admixed particles was packed by tapping, the packing fraction with modified admixed particles was higher than that with raw admixed particles. This implied that the adequate adhesive force of admixed particles is different by the applied compression force value.
Keywords: Admixture of nano-particles; Chemical surface modification; Compressed particle bed; Packing fraction

Effects of filter structure, flow velocity, particle concentration and fouling on the retention efficiency of ultrafiltration for sub-20 nm gold nanoparticles - Lee, Handol; Segets, Doris; Süß, Sebastian; Peukert, Wolfgang; Chen, Sheng Chieh; Pui, David Y.H. (Separation and Purification Technology, 2020)
Ultrafiltration techniques with membranes of pore sizes under 100 nm have been widely applied in drinking water, wastewater, semiconductor and pharmaceutical process water treatments for nanoparticle (NP) and pathogen removal. The most direct way to evaluate the membrane performance is to experimentally obtain the size fractional retention efficiency. However, the real-life performance of the membrane in terms of fouling (or loading) characteristics and the effects of the concentration of challenging particles and rate of flux (or filtration velocities) on the filtration efficiency during fouling have not been well understood. In this study, systematic filtration experiments for filtration efficiency at clean and loaded conditions were conducted for three different 50 nm rated membrane filters, including PTFE (Polytetrafluoroethylene), PCTE (Polycarbonate Track-Etched) and MCE (Mixed Cellulose Ester) membranes, against 5, 10 and 20 nm Au NPs at different feed concentrations and fluxes. The results showed that the effects of feed concentration and flux are significant. This study provides important insights of retention mechanisms and efficiency for different ultrafiltration membrane structures at varied filtration velocities and fouling characteristics giving clear directions of future NP ultrafiltration research.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Concentration effects; Diffusion deposition; Fouling effects; Surface interactions; Ultrafiltration

Effects of Medium pH and Preconditioning Treatment on Protein Adsorption on 45S5 Bioactive Glass Surfaces - Höhn, Sarah; Zheng, Kai; Romeis, Stefan; Brehl, Martin; Peukert, Wolfgang; de Ligny, Dominique; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Advanced Materials Interfaces, 2020)
Protein adsorption on 45S5 bioactive glass (BG, Bioglass) surfaces influences the biocompatibility of Bioglass and the cellular response to the material. The medium pH greatly affects protein adsorption behavior. However, the influence of pH variation on protein adsorption on Bioglass has not been investigated in detail before, although an acidifying pH has been observed in fractured or injured bone tissues. This study investigates how the medium pH (pH 7, 5, and 2) affects protein (serum albumin) adsorption on Bioglass with or without preconditioning in simulated body fluid (SBF). The results show that Bioglass can adsorb a larger amount of bovine serum albumin (BSA) than bioinert glasses at all tested pHs. The BSA adsorption on Bioglass surfaces is pH-dependent and a larger amount of adsorbed BSA is observed at lower pH (5 and 2). After preconditioning, BSA adsorption is significantly enhanced. However, the trend of pH-dependent adsorption is attenuated. No significant difference in BSA adsorption is observed at different pHs after preconditioning. The results reveal for the first time the influence of medium pH on protein adsorption on Bioglass with or without preconditioning treatment in SBF, which provides useful information for developing Bioglass based biomedical devices that will be in contact with protein-containing physiological fluids during applications.
CRIS-Team Scopus Importer:2020-05-29
Keywords: 45S5 Bioglass; bovine serum albumin; pH influence; preconditioning; surface reactivity

Effects of pH of processing-medium on re-dispersion of spray dried, crystalline nanoparticles of pure naproxen - Braig, Veronika; Konnerth, Christoph-Günther; Peukert, Wolfgang; Lee, Geoffrey (International Journal of Pharmaceutics, 2019)
Crystalline nanodispersions of naproxen stabilized with hydroxypropyl cellulose were prepared at different pHs both below and above the pK(a) of the drug. After spray drying together with lactose, the measured particle size of the rehydrated dispersions using laser light scattering/Mie analysis was found to depend strongly on the pH of the original, processed nanodispersion. The pH-dependent solubility of this weak acid resulted in formation of a dissolved fraction of drug in the nanodispersions, this being higher as the pH increases. There was therefore a loss of crystalline naproxen during processing at higher pH, with fewer and/or smaller nanoparticles in the nanodispersion after nanomilling. After spray drying, the dissolved naproxen fraction formed an amorphous solid, as shown by differential scanning calorimetry and X-ray powder diffraction. The amorphous fraction redissolves on re-hydration. An improved disaggregation and smaller particle size of the nanoparticles at higher pH was observed because of the lower amount of crystalline nanoparticles now present. If the pH of the nanodispersion during processing is kept below the pK(a) for a weak acid, then a high yield of nanoparticles should be expected with little formation of an amorphous phase of the drug.
CRIS-Team WoS Importer:2019-02-22

Efficient drug-delivery using magnetic nanoparticles–biodistribution and therapeutic effects in tumour bearing rabbits. - Peukert, Wolfgang; Tietze, Rainer; Lyer, Stefan; Dürr, Stephan; Struffert, Tobias; Engelhorn, Tobias; Schwarz, Marc; Eckert, Elisabeth; Göen, Thomas; Vasylyev, Serhiy; Trahms, Lutz; Dörfler, Arnd; et al. (Nanomedicine : nanotechnology, biology, and medicine, 2013)
To treat tumours efficiently and spare normal tissues, targeted drug delivery is a promising alternative to conventional, systemic administered chemotherapy. Drug-carrying magnetic nanoparticles can be concentrated in tumours by external magnetic fields, preventing the nanomaterial from being cleared by metabolic burden before reaching the tumour. Therefore in Magnetic Drug Targeting (MDT) the favoured mode of application is believed to be intra-arterial. Here, we show that a simple yet versatile magnetic carrier-system (hydrodynamic particles diameter <200nm) accumulates the chemotherapeutic drug mitoxantrone efficiently in tumours. With MDT we observed the following drug accumulations relative to the recovery from all investigated tissues: tumour region: 57.2%, liver: 14.4%, kidneys: 15.2%. Systemic intra-venous application revealed different results: tumour region: 0.7%, liver: 14.4 % and kidneys: 77.8%. The therapeutic outcome was demonstrated by complete tumour remissions and a survival probability of 26.7% (P=0.0075). These results are confirming former pilot experiments and implying a milestone towards clinical studies. FROM THE CLINICAL EDITOR This team of investigators studied drug carrying nanoparticles for magnetic drug targeting (MDT), demonstrating the importance of intra-arterial administration resulting in improved clinical outcomes in the studied animal model compared with intra-venous.
Keywords: treatment; drug; delievery; magnetic; nanoparticles

Efficient quenching sheds light on early stages of gold nanoparticle formation - Biegel, Markus; Schikarski, Tobias; Cardenas Lopez, Paola; Gromotka, Lukas; Lübbert, Christian; Völkl, Andreas; Damm, Cornelia; Walter, Johannes; Peukert, Wolfgang (RSC Advances, 2023)
The formation mechanism of plasmonic gold nanoparticles (Au NPs) by fast NaBH4 induced reduction of the precursors is still under debate. In this work we introduce a simple method to access intermediate species of Au NPs by quenching the solid formation process at desired time periods. In this way, we take advantage of the covalent binding of glutathione on Au NPs to stop their growth. By applying a plethora of precise particle characterization techniques, we shed new light on the early stages of particle formation. The results of in situ UV/vis measurements, ex situ sedimentation coefficient analysis by analytical ultracentrifugation, size exclusion high performance liquid chromatography, electrospray ionization mass spectrometry supported by mobility classification and scanning transmission electron microscopy suggest an initial rapid formation of small non-plasmonic Au clusters with Au10 as the main species followed by their growth to plasmonic Au NPs by agglomeration. The fast reduction of gold salts by NaBH4 depends on mixing which is hard to control during the scale-up of batch processes. Thus, we transferred the Au NP synthesis to a continuous flow process with improved mixing. We observed that the mean volume particle sizes and the width of the particle size distribution decrease with increasing flow rate and thus higher energy input. Mixing- and reaction-controlled regimes are identified.
CRIS-Team Scopus Importer:2023-07-21

Efficient synthetic access to cationic dendrons and their application for ZnO nanoparticles surface functionalization: New building blocks for dye-sensitized solar cells - Gnichwitz, Jan-Frederik; Marczak, Renata; Werner, Fabian; Lang, Nina; Jux, Norbert; Guldi, Dirk Michael; Peukert, Wolfgang; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A new concept for the efficient synthesis of cationic dendrons, 4-tert-butyl-1-(3-(3,4-dihydroxybenzamido)benzyl)pyridinium bromide (17), 1,1′-(5-(3,4-dihydroxybenzamido)-1,3-phenylene)bis(methylene) bis(4-tert-butylpyridinium) bromide (18), N1,N7-bis(3-(4-tert-butyl-pyridium- methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenyl-amino) -3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (19), and N1,N7-bis(3,5-bis(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3, 5-bis(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3, 4-dihydroxybenzamido)heptanediamide hexabromide (20), and their facile binding to zinc oxide (ZnO) nanostructures is introduced. Dendrons containing highly reactive benzylic bromides reacted readily with 4-tert-butyl-pyridine and resulted in cationic dendrons. Furthermore, these permanently positively charged dendrons were equipped with a catechol anchor group. This enabled ZnO surface functionalization by simple immersion. The adsorption of 17, 18, 19, and 20 on the colloidal nanoparticles was monitored by Langmuir isotherms. The highest obtained experimental loadings correspond to 99.5%, 98.6%, 99.1%, and 42.5% of the particle surface for 17, 18, 19, and 20, respectively. These results indicate insufficient adsorption of the largest molecule 20 leading to reduced colloidal stability of the nanoparticles, while an enhanced stability after grafting with 17, 18, and 19 was observed. Mesoporous films suitable for the use as electrodes in dye-sensitized solar cells (DSSCs) were prepared. Subsequently, the films were functionalized with 18, 19, or 20 and sensitized with zinc-5,15-bis-[2′,6′-bis-2″,2″-bis-(carboxy)- ethyl-methyl-4′-tert-butyl-pheny]-10,20-bis-(4′-tert-butylphenyl) porphyrin-octasodium-salt. UV-vis absorption spectra confirmed that 18, 19, and 20 are suitable for the stable electrostatic attachment of the dye. Current-voltage characteristics of complete cells demonstrated that increasing positive functionalization of the ZnO surface leads to decreased open circuit voltages (V ). All V values were around 0.4 V with a maximum for the 18 functionalized ZnO film of 0.45 V. The maximum cell efficiency obtained (0.31%) is rather high, considering the narrow spectral absorption of the dye and the rather thin ZnO films used. Finally, incident photon to current efficiency (IPCE) measurements confirmed photoinduced electron injection from the dye. These features are important assets for applications in particle technology and even facilitated advanced devices like a supramolecular DSSC complete with a subsequent layer of negatively charged porphyrins. © 2010 American Chemical Society.

Ein verallgemeinertes Modellierungswerkzeug für die numerisch effiziente Beschreibung mehrphasiger Fällungsprozesse - Peukert, Wolfgang; Haderlein, Michael; Segets, Doris; Sterbak, Martin (Chemie Ingenieur Technik, 2016)
Die Fällung in T-Mischern ist ein wichtiges Verfahren zur Partikelsynthese in wässriger Phase. Mischintensität, Komplexbildung und verschiedene Feststoffbildungsprozesse wie Keimbildung und Wachstum bestimmen maßgeblich die späteren Eigenschaften Dispersität und Zusammensetzung. Um die äußerst komplexe Interaktion dieser Prozesse numerisch zu beschreiben, wurde ein allgemein einsetzbares Modellierungswerkzeug entwickelt. Ein überarbeitetes Mischmodell gewährleistet Recheneffizienz und Flexibilität. Die Bildung chemischer Komplexe spielt für die Berechnung der Übersättigung eine entscheidende Rolle. Die Berechnung des chemischen Gleichgewichts wird durch die analytische Herleitung der Jacobi-Matrix des entsprechenden Gleichungssystems stark beschleunigt. Die Bildung beliebig vieler Feststoffphasen wird durch gekoppelte Populationsbilanzgleichungen modelliert, wobei auch hier mit der direct quadrature method of moments (DQMOM) ein numerisch effizientes Verfahren genutzt wird. Abschließend wird die Anwendung dieser Methode an einem anspruchsvollen Beispiel mit komplexer Hydrochemie und zahlreichen Feststoffphasen gezeigt. Diese Arbeit ist ein Teil von Dynsim-FP (SPP 1679)
Keywords: simulation; fällung; populationsbilanz

Electrical properties of solution processed layers based on Ge-Si alloy nanoparticles - Meric, Zeynep; Mehringer, Christian; Jank, Michael. P. M.; Peukert, Wolfgang; Frey, Lothar (MRS Advances, 2016)
Ge-Si alloy nanoparticles (NPs) covering the full range of compositions were studied in regard to their suitability as semiconducting channel layer in thin-film transistors (TFTs). Special focus is given to the influence of annealing and encapsulation techniques on the contact and channel properties. Therefore, electrical characterization methods separating contact from channel characteristics are highlighted and applied. It is demonstrated that appropriate passivation of the nanoparticle surfaces can improve the Ion/Ioff ratios by modulation of the density of free charge carriers and also can suppress hysteresis effects. Ge-rich NP alloys can generally be passivated more effectively regardless if passivation is done with solution-processed poly(methyl methacrylate) (PMMA) or by aluminum oxide (Al2O3) from Atomic Layer Deposition (ALD). Sufficient annealing improves the contact formation between aluminum electrodes and Ge-Si particles by modification of charge injection. The presented analysis leads to a better understanding interface and surface effects in porous nanoparticle semiconductors for application in TFT devices.
Keywords: thin film; passivation; nanostructure

Electrophoretic Deposition of alpha-Fe2O3/Chitosan Nanocomposite Coatings for Functional and Biomedical Applications - Cabanas Polo, Sandra; Distaso, Monica; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Nanoscience and Nanotechnology, 2015)
Promising composite coatings based on hematite (alpha-Fe2O3) mesocrystals of size 110 nm and chitosan (CHT) molecules for different biotechnological applications have been successfully obtained by electrophoretic deposition (EPD). Homogeneous and reproducible coatings have been obtained by studying and controlling the chemical interactions between both phases (alpha-Fe2O3 and CHT). A voltage of 25 V and a deposition time of 5 min were chosen as best deposition conditions, which resulted in highly homogeneous coatings with well-distributed alpha-Fe2O3 particles. According to TGA measurements, the content of alpha-Fe2O3 and chitosan in the final composite coating were found to be 74 and 26 wt%, respectively. The presence of both phases in the composite coating was determined by XRD analysis and the coatings microstructure was observed by SEM.
Keywords: Iron Oxide Nanoparticles; Chitosan; Composite Coating; Electrophoretic Deposition

Electrophoretic deposition of anisotropic α-Fe2O3/PVP/chitosan nanocomposites for biomedical applications - Ramos Rivera, Laura; Distaso, Monica; Peukert, Wolfgang; Boccaccini, Aldo R. (Materials Letters, 2017)
Electrophoretic deposition (EPD) has been used to fabricate composite coatings based on anisotropic hematite particles ( extgreeka-Fe2O3) comprising residual poly-N-vinyl-pyrrolidone (PVP) and chitosan (CHT) on stainless steel substrates. The experimental conditions towards homogeneous surface, non-delamination and good distribution of extgreeka-Fe2O3/PVP particles are described. The coatings were characterized by SEM, XRD and TGA. A molecular interaction between PVP adsorbed on the surface of the particles and CHT is identified.
EAM Import::2019-03-14
Keywords: Electrophoretic deposition; Hierarchical structures; Porous layers; PVP/Chitosan interaction

Electrophotographic Multilayer Powder Pattern Deposition for Additive Manufacturing - Stichel, Thomas; Brachmann, Clemens; Raths, Max; Dechet, Maximilian; Schmidt, Jochen; Peukert, Wolfgang; Frick, Thomas; Roth, Stephan (JOM Journal of the Minerals, Metals and Materials Society, 2019)
The use of electrophotographic polymer powder transfer for the preparation of patterned powder layers is discussed with respect to a possible multimaterial application in powder bed-based additive manufacturing technologies such as selective laser sintering (SLS). Therefore, an experimental setup with a two-chamber design was realized, enabling the electrophotographic transfer of SLS powder materials at typical process conditions. The powder development (pick-up) step was investigated thoroughly for different powder materials to provide deep understanding of the underlying electrostatic effects and the influence of distinct powder properties. While using two different development modes, differences in the development results were correlated to differences in their particle size distribution, bulk density, and relative permittivity. Moreover, a new strategy was invented, allowing the residual electrophotographic powder deposition to be in general independent from the already produced part height. This is known to be a huge challenge but is mandatory for the buildup of three-dimensional multimaterial components.
CRIS-Team Scopus Importer:2020-02-21

Electrostatic and steric stabilization of precipitated nanoscaled barium sulphate - Peukert, Wolfgang; Gradl, Johannes; Schwarzer, Hans-Christoph (2006 AIChE Spring National Meeting - 5th World Congress on Particle Technology, 2006)
Aggregation plays an important role in synthesizing nanoscaled particles e.g. by a precipitation process in a T-mixer. The possibility to stabilize barium sulphate suspensions electrostatically as well as sterically by adding different polymers is studied experimentally. The influence of the initial molar ration of Ba /SO " ions on the resulting particle size distribution is shown. To investigate the influence of the chemical composition and of the conformation of the polymer on the potential of stabilizing colloidal suspensions, which is coupled directly to their adsorption behaviour on the particle surface, three different polymers (PVA80 poly vinyl alcohol - 80%-hydrolyzed, PVA98 poly vinyl alcohol - 98%-hydrolyzed and Dapral GE202) are used as capping agents. In this study operating conditions are searched, where stabilizing by polymers is possible. However, polymers do not only influence the surface properties of the precipitated nanoparticles but reduce the turbulence of the flow field and consequently damp the mixing intensity. This is reflected in larger mean particle sizes of the precipitate.
Keywords: Aggregation; Barium sulphate; Electrostatic and steric stabilization; Polymer adsorption; Precipitation; Turbulence reduction

Elucidation of the Formation Mechanism of Metal-Organic Frameworks via in-Situ Raman and FTIR Spectroscopy under Solvothermal Conditions - Embrechts, Heidemarie; Kriesten, Martin; Hoffmann, Kilian; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Journal of Physical Chemistry C, 2018)
The metal–organic framework MIL-53(Al) serves as a model system in this study. Its formation mechanism in N,N-dimethylformamide (DMF) is elucidated through simultaneous FTIR and Raman spectroscopy and turbidity measurements collected under in-situ synthesis conditions in a custom-designed solvothermal reactor coupled with reaction sampling. Different synthesis steps are followed over synthesis time including a prenucleation building unit (PNBU) consisting of one linker molecule and one aluminum atom, the assembly of the PNBUs to MIL-53 nuclei in solution, the decomposition of DMF to formic acid and dimethylammonium, and finally the precipitation of the crystalline MOF phase. The rearrangement of the PNBU to form MIL-53 is identified as the rate-limiting reaction step responsible for the long induction time at low temperatures (<80 °C). MOF nucleation and particle growth is followed directly in-situ through a novel method—comparison of the temporal evolution of the respective FTIR and Raman bands. Analysis of the particles isolated after various synthesis times indicates that MIL-53(H2BDC) of low crystalline long-range order is formed initially, which quickly rearranges to form more ordered, crystalline particles with DMF inside of the pores (MIL-53(DMF)). It is to be expected that the synthesis steps elucidated herein can be generalized to the solvothermal synthesis of other metal–organic framework structures from metal salts and organic acid li
Keywords: Organic acids; Fourier transform infrared spectroscopy; Chemical synthesis; Metal organic frameworks; Raman spectroscopy; Bis(1; 3; 5-Benzenetricarboxylate)Tricopper(Ii); MIL-101; Metalorganic Framework; Crystalline materials; Dimethylformamide; Metals: Organic polymers; Organic solvents; Organometallics; Synthesis (chemical); Crystalline particles; Formation mechanism; Metal organic framework; N; N-Dimethylformamide; Rate-limiting reaction; Solvothermal conditions; Solvothermal synthesis; Turbidity measurements

Emerging Organic Surface Chemistry for Si Anodes in Lithium-Ion Batteries: Advances, Prospects, and Beyond - Chen, Zidong; Soltani, Askar; Chen, Yungui; Zhang, Qiaobao; Davoodi, Ali; Hosseinpour, Saman; Peukert, Wolfgang; Liu, Wei (Advanced Energy Materials, 2022)
Due to its uniquely high specific capacity and natural abundance, silicon (Si) anode for lithium-ion batteries (LIBs) has reaped intensive research from both academic and industrial sectors. This review discusses the ongoing efforts in tailoring Si particle surfaces to minimize the cycle-induced changes to the integral structure of particles or electrodes. As an upgrade or alternative to conventional coatings (e.g., carbons), the emerging organic moieties on Si offer new avenues toward tuning the interactions with various battery components that are key to electrochemical performances. The recent progress on understanding Si surfaces is reviewed with an emphasis on newly emerged diagnostic tools, which increasingly points to the critical role of organic components in stabilizing Si. The detailed analysis on the chemistry-structure-performance relationships in Si surface are discussed and the successful cases demonstrating the functions of the organic layers are provided, that is, via tailored interactions toward electrolyte or binder or conductive agents, are recapped. Various synthetic strategies for designing the surface organic layers are discussed and compared, highlighting the versatility and tunability of surface organic chemistry. The holistic considerations and promising research directions are summarized, shedding light on in-depth understanding and engineering Si surface chemistry toward practical LIBs application.
CRIS-Team WoS Importer:2022-07-29

eMoM: Exact method of moments—Nucleation and size dependent growth of nanoparticles - Pflug, Lukas; Schikarski, Tobias; Keimer, Alexander; Peukert, Wolfgang; Stingl, Michael (Computers & Chemical Engineering, 2020)
In this study we present a reformulation for a broad class of population balance equations that model nucleation and size dependent growth. This formulation enables the definition of new numerical methods, which have two advantages compared to existing schemes in the literature (e.g. finite volume type methods and methods based on the evolution of moments): i) higher precision due to non-smoothing and ii) less run-time in comparison to finite volume algorithms of equivalent accuracy. The described formulation represents the solution of the considered balance equation in terms of the solution of a scalar integral equation, which can then be exploited to establish efficient numerical solvers. The computation of a solution of an initial boundary value problem in space-time is thus reduced to a scalar integral equation, which considerably reduces the computational effort required for its approximation. The integral equation describes the exact evolution of the third moment of the solution, justifying the name for this method: the exact method of moments (eMoM).
CRIS-Team Scopus Importer:2020-03-20
Keywords: Crystallization; Fixed point equation; Growth; Integral equation; Method of moments; Nanoparticle; Nonlocal conservation laws; Nucleation; Population balance equation

Enhanced Crystallization of Lysozyme Mediated by the Aggregation of Inorganic Seed Particles - Weichsel, Ulrike; Segets, Doris; Thajudeen, Thaseem; Maier, Eva-Maria; Peukert, Wolfgang (Crystal Growth and Design, 2017)
We show that aggregation plays a major role in seeded growth of protein crystals. The seeded batch approach provides the opportunity to set the starting conditions for protein crystallization by adding a defined amount of well-characterized seed particles. The experimental observations for tetragonal hen egg-white lysozyme (LSZ) confirm the concept of the oriented aggregation of larger building blocks to form a protein crystal. It was shown that the aggregation of the seed particles/bioconjugates is advantageous for the product quality in terms of larger and more defined LSZ crystals and in terms of accelerated reaction kinetics. We present a population balance (PB) model for the seeded batch crystallization of LSZ considering the aggregation of growth units to form protein crystals. For the modeling of crystal growth, evolving particle size distributions (PSDs) of agglomerating LSZ molecules were measured by dynamic light scattering (DLS). Moreover, the aggregation of seed particles in LSZ solutions under crystallization conditions was investigated by DLS. In line with our expectations, the number of seeds was found to be important as it strongly affects the collision frequency in the aggregation term of our PB model. Finally, the applied model gives trends of the supersaturation depletion curves and orders of magnitude of the measured CSDs in particle size correctly, ranging from only a few nanometers up to micrometer-sized particles/crystals. Thus, by the combination of PB modeling and experimentally determined crystallization parameters, insights into the crystal formation mechanism were obtained. To the best of our knowledge, this is the first attempt to model growth within a crystal population by an aggregation mechanism induced by seeding with foreign particles.

Enhanced dissolution of naproxen from pure-drug, crystalline nanoparticles: A case study formulated into spray-dried granules and compressed tablets - Konnerth, Christoph-Günther; Peukert, Wolfgang; Braig, Veronika; Lee, Geoffrey (International Journal of Pharmaceutics, 2019)
This is a case study of the use of rapidly-dissolving naproxen crystalline nanoparticles to prepare compressed tablets. The dissolution rates of different formulations were determined: the crystalline pure-drug nanodispersion, a pure-drug microsuspension, a granule prepared by spray drying the nanodispersion with mannitol, and a tablet prepared by compressing the granule with a bulking agent and a disintegrant. The goal was to determine the influence of each of the process steps on the rapid dissolution of the nanodispersion. A procedure was developed to allow sampling during the first 120 s of dissolution. Dissolution of the nanodispersion was completed after 60 s under both sink and non-sink conditions. Spray drying with mannitol delayed dissolution slightly under both sink and non-sink conditions. Under sink conditions a microsuspension (volume median size 11 µm) showed similar rapid dissolution to the nanodispersion. We propose this to be a result of rapid shrinkage of the microparticles on dissolution under sink conditions. This nullifies any effects of specific surface on dissolution rate. Under non-sink conditions the microparticles retain their lower specific surface for a longer time during dissolution and dissolve therefore more slowly. When compressed into tablets, the dissolution rates of nanoparticles or microparticles were determined primarily by the tablet disintegration time; the influence of sink or non-sink conditions was only observable after disintegration.
UnivIS-Import:2019-08-15:Pub.2019.nat.dchph.lphte.enhanc
Keywords: Low-soluble drug; Dissolution; Spray-drying; Nanosuspension; Tablet

Enhanced Nucleation of Lysozyme Using Inorganic Silica Seed Particles of Different Sizes - Weichsel, Ulrike; Segets, Doris; Janeke, Stefanie; Peukert, Wolfgang (Crystal Growth and Design, 2015)
In this work we investigate the impact of differently sized plain silica nanoparticles (NPs) between 10 and 200 nm on the crystallization of lysozyme (LSZ). In the first part of our work we investigate the electrostatic interactions between LSZ and NPs by zeta potential measurements and place special emphasis on the adsorption behavior of LSZ@SiO2. The determined adsorption isotherms - derived from UV-vis spectroscopy - indicate that with increasing particle size more LSZ is adsorbed per NP surface area probably due to a size-dependent surface chemistry and the variation of surface curvature. Second, seeded crystallization experiments both at the microliter and milliliter scale and thus close to a technically relevant scale were performed. A clearly extended crystallization window upon the addition of seed particles toward lower protein and salt concentrations was found. Moreover, induction times of crystal formation and crystallization times were considerably reduced. These effects were intensified with the addition of larger seed particles. In general, with the addition of silica seed particles, a shift of the final crystal size distribution to larger structures is observed.

Enhancement of polyamide laser sinter powder reusability by acid catalyzed hydrolysis - Hesse, Nicolas; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2020)
This contribution introduces a method to reverse the deterioration in melt rheological behaviour (‘ageing’) of polyamide 12 that has previously been used in powder bed fusion processing by reduction of the polymers molecular weight via acid catalysed hydrolysis. Chosen hydrolysis conditions allow for a reconditioning below melting temperature and therefore leave the particulate nature of the powder intact while significantly improving the polymers rheological properties. The influences of different temperatures, acids and pH-values are investigated and the processability of recycled powders is assessed by melt rheological, optical and thermal characteristics.
Keywords: powder bed fusion; selective laser sintering; polyamide 12; powder reusability; hydrolysis; molecular chain length; zero shear viscosity

Enhancing In Vitro Bioactivity of Melt-Derived 45S5 Bioglass® by Comminution in a Stirred Media Mill - Romeis, Stefan; Hoppe, Alexander; Eisermann, Claudia; Schneider, Nadine; Boccaccini, Aldo R.; Schmidt, Jochen; Peukert, Wolfgang (Journal of the American Ceramic Society, 2014)
45S5 Bioglassâ (45S5 BG) is a frequently applied Type A bioactive material, capable of forming an inherent bond to bone and soft tissue. Currently, applied melt-derived bioactive glass powders (BG) exhibit particle sizes between a few to several hundred micrometers. Recent studies on nanometer-sized bioactive glasses (nBGs), produced by bottom-up methods like sol– gel processing or flame spray pyrolysis, have indicated their great potential for several biomedical applications. In this study, the feasibility of top-down processing starting from bulk 45S5 BG by wet comminution in a stirred media mill was investigated. The products were assessed by in vitro hydroxycarbonate apatite (HCAp) formation in simulated body fluid, which is a marker for bioactive behavior. The study reveals the paramount influence of the used solvent for a successful topdown processing: In comparison with the as-received material bioactivity is lost for powders processed in water, preserved for comminution in ethanol and increased for powders processed using the alcohols n-butanol, n-pentanol, and n-hexanol. It was also found that only for the latter solvents, the chemical composition of the glass is maintained during comminution. Flakelike, slightly porous particles with specific surface areas of  25–30 m2/g are obtained. Thus, the presented comminution approach offers a convenient technique to process 45S5 BG with enhanced bioactivity.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.enhanc

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances - Düsenberg, Björn; Kopp, Sebastian-Paul; Tischer, Florentin; Schrüfer, Stefan; Schmidt, Jochen; Schmidt, Michael; Schubert, Dirk W.; Peukert, Wolfgang; Bück, Andreas; Roth, Stephan (Polymers, 2022)
Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives on the surface are used to evaluate the coating process. The thermal properties are analyzed by use of differential scanning calorimetry. Most important, the influence of the CCS on the powder charge is shown by measurements of the electrostatic surface potential at first and the powder deposition itself is performed and analyzed with selected formulations afterwards to show the potential of this method. Finally, tensile strength specimens are produced with the conventional deposition method in order to show the usability of the CCS for current machines.<br
Keywords: additive manufacturing; charge control substances; photoelectric powder deposition; polypropylene; dry coating

En route towards a comprehensive dimensionless representation of precipitation processes - Schikarski, Tobias; Avila, Marc; Peukert, Wolfgang (Chemical Engineering Journal, 2022)
Precipitation of (nano-) particles is a unit operation for the preparation of suspensions. Despite its widespread use, no general understanding is established of how different operating conditions, such as mixing rates or reactant concentrations, affect the precipitation outcome (e.g. the particle size distribution). We obtain overarching relations between the operating conditions and the precipitation outcome by deriving dimensionless numbers governing the precipitation process. In particular, we consider the interdiffusion of two chemical compounds reacting to a sparingly soluble salt by coupling the reaction–diffusion equations for the solute concentrations, to a population balance equation for the evolution of the dispersed phase including nucleation and growth. We vary the relevant process parameters for different chemical systems and uncover three dimensionless numbers, which fully determine the precipitation outcome under the assumption of fast chemical reactions. Two of these dimensionless numbers are Damköhler numbers, which put the relevant mixing kinetics in relation to the relevant time scales for the nucleation and the growth kinetics, respectively. The third dimensionless number corresponds to a dimensionless solid concentration. Simple functional expressions for the Damköhler numbers valid for any chemical system allow estimating whether the precipitation product is controlled by mixing, or solely by the kinetics of solid formation. In the mixing-controlled regime, scaling laws relate the mean particle sizes and the number of particles to the Damköhler number.
Keywords: Reactive precipitation; Nanoparticles; Nucleation; Growth; Damköhler number; Population balance equation

EPR investigations of non-oxidized silicon nanoparticles from thermal pyrolysis of silane - Jank, Michael; Frey, Lothar; Peukert, Wolfgang; Körmer, Richard; Wu, Jia; Otto, Michael (Physica Status Solidi, 2011)
Electron paramagnetic resonance (EPR) investigations of non-oxidized crystalline silicon nanoparticles (SiNP) from thermal silane pyrolysis revealed that the dangling bond (db) concentration strongly depends on the synthesis temperature. For SiNP synthesized at 1000-1200 °C and processed entirely in inert atmosphere, approximately 1013 cm-2 dbs were found which is at least one order of magnitude higher than the values previously reported for oxidized SiNP. After the synthesis, the dbs can be quenched by the addition of bromine (Br2) that proves their location at the particle surface. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-03-09:Pub.2011.tech.IE.LEB.eprinv
Keywords: Electron paramagnetic resonance; Nanoparticles; Pyrolysis; Silicon

Estimation of bivariate probability distributions of nanoparticle characteristics, based on univariate measurements - Furat, Orkun; Frank, Uwe; Weber, Matthias; Wawra, Simon; Peukert, Wolfgang; Schmidt, Volker (Inverse Problems in Science and Engineering, 2020)
The properties of complex particle systems typically depend on multivariate distributions of particle properties, like size and shape characteristics. Multidimensional particle property distributions can be a powerful tool to describe these systems. However, only few techniques exist which are able to simultaneously measure more than one property of individual particles in fast and efficient ways. It is shown how two-dimensional property spaces can be constructed by the combination of two univariate measurements to obtain bivariate particle size distributions. The proposed method is a general approach, which can be applied to a wide spectrum of particle systems and measurement devices. In this paper, the results of a case study are presented, which allow the estimation of bivariate distributions of length and diameter of nanorods, solely using univariate distributions of their particle mass and extinction-weighted sedimentation coefficient distributions. These quantities contain joint information about the particle lengths and diameters, which is used for the reconstruction. The method is validated in a simulation study in which the bivariate distribution to be reconstructed and the reconstruction parameters are varied. In addition, regularization techniques are introduced to reduce methodical errors. This approach can be transferred to other particle systems and measurement techniques, for which functional relationships between particle properties and measured quantities are well describe
Keywords: particle size distributions; reconstruction; inverse problem; Multidimensional characterization; copulas

Evaluation of the film formation and the charge transport mechanism of indium tin oxide nanoparticle films - Mahajeri, Mahdi; Voigt, Michael; Klupp Taylor, Robin; Reindl, Armin; Peukert, Wolfgang (Thin Solid Films, 2010)
The structure formation and charge transfer of thin nanoparticulate indium tin oxide (ITO) films prepared by dip-coating was studied as a function of stabilizer before and after annealing at different temperatures. The analysis of the film structure by optical methods revealed that it is a function of the stability. Suspensions containing an optimum stabilizer concentration of 0.1 mol/l resulted in densely packed films with a peak specific conductivity of 8.3 S cm− 1 after annealing at 550 °C for 1 h in air and 121 S cm− 1 after annealing in forming gas at 250 °C for 1 h, respectively. Furthermore, for the densely packed films fluctuation-induced tunnelling was found to be the dominant charge transport mechanism, whereas for the low density films a thermally activated charge transport was observed. That the films of maximum density showed a metallic charge transport behaviour at temperatures above 300 K indicated the optimal contact between ITO particles had been achieve
Keywords: Indium tin oxide; Nanoparticles; Dispersion; Stability; Transmittance; Conductance; Charge transport

Evolution of the fractal dimension for simultaneous coagulation and sintering - Schmid, Hans-Joachim; Al Zaitone, Belal; Artelt, Christian; Peukert, Wolfgang (Chemical Engineering Science, 2006)
Simulation results on the evolution of aggregate structure in aerosol processes with coagulation and sintering as the dominant mechanisms are presented. A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is applied. The model is based on a stochastic diffusion controlled cluster–cluster aggregation algorithm and sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow in order to maintain mass conservation. This leads to computer simulated structured aggregates which are then subject to evaluation. Two different methods to determine the fractal dimension are presented which give comparable results. It is shown that even very small particles show the same fractal behavior. Furthermore, equilibrium structures assuming a constant ratio of the characteristic collision time to the characteristic fusion time are considered as well as the kinetics of structural changes due to a change in the ambient condition
Keywords: Simulation; Sintering; Fractals; Coagulation; Particle formation; Nanostructure

Evolution of the Ligand Shell Around Small ZnO Nanoparticles During the Exchange of Acetate by Catechol: A Small Angle Scattering Study - Schindler, Torben; Lin, Wei; Schmutzler, Tilo; Lindner, Peter; Peukert, Wolfgang; Segets, Doris; Unruh, Tobias (ChemNanoMat, 2018)
The core‐shell structure of colloids surrounded by ligands is of great importance for their later application as it can significantly alter the chemical and physical properties of the nanoparticles (NPs). A combination of small angle X‐ray and neutron scattering (SAXS/SANS) in the native solution with additional ex situ measurements (titration‐UV) was applied to study the NP/ligand interface of ZnO NPs after functionalization with catechol derivatives. Based on SAXS data, it was found that within the multimodal particle size distribution the fraction of agglomerates is shifted to smaller sizes and nearly disappeared upon the binding of ethyl 3,4‐dihydroxybenzoate (CAT) molecules. This is ascribed to improved stabilization at the primary particle level by CAT molecules. By combining the neutron scattering contrast with the input of bound CAT molecules from a previously developed titration‐UV method, the heterogeneous composition of the ligand shell became accessible for the first tim
Keywords: quantum dots; Raman spectroscopy; core-shell; nanoparticles; small angle scattering

Experimental and numerical investigations of the influence of fluid dynamics on the precipitation of nanoscaled particles - Gradl, Johannes; Peukert, Wolfgang (4, 2007)
Continuous precipitation in a T-mixer is a promising way for the economic production of commercial amounts of nanoscaled particles. The challenge is to tailor the product properties of the precipitated particles, i.e. to control the particle size distribution (PSD). The coupling of all relevant subprocesses is the key for predicting the PSD. In this work the influence of the flow field conditions in a mixer on the precipitation process is investigated experimentally as well as numericall
Keywords: Mixing; Precipitation; Population balance equation

Experimental and Theoretical Studies of the Colloidal Stability of Nanoparticles−A General Interpretation Based on Stability Maps - Segets, Doris; Marczak, Renata; Schäfer, Stefan; Paula, Carolin; Gnichwitz, Jan-Frederik; Hirsch, Andreas; Peukert, Wolfgang (Acs Nano, 2011)
The current work addresses the understanding of the stabilization of nanoparticles in suspension. Specifically, we study ZnO in ethanol for which the Influence of particle size and reactant ratio as well as surface coverage on colloidal stability in dependence of the purification progress was investigated. The results revealed that the well-known zeta-potential determines not only the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. The acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Next to DLVO calculations based on the theory of Derjaguin, Landau, Verwey and Overbeek using a core shell model we find that the stability is better understood in terms of dimensionless numbers which represent attractive forces as well as electrostatic repulsion, steric effects, transport properties, and particle concentration. Evaluating the colloidal stability in dependence of time by means of UV-vis absorption measurements a stability map for ZnO is derived. From this map it becomes clear that the dimensionless steric contribution to colloidal stability scales with a stability parameter including dimensionless repulsion and attraction as well as particle concentration and diffusivity of the particles according to a power law with an exponent of -0.5. Finally, we show that our approach is valid for other stabilizing molecules like cationic dendrons and is generally applicable for a wide range of other material systems within the limitations of vanishing van der Weals forces in refractive index matched situations, vanishing zeta-potential and systems without a stabilizing shell around the particle surface.
Keywords: nanoparticles; stabilization; particle size; electrostatic; repulsion

Experimental study of metal nanoparticle synthesis by an arc evaporation/condensation process - Förster, Henning; Wolfrum, Christian; Peukert, Wolfgang (Journal of Nanoparticle Research, 2012)
The generation of copper nanoparticles in an arc furnace by the evaporation/condensation method is systematically investigated. The evaporation/condensation process is advantageous because it allows direct synthesis using pure metals as starting materials avoiding reactions of expensive and potentially poisonous precursors. In the presented system, a transferred direct current arc provides the energy for evaporation of the metal target. In order to prevent an oxidation of the particles in the process, the synthesis is conducted in an atmosphere of inert gases (purity grade 5.0). The arc stability and its effect on particle synthesis are investigated. The experiments reveal excellent long-term arc stability for at least 8 h continuous operation delivering aerosols with high reproducibility (+/- 10% of average particle size). The influences of the arc current and length, the flow rates of the applied gases and the injection of hydrogen in the plasma zone on the particle size distributions and the agglomerate structure are studied. The produced copper nanoparticles are characterized by scanning mobility particle sizing and scanning electron microscopy. The average particle size could be well controlled in a size range 4-50 nm by selecting appropriate operating parameters.
Keywords: Metal nanoparticles; Synthesis; Arc evaporation/condensation; Aerosol

Extension of the Deep UV-Capabilities in Multiwavelength Spectrometry in Analytical Ultracentrifugation: The Role of Oil Deposits - Walter, Johannes; Segets, Doris; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2016)
The optical performance of an analytical ultracentrifuge equipped with a fiber-coupled detector is investigated with special emphasis on the influence of oil leakage on the long-term deep ultraviolet stability. Two strategies for enhanced optical performance are presented. The first includes regeneration of fiber transmittance under atmospheric conditions, whereas the second utilizes an optimized vacuum system consisting of a turbomolecular pump.
EAM Import::2019-03-14

Fabrication, charge carrier transport, and application of printable nanocomposites based on indium tin oxide nanoparticles and conducting polymer 3,4-ethylenedioxythiophene/polystyrene sulfonic acid - Maksimenko, Ilja; Kilian, Daniel; Mehringer, Christian; Voigt, Michael; Peukert, Wolfgang; Wellmann, Peter (Journal of Applied Physics, 2011)
Printable transparent hybrid composites consisting of indium tin oxide (In2O3:Sn; ITO) nanoparticles and conducting polymer 3,4-polyethylenedioxythiophene (PEDOT) as matrix material were developed. The basic idea is to fill up the pores of the highly porous nanoparticulate ITO network to improve the interparticle contact and hence the conductivity of printed ITO thin films. Ready-to-use and stable aqueous dispersions were fabricated starting from ITO nanoparticles and aqueous formulation of conducting PEDOT and polystyrene sulfonic acid (PSS). This report presents and discusses key factors to obtain stable ITO-PEDOT dispersions with different mixing ratios and their application for printable devices as transparent electrode material. It was found that the f-potential value is crucial for preparation of stable dispersions. Electrical and optical properties of the hybrid ITO-PEDOT coatings were analyzed. Temperature dependent resistivity measurements reveal that conduction occurs by fluctuation induced tunneling. Transparent and conducting nanocomposite layers with a conductivity as high as 132 X1cm1 were fabricated by a low-temperature (T¼130 C) and entirely vacuum-free process. An all-printed electroluminescent lamp on a flexible substrate was realized as a demonstrator showing the applicability of such coatings for voltage-driven optoelectronic devices.<br

Fabrication of nanoparticulate inks for applications in printable electronics - Reindl, Armin; Aldabergenova, Saule; Altin, Ergün; Frank, Gerhard; Peukert, Wolfgang (4, 2007)
Semiconducting nanoparticles were dispersed systematically in organic solvents using a variety of methods. In the case of silicon particles prepared by gas phase synthesis a high specific energy input is necessary to obtain intrinsically stable suspensions. Therefore Si nanoparticles were dispersed for 24 hours in 1-butanol using a stirred media mill. Via this process intrinsically stable suspensions of Si nanoparticles were produced. The evolution of morphology, particle size and structure was investigated by dynamic light scattering, X-ray diffraction, Raman spectroscopy, and high resolution transmission electron microscopy as a function of dispersing time. The microstructural development with varying crystallite size and crystalline volume fraction was analyzed by Raman spectroscopy and directly confirmed by transmission electron microscopy measurements. The surface chemistry of the Si nanoparticles was analyzed by diffuse reflectance infrared Fourier transform spectroscop
Keywords: Raman spectroscopy; HRTEM; Stirred media mill; Silicon nanoparticles; XRD

Facile route to morphologically tailored silver patches on colloidal particles - Klupp Taylor, Robin; Bao, Huixin; Vasylyev, Serhiy; Peukert, Wolfgang; Tian, Chenting (Langmuir, 2010)
Here we demonstrate, for the first time, the heterogeneous nucleation and growth of silver patches on submicrometer silica spheres. While patches can be grown directly onto native silica particles, it is shown that a higher patch yield can be obtained by first treating the silica with a mixture of an alkanolamine and silver nitrate. Variation of the pretreatment and subsequent coating reactions allowed the patch yield, number, size, thickness, and shape to be adjusted. The patchy particles were shown to possess plasmon modes extending from the visible into the near-IR region, making these structures highly interesting for both their asymmetric morphological and functional properties.
Keywords: tailored; particle; colloid; heterogeneous; nucleation

Facile synthesis and post-processing of eco-friendly, highly conductive copper zinc tin sulphide nanoparticles - Ahmad, Rameez; Distaso, Monica; Azimi, Seyed Hamed; Brabec, Christoph; Peukert, Wolfgang (Journal of Nanoparticle Research, 2013)
Cu2ZnSnS4 (CZTS) nanoparticles have shown promising properties to be used as an energy harvesting material. They are usually synthesised under inert atmosphere or vacuum, whereas the subsequent step of film formation is carried out under an atmosphere of sulphur and/or Sn in order to avoid the decomposition of CZTS nanoparticles into binary and ternary species as well as the formation of the corresponding oxides. In the present paper we show that both the synthesis of CZTS nanoparticles and the film formation from the corresponding suspension can be considerably simplified. Namely, the synthesis can be carried out without controlling the atmosphere, whereas during the film annealing a nitrogen atmosphere is sufficient to avoid the depletion of the CZTS kesterite phase. Furthermore, an integrated approach including in-depth Raman analysis is developed in order to deal with the challenges associated with the characterization of CZTS nanoparticles in comparison to bulk systems. The formation of competitive compounds during the synthesis such as binary and ternary sulphides as well as metal oxides nanoparticles is discussed in detail. Finally, the as-produced films have ten times higher conductivity than the state of the art.
Keywords: By-products; Defects; Kesterite; Raman spectroscopy; Stannite CZTS nanoparticles; Thermodynamic study

Facile Synthesis of Gallium (III)-Chitosan Complexes as Antibacterial Biomaterial - Akhtar, Muhammad Asim; Hadzhieva, Zoya; Ilyas, Kanwal; Ali, Muhammad Saad; Peukert, Wolfgang; Boccaccini, Aldo R. (Pharmaceutics, 2021)
Even though antibiotic treatment remains one of the most common tools to handle bacterial infections, the excessive antibiotic concentration at the target site may lead to undesired effects. Aiming at the fabrication of antibiotic-free biomaterials for antibacterial applications, in this work, we propose the synthesis of gallium (III)-chitosan (Ga (III)-CS) complexes with six different gallium concentrations via an in situ precipitation method. Fourier Transform infrared spectroscopy indicated the chelation of chitosan with Ga (III) by peak shifts and changes in the relative absorbance of key spectral bands, while energy-dispersive X-ray spectroscopy indicated the homogenous distribution of the metal ions within the polymer matrix. Additionally, similar to CS, all Ga (III)-CS complexes showed hydrophobic behavior during static contact-angle measurements. The antibacterial property of the complexes against both Gram-negative and Gram-positive bacteria was positively correlated with the Ga (III) concentration. Moreover, cell studies confirmed the nontoxic behavior of the complexes against the human osteosarcoma cell line (MG-63 cells) and mouse embryonic fibroblasts cell line (MEFs). Based on the results of this study, new antibiotic-free antibacterial biomaterials based on Ga (III)-CS can be developed, expanding the scope of CS applications in the biomedical field.

Fast and Slow Ligand Exchange at the Surface of Colloidal Gold Nanoparticles - Dinkel, Rebecca; Braunschweig, Björn; Peukert, Wolfgang (Journal of Physical Chemistry C, 2016)
Applications of gold nanoparticles often demand that the particle's ligand shell is modified after particle formation. Obviously, there is a great need for a molecular understanding of this process which is often not accessible in situ. Here, we have applied second-harmonic light scattering (SHS) to investigate the ligand exchange at the surface of colloidal gold nanoparticles in situ and in real time. We demonstrate that the ligand exchange at the surface of citrate-covered Au nanoparticles with 3-mercapto-1-propanesulfonate (MPS) must be described by a fast (<100 s) and a slow reaction process (<23 min), which can be attributed to MPS adsorption on low- and high-coordinated Au surface sites. Using a modified Langmuir isotherm, the average Gibbs free energy of adsorption extgreekDG (-46 kJ/mol) and the surface coverage extgreekG ( 3.5 extgreekmmol/m2) for MPS on Au nanoparticles were determined. The latter was found to be much smaller compared to planar gold surfaces which points to coadsorption of MPS with citrate on high-coordinated sites, i.e., Au terraces. On more reactive low-coordinated Au sites, i.e., edge sites, citrate is easily replaced by MPS. In fact, we find that a substantial portion (49%) of the surface-adsorbed MPS is present on these low-coordinated sites.
EAM Import::2019-03-14

FIMOR: An efficient simulation for ZnO quantum dot ripening applied to the optimization of nanoparticle synthesis - Haderlein, Michael; Segets, Doris; Gröschel, Michael; Pflug, Lukas; Leugering, Günter; Peukert, Wolfgang (Chemical Engineering Journal, 2015)
This work presents the application of a Fully Implicit Method for Ostwald Ripening (FIMOR) for simulating the ripening of ZnO quantum dots (QDs). Its stable numerics allow FIMOR to employ the full exponential term of the Gibbs–Thomson equation which significantly outperforms the common Taylor-approximation at typical QD sizes below 10 nm. The implementation is consistent with experimental data for temperatures between 10 and 50 °C and the computational effort is reduced by a factor of 100–1000 compared to previous approaches. This reduced the simulation time on a standard PC from several hours to a few minutes. In the second part, we demonstrate the high potential and accuracy of FIMOR by its application to several challenging studies. First, we compare numeric results obtained for ripening of ZnO QDs exposed to temperature ramps with experimental data. The deviation between simulation and experiment in the mean volume weighted particle size was as small as 5%. Second, a map for the process parameter space spanned by ripening time and temperature is created based on a large number (>50) of FIMOR runs. From this map appropriate process parameters to adjust a desired dispersity are easily deduced. Further data analysis reveals in agreement with literature findings that the particle size distribution converges towards a self-preserving stable shape. Equations describing the time dependent particle size distribution with high accuracy are presented. Finally, we realized the transfer from low volume batch experiments to continuous QD processing. We modeled the continuous ZnO synthesis in a fully automated microreaction plant and found an excellent agreement between the numeric prediction and the experimental results by considering the residence time distribution.

First studies on the rheological behavior of suspensions in ionic liquids - Peukert, Wolfgang; Altin, Ergün; Gradl, Johannes (Chemical Engineering & Technology, 2006)
The suspension rheology of hematite in the ionic liquid Ecoeng ™.212 was studied in detail and compared to the pure ionic liquid. This is the first report on the rheological behavior of suspensions in ionic liquids, and it is postulated that colloidal stability and rheology must be considered to understand these results, and to overcome limitations on the production of nanosized particles in industrial applications. Concentrated suspensions of particles in the nanometer range show non-Newtonian flow behavior including shear thinning and shear thickening. These phenomena are mainly caused by particle-particle interactions in the suspension, and control of these interactions is critical. The influences of temperature and solid concentration on flow behavior were shown for the pure liquid and the suspensions. It is seen that the ionic liquid follows the Arrhenius equation for non-associating electrolytes. It is possible to shift all hematite suspension curves to a master curve according to the model of Gleiβle and Baloch. Furthermore, the flow behavior of the suspensions can be modeled with the well-known Herschel-Bulkley plot. A 10 wt % suspension of FeO follows Newtonian behavior over the entire range, similar to the pure ionic liquid. It is believed that the ionic liquid has an influence on the stability of the particles, leading to a decrease of attractive particle-particle forces. © 2006 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Ionic liquids; Rheology; Suspensions

Flowsheet simulation of integrated precipitation processes - Michaud, Mark; Haderlein, Michael; Segets, Doris; Peukert, Wolfgang (Dynamic Flowsheet Simulation of Solids Processes, 2020)
This work presents the fundamentals and exemplary applications of a generalized model for precipitation, aggregation and ripening processes including the formation of solid phases with two dimensions. The particle formation is governed by awidely applicable population balance approach. Solid formation processes are described via the numerically efficient Direct Quadrature Method of Moments (DQMOM), which can calculate the evolution of multiple solid phases simultaneously. The particle size distribution (PSD) is approximated by a summation of delta functions while the moment source term is approximated by a two-point quadrature. The moments to calculate the multivariate distributions are chosen carefully to represent the second order moments. Solid formation is based on themodel of Haderlein et al. (2017) and is extended by a multidimensional aggregation model. Now, the influences of mixing, complex hydrochemistry and particle formation dynamics including nucleation, growth and aggregation on multiphase precipitation processes are modelled and simulated along independent dimensions with high efficiency.
CRIS-Team Scopus Importer:2020-08-28

Formation and Dissolution of Twin ZnO Nanostructures Promoted by Water and Control over Their Emitting Properties - Distaso, Monica; Mackovic, Mirza; Spiecker, Erdmann; Peukert, Wolfgang (Chemistry - A European Journal, 2014)
By using ZnO as a model system, the formation of twinned nanostructures has been investigated under microwave irradiation, exploiting experimental conditions ranging from purely solvothermal when N,N-dimethylformamide was used, to purely hydrothermal when water was the solvent. A progressive increase in size, elongation and roughness of the surface was observed with increasing water content in the solvent mixture. Particular attention was paid to the reactivity of the ZnO surfaces towards dissolution. Our results show that the formation of twinned nanorods is a dynamic process and that the coupling interphase itself is highly reactive. Consequently, the twinned rods undergo a number of complex dissolution processes that are responsible for the appearance of a wide distribution of defects either on the surface or inside the structure. Poly(N-vinyl pyrrolidone) influences the photoluminescent properties of the as-synthesised materials and allows control of the ratio of the intensity of the UV and visible emission.

Formation of drug-loaded nanoemulsions in stirred media mills - Schwendner, Julia; Konnerth, Christoph-Günther; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang (Advanced Powder Technology, 2019)
The feasibility of stirred media mills for the production of nanoemulsions loaded with active pharmaceutical ingredients (API)using plant oils as disperse phase and different types of the non-ionic emulsifier polysorbate is demonstrated. The influence of the emulsion formulation, namely oil type, surfactant and surfactant-to-oil-weight-ratio (SOR)on the product droplet size at constant stressing conditions is studied in detail. At similar stressing conditions and SOR, the type of the used plant oil and surfactant did not influence the product droplet size and the smallest achievable median droplet size was 20 nm. The API saturated oil phases and the pure oil phases exhibit similar viscosities, emulsification kinetics and final product droplet sizes, i.e. no influence of the API on the emulsification process could be identified. However, a strong dependency of the emulsion droplet size on the SOR has been observed. Moreover, very good long-term stabilities could be achieved for the obtained emulsions. A release test with fenofibrate-loaded peanut oil-polysorbate 80-water nanoemulsions showed remarkably fast drug distribution as compared to a formulation containing the same amount of the non-dissolved micronized drug.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Active pharmaceutical ingredients; Formulation; In vitro release study; Nanoemulsion; Stirred media mill

Formation of Mefenamic Acid Nanocrystals with Improved Dissolution Characteristics - Konnerth, Christoph-Günther; Braig, Veronika; Schmidt, Jochen; Lee, Geoffrey; Peukert, Wolfgang; Ito, Atsutoshi (Chemie Ingenieur Technik, 2017)
An industrially feasible formulation approach combining media milling and spray-drying was applied to improve dissolu- tion characteristics of the poorly soluble drug mefenamic acid (MA). The approach was studied for two MA polymorphs at different stressing and pH conditions. It was found that final MA product particle sizes are rather determined by the solid-liquid equilibrium than by mechanical fracture. Obtained drug particles are only composed of the most stable poly- morph. Direct compressed tablets containing MA nanocrystals exhibit a significant improvement of in vitro dissolution kinetics as compared to tablets with micronized drug particles.
UnivIS-Import:2017-12-18:Pub.2017.nat.dchph.lphte.format
Keywords: Dissolution rate enhancement; Media milling; Nanocrystal; Polmorphism; Poorly water-soluble drug; Spray drying

Formation of nanoemulsions by stirred media milling - Schmidt, Jochen; Romeis, Stefan; Konnerth, Christoph-Günther; Damm, Cornelia; Peukert, Wolfgang (Proceedings 7th World Congress on Particle Technology, WCPT 2014, 2015)
Emulsions are widely used in the pharmaceutical and food industry. In recent years an increasing use of emulsion-based delivery systems for bioactive substances involving small particle sizes is notable. Apart from spontaneous formation of microemulsions, in general energy has to be introduced into the system, i.e. The formation process of nanoemulsions (thermodynamically metastable systems) is not spontaneous and the droplet-breakup process needs application of external energy input. Within this account we show that highly stable nanoemulsions can be produced by an alternative and scalable process applying stirred media milling. Alkane (hexadecane, dodecane)-Tween85-water-systems have been used as model emulsion systems to demonstrate the feasibility of the approach. The influence of fundamental process parameters such as emulsion formulation (c.f. oil mass fraction and oil-to-emulsifier mass ratio), stressing conditions (grinding bead size and stirrer tip speed), process time and especially temperature on the emulsion droplet size and size distribution has been studied in detail. Low oil-to-emulsifier ratios are most appropriate with respect to obtaining small mean droplet sizes and narrow droplet size distributions. It is shown that the smallest mean droplet sizes (at constant oil-to-emulsifier ratio) are obtained at the lowest oil mass concentrations. Product emulsions of Sauter diameters x below 25 nm have been obtained in the hexadecane-Tween85-water system using ZrO grinding beads of 100 μm and 400 μm in diameter, respectively. Interestingly, working at high stress intensities is not appropriate: higher stress intensities lead to a more intense mixing that increases the coalescence rate. Remarkably, lowering the process temperature below the solidification temperature of the oil phase, i.e. 'grinding' of the solid oil, is advantageous as compared to emulsification of the liquid oil: Coalescence and ripening can be significantly reduced. Smallest product droplets with x < 10 nm are obtained in the hexadecane-Tween85-water system after a short processing time of clearly below 1 hour. The feasibility of the process proposed to produce nanoemulsions using oil phases loaded with the hydrophobic organic compounds pyrene and trans-stilbene is demonstrate
Keywords: formulation; nanoemulsion; oil-in-water emulsion; stirred media mill

Formation of nanoemulsions in stirred media mills - Schmidt, Jochen; Damm, Cornelia; Romeis, Stefan; Peukert, Wolfgang (Chemical Engineering Science, 2013)
Alkane-Tween85-water-systems have been used as model emulsion systems to demonstrate the feasibility of emulsification in stirred media mills. The influence of fundamental process parameters, i.e. emulsion formulation (oil mass fraction and oil-to-emulsifier mass ratio), stress conditions (grinding bead size and stirrer tip speed), process time and especially temperature on the emulsion droplet size and size distribution has been studied for this approach. By lowering the process temperature below the solidification temperature of the oil phase, coalescence and ripening can be significantly reduced. Smallest product droplets with x<10nm thus are obtained even for nominal oil mass fractions up to 20wt% in the hexadecane-Tween85-water system. The feasibility of the process proposed to produce nanoscale emulsions using oil phases loaded with compounds such as pigments and other fillers is demonstrated. © 2013 Elsevier Ltd.
Keywords: Formulation; Nanoemulsion; Oil-in-water emulsion; Stirred media mill; Surfactant; Tween85

Formation of spherical micron-sized polyamide particles for additive manufacturing via liquid-liquid phase separation - Dechet, Maximilian; Kloos, Stephanie; Peukert, Wolfgang; Schmidt, Jochen (AIP Conference Proceedings, 2019)
Selective laser sintering (SLS) is an additive manufacturing (AM) process that yields excellent part qualities with good mechanical properties. The SLS process employs micron-sized polymer particles, which are selectively fused by a laser. While there seem to be hardly any boundaries regarding design, there are quite some restrictions concerning the variety of commercially available SLS materials. With a market share of roughly 90%, polyamide 12 (PA12) is currently the most widely used polymer material for SLS. In order to increase the understanding of the precipitation based manufacturing process for polyamide powders, production of polyamide 11 powders via precipitation in ethanol was investigated. The polymer particles need to be optimized regarding size, shape, flowability and packing characteristics. In this contribution particle manufacturing via liquid-liquid phase separation is discussed. Bulk polymer material of polyamide 11 is directly converted to spherical micron sized particles in a single unit operation. The produced particles are characterized regarding their size and morphology. Furthermore, also structural characteristics, crystallinity and flowability are analyzed and the product properties are correlated with process parameters. We discuss the potential of this process for the production of novel, easy-to-handle polymer particle systems for SLS.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Polymer powder; Precipitation; Selective laser sintering

Formulation of carbon black-ionomer dispersions for thin film formation in fuel cells - Hoffmann, Eva-Maria; Zhang, Su; Thoma, Martin; Damm, Cornelia; Peukert, Wolfgang (Particuology, 2019)
The performance of proton exchange membrane fuel cells (PEMFC) is strongly determined by the structure and composition of the electrode layer. The interactions between the ionomer, carbon black particles, and solvent affect the suspension properties and thus the layer morphology. We analyze the effect of the ionomer-to-carbon (I/C) weight ratio for two different types of carbon black on the suspension and layer characteristics. Highly branched carbon blacks with a high surface area tend to form less cracked layers. As less branched carbons can pack together more closely, a smaller pore size results in a larger capillary pressure during drying and thus more cracks. The added ionomer adsorbs on the carbon particles and improves the colloidal stability of the carbon black particles. The carbon black aggregates are thus smaller, resulting in closer packing and thinner layers. Moreover, the addition of the ionomer increases the critical coating thickness (CCT) of the layers because drying stresses are dissipated by the deformation of the ionomer, preventing crack formation. An optimum I/C weight ratio is identified for optimal layer formation and minimized crack formation.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Carbon black; Cracking; Layer formation; Perfluorosulfonic acid (PFSA) ionomer; Porosity

Fortschritte beim Erzeugen, Formulieren und Handhaben feinster Feststoffe; Product Design mit maßgeschneiderten Grenzflächen - Peukert, Wolfgang (Produktgestaltung und Grenzflächen, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.fortsc
Keywords: Grenzflächen; product; design

From evaporation-induced self-assembly to shear-induced alignment - Srikantharajah, Rubitha; Schindler, Torben; Landwehr, Inga; Romeis, Stefan; Unruh, Tobias; Peukert, Wolfgang (Nanoscale, 2016)
The functionality of compact nanostructured thin films depends critically on the degree of order and hence on the underlying ordering mechanisms during film formation. For dip coating of rigid nanorods the counteracting mechanisms, evaporation-induced self-assembly (EISA) and shear-induced alignment (SIA) have recently been identified as competing ordering mechanisms. Here, we show how to achieve highly ordered and homogeneous thin films by controlling EISA and SIA in dip coating. Therefore we identify the influences of the process parameters including temperature, initial volume fraction and nanorod aspect ratio on evaporation-induced convective flow and externally applied shear forces and evaluate the resulting films. The impact of evaporation and shear can be distinguished by analysing film thickness, surface order and bulk order by careful in situ SAXS, Raman and SEM-based image analysis. For the first time we derive processing guidelines for the controlled application of EISA and SIA towards highly ordered thin nematic films.

From in situ characterization to process control of quantum dot systems - Peukert, Wolfgang; Segets, Doris; Haderlein, Michael; Pflug, Lukas; Leugering, Günter; Gröschel, Michael (7th World Congress on Particle Technology, WCPT 2014, 2015)
Keywords: in situ; characterization; process design; optical properties; quantum dots

From molecules to materials: The cluster of excellence "engineering of Advanced Materials" at Friedrich-Alexander University of Erlangen-Nuremberg - Peukert, Wolfgang; Wasserscheid, Peter; Hirsch, Andreas (Advanced Materials, 2011)
Engineering of Advanced Materials - Hierarchical Structure Formation for Functional Devices (EAM) focus on the development of advanced materials with properties customized on the nano and mesoscale. The EAM network comprises scientists from different departments including Applied Mathematics, Chemical Engineering, Chemistry, Computer Science, Electrical Engineering, Materials Science, and Mechanical Engineering and Physics. The development of EAM has been encouraged by the acquisition of world-class scientific instruments. These include an FEI Titan 80-300 transmission electron microscope enhancing an aberration corrector to enable the high resolution imaging of nanomaterials in unprecedented clarity. The instrument also includes a full suite of state of the art spectroscopic and tomographic techniques. EAM is also focusing on hybrid electronic systems which exploit the advantages of both organic and inorganic materials.

From single particle impact behaviour to modelling of impact mills - Vogel, Lutz; Peukert, Wolfgang (Chemical Engineering Science, 2005)
An approach to quantify the impact grinding performance of different materials is presented. Based on a dimensional analysis and on fracture mechanical considerations two material parameters, fMat. and Wm,min, are derived from theoretical considerations. fMat. characterises the resistance of particulate material against fracture in impact comminution. Wm,min gives the mass specific energy which a particle can absorb without fracture. Using this approach various materials in a wide size range, e.g. different polymers, crystalline substances, glass and limestone, can be characterised quantitatively. The derived material parameters are applied to the systematic and multi-scale modelling of grinding in impact mills. A population balance model is presented and the results of the simulation for two different impact mills are shown. The developed model allows for a clear separation of the influence of material properties, mill specific features and operating conditions, thus enabling a deeper understanding of the impact grinding process. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.mechve.fromsi
Keywords: Comminution; Grinding; Impact mills; Material characterisation; Population balance model; Simulation

From Sticky to Slippery: Self-Functionalizing Lubricants for in Situ Fabrication of Liquid-Infused Surfaces - Chiera, Salvatore; Koch, Vanessa; Bleyer, Gudrun; Walter, Teresa; Bittner, Carina; Bachmann, Julien; Vogel, Nicolas (ACS Applied Materials and Interfaces, 2022)
Liquid-infused surfaces offer a versatile approach to create self-cleaning coatings. In such coatings, a thin film of a fluid lubricant homogeneously coats the substrate and thus prevents direct contact with a second, contaminating liquid. For stable repellency, the interfacial energies need to be controlled to ensure that the lubricant is not replaced by the contaminating liquid. Here, we introduce the concept of self-functionalizing lubricants. Functional molecular species that chemically match the lubricant but possess selective anchor groups are dissolved in the lubricant and self-adhere to the surface, forming the required surface chemistry in situ from within the applied lubricant layer. To add flexibility to the self-functionalizing concept, the substrate is first primed with a thin polydopamine base layer, which can be deposited to nearly any substrate material from aqueous solutions and retains reactivity toward electron-donating groups such as amines. The temporal progression of the in situ functionalization is investigated by ellipsometry and quartz crystal microbalance and correlated to macroscopic changes in contact angle and contact angle hysteresis. The flexibility of the approach is underlined by creating repellent coatings with various substrate/lubricant combinations. The prepared liquid-infused surfaces significantly reduce cement adhesion and provide easy-to-clean systems under real-world conditions on shoe soles.
CRIS-Team Scopus Importer:2022-04-22
Keywords: coatings; liquid-infused surfaces; polydopamine; self-cleaning; surface functionalization

From trash to treasure in additive manufacturing: Recycling of polymer powders by acid catalyzed hydrolysis - Hesse, Nicolas; Jaksch, Andreas; Kaschta, Joachim; Groh, Dominik; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2023)
A persistent problem in laser powder bed fusion (PBF) additive manufacturing (AM) of polymers is the accumulation of used feedstock material that cannot be reprocessed due to alterations in the physical and chemical structure upon ageing at elevated temperatures. The chemical ageing of polyamide 12, the most frequently used feedstock in PBF of polymers, occurs due to solid-state post-condensation during the AM process and can be reversed by appropriate processing. This paper investigates the application of acid-catalyzed hydrolytic reconditioning to restore virgin powder properties from used and annealed feedstock material, highlighting a pathway to more sustainability in AM. The proposed method is optimized towards PBF-printing relevant properties and mechanical characteristics of parts build with the recycled feedstock material, which are benchmarked against conventional powder refreshing strategies.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Hydrolysis; Polyamide 12; Polymer ageing; Polymer recycling; Powder bed fusion; Powder characterization

From visions to products in industrial crystallization - Peukert, Wolfgang; Eble, A (SCOPUS, 2005)
The current industrial trends related to crystallization are characterized by strong needs for cost reduction for production of commodities followed by globalization and a general shift towards high added-value products. New products with higher added-value are developed which are characterized not only by their state of crystallinity but also by their size, structure, surface properties in order to allow integration of these products in highly integrated products. The need for very specific properties of crystalline particles is a main driving force of nanotechnology. Predictive models including mixing, reaction, and nucleation will help to understand crystallization and to better take control on the underlying mechanisms.
Keywords: Industrial crystallization; Crystallization; VDI

Functionalization of polymer particles for additive manufacturing processes by plasma treatment in a fluidized bed reactor - Sachs, Marius; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (8th International Conference for Conveying and Handling of Particulate Solids, CHoPS 2015, 2015)
Recently additive manufacturing processes such as laser beam melting (LBM) of polymers have gained more importance for industrial applications [1]. Tailor-made modification of polymers is essential in order to make these processes more efficient and to cover the industrial demands. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. To overcome this limitation, a new route to functionalize the surface of commercially available polymer particles (PA12) using an atmospheric plasma jet in combination with a fluidized bed reactor (FBR) has been investigated. Consequently, an improvement of adhesion and wettability [2] of the polymer surface without restraining the bulk properties of the powder is achieved. The atmospheric plasma jet process can provide reactive species at moderate temperatures which are suitable for polymer material. The functionalization of the polymer powders improves the quality of the devices build in a LBM-proces
Keywords: additive; manufacturing; polymer; tailor-made; functionalization; stability

Functionalization of polymer powders for SLS-processes using an atmospheric plasma jet in a fluidized bed reactor - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (AIP Conference Proceedings 1664, 2015)
Recently additive manufacturing processes such as selective laser sintering (SLS) of polymers have gained more importance for industrial applications [1]. Tailor-made modification of polymers is essential in order to make these processesmore efficient and to cover the industrial demands. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. To overcome this limitation, a new route to functionalize the surface of commerciallyavailable polymer particles (PA12; PE-HD; PP) using an atmospheric plasma jet in combination with a fluidized bed reactor has been investigated. Consequently, an improvement of adhesion and wettability [2] of the polymer surface without restraining the bulk properties of the powder is achieved. The atmospheric plasma jet process can provide reactive species at moderate temperatures which are suitable for polymer material. The functionalization of the polymer powders improves the quality of the devices build in a SLS-proces
Keywords: Atmospheric Plasma Jet; Polymer Functionalization; Fluidized Bed Reactor; SLS-Process

Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and its impact on selective laser melting processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
In order to improve thermoplastic particles (e.g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Melting (SLM) processes a new approach for functionalization of temperature-sensitive polymer powders at large scales is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as plasma gas, radicals including OH* are generated. The functionalization leads to an increase of surface energy of the treated polymer powder without changing the bulk properties. Application of the functionalized polymers in a SLM process to build single layers leads to an improvement of the melted layer
Keywords: Atmospheric pressure plasma jet; Polymer functionalization; Fluidized bed reactor

Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and the impact on SLM-Processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (29th International Conference of the Polymer Processing Society, 2014)
In order to improve thermoplastics (e. g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Beam Melting (SLM) processes a new approach to functionalize temperature sensitive polymer powders in a large scale is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as the plasma gas, radicals like OH* are created. The functionalization leads to an increase of the hydrophilicity of the treated polymer powder without changing the bulk properties. Using the polymers in a SLM process to build single layers of melted material leads to an improvement of the melted layers.
Keywords: fluidized bed reactor; atmospheric pressure plasma jet; polymer functionalization

Functionalization of steel surfaces with organic acids: Influence on wetting and corrosion behavior - Alonso Frank, Micael; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang; Boccaccini, Aldo R.; Virtanen, Sannakaisa (Applied Surface Science, 2017)
Self-assembled monolayers (SAMs) have been used to tailor surface properties of different metal surfaces. Typically SAMs can be bound to surface hydroxyls of a thin oxide layer that forms on the surface of a less noble metal and dominates its properties. The effects of SAMs with different anchoring groups and chain lengths regarding wettability, corrosion resistance and homogeneity of the layer were studied in detail. Alkyl carbonic and phosphonic acids were selected to create a hydrophobic layer on the surface of stainless steel ASIS 316L and on carbon steel N80. SAMs were formed by dip-coating of the samples in an organic acid ethanolic solution. Sum frequency generation (SFG) analysis together with contact angle and electrochemical measurements were carried out to explore correlations between tailored wettability, corrosion resistance, and layer homogeneity on one side, and the chain length, anchor group, concentration and immersion time on the other side. The homogeneity of the layers as well as the resulting surface hydrophobicity increased with an increase of the immersion time, the contact angle reached a maximum (ca. 120°) for an immersion time of approximately 2 days.
Keywords: Carbon steel N80; Hydrophobicity; Myristic acid; Octadecylphosphonic acid (ODPA); Stainless steel 316 L; Stearic acid; Sum frequency generation; Surface functionalization

Gallium-rich Pd-Ga phases as supported liquid metal catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewitz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (Nature chemistry, 2017)
A strategy to develop improved catalysts is to create systems that merge the advantages of heterogeneous and molecular catalysis. One such system involves supported liquid-phase catalysts, which feature a molecularly defined, catalytically active liquid film/droplet layer adsorbed on a porous solid support. In the past decade, this concept has also been extended to supported ionic liquid-phase catalysts. Here we develop this idea further and describe supported catalytically active liquid metal solutions (SCALMS). We report a liquid mixture of gallium and palladium deposited on porous glass that forms an active catalyst for alkane dehydrogenation that is resistant to coke formation and is thus highly stable. X-ray diffraction and X-ray photoelectron spectroscopy, supported by theoretical calculations, confirm the liquid state of the catalytic phase under the reaction conditions. Unlike traditional heterogeneous catalysts, the supported liquid metal reported here is highly dynamic and catalysis does not proceed at the surface of the metal nanoparticles, but presumably at homogeneously distributed metal atoms at the surface of a liquid metallic phas

Gas phase synthesis of anisotropic silicon germanium hybrid nanoparticles - Mehringer, Christian; Wagner, Richard; Jakuttis, Thomas; Butz, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Aerosol Science, 2014)
We demonstrate the capability of hot wall reactor gas phase synthesis to produce germanium (Ge) on silicon (Si) anisotropic particles. A two stage reactor setup is used to produce silicon nanoparticles (SiNPs) of 29.6 nm in diameter with a very narrow size distribution and to deposit Ge on them. The gaseous precursors are monosilane (SiH4) and monogermane (GeH4). In a SEM study Ge patch formation on the SiNPs due to Stranski–Krastanov growth is observed. The patch size as well as the number of patches per SiNP is dependent on the process temperature and the GeH4 partial pressure. By varying these parameters it is possible to synthesize Janus-like particles with only one e.g. facetted Ge patch per SiNP, as well as patchy particles carrying an average of four to eight patches. HRTEM analysis shows, that the Ge grows epitaxial and crystalline on the surface of the SiNPs. From geometric phase analysis (GPA) the termination of inserted (220) half planes corresponding to misfit dislocations can be deduced, indicating a largely relaxed lattice in the Ge patches. A continuous tilt of the (111) lattice planes in the Si core below a Ge patch indicates that elastic deformation also contributes to the strain relaxation.

Gas phase temperature measurements in a flame spray pyrolysis process by O2 pure rotational CARS - Peukert, Wolfgang; Seeger, Thomas; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Leipertz, Alfred (Laser Applications to Chemical, Security and Environmental Analysis 2012, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used. To preserve the original behavior of the sensitive flame spray pyrolysis process in situ, the gas phase temperatures were measured with pure rotational CARS. An O pure rotational CARS setup was applied due to the lack of N. The CARS technique benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. The temperature results indicate the dissipation of energy by radiation in the presence of particles since the flame temperatures are decreasing with increasing particle concentrations. © 2012 OS
Keywords: flame; spray; pyrolysis; gas; phase; particle; nano; radiation

Gas phase temperature measurements in the liquid and particle regime of a flame spray pyrolysis process using O2-based pure rotational coherent anti-Stokes Raman scattering - Peukert, Wolfgang; Engel, Sascha; Kögler, Andreas; Gao, Yi; Kilian, Daniel; Voigt, Michael; Seeger, Thomas; Leipertz, Alfred (Applied Optics, 2012)
For the production of oxide nanoparticles at a commercial scale, flame spray processes are frequently used where mostly oxygen is fed to the flame if high combustion temperatures and thus small primary particle sizes are desired. To improve the understanding of these complex processes in situ, noninvasive optical measurement techniques were applied to characterize the extremely turbulent and unsteady combustion field at those positions where the particles are formed from precursor containing organic solvent droplets. This particle-forming regime was identified by laser-induced breakdown detection. The gas phase temperatures in the surrounding of droplets and particles were measured with O2 -based pure rotational coherent anti-Stokes Raman scattering (CARS). Pure rotational CARS measurements benefit from a polarization filtering technique that is essential in particle and droplet environments for acquiring CARS spectra suitable for temperature fitting. Due to different signal disturbing processes only the minority of the collected signals could be used for temperature evaluation. The selection of these suitable signals is one of the major problems to be solved for a reliable evaluation process. Applying these filtering and signal selection steps temperature measurements have successfully been conducted. Time-resolved, single-pulse measurements exhibit temperatures between near-room and combustion temperatures due to the strongly fluctuating and flickering behavior of the particle-generating flame. The mean flame temperatures determined from the single-pulse data are decreasing with increasing particle concentrations. They indicate the dissipation of large amounts of energy from the surrounding gas phase in the presence of particles.
Keywords: oxyide; nanoparticle; optical; noninvasive; droplet; combustion; raman; scattering

General concepts in nanoparticle technology and their possible implication on cultural science and philosophy - Peukert, Wolfgang (Powder Technology, 2005)
This paper consists of two parts. The first part describes generally applicable concepts in nanoparticle technology. A key objective in nanotechnology is to build functional structures from small building blocks, i.e. nanoparticles. Starting from the concept of product engineering we investigate the basic preconditions for tailoring functional structures and their properties. Formation of macroscopic structures is only possible through microscopic control of particulate interfaces, i.e. of particle interactions. Particle interactions result mainly from the molecular properties of the respective surfaces which are governed by quantum mechanics. However, in many cases particle interactions can be sufficiently described by classical force laws. The sum of all these forces plus external forces leads to the desired structure. The second part of this paper draws conclusions from these physical principles and dares to apply these to philosophy and cultural sciences. It seems that encounters between entities, in this case individuals, small groups, countries, for instance, leads to the development of social structures and in most general sense to culture. Changing the interactions between the entities will lead to different structures. The conclusion is straightforward but extremely complex in general: We as individuals are tailoring life and culture by our way of interacting. © 2005 Elsevier B.V. All rights reserved.
Keywords: Cultural sciences; Nanoparticles; Philosophy; Product engineering; Structure formation

Generally applicable breakage functions derived from single particle comminution data - Meier, Matthias; John, Edgar; Wieckhusen, Dierk; Wirth, Wolfgang; Peukert, Wolfgang (Powder Technology, 2009)
Nine different substances with widely varying properties have been impacted on a rigid target at different velocities. The obtained fragment size distributions have been analyzed in order to obtain a mathematical expression for the breakage functions. The breakage function was modeled as a bimodal logarithmic normal distribution. It was found that the parameters of these approximated breakage functions change with impact energy in the same way for all substances. It could be shown that the breakage function is both size and material dependent. The material dependency can be expressed via the dimensionless stressing parameter f* (Mat) . x . (W* (m.kin) - W* (m.min)), where f* (Mat) and x . W* (m.min) are breakage parameters that can be determined from single particle comminution experiments or estimated from other mechanical properties (namely the brittleness index of the material). No difference in the breakage functions was found for impacts under 60 degrees and 90 degrees. The results of this work allow the prediction of breakage functions for impacting particles. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Comminution; Grinding; Breakage function; Single particle experiments; Material properties

Germanium-silicon alloy and core-shell nanocrystals by gas phase synthesis - Mehringer, Christian; Kloner, Christian; Butz, Benjamin; Winter, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2015)
In this work we present a novel route to synthesize well defined germanium-silicon alloy (GexSi1-x) and core-shell nanocrystals (NCs) employing monosilane (SiH4) and monogermane (GeH4) as precursors in a continuously operated two-stage hot-wall aerosol reactor setup. The first hot-wall reactor stage (HWR I) is used to produce silicon (Si) seed particles from SiH4 pyrolysis in Argon (Ar). The resulting seeding aerosol is fed into the second reactor stage (HWR II) and a mixture of SiH4 and GeH4 is added. The ratio of the precursors in the feed, their partial pressures, the synthesis temperature in HWR II and the overall pressure are varied depending on the desired morphology and composition. Alloy particle production is achieved in the heterogeneous surface reaction regime, meaning that germanium (Ge) and Si are deposited on the seed surface simultaneously. The NCs can be synthesized with any desired composition, whilst maintaining a mean diameter around 30 nm with a geometric standard deviation (GSD) around 1.25. The absorption behavior and the related fundamental optical band gap energy in dependence on the alloy composition are exemplarily presented. They prove the possibility to tailor NC properties for electronical and opto-electronical applications. In the homogeneous gas phase reaction regime facetted Ge-Si core-shell structures are accessible. The Ge deposition on the seeds precedes the Si deposition due to different gas phase reaction kinetics of the precursors. The Si layer grows epitaxially on the Ge core and is around 5 nm thick.

Grafting porphyrins (face-to-edge/orthogonal versus face-to-face/parallel) to ZnO en route toward dye-sensitized solar cells - Werner, Fabian; Gnichwitz, Jan-Frederik; Marczak, Renata; Palomares, Emilio; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Journal of Physical Chemistry B, 2010)
Novel types of binding motives have been investigated within the context of sensitizing ZnO-based dyesensitized solar cells with metalloporphyrins. In particular, a complementary class of metalloporphyrin has been synthesized to probe the impact of a face-to-edge/orthogonal versus face-to-face/parallel orientation of the metalloporphyrin with respect to ZnO and has been compared to TiO-based dye-sensitized solar cells. Our studies provide a deep and detailed understanding of the individual electron-transfer processes at the ZnO/metalloporphyrin interface, that is, electron injection, recombination, and dye regeneration, by means of steady-state and time-resolved techniques. Interestingly, we found that for our novel ZnO/metalloporphyrin systems, the injection efficiencies are close to unity, despite their long, nonconjugated anchoring group length. © 2010 American Chemical Society.

Grain Structure Evolution of Al–Cu Alloys in Powder Bed Fusion with Laser Beam for Excellent Mechanical Properties - Rasch, Michael; Heberle, Johannes; Dechet, Maximilian; Bartels, Dominic; Gotterbarm, Martin; Klein, Lukas; Gorunov, Andrey; Schmidt, Jochen; Körner, Carolin; Peukert, Wolfgang; Schmidt, Michael (Materials, 2019)
Powder Bed Fusion with Laser Beam of Metals (PBF-LB/M) is one of the fastest growing technology branches. More and more metallic alloys are being qualified, but processing of aluminum wrought alloys without cracks and defects is still challenging. It has already been shown that small parts with low residual porosity can be produced. However, suering from microscopic hot cracks, the fracture behavior has been rather brittle. In this paper dierent combinations of temperature gradients and solidification rates are used to achieve specific solidification conditions in order to influence the resulting microstructure, as well as internal stresses. By this approach it could be shown that EN AW-2024, an aluminum-copper wrought alloy, is processable via PBF-LB/M fully dense and crack-free with outstanding material properties, exceeding those reported for commonly manufactured EN AW-2024 after T4 heat treatment.<br
Keywords: Powder Bed Fusion with Laser Beam; aluminum-copper wrought alloy; solidification conditions; hot cracking sensitivity; grain structure evolution

Graphene production with stirred media mills - Knieke, Catharina; Berger, Angela; Peukert, Wolfgang (2010 MRS Spring Meeting, 2010)
Since the discovery of stable graphene sheets by Novoselov und Geim in 2004 the one atom thick carbon material has been attracted great interest because of its outstanding physical, mechanical and chemical properties. Although there had been intensive research to find new ways in the preparation of single-layer graphene sheets in the last few years, especially the large-scale production of graphene still remains challenging. In this paper we present a new approach, which allows the high-yield production of graphene sheets in a simple stirred media milling process. Under mild milling conditions single- and multilayer graphene sheets have been successfully produced from commercial graphite powder in a liquid medium. During the delamination procedure, the graphite particles were stressed between the milling beads. Shear and compressive normal forces can lead under mild milling conditions, i.e. low stress energies, to a continuous mechanical peeling of graphene sheets from the graphite surface. By means of Atomic Force Microscopy a high yield of single- and multilayer graphene sheets was detected. A concentration of exfoliated sheets of 2 wt% starting from a 5 wt% suspension of coarse graphite particles could be determined after a milling time of only 3 h. This concentration is much higher than those, which were reached by most of the known chemical methods. Since stirred media milling can be realized as large-scale process, a high-yield and low-cost production of graphene flakes becomes possible at ambient temperatur
Keywords: C; carbon; scanning probe microscopy (SPM); fracture

Green and Scalable Fractionation of Gold Nanoclusters by Anion Exchange Chromatography: Proof of Principle and Scale-Up - Gromotka, Lukas; Lübbert, Christian; Traore, Nabi; Peukert, Wolfgang (ACS Applied Nano Materials, 2023)
The chromatographic separation of atomically precise glutathione-stabilized gold nanocluster (AuNC) mixtures is demonstrated for purely aqueous anion exchange chromatography (AEX) and compared to the results of hydrophilic interaction liquid chromatography (HILIC), which requires mixtures of water and acetonitrile. For isocratic HILIC separations, the influence of the mobile phase composition with respect to ionic strength and acetonitrile content is investigated. Individual AuNCs are identified by their optical properties directly from chromatograms and by comprehensive electrospray ionization differential mobility mass spectrometry. Separations by AEX are performed in aqueous mobile phases and are thus considered as a green and sustainable technique for the efficient fractionation of AuNCs. Henry coefficients are determined, which describe the retention behavior of single AuNCs and thus form the basis for modeling, optimization, and scale-up of the separation. The separation by AEX is optimized by linear salt gradient experiments. The scalability of the separation is demonstrated by increasing the AuNC feed concentration up to 64 g/L. Moreover, we quantify the amounts of individual AuNCs by inductively coupled plasma-optical emission spectroscopy after separation and close the mass balance demonstrating the reversible adsorption from the stationary phase. Our AEX approach is superior to HILIC since it offers a higher resolution, provides access to larger clusters, is readily scalable, and is purely water-based. AEX is considered as a sustainable, scalable, and widely applicable technique for the isolation of all types of water-soluble single cluster species. Therefore, we anticipate applications for instance for highly specialized nanocatalysts, sensors, or in medicine.
CRIS-Team Scopus Importer:2023-05-12
Keywords: anion exchange; chromatography; gold nanocluster; hydrophilic; interactions; scalable; separation; sustainable

"Green'' Particle Technology? - Peukert, Wolfgang; Bück, Andreas (2022)
In this essay, we discuss the evolution of particle technology in the context of climate change. We begin with a brief outline of the history of particle technology. In addition to the fascination of fine particle systems, it will become clear that particles have also been associated with negative consequences of human activities since the industrial revolution and still are. Some examples of how dispersive systems contribute to solving current challenges are discussed. Finally, we identify white fields and open questions in particle engineering in the context of climate change hoping that this will stimulate further research.
Keywords: Particles; Particle technology; Sustainability

Green room temperature synthesis of silver-gold alloy nanoparticles - Traore, Nabi; Uttinger, Maximilian; Cardenas Lopez, Paola; Drobek, Dominik; Gromotka, Lukas; Schmidt, Jochen; Walter, Johannes; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale Advances, 2023)
Metallic alloy nanoparticles (NPs) exhibit interesting optical, electrical and catalytic properties, dependent on their size, shape and composition. In particular, silver-gold alloy NPs are widely applied as model systems to better understand the syntheses and formation (kinetics) of alloy NPs, as the two elements are fully miscible. Our study targets product design via environmentally friendly synthesis conditions. We use dextran as the reducing and stabilizing agent for the synthesis of homogeneous silver-gold alloy NPs at room temperature. Our approach is a one-pot, low temperature, reaction-controlled, green and scalable synthesis route of well-controlled composition and narrow particle size distribution. The composition over a broad range of molar gold contents is confirmed by scanning transmission electron microscopy-energy-dispersive X-ray spectroscopy (STEM-EDX) measurements and auxiliary inductively coupled plasma-optical emission spectroscopy measurements (ICP-OES). The distributions of the resulting particles in size and composition are obtained from multi-wavelength analytical ultracentrifugation using the optical back coupling method and further confirmed by high-pressure liquid chromatography. Finally, we provide insight into the reaction kinetics during the synthesis, discuss the reaction mechanism and demonstrate possibilities for scale-up by a factor of more than 250 by increasing the reactor volume and NP concentration.
Keywords: particle-size distribution; ray computed-tomography; bimetallic nanoalloys; dielectric function; formation mechanism; contrast agent; Au; Ag; sedimentation; dependence

Grenzflächen charakterisieren - Peukert, Wolfgang; Martinez Tomalino, Lars-Owe (Nachrichten aus der Chemie, 2008)
Nichtlineare optische Spektroskopie ist die erste Methode, mit der sich die Oberflächeneigenschaften von Partikeln in technischen Systemen direkt untersuchen lassen.
Keywords: Grenzflächen; Spektroskopie; Partikel; Vakuum; nano

Grinding in an air classifier mill - Part I: Characterisation of the one-phase flow - Toneva, Petya Ivanova; Epple, Philipp; Breuer, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2011)
In this and the related second paper [1], we present an in-depth study of the two-phase flow and the stressing conditions of particles in an air classifier hammer mill. This type of mill belongs to the mostly used mills at all. In order to develop a predictive grinding model not only the material's reaction to the applied stress but also the stressing conditions within the mill, e.g. impact velocity, incidence angle, number of stress events, have to be known. The latter are strongly affected by the interactions between the fluid and the solid phase within the mill. Systematic flow investigations in the vicinity of the impact elements and in the region of the internal classifier have been performed by Particle Image Velocimetry (PIV) and by numerical predictions of the fluid flow in the complete mill using a commercial CFD solver. Different pin geometries have been studied at various peripheral velocities of the grinding disk and the classifier. The classifier velocity does not influence the velocity profiles near the impact elements in the main flow direction and vice versa, the flow in the grinding zone has little influence on the classification. The velocity profile in front of the impact element, where the comminution process takes place, is constant with time and preserves a characteristic form independent of the operational conditions. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.grindi
Keywords: CFD; Comminution; Grinding; Impact mills; Multiphase flow; PIV

Grinding in an air classifier mill - Part II: Characterisation of the two-phase flow - Toneva, Petya Ivanova; Wirth, Karl-Ernst; Peukert, Wolfgang (Powder Technology, 2011)
Based on the insights about the air flow within the air classifier mill presented in the first part of the paper [1] the particle laden flow in the vicinity of the grinding pins and through the impeller wheel classifier is studied. The particle motion in the size range between 29 and 573 μm is investigated using Particle Image Velocimetry (PIV). The mathematical model for the fluid flow is extended to a fully coupled two-phase flow numerical calculation. The particle motion in the grinding zone is not influenced by the peripheral velocity of the impeller wheel classifier. The grinding disk velocity doesn't affect the particle behaviour at the classification region. The impact velocity at the grinding pins is independent from the particle size. The average impact velocity normal to the pin wall amounts for the cylindrical pin geometry to 68% and for the prismatic pin geometry to 80% of the peripheral grinding disk velocity. The particles entering the classifier region move with the air velocity in radial direction while their transport in sucking direction slows down in comparison to the air motion. Because of the flow separation between the classifier blades the majority of the particles undergo impacts at the blades and consequently undesired stochastic particle motion of the rebounding particles occurs. © 2011 Elsevier B.V.
Keywords: Air classifier mill; Classification; Grinding; Multiphase flow; Particle Motion

Growth of gold nanoshells on colloidal silica characterized by in situ second-harmonic generation - Sauerbeck, Christian; Schürer, Benedikt; Haderlein, Michael; Braunschweig, Björn; Peukert, Wolfgang; Klupp Taylor, Robin (Engineering Sciences and Fundamentals 2013 - Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)
Metal nanoparticles and metal composite nanoparticles can have unique optical properties due to localized surface plasmon resonances and are therefore of particular interest in various applications. The resonance frequency of such particles is a function of their composition and their geometry. Gold nanoshells are comprised of a dielectric core and a thin gold shell. The optical properties of such particles can be readily tuned over a wide range by changing the ratio of the core diameter to the shell thickness. In order to impart better control over the optical properties of gold nanoshells a detailed understanding of the shell formation is of great importance. For that purpose it is necessary to monitor changes in surface composition and morphology in situ and in real time. However, most experimental methods lack the desired surface sensitivity or cannot be applied in situ under the required experimental conditions. For that reason we have applied second-harmonic generation (SHG) spectroscopy as a powerful surface sensitive technique which shows great potential to probe surfaces of nanoparticles under relevant experimental conditions1-3. In our contribution, we present results from synchronized SHG and UV/Vis/NIR spectroscopies that were obtained on-line during the seeded growth of gold shells on silica core particles. UV/Vis/NIR spectroscopy allows the monitoring of the coverage of gold and to estimate whether the shells are closed or not, while SHG shows a remarkable sensitivity to changes in the surface morphology which has not been accessible by other in situmethods so far. Notably, at intermediate conditions where a still incomplete shell exists on the core particle during shell growth, we observe first a steep increase in the second-harmonic intensity that is followed by a subsequent rapid decrease in SHG intensity. As the SHG signal is a function of the fundamental electric field to the fourth power, we propose that the observed maximum in the temporal evolution of the SHG intensity is caused by a local field enhancement due to crevices that are being formed in between individual gold islands. As shell growth proceeds, the surface coverage of these crevices decreases and closed shells are formed which results in a substantially decreased SHG signal. This hypothesis is corroborated by additional angle-resolved SHG experiments and ex-situ electron microscopy of gold shells with different gold coverages and surface morphologie
Keywords: nanoparticle; composite; plasmon; resonance; second-harmonic; core; shell

Grundprinzipien der Produktgestaltung - Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)
Unit operations und Produktdesign sind die beiden wichtigsten Säulen der Verfahrenstechnik. Unter Produktdesign wird die Bildung, Formulierung und Charakterisierung von komplex zusammengesetzten Produkten verstanden. Die jeweiligen Anwendungen definieren dabei die geforderten Produkteigenschaften sowohl in den klassischen Feldern der chemischen Industrie als auch in neuen Feldern wie der druckbaren Elektronik, der Energie- und Umwelttechnik, den Lebenswissenschaften, der pharmazeutischen Technologie und der Nanotechnologie. Im Beitrag werden Grundprinzipien des Produktdesigns vorgeschlagen, die auf eine Vielzahl von Produkten einschließlich fester, flüssiger oder gasförmiger Partikelsysteme anwendbar sind. Ergebnisse aus dem Erlanger Exzellenzcluster "Engineering of Ad- vanced Materials" zeigen, dass die enge Zusammenarbeit zwischen Verfahrenstechnik, Materialwissenschaft und den Naturwissenschaften fruchtbare neue Optionen für die beteiligten Fachbereiche eröffnet. Rigorose mathematische Optimierung auf der Basis prädiktiver Modelle für Produkte und Prozesse katalysieren dabei neue Möglichkeiten zum Design partikelbasierter Produkte in Zukunftsbereichen wie etwa der Elektronik, Photonik oder dem 3D-Druck
Keywords: Partikel; System; Eigenschaften; Produkt

Guidelines for the production of nanoscaled particles and products - Peukert, Wolfgang; Schwarzer, Hans-Christoph; Leugering, Günter (Produktgestaltung in der Partikeltechnologie, 2002)
UnivIS-Import:2015-04-20:Pub.2002.tech.ITC.mechve.guidel
Keywords: nano; particle; product

GVC-Dezember-Tagung: Grenzflächen in der feststoffverfahrenstechnik - Peukert, Wolfgang (Chemie Ingenieur Technik, 2003)

GVC-Dezember-Tagung: Grenzflächen in der feststoffverfahrenstechnik - Peukert, Wolfgang (Chemie Ingenieur Technik, 2003)

Herausforderungen für die Lehre am Beispiel der mechanischen Verfahrenstechnik - Peukert, Wolfgang; Schmid, Hans-Joachim (Chemie Ingenieur Technik, 2003)
Rasche technologische Entwicklungen haben für Chemieingenieure bzw. Verfahrenstechniker neue Beschäftigungsmöglichkeiten eröffnet, wodurch sich zusätzliche Anforderungen an die Ausbildung ergeben. Der vorliegende Beitrag beschreibt die Lösungsansätze im Fachgebiet der Partikeltechnik: Es findet eine noch stärkere Betonung der Grundlagen statt, wobei Beispiele aus klassischen und neuen Anwendungen exemplarisch vertieft werden. Kernpunkt des Curriculums sind die Produkteigenschaften. Besonderes Gewicht wird außerdem auf die Betrachtung ganzer Prozesse gelegt. Die Vorlesungen sind in drei Ebenen strukturiert: Grundlagen, Grundoperationen und Prozesse/Anwendungen. Methodisch wird ein zweifacher Ansatz verfolgt: Die Lehre der grundlegenden Fakten wird ergänzt durch eine aktive Teilnahme der Studenten, insbesondere bei der Erarbeitung von Beispielen und in Labor- bzw. Rechnerpraktika. Durch eine ganzheitliche Sicht der Universitätsausbildung sollen auch „soft skills“ gefördert werden.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.heraus
Keywords: teaching; particle; technology

Herstellung und Charakterisierung von Pulvern für das selektive Laserstrahlschmelzen von Kunststoffen aus Flüssigphasenprozessen am Beispiel von PA11 - Dechet, Maximilian; Zhao, Meng; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (6. Industriekolloquium des Sonderforschungsbereichs 814 - Additive Fertigung, 2018)
Keywords: 3D-Druck • Additive Fertigung • Sonderforschungsbereich 814

Herstellung und Funktionalisierung neuartiger Pulverwerkstoffe für die additive Fertigung - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)

Herstellung von Polyolefinstrahlschmelzmaterialien mittels Schmelzeemulgieren zum Einsatz in der additiven Fertigung - Schmidt, Jochen; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang; Hiller, Saskia; Laumer, Tobias; Schmidt, Michael (Neue Entwicklungen in der Additiven Fertigung, 2015)
Im Rahmen dieses Beitrags wird das Schmelzeemulgieren als Verfahren zur Herstel-lung von Polymermikropartikeln vorgestellt. In diesem Prozess wird zunächst ein Polymergranulat in einer kontinuierlichen Phase in Gegenwart geeigneter Additive in einem Rührbehälter aufgeschmolzen, die Rohemulsion in einer Rotor-Stator-Einheit feinemulgiert und anschließend zu einer Suspension abgekühlt. Der Einfluss von Prozessparametern und Systemzusam-mensetzung auf das Emulgierergebnis wird diskutiert und die Anwendbarkeit des Verfahrens für polymere Mikropartikeln anhand von Polypropylen (PP) und Polyethylen (PE-HD) dargestellt. Die erhaltenen Suspensionen werden zur Überführung in Pulverform sprühgetrocknet und die Fließeigenschaften des Pulvers analysiert. Durch trockenes Beschichten mit pyrogener Kieselsäure kann die Fließfähigkeit der erhaltenen Partikeln weiter verbessert werden. Das Verfahren bietet somit einen neuen Zugang zur Herstellung neuer Ausgangsmaterialien für die Additive Fertigung.<br

Highly magnetizable superparamagnetic colloidal aggregates with narrowed size distribution from ferrofluid emulsion - Lobaz, Volodymyr; Klupp Taylor, Robin; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2012)
The formation of spherical superparamagnetic colloidal aggregates of magnetite nanoparticles by emulsification of a ferrofluid and subsequent solvent evaporation has been systematically studied. The colloidal aggregates occur as a dense sphere with magnetite nanoparticles randomly packed and preserved particle-particle separation due to chemisorbed oleic acid. The voids between nanoparticles are filled with solvent and free oleic acid. The latter was found to influence the formation of colloidal aggregates and their surface properties. The choice of surfactant, whether low molecular weight or polymeric, was shown to lead to the colloidal aggregates having tailored interfacial behavior. Magnetization measurements at ambient temperature revealed that the magnetite colloidal aggregates preserve the superparamagnetic properties of the starting nanoparticle units and show high saturation magnetization values up to 57. emu/g. The size distribution of magnetite nanoparticle colloidal aggregates produced by such an approach was found to be a function of emulsion droplet breakup - coalescence and stabilization kinetics and therefore is influenced by the emulsification process conditions and concentrations of the emulsion compounds. © 2012 Elsevier In
Keywords: Colloidal aggregate; Emulsion; Magnetite nanoparticle; Superparamagnetic particle

How to avoid interfering electrochemical reactions in ESI-MS analysis - Lübbert, Christian; Peukert, Wolfgang (Journal of Mass Spectrometry, 2019)
The presence of electrochemical reactions occurring in an electrospray processes at the point where the current enters the liquid is discussed since the early 1990's. This current transfer to the liquid results in oxidation or reduction of either electrolyte species in the liquid sprayed or of the electrode material in contact with the liquid. As a result, new chemical species are generated. These products of the electrochemical reaction might be detected as altered species in mass spectra; they might be volatile and not recognized at all or accumulate on the electrode surface and cause cross contamination later on. In other cases, it might happen that the products of the electrochemical reactions are the only detectable species formed from an otherwise nondetectable analyte. An electrospray setup in which electrochemical reactions do not interfere with the analyte under investigation excludes the electrochemical reaction as source of sample contamination and sample altering and may serve as reference setup for experiments focused on the electrochemical reaction itself. We present a simple and inexpensive current coupling approach and specify operation conditions for which any impact of the electrochemical reaction on the sample under investigation is inherently excluded. On the basis of a practical example, we show the impact of the electrochemical reaction on sample composition and demonstrate the benefit of using the proposed current coupling method. Because of the obvious benefit of this method and its simple realization, it has the potential to be employed as standard feeding approach, especially for electrosprays operated at small flow rates.
CRIS-Team Scopus Importer:2019-05-02
Keywords: corrosion; electrochemistry; electrospray; nanospray; negative ion mode

How to Estimate Material Parameters for Multiphase, Multicomponent Precipitation Modeling - Güldenpfennig, Andreas; Pflug, Lukas; Peukert, Wolfgang (Crystal Growth and Design, 2019)
The simultaneous precipitation of multiple solid phases inside a T-mixer was investigated both numerically and experimentally based on the model system BaSO 4 and BaCO 3 . With a population balance equation model including mixing, hydrochemistry, and solid formation kinetics, the global solid phase composition was calculated and compared to experimental results. We show that physical material parameters can be extracted from the simulations by matching calculated curves to measured data. In particular, the surface energies and solubility products of the solids, which are both crucial parameters to describe nucleation and often not known accurately enough, are discussed. The estimated parameters are in the same size range as literature values, and simulations are compared to experiments for variable anion concentration ratios, pH, and solid concentrations. The good agreement between the data for several different process conditions proves both the general validity of our multiphase model and the effectiveness of the presented method.
CRIS-Team Scopus Importer:2019-05-14

Human laryngeal mucus from the vocal folds: Rheological characterization by particle tracking microrheology and oscillatory shear rheology - Peters, Gregor; Wendler, Olaf; Böhringer, David; Gostian, Antoniu Oreste; Müller, Susanna; Canziani, Herbert; Hesse, Nicolas; Semmler, Marion; Berry, David A.; Kniesburges, Stefan; Peukert, Wolfgang; Döllinger, Michael (Applied Sciences, 2021)
Mucus consistency affects voice physiology and is connected to voice disorders. Neverthe-less, the rheological characteristics of human laryngeal mucus from the vocal folds remain unknown. Knowledge about mucus viscoelasticity enables fabrication of artificial mucus with natural properties, more realistic ex-vivo experiments and promotes a better understanding and improved treatment of dysphonia with regard to mucus consistency. We studied human laryngeal mucus samples from the vocal folds with two complementary approaches: 19 samples were successfully applied to particle tracking microrheology (PTM) and five additional samples to oscillatory shear rheology (OSR). Mucus was collected by experienced laryngologists from patients together with demographic data. The analysis of the viscoelasticity revealed diversity among the investigated mucus samples according to their rigidity (absolute G’ and G”). Moreover some samples revealed throughout solid-like character (G’ > G”), whereas some underwent a change from solid-like to liquid-like (G’ < G”). This led to a subdivision into three groups. We assume that the reason for the differences is a variation in the hydration level of the mucus, which affects the mucin concentration and network formation factors of the mucin mesh. The demographic data could not be correlated to the differences, except for the smoking behavior. Mucus of predominant liquid-like character was associated with current smokers.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Human laryngeal mucus; Oscillatory shear rheology; Particle tracking microrheology; Viscoelasticity; Vocal folds

Hybrid Metal-Dielectric Photonic Crystals with Enhanced Plasmonic-Photonic Interaction - Bahrami, M. Reza; Lobaz, Volodymyr; Peukert, Wolfgang; Korovin, Alexander V.; Peschel, Ulf; Romanov, Sergei G. (13th International Conference on Transparent Optical Networks (ICTON), 2011)
Control on the optical response of 2-dimensional colloidal photonic crystals was achieved by combining them with thin metal films. In such hybrids the light transport depends on the parameters of the sphere lattice and the topology of the metal film. This approach allows mixing Bloch modes and surface plasmon polariton modes in the total optical response of hybrid architectures. Stronger modification of the hybrid's optical properties was achieved in the case of tighter light confinement.
Keywords: hybrid photonic crystal; surface plasmon polariton; optical transmission

Hydrodynamic simulations of sedimenting dilute particle suspensions under repulsive DLVO interactions - Jung, David; Uttinger, Maximilian; Malgaretti, Paolo; Peukert, Wolfgang; Walter, Johannes; Harting, Jens (Soft Matter, 2022)
We present guidelines to estimate the effect of electrostatic repulsion in sedimenting dilute particle suspensions. Our results are based on combined Langevin dynamics and lattice Boltzmann simulations for a range of particle radii, Debye lengths and particle concentrations. They show a simple relationship between the slope K of the concentration-dependent sedimentation velocity and the range chi of the electrostatic repulsion normalized by the average particle-particle distance. When chi -> 0, the particles are too far away from each other to interact electrostatically and K = 6.55 as predicted by the theory of Batchelor. As chi increases, K likewise increases as if the particle radius increased in proportion to chi up to a maximum around chi = 0.4. Over the range chi = 0.4-1, K relaxes exponentially to a concentration-dependent constant consistent with known results for ordered particle distributions. Meanwhile the radial distribution function transitions from a disordered gas-like to a liquid-like form. Power law fits to the concentration-dependent sedimentation velocity similarly yield a simple master curve for the exponent as a function of chi, with a step-like transition from 1 to 1/3 centered around chi = 0.6.

Identification of material specific attrition mechanisms for polymers in dilute phase pneumatic conveying - Peukert, Wolfgang; Frye, Lars (Chemical Engineering and Processing, 2005)
In the approach presented, attrition of bulk solids in pneumatic conveying is regarded as a result of a process function (stress conditions) and a material function (influence of material properties). For dilute phase conveying the process function was determined by employing computational fluid dynamics (CFD). Opposed to what was expected initially, the numerical simulations indicate that sliding friction apparently is of importance in dilute phase conveying. This conclusion can be drawn from the low calculated impact angles in a pipe bend (rB/Dn = 5; Dn = 80 mm) which lie between 5 and 35°. Consequently, the tangential impact velocity components ranging from 33 to 44 m/s are considerably higher than the normal ones (5-25 m/s). These results were at first endorsed by observations made in experiments to determine the material function. The relative attrition behavior of four different polypropylenes (PP) under pure sliding friction conditions closely resembles that observed in attrition experiments carried out in a pipe bend of the above geometry, while differences are observed for normal impact conditions. But further experiments with polymethylmethacrylates (PMMA) and polystyrenes (PS) showed that here the attrition behavior encountered under normal impact conditions is similar to that observed in the pipe bend. With dynamic mechanical analysis (DMA) it was possible to show that PP on one hand and PMMA and PS on the other are attrited by different mechanisms and that the glass transition temperature of the polymers is a key factor in the determination of the prevailing attrition mechanism. © 2004 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.mechve.identi
Keywords: Attrition; Dynamic mechanical analysis (dma); Material function; Pneumatic conveying; Polymers; Process function

Identifying the apparent and true grinding limit - Knieke, Catharina; Sommer, Marc; Peukert, Wolfgang (Powder Technology, 2009)
Comminution in stirred media mills enables the production of ultrafine particles down to the nanometer range. The grinding results are mainly determined by two contrary mechanisms: particle breakage and agglomeration of the so-created fragments. These competing phenomena often lead to a plateau in particle size above a certain energy input. The degree of agglomeration and therefore the final aggregate size can be controlled by the addition of stabilizers and by the applied shear forces. In this paper the agglomeration behavior of silica particles under different milling and stability conditions is presented. Furthermore the particle breakage behavior in the nanometer range as the other size-determining mechanism will be discussed. In long term grinding experiments with different materials the kinetics of particle breakage as well as the grinding limit as the minimal achievable particle size could be obtained. Graphical abstract In wet grinding processes most materials show after certain milling time no further grinding progress and a plateau in particle size is reached. One can distinguish between the apparent grinding limit, which is an agglomerate size strongly depending on the stability of the suspension, and the true grinding limit. This true grinding limit is determined by microstructural changes inside the particles and can be influenced by material and process parameters.

Impact comminution in jet mills - Strobel, Alexander; Köninger, Benedikt; Romeis, Stefan; Wirth, Karl Ernst; Peukert, Wolfgang (Dynamic Flowsheet Simulation of Solids Processes, 2020)
Modelling the comminution in jet mills with respect to the complex twophase flow and the dynamic process behaviour is still a challenging task. The processed solids pass through several stages in the mill: The comminution process in the lower part, the pneumatic transport towards the classifier in the middle section, and the classification step at the top. In this contribution, the grinding kinetics and process behaviour during quasi-batch and fed-batch operational mode for different holdups, classifier speeds, and particle sizes are examined in detail. A previously developed method using well-characterized aluminium particle probes to access the stressing conditions is adapted for application in the investigated jet mill: The relative particle impact velocity is linked to the geometric changes of the particles upon impact. A high number of impact events happen in the mill, while at the same time, the average particle velocity is comparatively low. Besides the stressing conditions, breakage probabilities for the used glass beads are determined by single particle impact experiments and described by the model of Vogel and Peukert. Solids concentration measurements and high-speed imaging reveal the formation of particle clusters at the classifier and its periphery. These clusters have a massive impact on the classification step itself: Fine particles are trapped inside the clusters and are not discharged. Based on an adaption of the breakage model, and using the mean relative particle impact velocity determined by the particle probes, a model for the product mass flow is introduced.
CRIS-Team Scopus Importer:2020-08-28

Impact fragmentation of metal nanoparticle agglomerates - Peukert, Wolfgang; Seipenbusch, Martin; Toneva, Petya Ivanova; Weber, Alfred P. (Particle & Particle Systems Characterization, 2007)
Deagglomeration experiments were performed with agglomerates of nanoparticles of Ni and Pt. The fragmentation was induced by high velocity impaction of the agglomerates in a single-stage low pressure impactor and the fragmentation patterns were evaluated by TEM analysis. Weibull statistics are employed for a quantitative description of the fragmentation behavior. This study shows that for well-defined interparticle contacts, the impact fragmentation technique combined with the evaluation according to Weibull statistics, allows the recovery of the expected size dependencies. For Pt and Ag, the adhesion force particle size dependency was dominated by van der Waals forces. In contrast, the adhesion force between Ni particles in the size range from 12-28 nm revealed a much stronger increase with particle size. This phenomenon may be attributed to permanent magnetic dipole moments which are also reflected in the chain-like shape of the agglomerates. For nanoparticle agglomerates with less well-defined contacts, such as those in industrial environments, the method provides a promising application to reveal the bond strength and cohesiveness of nanoparticle powders. © 2007 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: Deagglomeration; Diffusional agglomeration; Nanoparticle agglomerates; Weibull statistics

Impact of DAA/water composition on PFSA ionomer conformation. - Hoffmann, Eva-Maria; Fischer, Daniela; Thoma, Martin; Damm, Cornelia; Lobaz, Volodymyr; Zhigunov, Alexander; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2020)
Performance of a proton exchange membrane fuel cell (PEMFC) is significantly determined by the structure and composition of the electrode layer. Electrode layers are formed from inks consisting of platinum-doped carbon black particles, perfluorosulfonic acid (PFSA) ionomer and a dispersing solvent. Interaction between these materials mainly influences suspension stability, ionomer conformation and therewith layer morphology. We characterize the interplay between a short sidechain (SSC) PFSA ionomer (Aquivion® D79-25BS) and a solvent mixture (diacetone alcohol (DAA) and water with different weight ratios) by using Hansen solubility/dispersibility parameters (HSP) and by experimental tests. It was found that HSPs are well suitable to describe the ionomer/solvent interactions. In particular, the HSP difference in terms of the hydrogen bonds is responsible for the poor affinity between ionomer and solvent at low DAA concentrations. With increasing DAA content the affinity between ionomer and solvent increases as indicated by better matching HSPs. For an ionomer concentration of 4 wt%, Aquivion always forms molecular solutions for all DAA-in-water mixing ratios. Self-organization of the ionomer molecules changes from densely packed/collapsed molecules with highly deprotonated sulfonic acid side groups at low DAA concentrations to unfolded Aquivion molecules with a low dissociation degree of the sulfonic acid groups at high DAA concentrations.

Impact of formulation and operating parameters on particle size and grinding media wear in wet media milling of organic compounds – A case study for pyrene - Flach, F.; Konnerth, Christoph-Günther; Peppersack, C.; Schmidt, Jochen; Damm, Cornelia; Breitung-Faes, S.; Peukert, Wolfgang; Kwade, Arno (Advanced Powder Technology, 2016)
This study presents the influence of process and formulation parameters on fine grinding of the crystalline organic model compound pyrene. Submicron particles were produced by wet media milling in water. By applying an electrosteric stabilization and optimized process parameters, particle sizes below 100 nm were obtained. Additionally, the influence of formulation and process parameters on grinding media wear were investigated. The product formulation with an ionic surfactant and a nonionic polymer was identified as a significant parameter to reduce the grinding wear. Furthermore, the set of operating parameters as well as the choice of grinding media material were found as key parameters to reduce product contamination. Grinding media wear is proportional to the specific energy input and can be minimized by optimizing the stress energy of grinding medi
Keywords: Stirred media milling; Organic crystals; Stabilization; Grinding media wear; Formulation

Impact of oxygen plasma treatment on the device performance of zinc oxide nanoparticle based thin-film transistors - Halik, Marcus; Peukert, Wolfgang; Braunschweig, Björn; Klaumünzer, Martin; Hirschmann, Johannes; Faber, Hendrik (ACS Applied Materials and Interfaces, 2012)
Thin-films of zinc oxide nanoparticles were investigated by photoluminescence spectroscopy and a broad defect-related yellow-green emission was observed. Oxygen plasma treatment was applied in order to reduce the number of defects, and the emission intensity was quenched to 4% of the initial value. Thin-film transistors that incorporate the nanoparticles as active semiconducting layers show an improved device performance after oxygen plasma treatment. The maximum drain current and the charge carrier mobility increased more than 1 order of magnitude up to a nominal value of 23 cm2 V−1 s−1 and the threshold voltage was lowered.
Keywords: nanoparticles; Plasma treatment; thin-film transistors; zinc oxide

Impact of solvent properties on the precipitation of active pharmaceutical ingredients - Schikarski, Tobias; Trzenschiok, Holger; Avila, Marc; Peukert, Wolfgang (Powder Technology, 2023)
In antisolvent precipitation, water and an organic drug-containing solvent induces particle formation. For each water-solvent mixture, the fluid properties such as viscosity, density and diffusion coefficient but also the drug solubility depend nonlinearily on the fluid mixture compositions. Each property in itself has a strong impact on the solid formation, and thus on the outcome of the precipitation. The simulation framework recently developed by Schikarski et al. [1] allows investigating separately the impact of each fluid property on the precipitation. For a T-mixer and a novel 3-inlet-mixer, we first show that the viscosity and density variations largely determine the macroscopic mixing behavior and, thus, the build-up of supersaturation. The composition-dependent diffusion properties of the drug molecules largely govern the transport-controlled nucleation and particle growth at small scales. In a second step, we numerically predict the experimentally obtained full particle size distribution of the precipitated Ibuprofen nanoparticles using different water-solvent mixtures and different operating conditions. Our numerical results are in excellent agreement with our experimental measurements using ethanol, methanol and 2-propanol as solvents.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Active pharmaceutical ingredients; Antisolvent precipitation; Binary mixtures; Computational fluid dynamics; Nucleation and growth of particles; Population balance equation; Water; ethanol; methanol; 2-propanol

Impact of stressing conditions and polymer-surfactant interactions on product characteristics of organic nanoparticles produced by media milling - Konnerth, Christoph-Günther; Flach, Frederik; Breitung-Faes, Sandra; Damm, Cornelia; Schmidt, Jochen; Kwade, Arno; Peukert, Wolfgang (Powder Technology, 2016)
Stirred media milling as a feasible method to produce organic nanoparticles was studied for the polycyclic aromatic hydrocarbon pyrene in aqueous environment using vinylpyrrolidone-vinyl acetate copolymer (KVA 64) and sodium dodecyl sulphate (SDS) as well as hydroxypropylcellulose (HPC-SSL) as stabilising agents during batch and continuous processing. The influence of stressing conditions described by means of stress energy, stress number as well as mass-specific energy input on product particle sizes is presented. Grinding kinetics observed for batch and continuous operation are comparable under similar stressing and formulation conditions. Furthermore, it was found that the use of small grinding media, i.e. stress conditions where low stress energies and high stress numbers apply, are advantageous with respect to fast kinetics and minimum energy consumption. Moreover, the relationship between product characteristics and formulation parameters, i.e. type and concentration of stabilising agents are thoroughly investigated. Complex formation of KVA 64 and SDS has been proven by means of tensiometry and fluorescence spectroscopy. It is demonstrated that solubilisation of pyrene occurs in the system and that product characteristics are not only determined by pure breakage events or colloidal stability issues but also by dissolution and ripening phenomena: Minimum product particle sizes at similar stressing conditions are observed under conditions where solubilisation and ripening are less pronounced, whereas larger product particles are observed in systems with high solubilisation capacities.
EAM Import::2019-03-13

Impact of the nanoparticle-protein corona on colloidal stability and protein structure - Peukert, Wolfgang; Gebauer, Julia; Malissek, Marcelina; Simon, Sonja; Knauer, Shirley; Maskos, Michael; Stauber, Roland; Treuel, Lennart (Langmuir, 2012)
In biological fluids, proteins may associate with nanoparticles (NPs), leading to the formation of a so-called "protein corona" largely defining the biological identity of the particle. Here, we present a novel approach to assess apparent binding affinities for the adsorption/desorption of proteins to silver NPs based on the impact of the corona formation on the agglomeration kinetics of the colloid. Affinities derived from circular dichroism measurements complement these results, simultaneously elucidating structural changes in the adsorbed protein. Employing human serum albumin as a model, apparent affinities in the nanomolar regime resulted from both approaches. Collectively, our findings now allow discrimination between the formation of protein mono- and multilayers on NP surfaces. © 2012 American Chemical Society.
Keywords: fluid; protein; nanoparticle; protein; corona; agglomeration; multilayer

Improvement of polymer properties for powder bed fusion by combining in situ PECVD nanoparticle synthesis and dry coating - Gomez Bonilla, Juan Sebastian; Düsenberg, Björn; Lanyi, Franz; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Plasma Processes and Polymers, 2021)
Polypropylene (PP) powders are coated with silica nanoparticles in a fluidized bed to improve the flow behavior of the powders and the processability in powder bed fusion. The nanoparticles are produced in situ via dusty plasma‐enhanced chemical vapor deposition (PECVD) in an atmospheric‐pressure Ar/O2 plasma jet fixed at the distributor plate of the fluidized bed. Hexamethyldisiloxane is used as a precursor of the nanoparticles. The influence of the oxygen concentration in the plasma gas and the number of treatment cycles on the chemical composition of the nanoparticles, the amount of nanoparticles deposited, and the flow properties of the coated PP powders is investigated. The chemical composition of the formed silica particles is determined by X‐ray photon spectroscopy and infrared spectroscopy. The results reveal that the composition of the nanoparticles is SiOxCy, that is, the portion of organic residues introduced by the precursor can be controlled by changing the oxygen concentration in the plasma gas. The mass of nanoparticles deposited on the polymer powder's surface, as determined by inductively coupled optical emission spectroscopy, shows a linear dependence of the number of cycles and the oxygen concentration in the plasma gas. A considerable improvement of the flow behavior of the PP powders is observed after PECVD treatment.<br
Keywords: nanocomposites; particle coating; plasma‐enhanced chemical vapor deposition; powder bed fusion; powder flowability

Improving the coloring of polypropylene materials for powder bed fusion by plasma surface functionalization - Gomez Bonilla, Juan Sebastian; Szymczak, Tim; Zhou, Xuemei; Schrüfer, Stefan; Dechet, Maximilian; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Additive Manufacturing, 2020)
Polypropylene (PP) powder is treated in a fluidized bed reactor with an atmospheric Ar/O2 plasma jet to investigate the influence of the plasma treatment on the coloring of the powders. The oxygen concentration in the plasma gas and duration of the treatment was varied. Contact angle and X-ray photoelectron spectroscopy measurements confirmed and quantified the formation of surface functionalities and their dependence on the process parameters. The plasma treatment contributes to a significant improvement of the dispersibility and coloring of PP. Powder bulk properties such as particle size distribution and flowability were not modified by the process. Effects of the plasma treatment on the material bulk properties are also negligible.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Color strength; Dispersibility; Plasma surface functionalization; Powder bed fusion; Powder coloring; Wettability

Increasing flowability and bulk density of PE-HD powders by a dry particle coating process and impact on LBM processes - Blümel, Christina; Sachs, Marius; Laumer, Tobias; Winzer, Bettina; Schmidt, Jochen; Schmidt, Michael; Peukert, Wolfgang; Wirth, Karl-Ernst (Rapid Prototyping Journal, 2015)
Purpose - The purpose of this paper is to demonstrate the processability of cohesive PE-HD particles in laser beam melting processes (LBM) of polymers. Furthermore, we present a characterization method for polymer particles, which can predict the quality of the powder deposition via LBM processes. Design/methodology/approach - This study focuses on the application of dry particle coating processes to increase flowability and bulk density of PE-HD particles. Both has been measured and afterwards validated via powder deposition of PE-HD particles in a LBM machine. Findings - For efficient coating in a dry particle coating process, the PE-HD particles and the attached nanoparticles need to show similar surface chemistry, i.e. both need to behave either hydrophobic or hydrophilic. It is demonstrated that dry particle coating is appropriate to enhance flowability and bulk density of PE-HD particles and hence considerably improves LBM processes and the resulting product quality. Originality/value - At present, in LBM processes mainly polyamide (PA), 12 particles are used, which are so far quite expensive in comparison to, for example, PE-HD particles. This work provides a unique and versatile method for nanoparticulate surface modification which may be applied to a wide variety of materials. After the coating, the particles are applicable for the LBM process. Our results provide a correlation between flowability and bulk density and the resulting product qualit
Keywords: Bulk density; Dry particle coating; Flowability; Hydrophilic; Hydrophobic; Polymers

Indentation and Self-Healing Mechanisms of a Self-Assembled Monolayer-A Combined Experimental and Modeling Study - Meltzer, Christian; Paul, Jonas; Dietrich, Hanno; Jäger, Christof; Clark, Timothy; Zahn, Dirk; Braunschweig, Björn; Peukert, Wolfgang (Journal of the American Chemical Society, 2014)
A combination of in situ vibrational sum-frequency generation (SFG) spectroscopy and molecular-dynamics (MD) simulations has allowed us to study the effects of indentation of self-assembled octadecylphosphonic acid (ODPA) monolayers on α-Al2O3(0001). Stress-induced changes in the vibrational signatures of C-H stretching vibrations in SFG spectra and the results of MD simulations provide clear evidence for an increase in gauche-defect density in the monolayer as a response to indentation. A stress-dependent analysis indicates that the defect density reaches saturation at approximately 155 MPa. After stress is released, the MD simulations show an almost instantaneous healing of pressure-induced defects in good agreement with experimental results. The lateral extent of the contact areas was studied with colocalized SFG spectroscopy and compared to theoretical predictions for pressure gradients from Hertzian contact theory. SFG experiments reveal a gradual increase in gauche-defect density with pressure before saturation close to the contact center. Furthermore, our MD simulations show a spatial anisotropy of pressure-induced effects within ODPA domains: molecules tilted in the direction of the pressure gradient increase in tilt angle while those on the opposite side form gauche-defects.
Keywords: spectroscopy; monolayer; self-assembly

Individualization and Stabilization of Zinc Oxide Nanorods by Covalent Functionalization with Positively Charged Catechol Derivatives - Burger, Alexandra; Srikantharajah, Rubitha; Peukert, Wolfgang; Hirsch, Andreas (Chemistry - A European Journal, 2017)
We present the formation of individualized and stabilized zinc oxide (ZnO) nanorods by functionalization with positively charged catechol derivatives by means of ligand exchange reactions. The electrosteric stabilization of ZnO nanorods was studied using two catechol derivatives, introducing either three(1) or six(2) pH independent positive charges per molecule and sterically demanding groups onto the surface. ZnO nanorods providing initially acetate (Ac) or 2-[2-(2-methoxyethoxy)-ethoxy]acetic acid (TODA) ligands on their surface were used. The ligand exchange was performed by using mono and mixed functionalization approaches, utilizing either exclusively the positively charged catechols or mixtures of the latter with small commercially available catechol derivatives, namely 4-methylcatechol (Me-cat), 4-tert-butylcatechol (tBu-cat), and dopamine hydrochloride (Dop). Using a combination of various analytical methods such as zeta potential, dynamic light scattering (DLS), UV/Vis, and scanning electron microscopy (SEM) measurements we found that the initial surfactants on the nanorods surface, the number of positive charges per molecule, the steric demand, and the added amount of the catechol derivative strongly influence the colloidal behavior of the nanorods. Stable suspensions containing individualized ZnO nanorods were successfully formed upon functionalization of ZnO-TODA nanorods with 30monolayers (MLs) of the higher charged catechol (2), as well as using mixtures of 20/10 and 18/10MLs of 2/Dop.
Keywords: catechol; colloidal sabilization; ligand exchange; surface functionalization; ZnO nanorods

Industrially scalable and cost-effective Mn2+ doped ZnxCd1-xS/ZnS nanocrystals with 70% photoluminescence quantum yield, as efficient down-shifting materials in photovoltaics - Levchuk, Ievgen; Wuerth, C.; Krause, F.; Osvet, Andres; Batentschuk, Miroslaw; Resch-Genger, Ute; Kolbeck, Claudia; Herre, Patrick; Steinrück, Hans-Peter; Peukert, Wolfgang; Brabec, Christoph (Energy and Environmental Science, 2016)
We present colloidally stable and highly luminescent ZnxCd1-xS:Mn/ZnS core–shell nanocrystals (NCs) synthesized via a simple non-injection one-pot, two-step synthetic route, which can be easily upscaled. A systematic variation of the reaction component, parameters and thickness of the ZnS shell yielded doped nanocrystals with a very high photoluminescence quantum yield ( extgreekFpl) of 70%, which is the highest value yet reported for these Mn-doped sulfide-semiconductor NCs. These materials can be synthesized with high reproducibility in large quantities of the same high quality, i.e., the same extgreekFpl using accordingly optimized reaction conditions. The application of these zero-reabsorption high quality NCs in the light conversion layers, deposited on top of a commercial monocrystalline silicon (mono-Si) solar cell, led to a significant enhancement of the external quantum efficiency (EQE) of this device in the ultraviolet spectral region between 300 and 400 nm up to ca. 12%. EQE enhancement is reflected by an increase in the power conversion efficiency (PCE) by nearly 0.5 percentage points and approached the theoretical limit (0.6%) expected from down-shifting for this Si solar cell. The resulting PCE may result in a BoM (bill of materials) cost reduction of app. 3% for mono-Si photovoltaic modules. Such small but distinct improvements are expected to pave the road for an industrial application of doped semiconductor NCs as cost-effective light converters for silicon photovoltaic (PV) and other optoelectronic applications.
EAM Import::2019-03-14

Infiltration behavior of liquid thermosets in thermoplastic powders for additive manufacturing of polymer composite parts in a combined powder bed fusion process - Setter, Robert; Riedel, Florentin; Peukert, Wolfgang; Schmidt, Jochen; Wudy, Katrin (Polymer Composites, 2021)
Polymer-based multimaterial additive manufacturing (AM) has developed into one of the most promising technologies of recent times. A processing concept was developed in previous studies, which targets the implementation of reactive liquids in a thermoplastic powder-bed for the creation of multimaterial polymer composite parts. This process aims to be the first AM process of its kind to fully utilize the potentials of both thermoplastic and thermoset polymers simultaneously. A highly important aspect for this process is the investigation of the infiltration behavior of the reactive liquids within the powder bed, since premature or delayed curing of the liquids could lead to deviations from the intended geometry as well as process errors due to material protrusions. This investigation presents an experimental and a mathematical approach to describe and predict the time which a droplet needs to completely infiltrate the powder bed. The results showed, that the experimental setup is viable to observe the droplet height over time at temperatures of up to 105°C and infiltration times below 500 ms. The mathematical model proved to be a powerful approximation to describe the infiltration behavior of a reactive liquid within a thermoplastic powder bed once a material-specific form factor is determined for each powder material. Through the process of elimination, the independence of the form factor was demonstrated for different powder parameters like the particle size. A theory is presented, which correlates the form factor to the microstructural shape and surface condition of the particles based on SEM images.
Keywords: additive manufacturing; reinforcement; 3D printing; thermoplastics; thermosets

Inflow boundary conditions determine T-mixer efficiency - Schikarski, Tobias; Trzenschiok, Holger; Peukert, Wolfgang; Avila, Marc (Reaction Chemistry & Engineering, 2019)
We report on a comprehensive experimental-computational study of a simple T-shaped mixer for Reynolds numbers up to 4000. In the experiments, we determine the mixing time by applying the Villermaux-Dushman characterization to a water-water mixture. In the numerical simulations, we resolve down to the smallest (Kolmogorov) flow scales in space and time. Excellent agreement is obtained between the experimentally measured mixing time and numerically computed intensity of segregation, especially in the turbulent regime, which validates both approaches. We confirm that the mixing time is mainly determined by the specific power input, as assumed in most mixing-models. However, we show that by suitably manipulating the inflow conditions, the power input necessary to achieve a given mixing time can be reduced by a factor of six. Our study enables detailed investigations of the influence of hydrodynamics on chemical reactions and precipitation processes, as well as the detailed testing of turbulence and micromixing models.
CRIS-Team WoS Importer:2019-03-15

Influence of annealing temperature and measurement ambient on TFTs based on gas phase synthesized ZnO nanoparticles - Walther, Sabine; Schäfer, Stefan; Jank, M. P. M.; Thiem, H.; Peukert, Wolfgang; Frey, Lothar; Ryssel, Heiner (Microelectronic Engineering, 2010)
In this paper, we report on the applicability of gas phase synthesized ZnO nanoparticles for printed electronics. Electrical characteristics of thin film transistors with an active layer based on ZnO nanoparticle dispersions are presented. A low charge carrier mobility and a low Ion/Ioff ratio are found for the devices when measured in nitrogen atmosphere. The mobility is limited by the rough interface between semiconductor and dielectric. Additional electrical measurements in dry air reveal a dependency of the Ion/Ioff ratio on surface states of the ZnO particles. It is shown that adsorption of oxygen on ZnO nanoparticles leads to improved transistor characteristics.
Keywords: Nanoparticle; Printable electronics; Thin film transistor; Zinc oxide

Influence of mechanical properties on impact fracture: Prediction of the milling behaviour of pharmaceutical powders by nanoindentation - Meier, Matthias; John, Edgar; Wieckhusen, Dierk; Wirth, Wolfgang; Peukert, Wolfgang (Powder Technology, 2009)
The impact grinding behaviour of materials can be characterized by the two breakage parameters f(Mat) and xW(m,min) [Vogel and Peukert, Powder Technol. 129 (2003) 101-110]. These parameters are usually determined by single particle milling tests. The parameters are useful for predicting the selection function and the breakage function and thus enable modelling of impact milling processes. So far, no detailed correlations have been established between the breakage parameters f(Mat) and xW(m,min) In and intrinsic material properties. In this work, we study the correlation between the breakage parameters of pharmaceutical powders and their mechanical properties (hardness, Young's modulus and fracture toughness) that are determined from indentation experiments. It will be shown that f(Mat) and xW(m,min) can be expressed in terms of the brittleness index (defined as the ratio of hardness to fracture toughness H/K-c). This correlation allows the prediction of the breakage probability of a material by using only a small number of crystals. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Comminution; Grinding; Breakage probability; Material properties; Nanoindentation; Single particle tests

Influence of mixing on precipitation of nanoparticles - Peukert, Wolfgang; Schwarzer, Hans-Christoph (Chemie Ingenieur Technik, 2002)
Precipitation is a promising method for the economic production of commercial amounts of nanoparticles because it is fast, and operable at ambient temperature. However, process control – due to the rapidity of the involved processes of mixing, nucleation, growth, and agglomeration – and stabilization against agglomeration represent challenges. This paper shows how these challenges can be successfully handled. The focus of this work is therefore set on how to tailor the particle-size distribution in continuous precipitation. Precipitation experiments with barium sulfate in a T-mixer are presented. It was found that the size of the precipitated primary particles is strongly dependent on the mixing intensity. On increasing the mixing intensity, it was possible to generate particles of approximately 50 nanometers in diameter. The second challenge, to stabilize the particles against agglomeration, was successfully met by adsorbing potential-determining ions on the particle surfaces, i.e., by increasing repulsive particle interactions. Thus, stable suspensions of barium sulfate nanoparticles were obtained.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.influe
Keywords: precipitation; nanoparticle; mixing

Influence of Mixing on the Precipitation of Organic Nanoparticles: A Lagrangian Perspective on Scale-up Based on Self-Similar Distributions - Schikarski, Tobias; Trzenschiok, Holger; Avila, Marc; Peukert, Wolfgang (Chemical Engineering & Technology, 2019)
Precipitation of nanoparticles is applied in various fields with a rising interest in the formulation of poorly soluble drugs. The impact of fluid mixing on the precipitation of organic nanoparticles is analyzed. Direct numerical simulations are applied to determine the spatiotemporal evolution of the liquid phase composition and to estimate the particle evolution along Langragian trajectories. The simulation results are compared with laboratory experiments of mixing and particle size evolution, which use a recently developed approach to rapidly stabilize the precipitated nanoparticles. The impact of mixing on precipitation is revealed, thereby enabling a parameter-free estimation of the mean particle sizes and the particle size distributions. The distributions of residence time, supersaturation time, and particle size are self-similar for Reynolds numbers in the turbulent regime and allow the derivation of scale-up rules.
CRIS-Team Scopus Importer:2019-06-25
Keywords: Direct numerical simulations; Ibuprofen; Lagrangian mixing; Nanoparticle precipitation; T-micromixer

Influence of Nanoparticle Reinforcement on the Mechanical Properties of Ultrafine-Grained Aluminium Produced by ARB - Schmidt, Christian; Knieke, Catharina; Maier, Verena; Höppel, Heinz Werner; Peukert, Wolfgang; Göken, Mathias (Materials Science Forum, 2011)
Dispersed nanoparticles are introduced from stabilized suspensions during the accumulative roll bonding process in aluminium AA1050A by air gun spraying up to a final volume fraction of 0.1 % after eight cycles. Additional strengthening caused by particle insertion is observed and strongly depends on the suspension medium and stabilizing agent as both influence interfacial bonding of the particles to the matrix. The particle insertion furthermore results in reduced peel strength of the sheets irrespective of particle material and size caused by a reduction of effective metal to metal bonding area during rolling through the presence of the particle

Influence of particle size and concentration on the second-harmonic signal generated at colloidal surfaces - Schneider, L.; Schmid, Hans-Joachim; Peukert, Wolfgang (Applied Physics B-Lasers and Optics, 2007)
Second harmonic generation (SHG) spectroscopy is a recently developed technique for the investigation of surface properties of particles. To apply the method to technical colloidal systems, the dependences of several experimental parameters on the signal have to be studied. In this work the influence of particle concentration on the SHG signal from the surfaces of colloids (polystyrene beads in a size range of 0.1 mu m to 2.9 mu m) is investigated. A simple model, based on Lambert-Beer's law, to describe the measured dependences is derived. The model agrees with the experimental observations for particles smaller 1.1 mu m and with a small modification also for larger particles. Based on the new model an analytical equation for determining the optimum concentration, where highest signals in colloidal SHG spectroscopy measurements are obtained, is derived.

Influence of process parameters on breakage kinetics and grinding limit at the nanoscale - Knieke, Catharina; Romeis, Stefan; Peukert, Wolfgang (Aiche Journal, 2011)
In long-term milling experiments, in a stirred media mill, a grinding limit where no further particle breakage occurs was identified. During mechanical stressing of the particles, defects are generated in the crystalline lattice, which allows real fracture of nanoparticles. Below a critical size, defects cannot be stored or generated in the crystallites and the overall limit of grinding is reached. This limit is strongly influenced by material properties and hardly affected by most of the process conditions. However, the breakage kinetics strongly depend on the process parameters and suspension conditions as long as the grinding limit is not reached. Based on these findings, two mechanisms of nanoparticle breakage are proposed. Proper choice of process parameters saves not only up to 90% of the energy input to reach the grinding limit but also leads to a higher product quality in terms of crystallinity and less milling bead wear.

Influence of Tail Groups during Functionalization of ZnO Nanoparticles on Binding Enthalpies and Photoluminescence - Segets, Doris; Lin, Wei; Schmidt, Jochen; Peukert, Wolfgang; Mahler, Michael; Schindler, Torben; Unruh, Tobias; Meyer, Bernd (Langmuir, 2017)
We report on the tailoring of ZnO nanoparticle (NP) surfaces by catechol derivatives (CAT) with different functionalities: tert-butyl group (tertCAT), hydrogen (pyroCAT), aromatic ring (naphCAT), ester group (esterCAT), and nitro group (nitroCAT). The influence of electron-donating/-withdrawing properties on enthalpy of ligand binding (ΔH) was resolved and subsequently linked with optical properties. First, as confirmed by ultraviolet/visible (UV/vis) and Fourier transform infrared (FT-IR) spectroscopy results, all CAT molecules chemisorbed to ZnO NPs, independent of the distinct functionality. Interestingly, the ζ-potentials of ZnO after functionalization shifted to more negative values. Then, isothermal titration calorimetry (ITC) and a mass-based method were applied to resolve the heat release during ligand binding and the adsorption isotherm, respectively. However, both heat- and mass-based approaches alone did not fully resolve the binding enthalpy of each molecule adsorbing to the ZnO surface. This is mainly due to the fact that the Langmuir model oversimplifies the underlying adsorption mechanism, at least for some of the tested CAT molecules. Therefore, a new, fitting-free approach was developed to directly access the adsorption enthalpy per molecule during functionalization by dividing the heat release measured via ITC by the amount of bound molecules determined from the adsorption isotherm. Finally, the efficiency of quenching the visible emission caused by ligand binding was investigated by photoluminescence (PL) spectroscopy, which turned out to follow the same trend as the binding enthalpy. Thus, the functionality of ligand molecules governs the binding enthalpy to the particle surface, which in turn, at least in the current case of ZnO, is an important parameter for the quenching of visible emission. We believe that establishing such correlations is an important step toward a more general way of selecting and designing ligand molecules for surface functionalization. This allows developing strategies for tailored colloidal surfaces beyond empirically driven formulation on a case by case basi
Keywords: functionalization; nanoparticle; photoluminesence

Influence of the counterion on the synthesis of ZnO mesocrystals under solvothermal conditions - Klupp Taylor, Robin; Distaso, Monica; Taccardi, Nicola; Wasserscheid, Peter; Peukert, Wolfgang (Chemistry - A European Journal, 2011)
Polymers and coordinating solvents have been shown to serve as templating agents to assist the precipitation of ZnO nanoparticles and address their morphology. In this work we show for the first time that a difference in the coordination strength between the polymer (poly-N-vinylpyrrolidone (PVP)) and the two Zn precursor salts (nitrate and acetate) is able to promote or suppress the formation of mesocrystalline structures and even more importantly to tune their three-dimensional organization. On the basis of FTIR and C NMR spectroscopic studies, we propose that not only the polymer (PVP) but also the solvent (DMF) play a key role as directing agents. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: NMR spectroscopy; optical properties; oriented attachment; poly-N-vinylpyrrolidone; ZnO mesocrystals

Influence of the polydispersity of pH 2 and pH 3.5 beta-lactoglobulin amyloid fibril solutions on analytical methods - Heyn, Timon R.; Garamus, Vasil M.; Neumann, Hendrikje R.; Uttinger, Maximilian; Guckeisen, Tobias; Heuer, Monique; Selhuber-Unkel, Christine; Peukert, Wolfgang; Keppler, Julia K. (European Polymer Journal, 2019)
It is well known that amyloid beta-lactoglobulin (BLG) fibril solutions contain a heterogeneous mixture of amyloid aggregates and non-amyloid material. However, few information are available on how strongly separated fractions of different morphologies (straight fibrils at pH 2 and worm-like aggregates at pH 3.5) vary with respect to physicochemical properties and building blocks as most analyses are conducted with unfractionized solutions where superposition effects occur. The pH-value shift resulted in an altered degree of acid hydrolysis which led to dissimilar building blocks of the aggregates (peptides at pH 2, non-hydrolyzed protein at pH 3.5). The respective separated amyloid and non-amyloid fractions showed significantly different size (SAXS, SEC, AUC) and charge properties (Zeta potential) than the whole samples. Strong superposition effects were evident with common analyses such as FTIR, TRP fluorescence and Thioflavin-T. At the same time, structural differences of pH 2 and pH 3.5 aggregates could be presented more clearly.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Amyloid aggregates; AUC; Beta-lactoglobulin; Building-blocks; Fibrils; Polydispersity; SAXS; Superposition effects; Whey-protein; Worm-like fibrils

Inorganic layers on polymeric films - influence of defects and morphology on barrier properties - Peukert, Wolfgang; Hanika, Markus; Langowski, Horst-Christian; Moosheimer, Ulrich (Chemical Engineering & Technology, 2003)
Flexible polymeric films are not only widely used in conventional packaging as substitute for glass and aluminum foil packaging but are also proposed as encapsulation for novel products, like flexible solar cells or organic light-emitting devices. The two essential properties of the polymeric packaging are flexibility and good permeation barrier properties against gases and vapors. This article deals with vacuum web coating as a common way of increasing barrier properties of polymeric films and the problems related to this procedure. Defects caused by particles and surface imperfections are found to dominate the permeation rate for such coated polymeric films. Atomic force microscopy, electron and also optical microscopy was used for analysis of the coating layer. Three-dimensional numerical simulations were performed for modeling of the influence of defect size, spacing and film thickness. Results of numerical modeling and of many practical experiments show that the permeability is almost independent of the substrate film thickness when a critical thickness is exceeded. In most cases the defects can be treated as independent of each other. The gas permeability of vacuum web-coated polymeric films can be quantitatively predicted by a simple formula. For gases, like oxygen, it is shown that a statistic analysis of the defect sizes by optical microscopy is sufficient. For water vapor transmission, however, the structure of the coating layer itself has also to be taken into account.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.inorga
Keywords: layer; polymer; film; morphology

In situ cracking of silica beads in the SEM and TEM - Effect of particle size on structure-property correlations - Paul, Jonas; Romeis, Stefan; Mackovic, Mirza; Marthala, Venkata; Herre, Patrick; Przybilla, Thomas; Hartmann, Martin; Spiecker, Erdmann; Schmidt, Jochen; Peukert, Wolfgang (Powder Technology, 2015)
Stöber Fink Bohn (SFB) silica is a well-known colloidal system: monodisperse spherical particles are readily obtained by this wet chemical synthesis route. Despite the frequent application of SFB silica, its mechanical properties are not comprehensively understood. Within this account, size dependent mechanical properties of single SFB particles are systematically investigated using in situ SEM and TEM techniques: particle properties are addressed in the size range of 1.5 μm down to 200 nm. Both, untreated particles and heat treated particles densified at 1000 °C are investigated. Structural characterization by vibrational spectroscopy, by solid state nuclear magnetic resonance spectroscopy, by scanning electron microscopy and by focused ion beam machining allows correlating mechanical properties and the internal particle structure. For untreated particles comprised of a weakly cross-linked silica network a high degree of plasticity associated with low Young’s moduli and hardness values is found. At large strains only cracking without full fracture of the particles occurs, whereby the crack path is clearly linked to the synthesis conditions: for larger particles obtained from a multistep growth process cracks propagate along weak intraparticle interfaces and are deflected around an inner core structure. After the thermal treatment cross-linking of the silica network is significantly enhanced and Young’s moduli comparable to vitreous silica accompanied by increased hardness values are found. Only the smallest particles exhibit cracking; fracture into two or more pieces is distinguished for particles above 500 nm. It is found by SEM imaging that the relative occurrence of cracking into several pieces is increasing with size - a behaviour associated with the brittle to ductile transition of silica. By testing a large quantity of particles, statistical significance is ensured.

In situ deformation and breakage of silica particles inside a SEM - Romeis, Stefan; Paul, Jonas; Herre, Patrick; Hanisch, Mathias; Klupp Taylor, Robin; Schmidt, Jochen; Peukert, Wolfgang (7th World Congress on Particle Technology, WCPT 2014, 2015)
Mechanical properties and particle breakage behavior in the submicron size range are of fundamental importance for many particle related processes and applications. Although many (in situ) studies have been dedicated to materials' size dependent mechanical characterization, particles as free standing structures have been omitted widely. An important, yet open question is the structure property relationship at small scales. Within this account, the application of a custom built manipulator for particle compression inside a scanning electron microscope (SEM) is presented: Stöber-Fink-Bohn (SFB) particles with mean diameters of 500 nm and 1000 nm are subjected to heat treatments and their mechanical properties are directly correlated to the internal structure. The as-synthesized SFB particles exhibit a complex and size dependent internal structure. Mechanical properties undermatching the values of fused silica are found and only plastic cracking at large strains is observed: cracks are formed at the surface and propagate in radial direction towards the particle center. Heat treatment leads to densification. The degree of changes is controlled by temperature and treatment time. Starting from initially low values, Young's modulus and hardness are increasing with treatment temperature. Properties of fused silica are approached or even exceeded after a treatment at 1000°C. A significant level of plasticity and high sustained deformations are still found. Whereas small particle show ductile cracking, the heat treated micron sized particles show a brittle behavior. A brittle to ductile transition in the size range of 500 nm to 1000 nm is thus identified.
Keywords: heat treatment; in situ manipulation; mechanical properties; Stöber silica; Submicron particles

In situ investigations on the amorphous to crystalline phase transformation of precursors for methanol synthesis catalysts - Güldenpfennig, Andreas; Distaso, Monica; Peukert, Wolfgang (Chemical Engineering Journal, 2019)
Two in situ methods are presented to study phase transformations in the synthesis of Cu/Zn hydroxycarbonates as catalyst precursors for industrial methanol production. In contrast to the well-established application of in situ FTIR probes in the detection of liquid phase concentrations, we evaluated spectra arising from the structural changes in the solid phase during the transformation of amorphous georgeite to nanocrystalline zincian malachite. Further, a novel microreaction system is employed to gain statistical insight on the scattering of the reaction time as a function of various process parameters. The obtained transformation kinetics during aging are described by a model based on the theory of solvent-mediated phase transformations showing excellent agreement with experimental results. The quantitative impact of temperature, concentration and zinc content on dissolution, nucleation and growth of the respective phases is discussed.
CRIS-Team WoS Importer:2019-04-23

In Situ Monitoring of Particle Formation with Spectroscopic and Analytical Techniques Under Solvothermal Conditions - Embrechts, Heidemarie; Hartmann, Martin; Peukert, Wolfgang; Distaso, Monica (Chemical Engineering & Technology, 2020)
The formation of multifunctional materials involves various simultaneous and closely entangled physicochemical processes including nucleation, growth, aggregation, and in some cases also growth by oriented aggregation. These elementary particle formation processes occur in broad size ranges from the molecular to micrometer level and time scales ranging from seconds to hours. This contribution demonstrates that the in situ monitoring of reaction mixtures and dispersions with several simultaneous analytical and spectroscopic techniques is an effective and widely applicable strategy to achieve an in-depth understanding of the formation of complex particulate structures and to move towards the rational design of materials.
CRIS-Team Scopus Importer:2020-04-21
Keywords: Carbon nanodots; Mesocrystals; Metal-organic frameworks; Oriented attachment; Particle formation

In situ Raman and FTIR spectroscopic study on the formation of the isomers MIL-68(Al) and MIL-53(Al) - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (RSC Advances, 2020)
The topological metal-organic framework isomers MIL-53 and MIL-68 form from similar educts but differ in their pore geometries. They have been known for several years, but their synthesis is always reported separately. In consequence, the underlying mechanism and decisive synthesis parameters leading to the formation of either MIL-53 or MIL-68 are not understood. The present study shows how to induce the formation of MIL-68(Al) rather than MIL-53(Al) at low synthesis temperatures in N,N-dimethylformamide (DMF) using a modulated synthesis approach. MIL-68(Al) is identified as the intermediate product of formic acid modulated synthesis, which converts into the thermodynamically stable MIL-53(Al) product at longer synthesis times. The interactions of formic acid with the synthesis precursors responsible for inducing MIL-68(Al) formation are investigated with in situ Raman and FTIR spectroscopy. In contrast to the commonly assumed modulation mechanism of competitive coordination of linker and modulator with the metal node, formic acid is shown to form hydrogen bonds via the carboxylic group of the terephthalic acid (H2BDC) linker, slowing prenucleation building unit and subsequent crystal growth. MIL-68(Al) formation is favored by the combination of a deficiency of terephthalic acid in solution and a slow MOF growth rate. Dissolved H2BDC in solution is proposed to hinder MIL-68(Al) formation by serving as a molecular template for the rhombic MIL-53(Al) pore channels.
CRIS-Team Scopus Importer:2020-03-17

In situ spectroscopy of ligand exchange reactions at the surface of colloidal gold and silver nanoparticles. - Peukert, Wolfgang; Dinkel, Rebecca; Braunschweig, Björn (Journal of Physics: Condensed Matter, 2017)
Gold and silver nanoparticles with their tunable optical and electronic properties are of great interest for a wide range of applications. Often the ligands at the surface of the nanoparticles have to be exchanged in a second step after particle formation in order to obtain a desired surface functionalization. For many techniques, this process is not accessible in situ. In this review, we present second-harmonic scattering (SHS) as an inherently surface sensitive and label-free optical technique to probe the ligand exchange at the surface of colloidal gold and silver nanoparticles in situ and in real time. First, a brief introduction to SHS and basic features of the SHS of nanoparticles are given. After that, we demonstrate how the SHS intensity decrease can be correlated to the thiol coverage which allows for the determination of the Gibbs free energy of adsorption and the surface coverage.
Keywords: nanoparticle; property; second; harmonic; scattering

In situ spectroscopy of the ligand exchange at the surface of colloidal Au nanoparticles - Dinkel, Rebecca; Braunschweig, Björn; Peukert, Wolfgang (ABSTRACTS OF PAPERS OF THE AMERICAN CHEMICAL SOCIETY, 2016)

In Situ Study on the Evolution of Multimodal Particle Size Distributions of ZnO Quantum Dots: Some General Rules for the Occurrence of Multimodalities - Schindler, Torben; Walter, Johannes; Peukert, Wolfgang; Segets, Doris; Unruh, Tobias (Journal of Physical Chemistry B, 2015)
Properties of small semiconductor nanoparticles (NPs) are strongly governed by their size. Precise characterization is a key requirement for tailored dispersities and thus for high-quality devices. Results of a careful analysis of particle size distributions (PSDs) of ZnO are presented combining advantages of UV/vis absorption spectroscopy, analytical ultracentrifugation, and small-angle X-ray scattering (SAXS). Our study reveals that careful cross-validation of these different methods is mandatory to end up with reliable resolution. PSDs of ZnO NPs are multimodal on a size range of 2-8 nm, a finding that is not yet sufficiently addressed. In the second part of our work the evolution of PSDs was studied using in situ SAXS. General principles for the appearance of multimodalities covering a temperature range between 15 and 45 °C were found which are solely determined by the aging state indicated by the size of the medium-sized fraction. Whenever this fraction exceeds a critical diameter, a new multimodality is identified, independent of the particular time-temperature combination. A fraction of larger particles aggregates first before a fraction of smaller particles is detected. Fixed multimodalities have not yet been addressed adequately and could only be evidenced due to careful size analysis.

In-Situ surface characterization of nano- and microparticles by optical Second Harmonic Generation - Schürer, Benedikt; Wunderlich, Sarina; Peschel, Ulf; Peukert, Wolfgang (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites, 2010)
Nonlinear optical spectroscopic techniques, namely Second Harmonic Generation (SHG) spectroscopy and Sum Frequency Generation (SFG), are highly interface sensitive and can be used to obtain information exclusively from the surface of particles. Second Harmonic Generation (SHG) has proven to be a versatile technique that can be used to probe different kinds of surface properties of dispersed particle systems in in-situ. Prominent examples are the direct study of molecular adsorption at the surface of particles and the determination of surface potentials of nano- and microparticles. However, in most of these studies well-defined spherical and monodisperse particles with low number densities were used. Here we demonstrate the application of the SHG technique for the study of more complex and technically relevant particle systems. We discuss the influence of particle concentration and particle size distribution. Moreover, we apply a novel nonlinear Mie Model that is capable to simulate the SH scattering from the surface of spherical particles and we show that the model can be used to extract information about molecules at the particle liquid interfac
Keywords: Nonlinear Mie model; Nanoparticles; Second Harmonic Generation; Optics; Surface characterization

In Situ Surface Characterization of Polydisperse Colloidal Particles by Second Harmonic Generation - Schürer, Benedikt; Peukert, Wolfgang (Particulate Science and Technology, 2010)
Optical second harmonic generation (SHG) has a high potential for studying surface properties of colloidal particles in situ with a high temporal resolution. In the past the SHG technique has been applied successfully to determine the surface potential of colloidal particles and emulsion droplets and to study adsorption processes at the interface of solid and liquid particles. However, in previous studies mainly monodisperse particles were used. Here we demonstrate that it is also possible to study adsorption processes on polydisperse particle systems with SHG by comparing in situ adsorption measurements on monodisperse and on polydisperse mixtures of polystyrene (PS) particles. In addition, the results suggest that SHG is also applicable for surface characterization of polydisperse samples at high particle concentrations, where absorption and scattering of the particles is dominant.

In-situ X-ray diffraction analysis of the recrystallization process in Cu2ZnSnS4nanoparticles synthesised by hot-injection - Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Azimi, Seyed Hamed; Hou, Yi; Peukert, Wolfgang; Brabec, Christoph; Hock, Rainer (Thin Solid Films, 2015)
Kesterite CuZnSnS(CZTS) is a promising material for thin film solar cell applications. The biggest advantages of this compound lie in the abundance and non-toxicity of the contained elements. Low temperature hot injection synthesis can provide an economic way to produce CZTS nanoparticles for application in solution processed solar cells. Powder X-ray diffraction (PXRD) measurements on the as-synthesised particles suggest that the crystal structure is cubic and can be best described as sphalerite-like. This means that the cations in the CZTS are statistically distributed on the cation sites of the crystal lattice rather than well-ordered like in the tetragonal kesterite structure. An in-situ PXRD measurement while annealing the particles up to 550 °C revealed a recrystallization process that transforms the structure from cubic to tetragonal meaning an ordering of the cations.
Keywords: Copper zinc tin sulphide; Cubic phase; Hot-injection synthesis; In-situ; Phase transition; Tetragonal phase; X-ray diffraction

In-Situ X-ray Diffraction Analysis of the Recrystallization Process in Cu2ZnSnS4 Nano Particles Synthesized by Hot-Injection - Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Azimi, Hamed; Hou, Yi; Peukert, Wolfgang; Brabec, Christoph; Hock, Rainer (Thin Solid Films, 2015)
Kesterite Cu2ZnSnS4 (CZTS) is a promisingmaterial for thin film solar cell applications. The biggest advantages of this compound lie in the abundance and non-toxicity of the contained elements. Low temperature hot injection synthesis can provide an economic way to produce CZTS nanoparticles for application in solution processed solar cells. Powder X-ray diffraction (PXRD) measurements on the as-synthesised particles suggest that the crystal structure is cubic and can be best described as sphalerite-like. This means that the cations in the CZTS are statistically distributed on the cation sites of the crystal lattice rather than well-ordered like in the tetragonal kesterite structure. An in-situ PXRD measurement while annealing the particles up to 550 °C revealed a recrystallization process that transforms the structure from cubic to tetragonal meaning an ordering of the cations.
EAM Import::2019-03-13

Integrated processes for nanoscale products with new application properties Integrierte Prozesse für nanoskalige Produkte mit neuen Anwendungseigenschaften - Peukert, Wolfgang; et al. (Chemie Ingenieur Technik, 2005)

Interaction of light with hematite hierarchical structures: Experiments and simulations - Distaso, Monica; Zhuromskyy, Oleksandr; Seemann, Benjamin; Pflug, Lukas; Mackovic, Mirza; Encina, Ezequiel Roberto; Klupp Taylor, Robin; Müller, Rolf; Leugering, Günter; Spiecker, Erdmann; Peschel, Ulf; Peukert, Wolfgang (Journal of Quantitative Spectroscopy & Radiative Transfer, 2017)
Mesocrystalline particles have been recognized as a class of multifunctional materials with potential applications in different fields. However, the internal organization of nanocomposite mesocrystals and its influence on the final properties have not yet been investigated. In this paper, a novel strategy based on electrodynamic simulations is developed to shed light on how the internal structure of mesocrystals influences their optical properties. In a first instance, a unified design protocol is reported for the fabrication of hematite/PVP particles with different morphologies such as pseudo-cubes, rods-like and apple-like structures and controlled particle size distributions. The optical properties of hematite/PVP mesocrystals are effectively simulated by taking their aggregate and nanocomposite structure into consideration. The superposition T-Matrix approach accounts for the aggregate nature of mesocrystalline particles and validate the effective medium approximation used in the framework of the Mie theory and electromagnetic simulation such as Finite Element Method. The approach described in our paper provides the framework to understand and predict the optical properties of mesocrystals and more general, of hierarchical nanostructured particles.
Keywords: Effective medium approximation; FEM; Maxwell-Garnett theory; Mesocrystals; Scattering; T-Matrix

Interfacial energy estimation in a precipitation reaction using the flatness based control of the moment trajectories - Vassilev, Vassil; Gröschel, Michael; Schmid, Hans-Joachim; Peukert, Wolfgang; Leugering, Günter (Chemical Engineering Science, 2010)
In this paper, we consider a model for precipitation experiments based on the population balance equation. The study revealed a high sensitivity of the system with respect to the modeling of intrinsic parameters, motivating a comprehensive validation of the estimates. In the forward simulation the impact of the influencing parameters including surface energy, nucleus size and distribution is investigated. Subsequently we construct a simplified model of the precipitation process in such a way that it is orbitally flat in terms of control theory, which enables the inverse calculation of the parameters. The numerical results of the inverse simulation for the interfacial energy have been compared to a physical model. The possibility of solving the inverse problem provides a promising way of estimating hardly measurable quantities for more complex molecules.

Interplay of Internal Structure and Interfaces on the Emitting Properties of Hybrid ZnO Hierarchical Particles - Distaso, Monica; Bertoni, Giovanni; Todisco, Stefano; Marras, Sergio; Gallo, Vito; Manna, Liberato; Peukert, Wolfgang (ACS Applied Materials and Interfaces, 2017)
The design of hybrid organic/inorganic nanostructures with controlled assembly drives the development of materials with new or improved properties and superior performances. In this paper, the surface and internal structure of hybrid ZnO poly-N-vinylpyrrolidone (ZnO/PVP) mesocrystals are investigated in detail and correlated with their emitting properties. A photoluminescence study at room temperature reveals that the as-synthesized particles show a remarkable ultraviolet (UV) emission, whereas an emission from defects in the visible region is not observed. On the other hand, a visible emission is achieved upon calcination of the hybrid ZnO/PVP particles in air, and its intensity is found to increase with the calcination temperature and, in some cases, to overwhelm the UV emission. A molecular description is proposed for the absence of a visible emission from defects in the as-synthesized ZnO/PVP mesocrystals on the basis of Fourier transform infrared (FTIR) and solid-state (13)C NMR (SSNMR) spectroscopy. An in-depth electron microscopy study sheds light on the internal organization of mesocrystals and reveals the formation of nanoreactors, that is, particles with enclosed porosity, upon thermal treatment.
Keywords: structure-function relationship; nanoreactors; postprocessing; coordination; nanocomposites; mesocrystals

Intracellular Drug Delivery with Anodic Titanium Dioxide Nanotubes and Nanocylinders - Hasanzadeh Kafshgari, Morteza; Mazare, Anca Valentina; Distaso, Monica; Goldmann, Wolfgang; Peukert, Wolfgang; Fabry, Ben; Schmuki, Patrik (ACS Applied Materials and Interfaces, 2019)
Titanium dioxide (TiO 2 ) holds remarkable promises for developing current theranostic strategies. Anodic TiO 2 nanostructures as a porous scaffold have offered a broad range of useful theranostic properties; however, previous attempts to generate single and uniform TiO 2 one-dimensional nanocarriers from anodic nanotube arrays have resulted in a broad cluster size distribution of arbitrarily broken tubes that are unsuitable for therapeutic delivery systems due to poor biodistribution and the risk of introducing tissue inflammation. Here, we achieve well-separated, uniformly shaped anodic TiO 2 nanotubes and nanocylinders through a time-varying electrochemical anodization protocol that leads to the generation of planar sheets of weakly connected nanotubes with a defined fracture point near the base. Subsequent sonication cleanly detaches the nanotubes from the base. Depending on the position of the fracture point, we can fabricate single-anodic nanocylinders that are open on both ends and nanotubes that are closed on one end. We proceed to show that anodic nanotubes and nanocylinders are nontoxic at therapeutic concentrations. When conjugated with the anticancer drug doxorubicin using a pH-responsive linker, they are readily internalized by cells and subsequently release their drug cargo into acidic intracellular compartments. Our results demonstrate that uniformly sized anodic TiO 2 nanotubes and nanocylinders are suitable for subcellular delivery of therapeutic agents in cancer therapy.
CRIS-Team Scopus Importer:2019-05-09
Keywords: electrochemical anodization; intracellular drug delivery; nanocylinders; nanotubes; titanium dioxide

Intrinsically stable dispersions of silicon nanoparticles. - Reindl, Armin; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2008)
Stable suspensions of silicon nanoparticles (SiNP) were fabricated by dispersion in 1-butanol as well as ethanol without the application of an additive. In order to achieve an in-depth insight into the stabilizing mechanism, the particle-particle interactions need to be considered. In this respect the total interaction energy of the silicon nanoparticles in 1-butanol and ethanol was calculated for three model systems according to the DLVO theory: (1) two solid silicon spheres, (2) two spheres with a silicon core and an amorphous silicon dioxide shell, and (3) two spheres with a silicon core, an amorphous silicon dioxide shell and a monolayer of adsorbed solvent molecules. The results of the calculations are evaluated and discussed with regard to experimental data obtained by diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), high resolution transmission electron microscopy (HRTEM), and zeta potential measurements.

Intrinsic and Extrinsic Incorporation of Indium and Single-Walled Carbon Nanotubes for Improved ZnO-Based DSSCs - Schol, Peter; Zhang, Wen Shan; Scharl, Tobias; Kunzmann, Andreas; Peukert, Wolfgang; Schröder, Rasmus R.; Guldi, Dirk Michael (Advanced Energy Materials, 2022)
A common goal in renewable energy research is the production of semiconductor layers with matching additives to gain desirable effects and advantages. Important examples are adjustment of the band gap, enhancing the conductivity, tailoring roughness of the semiconductor, or reducing the recombination rate of charge carriers. In this work a twofold approach is demonstrated. First, the intrinsic incorporation of indium into zinc oxide tunes the band gap of the semiconductor layer of the DSSCs. Second, single-walled carbon nanotubes (SWCNT) as an extrinsic additive improves the charge transport capabilities. To better combine the SWCNTs with the semiconductor layer a protective ZnO shell is grown on the SWCNTs. A combination of current–voltage, incident photon to current efficiency, and electrochemical impedance spectroscopic assays corroborates the positive effects of both additives on the cell performance. The effective charge-carrier diffusion lengths are enhanced from 0.52 µm for pure ZnO to 5.12 µm for low SWCNT concentrations and 15 mol% of indium. This, as well as the increase in collection efficiency from 30.3% to 62.3% enables enhanced transport in these novel devices. A final device utilizing 0.1 wt% SWCNT@ZnO20nm and In15Zn85O yields a current density of 16.49 mA cm−2 and an efficiency of 4.46%.
CRIS-Team Scopus Importer:2022-03-11
Keywords: indium–zinc oxide photoanodes; n-type DSSCs; semiconductor doping; single-wall carbon nanotubes

Invertible architectures from amphiphilic polyesters. - Peukert, Wolfgang; Voronov, Andriy; Kohut, Ananiy; Gevus, O.; Tokarev, Victor; Voronov, Stanislav (Langmuir, 2006)
We synthesized and characterized novel amphiphilic polyesters with both hydrophilic and hydrophobic functionalities. The polyesters are soluble in organic and aqueous media and reveal the formation of inverse architectures whose behavior could be correlated to their chemical structure. We foresee that the amphiphilic properties of the polyesters reported here are obviously the basis of new architectures both in solution and on the solid surfaces, which could be used in a broad range of applications. The described synthesis of the copolymers is very simple and is based on commercially available products. That makes this approach attractive in various uses.
Keywords: synthesis; characterization; polymer; functionality

Invertible polymers for the stabilization of nanoparticles - Peukert, Wolfgang; Kohut, Ananiy; Voronov, Andriy (NSTI-Nanotech 200, 2007)
Novel amphiphilic polyesters with both hydrophilic and hydrophobic functionalities being alternately distributed along polymer backbones have been synthesized and characterized. The polyesters are soluble in organic and aqueous media and reveal the formation of inverse architectures whose behavior could be correlated to their chemical structure. This work offers a new approach to building up self-adjustable invertible polymer coatings at solid surfaces. The approach is based on a two-step process. In the first step, the surface of dispersed titania or silicon wafers has been functionalized with the aid of a reactive copolymer, viz., poly(styrene-alt-maleic anhydride) (PSM), to which, in the second step, the chains of amphiphilic polyester have been tethered. The modified titania can form stable suspensions in both polar and nonpolar media. An environmentally induced switching of the surface properties has been observed via the AFM of silicon wafers with tethered polyester chains.
Keywords: Colloidal stability; Invertible polymers; Synthesis

Investigating the Surface of Nanoparticles by Second Harmonic Generation - Wunderlich, Sarina; Peschel, Ulf; Schürer, Benedikt; Peukert, Wolfgang (Conference on Lasers and Electro-Optics (CLEO)/Quantum Electronics and Laser Science Conference (QELS), 2010)
We investigate Second Harmonic Generation at the surface of nanoparticles both by modeling and experiment. We present an ab initio simulation method, which allows deducing surface properties as well as the nature of adsorbed molecules. (C) 2010 Optical Society of America

Investigation of a flame spray pyrolysis process using several optical measurement techniques - Münsterjohann, Bettina; Huber, Franz; Stanzel, Melanie; Peukert, Wolfgang; Will, Stefan (International Congress Engineering of Advanced Materials, 2017)
The flame spray pyrolysis (FSP) process is one of the mostly used gas-phase techniques in industry and research to produce a broad spectrum of complex and functional nanoparticles on acommercial scale. Nanoparticulate oxides, including zinc oxide (ZnO), gallium(III)-oxide (Ga2O3) or indium(III)-oxide (In2O3) are low cost and promising materials for electronic and optical devices. To cover the high demand of these interesting materials, FSP turned out to be an economic, energy- and cost-efficient syntheses method. In the flame droplet formation, evaporation, combustion, nanoparticle formation and finally particle growth, agglomeration and sintering takes place. For the production of nanoparticles with well-defined properties, a detailed understanding of the interplay between these different particle formation steps and the influence of varying process conditions on the resulting nanoparticles is essential. However, due to the highly turbulent and multiphase character of the spray flame it is still limited.As the droplet formation and evaporation is one of the first crucial steps in the FSP process, it was characterized by Mie-scattering, Phase-Doppler Anemometry (PDA) and shadowgraphymeasurements under different process conditions. PDA allows for pointwise droplet velocity and droplet size measurements whereas the spray geometry with its spray angle and height was analyzed by shadowgraphy measurements and Mie-scattering. The ethanol spray was investigatedat both conditions with and without a flame so that the influence of evaporation and combustion on the droplet formation can be analyzed. In order to localize the nucleation zone where particle formation takes place, chemiluminescence measurements were performed for different material systems like pure metal oxides (ZnO, TiO2, SnO, Ga2O3, In2O3) and mixed oxides (ITO, indium zinc oxide, gallium zinc oxide). Furthermore the influence of varying precursor flow rates (2.5 l/min to 10 l/min) and precursor concentrations (0.1 mol/l to 0.5 mol/l) on the size and location of the nucleation zone was investigated. As temperature is one of the most important factors influencing particle size, morphology and crystallinity initial tests for measurements of temperature fields by Two-Line Atomic Fluorescence (TLAF) were performed. Finally, the sizes of the aggregates formed were determined by wide-angle light scattering (WALS
Keywords: PDA; shadowgraphy; Mie-scattering; chemiluminescence; TLAF; WALS

Investigation of the size-property relationship in CuInS2 quantum dots - Akdas, Tugce; Walter, Johannes; Segets, Doris; Distaso, Monica; Winter, Benjamin; Birajdar, Balaji; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2015)
In this work we investigated fundamental properties of CuInS2 quantum dots in dependence of the particle size distribution (PSD). Size-selective precipitation (SSP) with acetone as poor solvent was performed as an adequate post-processing step. Our results provide deep insight into the correlation between particle size and various optical characteristics as bandgap energy, absorption and emission features and the broadness of the emission signal. These structure-property relationships are only achieved due to the unique combination of different analytical techniques. Our study reveals that the removal of 10 wt% of smallest particles from the feed results in an enhancement of the emission signal. This improvement is ascribed to a decreased quenching of the emission in larger particles. Our results reveal the impact of PSDs on the properties and the performance of an ensemble of multicomponent QDs and anticipate the high potential of controlling PSDs by well-developed post-processing.

In vitro reactivity of Cu doped 45S5 Bioglass® derived scaffolds for bone tissue engineering - Hoppe, Alexander; Meszaros, Robert; Staehli, Christoph; Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang; Marelli, Benedetto; Nazhat, Showan N.; Wondraczek, Lothar; Lao, Jonathan; Jallot, Edouard; Boccaccini, Aldo R. (Journal of Materials Chemistry B, 2013)
Cu-doped 45S5 bioactive glasses with varying Cu contents were fabricated and used to process 3D porous scaffolds via the foam replica technique. Cu-doping results in the weakening of the glass network and a decrease in its glass transition temperature. Acellular in vitro studies revealed very high bioactivity independent of Cu doping as indicated by the fast formation of a carbonated hydroxyapatite layer (CHA) on scaffold surfaces after immersion in simulated body fluid (SBF). The kinetics of the glass-ceramic scaffold's transition to an amorphous calcium phosphate layer (ACP) and the crystallisation of CHA were explored by FT-IR and SEM analyses. The elemental distribution in the scaffold/fluid interface region was monitored by the advanced micro-PIXE-RBS (particle induced X-ray emission/Rutherford backscattering spectrometry) method. Cu-containing glasses showed slower release of Si, Ca and P from the scaffold periphery, whereas traces of Cu were found incorporated in the CaP layer on the scaffold surface. Cu release kinetics from the scaffolds in SBF were found to depend on culturing conditions while highest Cu concentrations of ∼3.1 ppm and ∼4.6 ppm under static and quasi-dynamic conditions, respectively, were observed. Since Cu exhibits potential angiogenic and osteogenic properties, the Cu-containing scaffolds are suggested as promising materials for bone tissue engineering applications. © 2013 The Royal Society of Chemistry.
UnivIS-Import:2015-03-09:Pub.2013.tech.IW.LM.invitr_2

Ionomer and protein size analysis by analytical ultracentrifugation and electrospray scanning mobility particle sizer - Wawra, Simon; Thoma, Martin; Walter, Johannes; Lübbert, Christian; Thajudeen, Thaseem; Damm, Cornelia; Peukert, Wolfgang (European Biophysics Journal, 2018)
Keywords: Analytical ultracentrifugation; Scanning mobility particle sizer; Combined analysis; Multiwavelength detector

Isoelectric Point of Proteins at Hydrophobic Interfaces - Lautenbach, Vanessa; Hosseinpour, Saman; Peukert, Wolfgang (Frontiers in Chemistry, 2021)
Structural and colloidal stability of proteins at different surfaces and interfaces is of great importance in many fields including medical, pharmaceutical, or material science. Due to their flexibility, proteins tend to respond to their environmental conditions and can undergo structural and conformational changes. For instance, alterations in physiological factors such as temperature, ions concentration, or pH as well as the adsorption to an interface can initiate protein aggregation. Therefore, at different surfaces and interfaces the characterization of the structural and colloidal stability of proteins, which is mainly influenced by their electrostatic and hydrophobic interactions, is of fundamental importance. In this study, we utilized sum frequency generation (SFG) spectroscopy to assess the role of solution pH on the polarity and magnitude of the electric field within the hydration shell of selected model proteins adsorbed to a hydrophobic surface. We used polystyrene (PS) as a model hydrophobic surface and determined the isoelectric point (IEP) of four structurally different model proteins. Comparing the measured IEP of proteins at the PS/solution or air/solution interface with that determined in the bulk solution via zeta potential measurement, we found significant similarities between the IEP of surface adsorbed proteins and those in the bulk aqueous phase. The pH dependence behavior of proteins was correlated to their amino acid composition and degree of hydrophobicit
Keywords: proteins; isoelectric point; sum frequency generation spectroscopy; surface hydrophobicity; zeta potential

Isoelectric points of proteins at the air/liquid interface and in solution - Guckeisen, Tobias; Hosseinpour, Saman; Peukert, Wolfgang (Langmuir, 2019)
Electrostatic interactions play essential roles in determining the function, colloidal stability, and adsorption of proteins on different surfaces and interfaces. Therefore, a molecular level understanding of the charge state of the proteins under different conditions is required to explain their macroscopic properties. In this study we have employed an inherently surface sensitive spectroscopic tool, sum frequency generation spectroscopy, to determine the charge state of a wide range of proteins as a function of pH at the liquid/air interface via measurement of the degree of orientation of water molecules. We compared the isoelectric point of the 12 investigated proteins at the liquid/air interface with that in the bulk solution obtained through zeta potential measurements. Ellipsometry is performed to determine the film thickness at the liquid/air interface at different charge states. In particular, protein aggregation at the isoelectric point is reflected by increased film thickness. For all proteins, the interfacial point of zero charge is close (with less than 1 pH unit variation) to that in the bulk solution.
Keywords: protein; potential; charge; surface

Isolation and Purification of Single Gold Nanoclusters by Alternate Pumping Chromatography - Supper, Malvina; Birner, Virginia; Gromotka, Lukas; Peukert, Wolfgang; Kaspereit, Malte (Separations, 2023)
Alternate pumping chromatography is applied to obtain atomically precise glutathione-stabilized gold nanoclusters in high purity from synthesized mixtures. On the basis of anion exchange chromatography, the feasibility of isolating a single cluster, Au10 GSH10, as well as two different clusters simultaneously (Au25 GSH18 and Au29 GSH20) is demonstrated. In addition, Au18 GSH14, which is present only in trace amounts, is successfully enriched. A simple design procedure is proposed that allows using columns with different retention behavior. Successful experiments with large injection amounts confirm the potential of the concept for preparative-scale productions of high-quality nanoparticulate product

Kinetics of radical formation during the mechanical activation of quartz - Damm, Cornelia; Peukert, Wolfgang (Langmuir, 2009)
The kinetics of radical formation during the mechanical activation of quartz by wet grinding or sonication was investigated using 2,2-diphenyl-1- picrylhydrazyl (DPPH) as a scavenger. The consumption of DPPH during the sonication of quartz in an ethanol suspension is a zeroth-order process. A linear relationship between the rate constant of the DPPH consumption and the quartz concentration in the suspension indicates that radical formation under sonication increases with the growing total surface area of the quartz particles. Sonication leads to the formation of free radicals by the mechanical activation of the particle surface. The kinetics of the DPPH consumption during wet grinding of quartz in a stirred media mill is described successfully by a modified zeroth-order rate law taking the total surface area of the quartz particles into account. The surface-normalized rate constant of the DPPH consumption decreases from 1.8 × 10 mol L h m to 4.8 × 10 mol L h m if the specific surface area of the feed material increases from 0.5 to 84 m/g. This finding indicates that the breakage of the quartz particles contributes much more to radical formation than does the mechanical activation of the particles in the mill because the breakage rate increases with growing particle diameter. Ethanol but not DPPH was found on the surface of the ground quartz particles. From this finding, it can be concluded that radicals on the surface of the quartz particles react with ethanol, leading to the formation of ethanol radicals and H radicals. DPPH reacts with the H radicals. As a side reaction, radicals can react with oxygen, leading to the formation of peroxides. © Copyright 2009 American Chemical Society.

Kunststoffpulver für die Additive Fertigung: Vorhersage des Prozessverhaltens mittels prozessangepasster Analyse / Plastic powder for Additive Manufacturing: Prediction of process behavior based on process adapted characterization - Wudy, Katrin; Schmidt, Jochen; Lanzl, Lydia; Zhao, Meng; Jaksch, Andreas; Dechet, Maximilian; Hesse, Nicolas; Drummer, Dietmar; Peukert, Wolfgang (Vom Pulver zum multifunktionalen Bauteil, 2019)

Laser Beam Melting in Powder Bed of nonspherical aluminium microparticles dry coated with metal nanoparticles - Karg, Michael; Ahuja, Bhrigu; Schmidt, Jochen; Winzer, Bettina; Wirth, Karl-Ernst; Peukert, Wolfgang; Schmidt, Michael (Proceedings [Elektronski vir] / 6th International Conference on Additive Technologies iCAT2016, 2016)
Out of all Al alloys, Laser Beam Melting in Powder Bed (LBM) is almost exclusively used to process Al-Si cast alloys today. Feasibility of LBM of high-performance Al-Cu wrought alloys was published previously by the authors. Prealloyed powders are used for LBM. Small amounts or less common application-specific alloys must be atomized on request which is expensive, time consuming and of varying quality. Instead, during LBM alloys might form from mixtures of few basic powders. If density differs strongly as e. g. with Al and Cu, powders de-mix uncontrollably due to gravity. In LBM, spherical inert gas atomized powders are used. Cheaper non-spherical air atomized Al powders deposit insufficiently homogeneous in thin powder layers. LBM of Metal Matrix Composites (MMC) was shown using mechanical alloying that was time-consuming, affected particle size and shape. The goal of this contribution is to investigate the feasibility of an approach towards larger freedom of choice in LBM regarding all aforementioned dimensions of alloy composition, MMC creation and non-spherical base powders. Metal nanoparticles (np) were dry coated onto air atomized Al alloy micro particles. Powders with adhering np and LBM products were analyzed and compared to previous results.</
Keywords: metal nanoparticle adhesion; air atomized aluminium powder Metal Matrix Composite MMC; in-situ alloying; Selective Laser Melting SLM; powder bed fusion

Layer-by-Layer Assemblies of Catechol-Functionalized TiO2 Nanoparticles and Porphyrins through Electrostatic Interactions - Burger, Alexandra; Costa, Ruben Dario; Lobaz, Volodymyr; Peukert, Wolfgang; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2015)
In the current work, we present the successful functionalization and stabilization of P-25 TiO2 nanoparticles by means of N1,N7-bis(3-(4-tert-butyl-pyridium-methyl)phenyl)-4-(3-(3-(4-tert-butyl-pyridinium-methyl)phenylamino)-3-oxopropyl)-4-(3,4-dihydroxybenzamido)heptanediamide tribromide (1). The design of the latter is aimed at nanoparticle functionalization and stabilization with organic building blocks. On one hand, 1 features a catechol anchor to enable its covalent grafting onto the TiO2 surface, and on the other hand, positively charged pyridine groups at its periphery to prevent TiO2 agglomeration through electrostatic repulsion. The success of functionalization and stabilization was corroborated by thermogravimetric analysis, dynamic light-scattering, and zeta potential measurements. As a complement to this, the formation of layer-by-layer assemblies, which are governed by electrostatic interactions, by alternate deposition of functionalized TiO2 nanoparticles and two negatively charged porphyrin derivatives, that is, 5,10,15,20-(phenoxyacetic acid)-porphyrin (2) and 5,10,15,20-(4-(2-ethoxycarbonyl)-4-(2-phenoxyacetamido)heptanedioic acid)-porphyrin (3), is documented. To this end, the layer-by-layer deposition is monitored by UV/Vis spectroscopy, scanning electron microscopy, ellipsometry, and profilometry techniques. The resulting assemblies are utilized for the construction and testing of novel solar cells. From stable and repeatable photocurrents generated during several ön-offc̈ycles of illumination, we derive monochromatic incident photo-to-current conversion efficiencies of around 3 \

Ligand-assisted thickness tailoring of highly luminescent colloidal CH3NH3PbX3 (X = Br and I) perovskite nanoplatelets - Levchuk, Ievgen; Herre, Patrick; Brandl, Marco; Osvet, Andres; Hock, Rainer; Peukert, Wolfgang; Schweizer, Peter; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph (Chemical Communications, 2017)
Quantum size-confined CHNHPbX (X = Br and I) perovskite nanoplatelets with remarkably high photoluminescence quantum yield (up to 90%) were synthesized by ligand-assisted re-precipitation. Thickness-tunability was realized by varying the oleylamine and oleic acid ligand ratio. This method allows tailoring the nanoplatelet thickness by adjusting the number of unit cell monolayers. Broadly tunable emission wavelengths (450-730 nm) are achieved via the pronounced quantum size effect without anion-halide mixing.

Liquid filtration of nanoparticles through track-etched membrane filters under unfavorable and different ionic strength conditions: Experiments and modeling - Peukert, Wolfgang; Segets, Doris; Süß, Sebastian; Chen, Sheng-Chieh; Pui, David; Lee, Handol (Journal of Membrane Science, 2017)
Nanoparticle deposition experiments under unfavorable conditions were conducted experimentally and theoretically. The 0.2 and 0.4 µm rated track-etched membrane filters were challenged with 60, 100, 147, 220, 350 and 494 nm polystyrene latex (PSL) particles with different ionic strengths ranging from 0.005 to 0.05 M. The capillary tube model, with replacing the viscosity of air to water, was used to estimate the initial efficiency, or the transport efficiency of the particles to the filter surface, which was corrected in a second step by allowing the detachment of the nanoparticles according to the sum of adhesive and hydrodynamic torques. The adhesive torques were derived from surface interactions accessed by the extended DLVO theory. Calculation results showed that the adhesive torque of a particle located in the calculated primary minimum was slightly larger than the hydrodynamic torque, resulting in particle deposition. However, experimental data clearly indicated that detachment occurred. This could only be explained by the presence of additional hydration forces, leading to a larger separation which became relevant at high ionic strengths. By including hydration into our theoretical framework, experiment and theory were in very good agreement under all different ionic strength conditions. The findings allow a basic understanding of surface interactions between nanoparticles and membranes in micro- and ultra-filtration applications for drinking water production, wastewater treatment and particle free water production in industries.
Keywords: Adhesive and hydrodynamic torque; Derjaguin-Landau-Verwey-Overbeek (DLVO) theory; Microfiltration; Short range hydration effects; Track-etched polycarbonate membrane filter

Local densification of a single micron sized silica sphere by uniaxial compression - Romeis, Stefan; Paul, Jonas; Herre, Patrick; de Ligny, Dominique; Schmidt, Jochen; Peukert, Wolfgang (Scripta Materialia, 2015)

London-van der Waals adhesiveness of rough particles - Lin, Qi; Rudolph, Victor; Peukert, Wolfgang (Powder Technology, 2006)
Van der Waals forces often dominate interactions and adhesion between fine particles and, in turn, decisively influence the bulk behaviour of powders. However, so far there is no effective means to characterize the adhesive behaviour of such particles. A complication is that most powder particles have rough surfaces, and it is the asperities on the surfaces that touch, confounding the actual surface that is in contact. Conventional approaches using surface energy provide limited information regarding adhesion, and pull-off forces measured through atomic force microscope (AFM) are highly variable and difficult to interpret. In this paper we develop a model which combines the Rumpf-Rabinovich and the JKR-DMT theories to account simultaneously for the effects of surface roughness and deformation on adhesion. This is applied to a 'characteristic asperity' which may be easily obtained from AFM measurements. The concept of adhesiveness, a material property reflecting the influences of elastic deformability, surface roughness, and interfacial surface energy, is introduced as an efficient and quantitative measure of the adhering tendency of a powder. Furthermore, a novel concept of specific adhesiveness is proposed as a convenient tool for characterizing and benchmarking solid materials. This paper provides an example to illustrate the use of the proposed theories. © 2005 Elsevier B.V. All rights reserve
Keywords: Adhesion; Adhesiveness; Effective contact area; Fine particles; Specific adhesiveness; Van der Waals force

Low temperature formation of CuIn1 - xGaxSe2solar cell absorbers by all printed multiple species nanoparticulate Se + Cu-In + Cu-Ga precursors - Möckel, Stefan; Wernicke, Tobias; Arzig, Matthias; Köder, Philipp; Brandl, Marco; Ahmad, Rameez; Distaso, Monica; Peukert, Wolfgang; Hock, Rainer; Wellmann, Peter (Thin Solid Films, 2015)
In this work an all nanoparticulate precursor for application in Cu(InGa)Sesolar cell absorbers is presented. Binary Cu-In nanoparticles, Cu-Ga powder and elemental Se nanoparticles were mixed in dispersion and deposited on Mo-coated substrates. Research was focused on Cu(InGa)Selayer formation kinetics, phase composition characterised by differential scanning calorimetry and in-situ X-ray diffraction (XRD). Furthermore phase composition and morphology were studied by ex-situ XRD, Raman spectroscopy and scanning electron microscopy. The results revealed a fast consumption of the precursor and the formation of CuInSebelow 340 °C. Binary secondary phases were not observed at any temperature.
Keywords: Low-temperature; Copper indium gallium diselenide; Chalcopyrite; Nanoparticulate precursors; In-situ X-ray diffraction; Bimetallic nanoparticles

Lubrication of Individual Microcontacts by a Self-Assembled Alkyl Phosphonic Acid Monolayer on α-Al2O3(0001) - Paul, Jonas; Meltzer, Christian; Braunschweig, Björn; Peukert, Wolfgang (Langmuir, 2016)
We report on the tribological behavior of a self-assembled alkyl phosphonic acid monolayer on the microscale using the colloidal probe technique. Friction-load data and adhesion forces were measured with borosilicate glass particles on uncoated and octadecylphosphonic acid (ODPA) coated α-AlO(0001) surfaces. A significant decrease in friction force was observed after surface coating, while the adhesion force was only moderately reduced. We assume the lubrication effect of the ODPA self-assembled monolayer (SAM) to be close to the maximum obtainable of alkyl phosphonic acids in the studied system due to the high molecular order which was confirmed by vibrational sum-frequency generation. At small loads, a nonlinear dependence of friction force to load was maintained after surface coating. However, a shift from a contact behavior well described by the DMT model toward the JKR model occurred that is possibly related to the altered elastic properties of the coated surface. With increasing load, a linear friction-load behavior was observed on the coated samples. Molecular plowing and adhesive interactions were identified as responsible mechanisms. In all friction experiments, we could not detect any wear neither of the colloidal probes nor at the surfaces of uncoated and coated samples. This proves the high wear resistivity of the studied ODPA SAM.

Magnéli Phases Doped with Pt for Photocatalytic Hydrogen Evolution - Wierzbicka, Ewa; Domaschke, Maximilian; Denisov, Nikita; Fehn, Dominik; Hwang, Imgon; Kaufmann, Marlena; Kunstmann, Babette; Schmidt, Jochen; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Applied Energy Materials, 2019)
Defined TiOx suboxides (Magnéli phases) have rarely been investigated in photocatalysis. In the current work we describe a one-step synthesis of Magnéli-containing mixed phase nanoparticles that carry directly integrated minute amounts with a few hundred ppm of Pt. Nanoparticles can act as highly effective photocatalysts, e.g., mixed phase particles of 32% anatase, 11% rutile, and 57% Magnéli phases loaded with 290 ppm of Pt which provide a 50-100 times higher H2 evolution than plain anatase loaded with a similar amount of Pt. This high photocatalytic efficiency is ascribed to a multijunction of various Magnéli titania species and Pt.
CRIS-Team Scopus Importer:2019-12-20
Keywords: H; Magnéli phase; multiphase titania; photocatalysis; Pt cocatalyst

Magneli-Phases in Anatase Strongly Promote Cocatalyst-Free Photocatalytic Hydrogen Evolution - Domaschke, Maximilian; Zhou, Xuemei; Wergen, Lukas; Romeis, Stefan; Miehlich, Matthias; Meyer, Karsten; Peukert, Wolfgang; Schmuki, Patrik (ACS Catalysis, 2019)
Magneli phases of titanium dioxide (such as Ti4O7, Ti5O9, etc.) provide electronic properties, namely, a stable metallic behavior at room temperature. In this manuscript, we demonstrate that nanoscopic Magneli phases, formed intrinsically in anatase during a thermal aerosol synthesis, can enable significant photocatalytic H-2 generation-this without the use of any extrinsic cocatalyst in anatase. Under optimized conditions, mixed-phase particles of 30% anatase, 25% Ti4O7, and 20% Ti5O9 are obtained that can provide, under solar light, direct photocatalytic H-2 evolution at a rate of 145 mu mol h(-1) g(-1). These anatase particles contain 5-10 nm size intergrown phases of Ti4O7 and Ti5O9. Key is the metallic band of Ti4O7 that induces a particle internal charge separation and transfer cascade with suitable energetics and favorable dimensions that are highly effective for H-2 generation.
CRIS-Team WoS Importer:2019-04-23

Magnetic in situ determination of surface coordination motifs by utilizing the degree of particle agglomeration - Wolf, Andreas; Zink, Andreas; Stiegler, Lisa; Branscheid, Robert; Apeleo Zubiri, Benjamin; Müssig, Stephan; Peukert, Wolfgang; Walter, Johannes; Spiecker, Erdmann; Mandel, Karl (Journal of Colloid and Interface Science, 2023)
Most analytical techniques used to study the surface chemical properties of superparamagnetic iron oxide nanoparticles (SPIONs) are barely suitable for in situ investigations in liquids, where SPIONs are mostly applied for hyperthermia therapy, diagnostic biosensing, magnetic particle imaging or water purification. Magnetic particle spectroscopy (MPS) can resolve changes in magnetic interactions of SPIONs within seconds at ambient conditions. Herein, we show that by adding mono- and divalent cations to citric acid capped SPIONs, the degree of agglomeration can be utilized to study the selectivity of cations towards surface coordination motifs via MPS. A favored chelate agent, like ethylenediaminetetraacetic acid (EDTA) for divalent cations, removes cations from coordination sites on the SPION surface and causes redispersion of agglomerates. The magnetic determination thereof represents what we call a “magnetically indicated complexometric titration”. The relevance of agglomerate sizes for the MPS signal response is studied on a model system of SPIONs and the surfactant cetrimonium bromide (CTAB). Analytical ultracentrifugation (AUC) and cryogenic transmission electron microscopy (cryo-TEM) reveal that large micron-sized agglomerates are required to significantly change the MPS signal response. With this work, a fast and easy-to-use characterization method to determine surface coordination motifs of magnetic nanoparticles in optically dense media is demonstrated.
Keywords: Superparamagnetic iron oxide nanoparticles (SPIONs); Magnetic particle spectroscopy (MPS); Agglomeration; Colloidal surface chemistry; Cation coordination

Magnetic polyamide 11 powder for the powder bed fusion process by liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Groppe, Philipp; Granath, Tim; Düsenberg, Björn; Mandel, Karl; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2024)
Herein, we demonstrate the preparation of magnetic polyamide 11 feedstock powders for powder bed fusion (PBF) using liquid-liquid phase separation and crystallization. By adding magnetic nanomaterials during the precipitation process, the particulate additive is incorporated into the polymer matrix. This enables the production of filled systems at single particle level, which is advantageous in terms of the adjustable magnetic strength and homogeneity of the powder. Thermogravimetric analysis is used to determine the additive content and onset temperature of decomposition of composite powders, where additive-enhancement of PA11 powders with magnetic iron oxide nanoparticles showed a positive influence on the thermal stability of the feedstock. Successive analysis of particle size distribution, shape, colour, crystal structure, magnetic properties and thermal properties of the composite powders are carried out and their properties are discussed with respect to the PBF process. A decrease in particle size, width of the thermal process window and isothermal crystallization time can be attributed to the nucleating effect of the magnetic additive. The PBF processability of the composite feedstock is demonstrated by the production of magnetic tensile bar specimens from additive-enhanced PA11 powders with 1 wt.-% magnetic iron oxide.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Magnets; Nanocomposites; Polymer precipitation; Powder bed fusion; Powder characterization

Manufacturing and Application of PA11-Glass Fiber Composite Particles for Selective Laser Sintering - Dechet, Maximilian; Lanzl, Lydia; Werner, Yannick; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Manufacturing of nanoparticle-filled PA11 composite particles for selective laser sintering - Dechet, Maximilian; Lanzl, Lydia; Wilden, Alisa; Sattes, Maria-Melanie; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Material properties in fine grinding - Peukert, Wolfgang (European Congress on Comminution, 2002)
The impact of material properties in grinding processes is twofold: <dl class="listitem" id="list_"> • the objective of the comminution process is the production of well-defined product properties, • particles' transport to the stressing zone and particles' reaction to applied stresses depend on their inherent mechanical material properties. </dl> In order to understand the influence of material properties at various length scales, we draw a multiscale picture of comminution. At the most detailed level MD simulations may open insights into the otherwise not accessible zone directly at the crack tip. In continuum approaches, the energy flux from the elastically stressed specimen and the stress distribution around the crack can be modelled. Breakage probability obtained from particle stressing experiments or inversion of milling models can be described by a single master curve comprising two new material parameters. These results are used in mill models by clearly separating machine and material functions. In wet grinding, additional material parameters reflecting the particle–particle interactions are introduced, which control suspension rheology and particle stability. The paper concludes with some remarks on product engineering, i.e. concepts on how to optimise product quality.
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.materi
Keywords: comminution; material; properties; grinding

Material properties in fine grinding - Peukert, Wolfgang (International Journal of Mineral Processing, 2004)
The impact of material properties in grinding processes is twofold:the objective of the comminution process is the production of well-defined product properties,particles' transport to the stressing zone and particles' reaction to applied stresses depend on their inherent mechanical material properties.In order to understand the influence of material properties at various length scales, we draw a multiscale picture of comminution. At the most detailed level MD simulations may open insights into the otherwise not accessible zone directly at the crack tip. In continuum approaches, the energy flux from the elastically stressed specimen and the stress distribution around the crack can be modelled. Breakage probability obtained from particle stressing experiments or inversion of milling models can be described by a single master curve comprising two new material parameters. These results are used in mill models by clearly separating machine and material functions. In wet grinding, additional material parameter reflecting the particle-particle interactions are introduced, which control suspension rheology and particle stability. The paper concludes with some remarks on product engineering, i.e. concepts on how to optimise product quality. (C) 2004 Elsevier B.V All rights reserved.
Keywords: material properties; grinding; comminution

Measurement of length distribution of beta-lactoglobulin fibrils by multiwavelength analytical ultracentrifugation - Uttinger, Maximilian; Heyn, Timon R.; Jandt, Uwe; Wawra, Simon; Winzer, Bettina; Keppler, Julia K.; Peukert, Wolfgang (European Biophysics Journal, 2020)
The whey protein beta-lactoglobulin is the building block of amyloid fibrils which exhibit a great potential in various applications. These include stabilization of gels or emulsions. During biotechnological processing, high shear forces lead to fragmentation of fibrils and therefore to smaller fibril lengths. To provide insight into such processes, pure straight amyloid fibril dispersions (prepared at pH 2) were produced and sheared using the rotor stator setup of an Ultra Turrax. In the first part of this work, the sedimentation properties of fragmented amyloid fibrils sheared at different stress levels were analyzed with mulitwavelength analytical ultracentrifugation (AUC). Sedimentation data analysis was carried out with the boundary condition that fragmented fibrils were of cylindrical shape, for which frictional properties are known. These results were compared with complementary atomic force microscopy (AFM) measurements. We demonstrate how the sedimentation coefficient distribution from AUC experiments is influenced by the underlying length and diameter distribution of amyloid fibrils. In the second part of this work, we show how to correlate the fibril size reduction kinetics with the applied rotor revolution and the resulting energy density, respectively, using modal values of the sedimentation coefficients obtained from AUC. Remarkably, the determined scaling laws for the size reduction are in agreement with the results for other material systems, such as emulsification processes or the size reduction of graphene oxide sheets.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Amyloid fibrils; Analytical ultracentrifugation; Atomic force microscopy; Beta-lactoglobulin; Sedimentation analysis

Mechanical activation of trans-stilbene during wet grinding - Konnerth, Christoph-Günther; Damm, Cornelia; Schmidt, Jochen; Peukert, Wolfgang (Advanced Powder Technology, 2014)
The influence of process temperature on product particle size and solubility has been studied for wet grinding of trans-stilbene in ethanol. A positive effect of lowering the process temperature with respect to minimum product particle size was observed. Remarkably, the smallest product particle sizes x < 1 μm were found for the lowest process temperature (251 K) at short process times (< 30 min) and moderate stressing conditions. In contrast, for the same stressing conditions at room temperature (293 K) particles of approximate size x ≈ 8 μm are obtained. The product particle size is rather determined by the (temperature- and solvent-dependent) solid-liquid equilibrium, i.e. dissolution and precipitation phenomena, than by pure mechanical fracture. An increased solubility of stressed trans-stilbene with respect to the equilibrium solubility of the solid has been observed. By means of H NMR spectroscopy and thermodynamic considerations it is shown that the solubility increase is neither due to an isomerisation of the solid nor due to size effects. In fact, mechanical activation leads to an increase in solubility of the stressed solid which was clearly proven by means of solubility studies at different temperatures. The van't Hoff enthalpy of dissolution of the stressed solid decreased remarkably in comparison to the enthalpy of the non-stressed solid as shown by evaluation of van't Hoff plots.
Keywords: Enhanced solubility; Enthalpy of dissolution; Organic crystal; trans-Stilbene; Wet grinding

Mechanically induced phase transformation of zinc sulfide - Damm, Cornelia; Armstrong, Patrick; Roßkopf, Christian; Romeis, Stefan; Peukert, Wolfgang (Particuology, 2015)
Molecular dynamics (MD) simulations of the consecutive compression-decompression cycles of hexagonal zinc sulfide (wurtzite) nanoparticles predict an irreversible phase transformation to the cubic polymorph. The phase transformation commences at the contact area between the particle and the indenter and proceeds with the number of compression cycles. Dislocations are visible for a particle size above 5 nm. Results from wet grinding and dry powder compression experiments on a commercial wurtzite pigment agree qualitatively with MD simulation predictions. X-ray diffraction patterns reveal that the amount of cubic polymorph in the compressed samples increases with pressure applied to the powder. In comparison with powder compression, wet milling leads to a more pronounced phase transformation. This occurs because the particles are exposed to a large number of stress events by collision with the grinding media, which leads to the formation of defects and new surface crystallites by particle fracture. According to the MD simulations, phase transformation is expected to occur preferentially in surface crystallites because they experience the highest mechanical load. Because of the phase transformation, the wet ground and compressed samples exhibit a lower photoluminescence intensity than the feed material. In comparison with powder compression, milling reduces the photoluminescence intensity more substantially. This occurs because a higher defect concentration is formed. The defects contribute to the phase transformation and photoluminescence quenching.
Keywords: Molecular dynamics simulation; Polymorph transformation; Powder compression; Wet milling; Zinc sulfide

Mechanical particle properties - design, characterization and application - Romeis, Stefan; Peukert, Wolfgang; Paul, Jonas (International Conference for Conveying and Handling of Particulate Solids (CHoPS2015), 2015)
The (nano-)mechanics of particles across all length scales down to the nanoscale are highly relevant for many applications including adhesion, friction, powder flow, comminution and tribology. Nanomechanical elastic and inelastic particle properties have been measured systematically in a novel nanoindentation device installed within a scanning electron microscope to obtain simultaneously forcedisplacement information and optical images of deformed and broken particles. Quantitative data of intrinsic particle properties (and their respective distributions) are measured for oxide, metal and polymer particles. We discuss structure - property functions of particles in a quantitative way for selected applications, e.g. the production of bioactive glass and novel polymer particles in additive manufacturing.
Keywords: nano; mechanic; particle; powder; flow

Mechanical production and stabilisation of submicron particles in stirred ball media mills - Peukert, Wolfgang; Mende, Stefan; Stenger, Frank; Schwedes, Jörg (Powder Technology, 2003)
A joint research project between the Technical University of Braunschweig and the Technical University of München investigates the possibilities for the production of stable product suspensions in a particle size range smaller than 100 nm. This paper shows the experimental setup which allows the measurement of the most important electrochemical properties and the analysis of the particle size distribution of the product suspension as well as an adjustment of the pH value for stabilization during the comminution process. Results for comminution of fused corundum with different grinding media materials and grinding media sizes are shown. In addition, results showing the influence of the electrostatic stabilization on the grinding progress are presented. Further, the rheology of the product suspension is examined depending on grinding progress and suspension stabilit
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.mechan
Keywords: Ultrafine grinding; Submicron particles; Stirred media mill; ζ potential; Electrostatic stabilization; Fused corundum

Mechanical production and stabilisation of submicron particles in stirred ball media mills - Peukert, Wolfgang; Mende, Stefan; Stenger, Frank; Schwedes, Jörg (European Congress on Comminution, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.mechan_8
Keywords: stabilization; ball; mill

Mechanics of colloidal supraparticles under compression - Wang, Junwei; Schwenger, Jan; Feldner, Patrick; Ströbel, Andreas; Herre, Patrick; Romeis, Stefan; Peukert, Wolfgang; Merle, Benoit; Vogel, Nicolas (Science Advances, 2021)
Colloidal supraparticles are finite, spherical assemblies of many primary particles. To take advantage of their emergent functionalities, such supraparticles must retain their structural integrity. Here, we investigate their size-dependent mechanical properties via nanoindentation. We find that the deformation resistance inversely scales with the primary particle diameter, while the work of deformation is dependent on the supraparticle diameter. We adopt the Griffith theory to such particulate systems to provide a predictive scaling to relate the fracture stress to the geometry of supraparticles. The interplay between primary particle material and cohesive interparticle forces dictates the mechanical properties of supraparticles. We find that enhanced stability, associated with ductile fracture, can be achieved if supraparticles are engineered to dissipate more energy via deformation of primary particles than breaking of interparticle bonds. Our work provides a coherent framework to analyze, predict, and design the mechanical properties of colloidal supraparticle

Mechanische Erzeugung und Stabilisierung von Nanopartikeln in Rührwerkskugelmühlen - Peukert, Wolfgang; Stenger, Frank; Mende, Stefan; Schwedes, Jörg (Chemie Ingenieur Technik, 2002)
Die   Herstellung   von   Produkten   immer   höherer   Homogenität,   Löslichkeit   oder   Festigkeit  erfordert  oftmals  den  Einsatz  immer  feinerer  Partikeln  als  Rohstoff.  Zur  Herstellung  solcher  Partikelsysteme  kommen  zwei  Methoden  in  Frage.  Bei  der  Kondensationsmethode  entstehen  die  Partikeln  durch  Aggregation  molekular  in  gelöster    flüssiger    oder    gasförmiger    Form    vorliegender    Stoffe.    Vorteil    der    Kondensationsmethode ist die Möglichkeit der Herstellung hochreiner monodisperser sphärischer  Partikelsysteme.  Nachteil  ist  die  in  der  Regel  sehr  geringe  maximale  Produktionsleistung.    Die    Herstellung    feinster    Partikeln    durch    mechanische    Beanspruchung  und  Zerkleinerung  grober  Partikeln  wird  als  Dispersionsmethode  bezeichnet.    Für  eine  solche  Zerkleinerungsaufgabe  müssen  hohe  Energiedichten  zur  Verfügung  gestellt  werden,  wie  sie  z.  B.  in  Rührwerkskugelmühlen  realisiert  werden  können.  Rührwerkskugelmühlen  werden  vorwiegend  naß  betrieben.  Sie  werden  unter  anderem  zur  Zerkleinerung  von  Rohstoffen  für  die  chemische  und  pharmazeutische  Industrie,  die  Keramikindustrie,  die  Mikroelektronikindustrie,  die  Lebensmittelindustrie  sowie  zur  Dispergierung  feiner  Pigmente  in  der  Farben-  und  Lackindustrie eingesetzt. Ein   wesentliches   Problem   bei   der   Naßzerkleinerung   in   Rührwerkskugelmühlen   stellen    die    mit    zunehmender    Mahlgutfeinheit    steigenden    interpartikulären    Wechselwirkungen  dar.  Diese  Wechselwirkungen  beeinflussen  die  Stabilität  der  Mahlgutsuspension gegenüber Koagulation sowie deren rheologische Eigenschaften.  Ohne  zusätzliche  Stabilisierung  der  Produktpartikeln  entsteht  daher  in  vielen  Fällen  ein   Wechselspiel   zwischen   Bruch   und   Reagglomeration,   so   daß   bei   früheren   experimentellen  Untersuchungen  nach  dem  Erreichen  einer  Mahlgutfeinheit  von  ca.  0,5  μm  trotz  weiterer  Erhöhung  des  spezifischen  Energieeintrags  festgestellt  wurde,  daß die gemessene Mahlgutpartikelgröße wieder anstieg, obwohl die nach der BET-Methode gemessene spezifische Oberfläche ebenfalls anstieg.  In einem gemeinsamen DFG-Forschungsprojekt mit dem Lehrstuhl für Feststoff- und Grenzflächenverfahrenstechnik  der  TU  München  wurde  daher  untersucht,  wie  sich  das  Zerkleinerungsverhalten  im  Nanometer-Bereich  im  Vergleich  zur  Zerkleinerung  auf  Partikelgrößen  bis  etwa  1  μm  verändert.  Für  die  Zerkleinerung  im  Nanometer-Bereich  ist  die  Stabilisierung  der  Feststoffpartikeln  in  der  Suspension  zwingend  erforderlich.  Zu  diesem  Zweck  wurden  auftretende  Agglomerationserscheinungen  durch  die  elektrostatische  Stabilisierung  der  Mahlgutsuspension  unterbunden.  Ein  weiteres   Ziel   der   Untersuchungen   war   es,   festzustellen,   wie   die   maximal   in   Rührwerkskugelmühlen      erreichbare      Produktfeinheit      durch      verschiedene       Betriebsparameter beeinflußt wird.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.mechan
Keywords: nanoparticle; comminution; ball; mill

Mechanism of Silver Ion Reduction in Concentrated Solutions of Amphiphilic Invertible Polyesters in Nonpolar Solvent at Room Temperature - Voronov, Andriy; Kohut, Ananiy; Vasylyev, Serhiy; Peukert, Wolfgang (Langmuir, 2008)
Fast formation and efficient stabilization of silver nanoparticles from [Ag(NH3)(2)]OH are achieved in concentrated nonpolar solutions of amphiphilic invertible polyesters based on poly(ethylene oxide) (PEO) and aliphatic dicarboxylic acids. Surface-modified silver nanoparticles able to be dispersed in both a polar and nonpolar medium are developed in the form of a ready-to-use colloidal solution with an enhanced silver concentration. The PEO fragments of polyesters form cavities (also called pseudo-crown ester structures) that can bind metal ions. The reduction of bound metal ions proceeds. via oxidation of polyoxyethylene fragments. No chemical reducing agents are necessary in this approach. The polyesters act simultaneously as an efficient reducing agent and stabilizer. The main focus of the present research is to clarify the chemical mechanism of silver ion reduction in amphiphilic polyester solutions. A one-electron reduction mechanism is proposed to explain the formation of silver nanoparticles. The effect of the poly(ethylene oxide) fragment length and the polyester concentration are explored by examining several amphiphilic polyesters.

Mechanistic insights into silver-gold nanoalloy formation by two-dimensional population balance modeling - Traoré, N. E.; Schikarski, T.; Körner, A.; Cardenas Lopez, P.; Hartmann, Lukas; Fritsch, B.; Walter, Johannes; Hutzler, A.; Pflug, L.; Peukert, Wolfgang (Chemical Engineering Journal, 2024)
The large-scale synthesis of nanoparticles (NPs) with defined properties requires detailed understanding of the underlying formation mechanisms and kinetics. The formation mechanisms of bimetallic NPs are still not sufficiently understood due to the complex reaction chemistry, which makes the control of the supersaturation as the thermodynamic driving force challenging. Particle size, chemical composition, and the distribution of the elements within the particles change dynamically during particle formation. In this work, we propose a mechanism for the formation of bimetallic silver-gold alloy NPs via a green liquid-phase co-reduction synthesis and develop a two-dimensional population balance model to quantitatively describe the evolution of particle size distribution, composition, and optical properties. We shed light on the complex multi-stage formation mechanism of a highly relevant bimetallic NP system, lay the foundation for tailoring the process conditions to achieve targeted optical particle properties and unravel predictive property-process relationships.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Alloy Nanoparticle; Formation Mechanism; Gold Nanoparticle; Nanoparticle Synthesis; Population Balance Equation; Silver Nanoparticle

Mechanochemical aspects in wet stirred media milling - Romeis, Stefan; Schmidt, Jochen; Peukert, Wolfgang (International Journal of Mineral Processing, 2016)
Wet comminution in stirred media mills is a frequently applied fully scalable top-down method towards the production of micron- and submicron particles. Despite the vast field of mechanochemistry which encompasses an increase in reactivity due to the effect of mechanical energy input, there is still no clear picture of the involved mechanisms. In ultra-fine wet grinding the situation is further complicated due to the presence of the solvent: reactions of the stressed solid with the surrounding liquid phase can occur. In this paper several aspects of mechanochemistry occurring in stirred media mills are outlined through suitable experiments. Main focus lies on the comprehensive product characterization and on the role of the liquid phase. It is shown that the liquid phase influences product properties like particle size, porosity, particle shape, structure, chemical composition and the molecular termination of the surface. An increase in the reactivity of ground solids is manifested by a significant increase in dissolution in the aqueous phase during processing in water. Altogether, the liquid dispersion medium which can act as solvent is thus introduced as a new process parameter in stirred media milling and offers new prospects for innovative product design by top-down approaches.
Keywords: Amorphization; Glass; Liquid phase analysis; Mechanochemistry; Quartz; Reactivity; Solubility; Stirred media mills; Titania; Wet comminution

Mechano-chemical changes of nano sized α-Al2O3 during wet dispersion in stirred ball mills - Peukert, Wolfgang; Stenger, Frank; Götzinger, Martin; Jakob, Peter (Particle & Particle Systems Characterization, 2004)
The mechano-chemical changes in synthetic α-AlO during wet dispersion in a stirred ball mill, are studied. It is shown that a second phase is generated which can be identified as an aluminum hydroxide (Bayerite) by use of dynamic scanning calorimetry (DSC), X-ray diffraction (XRD), thermogravimetry (TG), Fourier transformed infrared (FTIR) spectroscopy and transmission electron microscopy (TEM). The amount of the Bayerite phase produced increases with milling time. A comparison of the evaluated amounts from TG- and DSC-measurements are in reasonable agreement. Furthermore, the measured BET surface area shows a strong dependence on the temperature of sample preparation. Depending on the temperature, the bayerite phase is seen to convert to the α-phase again and also forms meso- and possibly micro-pores, leading to a high BET surface area. In this paper, we highlight the necessity for using different methods to characterize the dispersion process, and for a correct interpretation of the measurement results.
Keywords: α-alumina; Bayerite; Mechano-chemical characterization; Wet dispersing

Mechanochemically induced sulfur doping in ZnO via oxygen vacancy formation - Daiko, Yusuke; Schmidt, Jochen; Kawamura, Go; Romeis, Stefan; Segets, Doris; Iwamoto, Y.; Peukert, Wolfgang (Physical Chemistry Chemical Physics, 2017)
Surface defects of ZnO nanoparticles were induced via mechanical stressing using a Turbula shaker mixer and a planetary ball mill, and the possibilities for surface modification and functionalization of the ZnO nanoparticles were exemplified by sulfur doping of activated ZnO. Raman spectroscopy reveals that the formation of oxygen vacancies (VO) does not only occur under high stressing conditions in a planetary ball mill but even upon rather 'mild stressing' in the shaker mixer. The temporal evolution of the vacancy concentration in ZnO stressed under different conditions can be described by a model that accounts for stress number and vacancy diffusion with diffusion coefficients of VO of 3.7 × 10-21 m2 s-1 and 2.4 × 10-20 m2 s-1 for stressing in the shaker and the planetary ball mill, respectively. The thickness of the VO layer was estimated to be about 1 nm. Thiourea was mixed with defective ZnO particles, and then heated at various temperatures for sulfur-doping. A linear relationship between the amount of induced VO and the level of sulfur doping was found. Remarkably, mechanical activation is indispensable in order to control the level of sulfur doping quantitatively. High-angle annular dark field scanning transmission electron microscopy (HAADF STEM) observations with energy dispersive X-ray spectroscopy (EDX) analysis clearly revealed that the doped sulfur atoms are concentrated at the particle surface. Thus, ZnO (core)/ZnS (shell) structures are obtained easily via mechanochemical activation and subsequent thermal treatment.

Mechanochemical modification of silica with poly(1-vinyl-2-pyrrolidone) by grinding in a stirred media mill - Voronov, Andriy; Kohut, Ananiy; Synytska, A.; Peukert, Wolfgang (Journal of Applied Polymer Science, 2007)
The polymerization of 1-vinyl-2-pyrrolidone (VP) mechanochemically initiated by grinding silica was investigated in a wet stirred media mill. The polymerization itself proceeds from the silica grinding without any additional initiator. We have found that the amount of grafted polymer increases with an increase in total ground silica surface. The suspension of polymer-modified silica nanoparticles showed high colloidal stability in water because of the appearance of grafted hydrophilic PVP on the surface during the reactive grinding. Because the nanoparticles SiO2-graft-PVP are bio-compatible, the developed polymer nanocomposite material can be of particular interest for the performance of membranes and for the fabrication of biocompatible hydrogels with enhanced mechanical properties and porosity. (c) 2007 Wiley Periodicals, Inc.
Keywords: graft hydrophilic polymers; nanoparticles; reactive grinding

Mechano-chemical radical formation and polymerization initiation during wet grinding of alumina - Damm, Cornelia; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2011)
The formation of free radicals during wet grinding of alumina in a stirred media mill was studied by using the test radical 2,2-diphenyl-1-picrylhydracyl (DPPH). The kinetics of mechano-chemical radical formation follows a zeroth-order rate law. Particle breakage as well as mechanical activation of the surface of the alumina particles contributes to the radical formation. The rate constants of the radical formation due to mechanical activation of the particle surface k and due to particle breakage k depend on the milling process parameters. The radical formation during wet grinding of alumina was exploited to initiate mechano-chemical polymerization reactions of acrylic acid and acryl amide, respectively. In this way nanoparticles functionalized with polyacrylic acid and polyacryl amide, respectively, are obtained. The influence of the milling process parameters on the kinetics of mechano-chemical radical formation and on the grafted amount of polymer is discussed on the basis of stress energy and number of stress events in the mill. A correlation between the grafted amount of polyacryl amide on the alumina particles and the total radical formation rate was found showing that the concentration of mechano-chemically formed free radicals governs the efficacy of a chemical reaction at activated particle surfaces. © 2011 Elsevier Inc.
Keywords: Alumina; Kinetics; Mechano-chemical polymerization; Radical formation; Stirred media mill

Mesoporous silica submicron particles (MCM-41) incorporating nanoscale Ag: synthesis, characterization and application as drug delivery coatings - Boccardi, Elena; Liverani, Liliana; Beltrán, A. M.; Günther, R.; Schmidt, Jennifer; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Porous Materials, 2018)
Keywords: Mesoporous particles; Scaffolds; Drug delivery; Silica; Silver

Microstructural characterization of hematite during wet and dry millings using Rietveld and XRD line profile analyses - Peukert, Wolfgang; Pourghahramani, Parviz; Altin, Ergün; Mallembakam, Madhusudhan Rao; Forssberg, Eric (Powder Technology, 2008)
The effects of extended milling in a stirred media mill and a tumbling mill on the structural changes in hematite have been examined using a combination of particle size analysis, BET surface areas, X-ray diffraction (XRD), thermal (TG and DSC) and FTIR measurements. Rietveld's whole profile fitting based on crystal structure refinement and the Warren-Averbach's method of X-ray line profile analysis were applied to monitor the microstructural evolution of the hematite phase. It is found that the BET surface area, X-ray amorphization phase content and XRD line breadths increase over the specific energy input. The use of stirred media mill exhibits larger surface areas, smaller particle sizes, more XRD line broadening and subsequently greater structural distortions compared to the tumbling mill for a given energy input; although the X-ray amorphous phase content remains unaffected by the grinding environments. The maximum X-ray amorphization degree of about 80 and 95% were calculated at a specific energy of 22,400 and 82,000 kJ/kg in the tumbling and stirred media mills respectively. The maximum specific BET surface area in the stirred media and tumbling milling increases to about 72.5 and 6.8 m/g after 82,000 and 22,400 kJ/kg energy consumption respectively. As a result of structural refinement during milling, the surface-weighted crystallite size in ground hematite are 17 and 4 nm after consuming 22,400 and 82,000 kJ/kg in the tumbling and stirred media mills respectively, corresponding to the volume-weighted crystallite size of 17 and 11 nm. For the same energy consumption in the mills, in turn, the root mean square strain, 〈 ε 〉, increases to about 4.4 × 10 and 4.9 × 10. The results of the two applied methods are compared and discussed in details. In addition, thermogravimetric analysis of the wet ground samples reveals that the TG curves represent two weight loss steps. A weight loss is observed around 100 °C in the sample which is attributed to the removal of adsorbed water due to the wet milling operations. A strong weight loss step starting from 100 to 400 °C is attributed to surface/bulk dehydroxilation of iron hydroxides. The weight loss increases with extending of the milling. In contrast, the dry milled samples yield negligible weight losses comparing with the wet ground samples. © 2007 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; Mechanical activation; Structural changes; Wet and dry milling

Microstructural evolution during deformation of tin dioxide nanoparticles in a comminution process - Armstrong, Patrick; Knieke, Catharina; Mackovic, Mirza; Frank, Gerhard; Hartmaier, Alexander; Göken, Mathias; Peukert, Wolfgang; Mackovic, Mirza (Acta Materialia, 2009)
Nanoparticles can be produced by wet grinding in stirred media mills if agglomeration is prevented by stabilization of the particles. Since the fracture mechanisms at the lower nanoscale are not yet understood, we studied the evolution of the microstructure within tin dioxide particles. Electrostatic stabilization allows the formation of tin dioxide with a mean particle size of 25 nm as measured by dynamic light scattering. High-resolution transmission electron microscopy (HRTEM) images show particles well below 10 nm and mean crystallite sizes of 9 nm were obtained from X-ray diffraction by applying the Rietveld refinement method. Additionally, TEM and HRTEM analyses were conducted to gain detailed insight into the microstructural effects governing the grinding process. Microscopy revealed surprisingly rich phenomena including the formation of shear bands, twinning and stacking faults that directly affect the grinding behavior. Interestingly the ceramic nanoparticles showed not only fracture patterns expected from brittle fracture but also many traces of plastic deformation. For comparison the uniaxial compression of particles up to 30 nm in diameter was simulated using molecular dynamics. The simulated particles shared microstructural details with the real samples, most importantly the shear bands which lead to significant plastic deformation. The internal microstructure produced during multiple particle stressing events in the mill and also observed in the simulations is directly linked to the fracture mechanism and the experimentally observed grinding limit. © 2009 Acta Materialia In
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.micros
Keywords: Molecular dynamics simulations; Nanomechanics; Nanostructure; Shear bands; Transmission electron microscopy (TEM)

Microstructure formation in dip-coated particulate films - Peukert, Wolfgang; Günther, Lübbe; Goerigk, Günter; Dingenouts, Nico (Journal of Colloid and Interface Science, 2006)
The microstructure-dependence of dip-coated particulate thin films on the stability of an aqueous silica sol used as coating bath is studied. Different stability conditions are adjusted in the sol by changing electrolyte concentration and pH value. Care was taken to avoid pronounced aggregation of the particles before the coating process. The characterization of the stability behavior gives clear evidence of a non-DLVO contribution at low pH values that is attributed to hydration forces. Structural evolution of the particulate network during film formation is studied using a dialysis accumulation procedure. The viscosity of the accumulated sol is measured as a function of shear rate and related to the drying characteristic of the coating process. Atomic force microscopy (AFM), small-angle X-ray scattering (SAXS) and N sorption are used to obtain information on the surface and volume structure of the dip-coated films. The structure of coatings is found to distinctly vary with stability parameters. This is attributed to changing interactions during the first drying stage. Finally, the influence of coating structures on the light transmission properties is determined. A comparison between the extinction of the uncoated and the coated substrate revealed a difference of up to ±50% in dependence on the microstructure. © 2005 Elsevier Inc. All rights reserved.
Keywords: Colloidal stability; Dip coating; Film structure; Particles; Pore size distribution; Rheology; Small-angle scattering

Minimization of catalyst loading on regenerative fuel cell positive electrodes based on Ti felts using atomic layer deposition - Schlicht, Stefanie; Barr, Maissa; Wu, Mingjian; Hoppe, Paula; Spiecker, Erdmann; Peukert, Wolfgang; Bachmann, Julien (ChemElectroChem, 2018)

Minkowski Tensor Shape Analysis of Cellular, Granular and Porous Structures - Peukert, Wolfgang; Schröder-Turk, Gerd; Mickel, Walter; Kapfer, Sebastian; Klatt, Michael; Schaller, Fabian; Hoffmann, Matthias; Kleppmann, Nicola; Inayat, Amer; Armstrong, Patrick; Hug, Daniel; Reichelsdorfer, Martin; et al. (Advanced Materials, 2011)
Predicting physical properties of materials with spatially complex structures is one of the most challenging problems in material science. One key to a better understanding of such materials is the geometric characterization of their spatial structure. Minkowski tensors are tensorial shape indices that allow quantitative characterization of the anisotropy of complex materials and are particularly well suited for developing structure-property relationships for tensor-valued or orientation-dependent physical properties. They are fundamental shape indices, in some sense being the simplest generalization of the concepts of volume, surface and integral curvatures to tensor-valued quantities. Minkowski tensors are based on a solid mathematical foundation provided by integral and stochastic geometry, and are endowed with strong robustness and completeness theorems. The versatile definition of Minkowski tensors applies widely to different types of morphologies, including ordered and disordered structures. Fast linear-time algorithms are available for their computation. This article provides a practical overview of the different uses of Minkowski tensors to extract quantitative physically-relevant spatial structure information from experimental and simulated data, both in 2D and 3D. Applications are presented that quantify (a) alignment of co-polymer films by an electric field imaged by surface force microscopy; (b) local cell anisotropy of spherical bead pack models for granular matter and of closed-cell liquid foam models; (c) surface orientation in open-cell solid foams studied by X-ray tomography; and (d) defect densities and locations in molecular dynamics simulations of crystalline coppe
Keywords: geometric; statistic; spatial; anisotropy; shape; morphology; crystal

Mixed Layers of β-Lactoglobulin and SDS at Air-Water Interfaces with Tunable Intermolecular Interactions - Engelhardt, Kathrin; Weichsel, Ulrike; Kraft, Elena; Segets, Doris; Peukert, Wolfgang; Braunschweig, Björn (Journal of Physical Chemistry B, 2014)
Mixtures of extgreekb-lactoglobulin (BLG) and sodium dodecyl sulfate (SDS) were studied at pH 3.8 and 6.7 under equilibrium conditions. At these pH conditions, BLG carries either a positive or a negative net charge, respectively, which enables tunable electrostatic interactions between anionic SDS surfactants and BLG proteins. For pH 3.8, vibrational sum-frequency generation (SFG) and ellipsometry indicate strong BLG–SDS complex formation at air–water interfaces that is caused by attractive electrostatic interactions. The latter complexes are already formed in the bulk solution which was confirmed by a thermodynamic study of BLG–SDS mixtures using isothermal titration calorimetry (ITC). For acidic conditions we determine from our ITC data an exothermal binding enthalpy of -40 kJ mol–1. Increasing SDS/BLG molar ratios above 10 leads to a surface excess of SDS and thus to a charge reversal from a positive net charge with BLG as the dominating surface adsorbed species to a negatively charged layer with SDS as the dominating surface species. The latter is evidenced by a pronounced minimum in SFG intensities that is also accompanied by a phase change of O–H stretching bands due to a reorientation of H2O within the local electric field. This phase change which occurs at SDS/BLG molar ratio between 1 and 10 causes a polarity change in SFG intensities from BLG aromatic C–H stretching vibrations. Conclusions from SFG spectra are corroborated by ellipsometry which shows a dramatic increase in layer thicknesses at molar ratios where a charge reversal occurs. The formation of interfacial multilayers comprising SDS-BLG complexes is, thus, caused by cancellation of electrostatic interactions which leads to agglomeration at the interface. In contrast to pH 3.8, behavior of BLG–SDS mixtures at pH 6.7 is different due to repulsive electrostatic interactions between SDS and BLG which lead to a significantly reduced binding enthalpy of -17 kJ mol–1. Finally, it has to be mentioned that SFG spectra show a coexistence of BLG and SDS molecules at the interface for BLG–SDS molar ratios > 2.
EAM Import::2019-03-12
Keywords: surface; tension; intermolecular; interaction; air; water; interface

Mobility-Classified Mass Spectrometry Reveals a Complete Picture of the Electrospray Outcome - Lübbert, Christian; Peukert, Wolfgang (Journal of Physical Chemistry A, 2020)
Electrospray ionization mass spectrometry supported by mobility classification (ESI-DMA-MS) is a strong technique for a comprehensive analysis of organic and inorganic clusters and small nanoparticles. In-depth understanding and optimization of the electrospray process are key for unlocking new fields of application and for extension of the accessible range of data. We show that the combination of mobility-classified mass spectrometry (DMA-MS) with an electrospray operated in a well-defined cone-jet mode is capable of providing a full picture of the outcome of the electrospray process including the evaporation residues of the parent droplets. Based on ESI-DMA-MS measurements of lysozyme, we find that clusters up to almost 1 MDa (around 60 lysozyme molecules per cluster) formed as evaporation residues of the parent droplets can be detected. The escape probability of lysozyme molecules from the parent droplets is polarity-dependent. A quantitative analysis of clusters is possible at analyte concentrations where the likeliness of finding more than a single molecule in the generated droplet is low. At higher concentrations, one can, however, quantify the analyte concentration from the detected size of the droplet evaporation residues. The approach is widely applicable for organic and inorganic nanostructures. The results allow clear statements on the conditions under which mixtures of larger molecules, clusters, and nanoparticles are accessible to quantitative analysis by mass spectrometry.
CRIS-Team Scopus Importer:2020-11-06

Modeling adhesion forces between deformable bodies by FEM and Hamaker summation. - Peukert, Wolfgang; Zhou, Hongben (Langmuir, 2008)
A new numerical approach is presented for predicting adhesion forces of particles at flat and rough surfaces. The new hybrid method uses the finite element method (FEM) for the determination of elastic and plastic particle deformation combined with numerical Hamaker summation. In the numerical approach, the influence of the plastic deformation can be fully included. We show how the adhesion force depends on the contact geometry and the material properties. For easy comparison with other models, the force-displacement behavior of the systems is presented. The numerical approach is supported by atomic force microscopy (AFM) measurements. The experimentally observed adhesion force hysteresis is described very well by the new approach. Although calculations in this article are focused on spherical particles, our approach can be extended to particles of arbitrary shapes.
Keywords: finite; element; method; simulation; prediction; adhesion; deformation

Modeling, analysis and optimization of particle growth, nucleation and ripening by the way of nonlinear hyperbolic integro-partial differential equations - Gröschel, Michael; Peukert, Wolfgang; Leugering, Günter (Trends in PDE Constrained Optimization, 2014)
We consider the processes of particle nucleation, growth, precipitation and ripening via modeling by nonlinear 1-D hyperbolic partial integro differential equations. The goal of this contribution is to provide a concise predictive forward modeling of the processes including appropriate goal functions and to establish a mathematical theory for the open-loop optimization in this context. Beyond deriving optimality conditions in the synthesis process, we present the application of a fully implicit method for Ostwald ripening of ZnO quantum dots which preserves its numeric stability even with respect to the inherent high sensitivities and wide disparity of scales. FIMOR represents an appropriate method that can be integrated to subordinate optimization studies which enables its future application in the context of continuous particle syntheses and microreaction technology (MRT
Keywords: Numerical simulation; Nonlinear integro-partial differential equation; Ostwald ripening; Optimization; Particle synthesis; Particle growth

Modeling and Simulation of Process Technology for Nanoparticulate Drug Formulations-A Particle Technology Perspective. - Uhlemann, Jens; Diedam, Holger; Hoheisel, Werner; Schikarski, Tobias; Peukert, Wolfgang (Pharmaceutics, 2020)
Crystalline organic nanoparticles and their amorphous equivalents (ONP) have the potential to become a next-generation formulation technology for dissolution-rate limited biopharmaceutical classification system (BCS) class IIa molecules if the following requisites are met: (i) a quantitative understanding of the bioavailability enhancement benefit versus established formulation technologies and a reliable track record of successful case studies are available; (ii) efficient experimentation workflows with a minimum amount of active ingredient and a high degree of digitalization via, e.g., automation and computer-based experimentation planning are implemented; (iii) the scalability of the nanoparticle-based oral delivery formulation technology from the lab to manufacturing is ensured. Modeling and simulation approaches informed by the pharmaceutical material science paradigm can help to meet these requisites, especially if the entire value chain from formulation to oral delivery is covered. Any comprehensive digitalization of drug formulation requires combining pharmaceutical materials science with the adequate formulation and process technologies on the one hand and quantitative pharmacokinetics and drug administration dynamics in the human body on the other hand. Models for the technical realization of the drug production and the distribution of the pharmaceutical compound in the human body are coupled via the central objective, namely bioavailability. The underlying challenges can only be addressed by hierarchical approaches for property and process design. The tools for multiscale modeling of the here-considered particle processes (e.g., by coupled computational fluid dynamics, population balance models, Noyes-Whitney dissolution kinetics) and physiologically based absorption modeling are available. Significant advances are being made in enhancing the bioavailability of hydrophobic compounds by applying innovative solutions. As examples, the predictive modeling of anti-solvent precipitation is presented, and options for the model development of comminution processes are discussed.
Keywords: comminution; modeling and simulation; nanocrystal; oral bioavailability; pharmaceutical material science; poorly soluble drug; precipitation; product design

Modelling of grinding in an air classifier mill based on a fundamental material function - Peukert, Wolfgang; Vogel, Lutz (KONA Powder and Particle Journal, 2003)
An approach to quantifying the impact grinding per formance of dif ferent materials is presented. Based on a dimensional analysis and on fracture mechanical considerations, two material parameters, f Mat.and W m,min, are derived theoretically. fMat . characterises the resistance of particulate material  against  fracture  during  impact  comminution.  Wm,min gives  the  mass-specif ic  energy  which  aparticle can absorb without fracture. Using this approach, various materials over a wide size range, e.g.  dif ferent  polymers,  crystalline  substances,  glass  and  limestone,  can  be characterised  quantitatively.  The  derived  material  parameters  are  applied  to  the  systematic  modelling  of  grinding  in impact mills. A population balance model is presented and the results of the simulation for an air classifier mill are shown. The developed model permits a clear separation of the inf luence of material properties, mill-specif ic features and operating conditions, thus enabling a deeper understanding of the impact grinding process
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.modell
Keywords: grinding; comminution; milling

Modelling the superposition of grinding and agglomeration in stirred ball mills by population balance models - Peukert, Wolfgang; Stenger, Frank; Sommer, Marc; Wagner, N; Diemer, R (Proceedings PARTEC 2004, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.ITC.mechve.modell_5

Modelling the two-dimensional growth and oriented attachment of goethite nanorods synthesized via oxidation of aqueous ferrous hydroxide slurries - Güldenpfennig, Andreas; Distaso, Monica; Klupp Taylor, Robin; Peukert, Wolfgang (Chemical Engineering Journal, 2018)
Keywords: Anisotropic growth; Goethite; 2D model; 3-Phase reaction; Oriented attachment; Reaction rate

Modelling titania formation at typical industrial process conditions: Effect of surface shielding and surface energy on relevant growth mechanisms - Artelt, Christian; Schmid, Hans-Joachim; Peukert, Wolfgang (Chemical Engineering Science, 2006)
This work investigates the effects of reduced accessible surface area of aggregate particles and of surface energy on relevant particle formation and growth mechanisms during titania formation from the vapour phase at industrial process conditions. Growth due to surface reaction and due to condensation is related to the fraction of the surface area that is exposed to the collision with single molecules. Surface shielding is found to hamper surface reaction and condensation once fractal aggregates start to form. It leads to significantly retarded precursor consumption and produces aggregate particles, which consist of more, but smaller primary particles. Surface energy data are varied within a range as proposed by available literature data. Moderate and high surface energy values result in a thermodynamic barrier to the formation of new particles and are shown to reduce the formation of seed particles by several orders of magnitude. This leads to the formation of aggregate particles which consist of a rather small number of primary particles and mainly grow by surface reaction. The primary contribution of condensation to growth of individual primary particles is shown to be very little. However, condensation should not be neglected as it has a strong impact on particle formation rates and hence on product characteristics such as the number of primary particles and primary particle siz
Keywords: Surface energy; Surface shielding; Nanoparticles; Population balance; Titania; Condensation; Aerosol process simulations

Model Reduction, Structure-property Relations and Optimization Techniques for the Production of Nanoscale Particles - Gröschel, Michael; Leugering, Günter; Peukert, Wolfgang (International Series of Numerical Mathematics, 2011)
The production of nanoscaled particulate products with exactly pre-defined characteristics is of enormous economic relevance. Although there are different particle formation routes they may all be described by one class of equations. Therefore, simulating such processes comprises the solution of nonlinear, hyperbolic integro-partial differential equations. In our project we aim to study this class of equations in order to develop efficient tools for the identification of optimal process conditions to achieve desired product properties. This objective is approached by a joint effort of the mathematics and the engineering faculty. Two model-processes are chosen for this study, namely a precipitation process and an innovative aerosol process allowing for a precise control of residence time and temperature. Since the overall problem is far too complex to be solved directly a hierarchical sequence of simplified problems has been derived which are solved consecutively. In particular, the simulation results are finally subject to comparison with experiments.
Keywords: Population balance equations; optimal control; model reduction; parameter identification

Molecular dynamics simulations of the contact between two NaCl nanocrystals - Peukert, Wolfgang; Götzinger, Martin; Miesbauer, Oliver (Nanotechnology, 2003)
The contact between two NaCl nano-crystals consisting of 6000–15 000 atoms was studied using molecular dynamics computer simulations. After placing two NaCl cuboids at varying distances, the adhesion forces and the resulting strains were measured. We observed jump to contact and found there is an upper limit of distance. Similarly, NaCl hemispheres possessing radii equal to 2.13, 3.26 and 4.15 nm were placed at varying distances from a NaCl cuboid. The relations between distance and force were determined. In the case of an indentation, the relations were described by power functions and compared with the widely used Hertzian theory. We were able to show that the exponent of the power function rises with increasing radius of the hemisphere. It apparently converges to a value of 1.5, which is in agreement with the Hertzian theory. It thus seems justified to assume that the studied system can be adequately described with continuum mechanics down to sizes of 5 nm. But for smaller systems continuum mechanics appears not to be adequate.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.molecu
Keywords: nano; crystal; dynamic; simulation

Molecular Mie model for second harmonic generation and sum frequency generation - Wunderlich, Sarina; Schürer, Benedikt; Sauerbeck, Christian; Peukert, Wolfgang; Peschel, Ulf (Physical Review B, 2011)
A theoretical model to simulate second harmonic and sum frequency generation from stratified spherical particles of arbitrary material is presented and compared with the widely used Rayleigh-Gans-Debye approximation and to experimental results from polystyrene particles with adsorbed malachite green molecules. In this model, the nonlinear polarization is caused by individual dipoles placed in the vicinity of the sphere and is simulated on a molecular basis. This offers greater flexibility to model more sophisticated systems.

Molecular order of mixed self-assembled monolayers studied by surface vibrational spectroscopy - Rumpel, Armin; Novak, Michael; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (Materials Engineering and Sciences Division - Core Programming Topic at the 2011 AIChE Annual Meeting, 2011)

Molecular structure of octadecylphosphonic acids during their self-assembly on α-Al2O3(0001) - Meltzer, Christian; Yu, Hui; Peukert, Wolfgang; Braunschweig, Björn (Physical Chemistry Chemical Physics, 2018)

Monitoring of Flow-Induced Aggregation and Conformational Change of Monoclonal Antibodies - Wolfrum, Sonja; Weichsel, Ulrike; Siedler, Michael; Weber, Carsten; Peukert, Wolfgang (Chemie Ingenieur Technik, 2017)
Keywords: Mechanical stress; Protein aggregation; Extrinsic fluorescent dyes; In situ methods; Fluorescence spectroscopy

Monitoring structure formation changes of amphiphilic polyesters in different. solvents by hyper-rayleigh scattering (HRS) - Schneider, Lars; Voronov, Andriy; Kohut, Ananiy; Peukert, Wolfgang (2007 AIChE Annual Meeting, 2007)

Monte Carlo simulation of aggregate morphology for simultaneous coagulation and sintering - Peukert, Wolfgang; Schmid, Hans-Joachim; Tejwani, Saurabh; Artelt, Christian (Journal of Nanoparticle Research, 2004)
A model for simulation of the three-dimensional morphology of nano-structured aggregates formed by concurrent coagulation and sintering is presented. Diffusion controlled cluster-cluster aggregation is assumed to be the prevailing coagulation mechanism which is implemented using a Monte-Carlo algorithm. Sintering is modeled as a successive overlapping of spherical primary particles, which are allowed to grow as to preserve overall mass. Simulations are characterized by individual ratios τ of characteristic collision to fusion time. A number of resulting aggregate-structures is displayed and reveals structure formation by coagulation and sintering for different values of τ. These aggregates are described qualitatively and quantitatively by their mass fractal dimension Df and radius of gyration. The fractal dimension increases from 1.86 for pure aggregation to ≈ 2.75 for equal characteristic time scales. As sintering turns out to be more and more relevant, increasingly compact aggregates start to form and the radius of gyration decreases significantly. The simulation results clearly reveal a strong dependence of the fractal dimension on the kinetics of the concurrent coagulation and sintering processes. Considering appropriate values of D f in aerosol process simulations may therefore be important in many cases. © 2005 Springer.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.montec
Keywords: Aerosol process simulation; Aggregate structure formation; Coagulation and sintering; Fractal dimension; Radius of gyration

Morphological impact of zinc oxide layers on the device performance in thin-film transistors - Faber, Hendrik; Klaumünzer, Martin; Voigt, Michael; Galli, Diana; Vieweg, Benito; Peukert, Wolfgang; Spiecker, Erdmann; Halik, Marcus (Nanoscale, 2011)
Zinc oxide thin-films are prepared either by spin coating of an ethanolic dispersion of nanoparticles (NP, diameter 5 nm) or by spray pyrolysis of a zinc acetate dihydrate precursor. High-resolution electron microscopy studies reveal a monolayer of particles for the low temperature spin coating approach and larger crystalline domains of more than 30 nm for the spray pyrolysis technique. Thin-film transistor devices (TFTs) based on spray pyrolysis films exhibit higher electron mobilities of up to 24 cm² V−1 s−1 compared to 0.6 cm² V−1 s−1 for NP based TFTs. These observations were dedicated to a reduced number of grain boundaries within the transistor channel.

Multi-component and multi-phase population balance model: The case of Georgeite formation as methanol catalyst precursor phase - Hartig, Martin Andreas Johannes; Jacobsen, Nikolas; Peukert, Wolfgang (Chemical Engineering Science, 2014)
A novel generally applicable multi-component and multi-phase population balance model is presented. The model classifies precipitation and crystallization systems into the number of components (i.e. building units of solid) and number of solid phases. The model includes reaction equilibria of metal ions in aqueous media, activity modeling, mixing, particle formation kinetics, population and mole balances. The new model is applied to the initial stages of copper catalyst precursor formation. The population balance model is simplified to a single-solid phase and multi-component precipitation. Simulations for several solid phases were performed at various experimental conditions. We show that the formation of the carbonate rich Georgeite phase is favored. The simulation results are verified by the measured global parameters pH and solid weight. Mixing plays a minor role in comparison to the variation of the reactant concentration. The timescale of precipitation including mixing, nucleation and crystal growth ranges from microseconds up to 1 s depending on the extent of secondary nucleation.
Keywords: multi-component; catalysis; solid; phase; mixing; aqeous; georgeite

Multidimensional Analysis of Nanoparticles with Highly Disperse Properties Using Multiwavelength Analytical Ultracentrifugation - Walter, Johannes; Löhr, Konrad; Karabudak, Engin; Reis, Wieland; Mikhael, Jules; Peukert, Wolfgang; Wohlleben, Wendel; Coelfen, Helmut (ACS nano, 2014)
The worldwide trend in nanoparticle technology toward increasing complexity must be directly linked to more advanced characterization methods of size, shape and related properties, applicable to many different particle systems in science and technology. Available techniques for nanoparticle characterization are predominantly focused on size characterization. However, simultaneous size and shape characterization is still an unresolved major challenge. We demonstrate that analytical ultracentrifugation with a multiwavelength detector is a powerful technique to address multidimensional nanoparticle analysis. Using a high performance optical setup and data acquisition software, information on size, shape anisotropy and optical properties were accessible in one single experiment with unmatched accuracy and resolution. A dynamic rotor speed gradient allowed us to investigate broad distributions on a short time scale and differentiate between gold nanorod species including the precise evaluation of aggregate formation. We report how to distinguish between different species of single-wall carbon nanotubes in just one experiment using the wavelength-dependent sedimentation coefficient distribution without the necessity of time-consuming purification methods. Furthermore, CdTe nanoparticles of different size and optical properties were investigated in a single experiment providing important information on structure-property relations. Thus, multidimensional information on size, density, shape and optical properties of nanoparticulate systems becomes accessible by means of analytical ultracentrifugation equipped with multiwavelength detectio
Keywords: nanoparticle; characterization; analytical; ultracetrifugation; CdTe; multidimensional

Multidimensional characterization of noble metal alloy nanoparticles by multiwavelength analytical ultracentrifugation - Cardenas Lopez, Paola; Uttinger, Maximilian; Traore, Nabi; Khan, Hamzah; Drobek, Dominik; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Pflug, Lukas; Peukert, Wolfgang; Walter, Johannes (Nanoscale, 2022)
In this study, we introduce a method for the simultaneous retrieval of two-dimensional size-composition distributions of noble metal Ag-Au alloy nanoparticles utilizing an analytical ultracentrifuge equipped with a multiwavelength extinction detector (MWL-AUC). MWL-AUC is used to measure coupled optical and sedimentation properties of the particles. The optical response of the nanoparticles is calculated using Mie's theory, where the particles' complex refractive index is corrected due to the effect of reduced mean free path of electrons. Using a combined analysis of the hydrodynamic and spectral data captured by MWL-AUC, the size and composition of the alloy particles is retrieved. Our method is validated through the analysis of synthetic data and by the very good agreement between experimental scanning transmission electron microscopy and our AUC data. The presented comprehensive characterization approach contributes to improved synthesis, scale-up and production of particulate systems as it provides a simple, fast and direct method to determine noble metal alloy nanoparticle size and composition distributions simultaneously.
CRIS-Team WoS Importer:2022-09-09

Multidimensional Fractionation of Particles - Frank, Uwe; Dienstbier, Jana; Tischer, Florentin; Wawra, Simon; Gromotka, Lukas; Walter, Johannes; Liers-Bergmann, Frauke; Peukert, Wolfgang (Separations, 2023)
The increasing complexity in particle science and technology requires the ability to deal with multidimensional property distributions. We present the theoretical background for multidimensional fractionations by transferring the concepts known from one dimensional to higher dimensional separations. Particles in fluids are separated by acting forces or velocities, which are commonly induces by external fields, e.g., gravitational, centrifugal or electro-magnetic fields. In addition, short-range force fields induced by particle interactions can be employed for fractionation. In this special case, nanoparticle chromatography is a recent example. The framework for handling and characterizing multidimensional separation processes acting on multidimensional particle size distributions is presented. Illustrative examples for technical realizations are given for shape-selective separation in a hydrocyclone and for density-selective separation in a disc separator.
Keywords: multidimensional separation; two-dimensional property distribution; size; shape; composition

Multidimensional Nanoparticle Characterization by Means of Analytical Ultracentrifugation and Multiwavelength Detection - Peukert, Wolfgang; Nacken, Thomas; Walter, Johannes; Thajudeen, Thaseem; Segets, Doris; Sherwood, Peter; Stafford, Walter (Chemie Ingenieur Technik, 2016)
Keywords: Nanoparticle; centrifugation

Multidimensional Particle Size Distributions and Their Application to Nonspherical Particle Systems in Two Dimensions - Frank, Uwe; Wawra, Simon; Pflug, Lukas; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2019)
Particle science and technology evolve toward ever increasing complexity with respect to the multidimensional particle properties of size, shape, surface, internal structure, and composition. In this study, the theoretical background is elaborated for multidimensional particle size distributions (PSDs) by transferring the concepts known from 1D size distributions to anisotropic particles comprising at least two different length dimensions, e.g., nanorods and platelets. After introducing 2D PSDs, the calculation of differently weighted probability density functions including their interconversion is presented. This is necessary in order to compare data resulting from different measurement techniques which probe different physical properties and thus provide differently weighted PSDs. In addition, it is shown how 1D distributions with reduced content of information can be deduced from 2D PSDs. As a proof-of-concept and for illustration purposes, this approach is applied to a 2D Gaussian size distribution. Furthermore, a generalized scheme is suggested which outlines the conversion of number, surface, and volume weighted densities within the 2D space. The application of these methods to the more general n-dimensional case is straightforward.
CRIS-Team Scopus Importer:2019-06-04
Keywords: 2D distributions; multidimensional characterization; particle size distributions; particle technology

Nanogap-controllable self-assembly of gold nanoparticles using nanotrench template - Sugano, Kouji; Hiraoka, Ryoji; Tsuchiya, Toshiyuki; Tabata, Osamu; Klaumünzer, Martin; Voigt, Michael; Peukert, Wolfgang (2011 16th International Solid-State Sensors, Actuators and Microsystems Conference, TRANSDUCERS'11, 2011)
This paper reports high-yield self-assembly process for gold nanoparticle with a diameter of 60 nm, which can precisely control an interparticle nanogap ranging from 0 to 60 nm, using a template-assisted self-assembly with a pair of circular nanotrenches. A center-to-center distance of nanotrenches was changed in order to control an interparticle nanopgap. We found that an assembly yield strongly depends on a particle-particle interaction and achieved nanogap-controlled particle arrangement with high yield by controlling the particle-particle interaction with an addition of an electrolyte. This technique would enable us to control plasmonic resonance property of a nanoparticles pair for many emerging applications. © 2011 IEE
Keywords: Nanoparticle; Nanogap; Self-Assembly; Plasmon

Nanomilling in stirred media mills - Peukert, Wolfgang; Stenger, Frank; Mende, Stefan; Schwedes, Jörg (Chemical Engineering Science, 2005)
This paper investigates the production of stable nanoparticle suspensions. The experimental set-up allows the online measurement of the most important electrochemical properties and the particle size distribution of the product suspension as well as an adjustment of the pH-value for stabilization during the comminution process. Electrostatic stabilization is a strong tool to produce stable nanoparticle suspensions for sparingly soluble oxide components. In this contribution the influence of different operational parameters at stable suspensions properties on the grinding result in the nanometer size range is presented. In addition to alumina, the concept of electrostatic stabilization during wet grinding of nanoparticles is also applied to tin oxide. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Comminution; Interface; Oxide particles; Particulate processes; Rheology; Stability

Nanomilling: the influence of suspension stability - Peukert, Wolfgang; Stenger, Frank (World Congress Particle Technology 4, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.nanomi
Keywords: milling; stability

Nanoparticle precipitation: Experimental investigation, modelling and process simulation - Peukert, Wolfgang; Schwarzer, Hans-Christoph (European Congress on Crystallization, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.nanopa
Keywords: simulation; nanoparticle

Nanoparticle precipitation in a T-mixer: Coupling experimentaland numerical investigations of the fluid dynamics with the solid formation processes - Peukert, Wolfgang; Gradl, Johannes; Schwertfirm, Florian; Schwarzer, Hans-Christoph; Schmid, Hans-Joachim; Manhart, Michael (ASME 2006 2nd Joint U.S.-European Fluids Engineering Summer Meeting Collocated With the 14th International Conference on Nuclear Engineering, 2006)
Mixing and consequently fluid dynamic is a key parameter to tailor the particle size distribution (PSD) in nanoparticle precipitation. Due to fast and intensive mixing a static T-mixer configuration is capable .for synthesizing continuously nanoparticles. The flow and concentration field of the applied mixer is investigated experimentally at different flow rates by Particle Image Velocimetry (PIV) and Laser Induced Fluorescence (LIF). Due to the PIV measurements the flow field in the mixer was characterized qualitatively and the mixing process itself is quantified by the subsequent LIF-measurements. A special feature of the LIF set up is to detect structures in the flow field, which are smaller than the Batchelor length. Thereby a detailed insight into the mixing process in a static T-Mixer is given. In this study a CFD-based approach using Direct Numerical Simulation (DNS) in combination with the solid formation kinetics solving population balance equations (PBE) is applied, using barium sulfate as modeling material. A Lagrangian Particle Tracking strategy is used to couple the flow field information with a micro mixing model and with the classical theory of nucleation. We found that the DNS-PBE approach including macro and micro mixing, combined with the population balance is capable of predicting the full PSD in nanoparticle precipitation for different operating parameters. Additionally to the resulting PSD, this approach delivers a 3D-information about all running subprocesses in the mixer, i.e. supersaturation built-up or nucleation, which is visualized for different process variables. Copyright © 2006 by ASME.
Keywords: mixing; fluid; dynamic; nanoparticle; precipitation

Nanoparticle production with stirred-media mills: Opportunities and limits - Knieke, Catharina; Carola, Steinborn; Romeis, Stefan; Peukert, Wolfgang; Breitung-Faes, Sandra; Kwade, Arno (Chemical Engineering & Technology, 2010)
Nanoparticles can be produced by wet grinding in stirred-media mills. In the lower nanometer range a true grinding limit exists, where the transferred energy from the grinding media is no longer sufficient to induce further breakage of the particles even after stressing events with high stress energies. Variations in process conditions lead to the conclusion that the grinding limit is hardly affected by most of the investigated process parameters. However, at high solids concentrations and/or small particle sizes, a drastic increase in suspension viscosity occurs, which leads to a dampening of the grinding media motion and to a reduction in the transferred stress energy. Hence, the rheological behavior can limit the grinding process, and a viscous dampening-related grinding limit can be reached prior to the true grinding limit. © 2010 WILEY-VCH Verlag GmbH & Co.
Keywords: Grinding limit; Nanoparticles; Rheology; Stirred-media mill; Ultrafine grinding

New approaches towards production of polymer powders for selective laser beam melting of polymers - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (32nd International Conference of the Polymer Processing Society, PPS 2016, 2017)
Keywords: wet grinding; dry coating; downer reactor; melt emulsification; laser beam melting of polymers; polypropylene (PP); polybutylene terephthalate (PBT)

New approach towards production of optimized polymer powders for additive manufacturing - Peukert, Wolfgang; Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst (8th International Conference for Conveying and Handling of Particulate Solids (CHoPS2015), 2015)
Rapid prototyping gradually is transferred to additive manufacturing opening many new applications. Especially powder- And beam-based processes such as laser beam melting (LBM) of polymers are promising. Major requirements for good processability in LBM of polymers are good flowability and high packing density. Within this contribution a novel process route for the production of micron-sized LBM powders [1] is presented exemplarily for polybutylene terephthalate (PBT). Wet comminution of the polymer is the first process step. Product particles with x < 10 μm are readily obtained by wet grinding [2]. The ground PBT microparticles are rounded in a heated downer reactor in the second process step. To increase the flowability of the spherical polymer particles further nanoparticles are adhered to the particle surface [3] in the third step. Spherical PBT microparticles of good flowability are obtained.
Keywords: powder; polymer; laser; beam; melting

New possibilities of accurate particle characterisation by applying direct boundary models to analytical centrifugation - Walter, Johannes; Thajudeen, Thaseem; Süß, Sebastian; Segets, Doris; Peukert, Wolfgang (Nanoscale, 2015)
Analytical centrifugation (AC) is a powerful technique for the characterisation of nanoparticles in colloidal systems. As a direct and absolute technique it requires no calibration or measurements of standards. Moreover, it offers simple experimental design and handling, high sample throughput as well as moderate investment costs. However, the full potential of AC for nanoparticle size analysis requires the development of powerful data analysis techniques. In this study we show how the application of direct boundary models to AC data opens up new possibilities in particle characterisation. An accurate analysis method, successfully applied to sedimentation data obtained by analytical ultracentrifugation (AUC) in the past, was used for the first time in analysing AC data. Unlike traditional data evaluation routines for AC using a designated number of radial positions or scans, direct boundary models consider the complete sedimentation boundary, which results in significantly better statistics. We demonstrate that meniscus fitting, as well as the correction of radius and time invariant noise significantly improves the signal-to-noise ratio and prevents the occurrence of false positives due to optical artefacts. Moreover, hydrodynamic non-ideality can be assessed by the residuals obtained from the analysis. The sedimentation coefficient distributions obtained by AC are in excellent agreement with the results from AUC. Brownian dynamics simulations were used to generate numerical sedimentation data to study the influence of diffusion on the obtained distributions. Our approach is further validated using polystyrene and silica nanoparticles. In particular, we demonstrate the strength of AC for analysing multimodal distributions by means of gold nanoparticles.

New Prospects for Particle Characterization Using Analytical Centrifugation with Sector-Shaped Centerpieces - Uttinger, Maximilian; Boldt, Sebastian; Wawra, Simon; Freiwald, Tobias; Damm, Cornelia; Walter, Johannes; Lerche, Dietmar; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2020)
Analytical centrifugation (AC) has recently shown great potential for the accurate determination of particle size distributions. The well-established LUMiSizer(R) is customized by a new design allowing for higher rotor speeds, improved thermal insulation, and measurement cell assembly. The latter enables sedimentation analysis of nanoparticles (NPs) in sector-shaped centerpieces. The measurement window of AC experiments is assessed by the Peclet (Pe) number. It is shown that at low Pe numbers (0.7 < Pe < 30), sedimentation, and diffusion can be accurately and simultaneously analyzed from the sedimentation boundaries within one experiment. Moreover, sedimentation properties can be reliably determined up to Pe numbers of 4000. The thermal characteristic throughout the sedimentation analysis is validated by measuring polystyrene particles at elevated temperatures. Moreover, the performance of the setup is demonstrated by determining the sedimentation properties of SiO2 NPs at intermediate Pe numbers in excellent agreement with results from analytical ultracentrifugation experiments. Finally, for the first time, an accurate analysis of the core–shell properties of Au NPs via AC is presented. By combining the analysis of sedimentation and diffusional properties at low Pe numbers, the shell thickness of the stabilizer cetyltrimethylammonium bromide alongside the core diameter distribution of the Au NPs is determined.
CRIS-Team Scopus Importer:2020-06-19
Keywords: analytical centrifugation; core–shell nanoparticles; layering effects; nanoparticle characterization; sedimentation analysis

n-Hexanol Enhances the Cetyltrimethylammonium Bromide Stabilization of Small Gold Nanoparticles and Promotes the Growth of Gold Nanorods - Schmutzler, Tilo; Schindler, Torben; Zech, Tobias; Lages, Sebastian; Thoma, Martin; Appavou, Marie-Sousai; Peukert, Wolfgang; Spiecker, Erdmann; Unruh, Tobias (ACS Applied Nano Materials, 2019)
Gold nanorods (AuNRs) are of interest for many applications, since their absorption in the regime of visible light can easily be tuned by their exact shape. To produce these AuNRs, a two-step synthesis that starts from small seed particles is used. These seed particles are stabilized by cetyltrimethyl-ammonium bromide (CTAB), which forms micelles at the used concentration (0.1 mol/L). In this work, the influence of the micelle morphology on the stabilization of these seed particles and the consequences on the formation of AuNRs is reported. The elongation of CTAB micelles by the addition of n-hexanol leads to much more stable seed particle dispersions and thus less polydisperse AuNRs. In contrast, a higher number of micelles compared to pure CTAB dispersions result from the addition of n-pentanol. This promotes the formation of larger seed particles and leads to lower yields of AuNRs. The gold nanoparticles are characterized by UV-vis-NIR absorption spectroscopy, transmission electron microscopy, and small-angle X-ray scattering (SAXS). The morphology of the micelles has been determined by a combination of SAXS and small-angle neutron scattering (SANS). The experimental results were used to calculate the collision kinetics of seed particles by using an improved approach of classical coagulation theory to consider the anisotropy of the micelles. The combination of these experiments with the calculations strongly supports the mechanistic model-that these gold seed particles are not stabilized by a CTAB bilayer but by the micelles itself. For the first time, the influence of the micellar size and shape on the stabilization mechanism of noble metal nanoparticles could be clarified. Theses findings contribute to the development of targeted design routes for distinct nanoparticle morphologies by the use of suitable dispersions.
CRIS-Team WoS Importer:2019-06-18

N-Methyl-2-pyrrolidone as a Reaction Medium for Gold(III)-Ion Reduction and Star-like Gold Nanostructure Formation - Mirdamadi Esfahani, Maleknaz; Görlitzer, Eric; Kunz, Ulrike; Vogel, Nicolas; Engstler, Joerg; Andrieu-Brunsen, Annette (ACS Omega, 2022)
The efficiency of a wet chemical route to synthesize gold nanostructures with tunable size and shape significantly depends on the applied solvent and the interaction of solvent molecules with other species such as gold ions. The ability of the organic solvent N-methyl-2-pyrrolidone (NMP) as a suitable medium for application in star-like gold nanostructure (AuNS) synthesis with a tunable morphology at ambient conditions has been investigated. The time-dependent analysis of the UV-vis absorption spectra of AuIIICl4- in a pure NMP solution illustrates the role of NMP as simultaneous complexing and reducing agents. Kinetic studies indicate that AuIIICl4- in NMP solution is reduced to AuICl2-, with no need to use another reducing agent, any external energy sources, or solvent pretreatment. This is because AuI species stay stable in this solution unless poly(vinylpyrrolidone) (PVP) catalyzes their disproportionation. Morphological studies by transmission electron microscopy (TEM) specify the high-yield synthesis of AuNS with monocrystalline spikes in a concentrated NMP solution by PVP. This study illustrates that the presence of seeds, as another agent to catalyze the disproportionation of AuI species, makes it possible to synthesize AuNS in varying concentrations of PVP in this medium. The role of PVP concentration and the presence of seeds in the formation kinetics, morphology, and optical properties is systematically discussed. The results achieved through this study develop a straightforward and safe procedure for AuNS synthesis in high yield in a water-miscible organic polar solvent with tunable morphology and optical properties. Considering the high capability of NMP to dissolve various types of polymers and hydrophobic ligands, synthesizing AuNS in this solvent opens a window to a practical and easy way to fabricate gold-based nanomaterials with fascinating optical properties.
Created from Fastlane, Scopus look-up

Noble-Metal-Free Photocatalytic Hydrogen Evolution Activity: The Impact of Ball Milling Anatase Nanopowders with TiH2 - Zhou, Xuemei; Liu, Ning; Schmidt, Jochen; Kahnt, Axel; Osvet, Andres; Romeis, Stefan; Zolnhofer, Eva; Marthala, Venkata; Guldi, Dirk Michael; Peukert, Wolfgang; Hartmann, Martin; Meyer, Karsten; et al. (Advanced Materials, 2016)
Ball milling TiO2 anatase together with TiH2 can create an effective photocatalyst. The process changes the lattice and electronic structure of anatase. Lattice deformation created by mechanical impact combined with hydride incorporation yield electronic gap-states close to the conduction band of anatase. These provide longer lifetimes of photogenerated charge carriers and lead to an intrinsic cocatalytic activation of anatase for H2 evolution.
Keywords: Anatase; Ball milling; Hydrogen evolution; Photocatalysis; Titanium hydride

Nonlinear spectroscopy meets particle interfaces: Revealing the interfacial structure of colloids - Sauerbeck, Christian; Schürer, Benedikt; Braunschweig, Björn; Peukert, Wolfgang (2012)

Novel approaches for the production of polymer powders for selective laser beam melting of polymers - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (Solid Freeform Fabrication 2016: Proceedings of the 26th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference, 2016)
The opening of new fields of application of powder-based additive manufacturing methods like selective laser beam melting of polymers currently is hindered by the limited availability of materials showing good processability. So far, virtually only polyamides are available as optimized powder materials. Two innovative methods for production of spherical polymer micro particles for selective laser melting are discussed: The first approach, stirred media milling and rounding, is applicable for a variety of polymers. It will be exemplarily discussed for polyesters and the dependency of product properties (particle size distribution, shape, crystallinity) on the process parameters in the comminution and in the rounding step will be assessed. The second method, melt emulsification, will be demonstrated for polypropylene. Moreover, the possibilities of dry coating to tailor particle properties are illustrated. The influence of powder properties on the processability and on the quality of the obtained devices is outlined.<br
Keywords: AdditivesCrystallinityEmulsificationLaser beamsMeltingParticle sizeParticle size analysisPolypropylenes Selective Laser Sintering; Nylon 12; Polybutylene Terephthalate; Innovative method; Laser beam melting; Particle properties; Polymer powders; Powder properties; Process parameters; Product property; Spherical polymers; Selective laser melting

Novel concepts for characterisation of heterogeneous particulate surfaces - Peukert, Wolfgang; Mehler, Carsten; Götzinger, Martin (Applied Surface Science, 2002)
Surface properties of fine particles are of high relevance in several technical applications, such as nanotechnology, adsorption or crystallisation. Particulate surfaces are not well-defined, may contain flaws and dislocations, internal stresses and all kinds of impurities. Thus, these surfaces are structurally and energetically heterogeneous. Their interactions are, therefore, poorly understood. Adsorption equilibria, adhesion forces or contact angles reflect the interaction of molecules and particles with surfaces and fluid phases. Modelling of these elementary processes leads to mean or distributed surface properties of technical surfaces and small particles. The dispersive interactions of heterogeneous surfaces are characterised by mean parameters like a Hamaker constant. Henry coefficients of gases on activated carbon, graphite and alumina have been quantitatively described as a function of the critical temperature and pressure of the respective adsorptive and the Hamaker constant of the solid. Conversely, Hamaker constants determined from adsorption experiments are used to predict measured adhesion forces of alumina particles. Polar interactions are described by a new approach derived from continuum models of liquids. The particle surface is characterised by a density distribution of partial charges on small surface patches. By means of a statistical mechanical approach Henry coefficients both in the gas and liquid phase can be described quantitativel
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.novelc_8
Keywords: Particle surfaces; Characterisation; Adsorption; Adhesion

Novel Concepts for Teaching Particle Technology - Peukert, Wolfgang; Schmid, Hans-Joachim (Chemical Engineering Education, 2002)
The introduction of particle technology in chemical engineering is discussed. The course focuses on product property approach. The course enhances the students's awareness of the whole process, the concepts for the formation of structured solids, product design and powder processing systems. Another course on particle characterization enables the students to choose an appropriate setup for arbitrary particle characterization task.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.novelc
Keywords: teaching; perticle; technology

Novel luminescent composite polymer fibers for warning and security systems - Peukert, Wolfgang; Damm, Cornelia; Schäfer, Karola; Möller, Martin; Gries, Thomas; Wang, Hailin; Pich, Andrij; Wilms, Christian; Seide, Gunnaer (Technische Textilien, 2012)
Novel luminescent, inorganic and organic nanopigments were developed for the preparation of polyethylene terephthalate (PET) fibers for applications in warning and security textiles. Luminescent nanopigments were designed by bottom-up procedures using precipitation synthesis or by top-down procedures using reactive grinding processes. The investigated nanopigments were zinc sulfide, doped with copper or manganese and strontium aluminate, doped with europium and dysprosium. Furthermore, organic dyestuffs and pigments (aldazines or perylenes) were investigated, some of them after encapsulation into silica nanoparticles. The obtained nanoparticles were applied to polymer melts for the production of filaments by extrusion processes. For this, the nanopigments were incorporated into masterbatches or liquid formulations. The filaments were finally investigated in texturing processes and were then further processed to textile fabrics. By usage of nanoscale luminescent pigments, higher luminescence, lower pigment dosage combined with better light, heat and wet fastness were achieved compared to conventionally used systems.
Keywords: luminiscent; polymer; nanopigment; precipitation; fiber

Novel luminescent composite polymer fibers for warning and security systems - Schäfer, Karola; Wang, Hailin; Pich, Andrij; Mol̈ler, Martin; Damm, Cornelia; Peukert, Wolfgang; Wilms, Christian; Seide, Gunnar; Gries, Thomas (Chemical Fibers International, 2012)
Conventional warning and security textiles based on molecular dispersed luminescent dyes exhibit limited photostability and wet fastness. The washing resistance of the textiles can be improved by using luminescent pigments instead of dyes for their coloration. The idea is to use the liquid agent for dispersion of the highly luminescent particles in this medium. The whole system is then injected into the extruder of the spin- fling unit and fibers are formed. The liquid agent stays inside the polymer and, therefore, has to be compatible with the polymer in order to avoid negative impact on the mechanical properties of the fibers. The evaluation of the dependence of changes of the properties and the process conditions is ambiguous, since the particle content and the amount of liquid dispersion agent was changed at the same time.
Keywords: textile; luminescent; dye; photostability; disperion; particle; extrusion

Novel process routes towards the production of spherical polymer powders for selective laser sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Kloos, Stephanie; Wirth, Karl-Ernst; Peukert, Wolfgang (AIP Conference Proceedings, 2019)
Additive manufacturing processes allow the production of individualized and complex parts without the use of molds or tools. Especially powder and beam-based AM processes like selective laser sintering (SLS) of polymers are promising, although the choice of commercial SLS powders is very limited. To further extend the applications of SLS, new and cheap materials with good processability must be supplied. Within this contribution two innovative methods for production of spherical polymer micro particles for SLS are discussed: The first approach is a process chain applicable to a wide range of polymers consisting of wet grinding in a stirred media mill followed by rounding of the obtained irregularshaped particles in a heated downer reactor and subsequent dry coating of the spherical particles for improvement of powder flowability. It will be outlined for glass-filled PBT systems. The second approach is melt emulsification with subsequent dry coating. In this process a polymer melt is emulsified by elongational and shear stresses in a rotor stator device. The method is exemplified for polypropylene (PP). Both approaches allow for production of spherical polymer micro particles. The effect of flowability, shape and bulk density on the powders' processabilities in SLS is assessed.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Additive manufacturing; Melt emulsification; Polymer powder; Rounding

Numerical and experimental investigation of the turbulent flow and mixing in a static T-mixer - Peukert, Wolfgang; Schwertfirm, Florian; Manhart, Michael; Gradl, Johannes; Schwarzer, Hans-Christoph (ASME 2006 2nd Joint U.S.-European Fluids Engineering Summer Meeting Collocated With the 14th International Conference on Nuclear Engineering, 2006)
Turbulent mixing plays an important role in chemical engineering, especially when the chemical reaction is fast compared to the mixing time. In this context a detailed knowledge of the flow field, the distribution of turbulent kinetic energy (TKE) and its dissipation rate is important, as these quantities are used for many mixing models. For this reason we conduct two direct numerical simulations (DNS) of a confined impinging jet reactor (CIJR) at Re = 500 and Sc = 1, with and without modelling the feeding pipes. The data is compared with particle image velocimetry (PIV) measurements and it is shown that only the simulation which includes the feeding pipes gives the correct flow field. This flow field is dominated by a stable vortex in the main mixing duct. High intensities of turbulent kinetic energy and dissipation are found in the impingement zone and decrease rapidly towards the exit of the CIJR. In the whole CIJR the turbulence is not in equilibrium. The mixing of the scalar is rapid in the impingement zone, but due to the fast decrease of the turbulent intensities and due to the relaminarisation of the flow the PDFs of the scalar distributions in cross sections of the CIJR take a bimodal form after the impingement zone. Copyright © 2006 by ASME.
Keywords: turbulence; mixing; kinetic; energy; simulation; jet; impinging

Numerical Investigation of Flow Patterns and Concentration Profiles in Y-Mixers - Babu, Harsha Vardhan; Sahu, Swati; Haderlein, Michael; Peukert, Wolfgang; Verma, Nishith (Journal of Chemical Engineering & Process Technology, 2016)
The fluid flow patterns and associated concentration fields in Y-mixers are investi- gated using lattice Boltzmann method-based models. The focus lies on the impact of the mixing angle on the flow and concentration fields, with the mixing angle varying between acute (q =10) and obtuse (q = 130) angles. Residence time dis- tributions are determined to study the effect of the angles on the mixing and velocity patterns, in particular, different flow regimes, i.e., stratified laminar, vor- tex, and engulfment flow. The results from the simulations are validated with liter- ature data and found to be in good agreement. Maximum mixing occurs in the 100 obtuse-angle Y-mixer, attributed to the extensive engulfment of flows in the mixing channel.<br
Keywords: Lattice Boltzmann methods; Micromixers; Computational fluid dynamics; Residence time distribution; Y-mixers

Numerical study of the packing density of fine powders by means of the Discrete Element Method - Blümel, Christina; Ribeiro Parteli, Eric Josef; Schmidt, Jochen; Wirth, Karl Ernst; Peukert, Wolfgang; Pöschel, Thorsten (85th Annual Meeting of the International Association of Applied Mathematics and Mechanics – GAMM 2014, 2014)
Numerical simulations by means of the Discrete Element Method (DEM) can provide a helpful tool in the investigation of the packing behavior of powders. In this type of numerical simulations, the Newton’s equations of motion for every single particle in the system are solved by taking into account all forces and torques acting on it, both due to external fields and due to interactions with other particles in the system

Observing Oriented Attachment during Mesocrystal Growth with in Situ Dynamic Light Scattering (DLS) - Embrechts, Heidemarie; Zhang, Siqi; Hock, Rainer; Peukert, Wolfgang; Distaso, Monica (Crystal Growth & Design, 2020)
Despite rapidly growing interest in the application of mesocrystals in catalysis, energy storage, and sensing, the understanding of mesocrystal formation mechanisms remains a relatively unexplored field, due to the time and space overlapping of different reaction steps, namely, the nucleation and growth of solid phase and, possibly, their self-assembly in 3D superstructures. In particular, the role of polymers used as templating matrices requires more in-depth investigation. Here, ZnO–PVP mesocrystals are used as a model system and their formation from molecular precursors is followed with simultaneous in situ dynamic light scattering (DLS) and turbidity measurements. The formation of 10 nm primary building blocks during the early stages of the synthesis and their subsequent oriented attachment into 200–1200 nm mesocrystalline superstructures are both directly observed with in situ DLS. The primary particle concentration at which oriented attachment (OA) begins to occur at an observable rate is proportional to the colloidal primary particle stability and is compared for different synthesis conditions with inline turbidity measurements. Synthesis with higher PVP concentrations and molecular weights results in increasingly sterically stabilized primary particles and the formation of larger ZnO–PVP mesospheres. The larger diameter of mesocrystals synthesized at higher PVP educt concentrations is attributed to partial screening of (electrostatic repulsive) interparticle interactions between mesocrystals and primary particles by attached surface PV
Keywords: Oxides; Nanoparticles; Dynamic light scattering; Chemical synthesis; Metal oxide nanoparticles

One-pot colloidal synthesis of plasmonic patchy particles - Bao, Huixin; Peukert, Wolfgang; Klupp Taylor, Robin (Advanced Materials, 2011)
The one-pot synthesis of patchy particles with morphologically tunable optical properties by the heterogeneous nucleation and growth of silver onto colloidal silica particles is described. Heat treatment of the silica and coating reaction conditions can be optimized in order to produce full yields of patchy particles. Dissolution of the cores leads to stable silver cages. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: asymmetric nanoparticles; colloids; core/shell nanoparticles; janus particles; silver

On the control of dispersion interactions between biological membranes and protein coated biointerfaces - Blackwell, Robert; Hemmerle, Arnaud; Baer, Andreas; Späth, Matthias; Peukert, Wolfgang; Parsons, Drew; Sengupta, Kheya; Smith, Ana-Suncana (Journal of Colloid and Interface Science, 2021)
Hypothesis: Interaction of cellular membranes with biointerfaces is of vital importance for a number of medical devices and implants. Adhesiveness of these surfaces and cells is often regulated by depositing a layer of bovine serum albumin (BSA) or other protein coatings. However, anomalously large separations between phospholipid membranes and the biointerfaces in various conditions and buffers have been observed, which could not be understood using available theoretical arguments. Methods: Using the Lifshitz theory, we here evaluate the distance-dependent Hamaker coefficient describing the dispersion interaction between a biointerface and a membrane to understand the relative positioning of two surfaces. Our theoretical modeling is supported by experiments where the biointerface is represented by a glass substrate with deposited BSA and protein layers. These biointerfaces are allowed to interact with giant unilamellar vesicles decorated with polyethylene glycol (PEG) using PEG lipids to mimic cellular membranes and their pericellular coat. Results: We demonstrate that careful treatment of the van der Waals interactions is critical for explaining the lack of adhesiveness of the membranes with protein-decorated biointerfaces. We show that BSA alone indeed passivates the glass, but depositing an additional protein layer on the surface BSA, or producing multiple layers of proteins and BSA results in repulsive dispersion forces responsible for 100 nm large equilibrium separations between the two surfaces.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Biointerfaces; Dispersion forces; Lifshitz theory; Reflection interference contrast microscopy (RICM); Van der Waals interactions

On the impact of accessible surface and surface energy on particle formation and growth from the vapour phase - Peukert, Wolfgang; Artelt, Cordula; Schmid, Hans-Joachim (Journal of Aerosol Science, 2005)
This work investigates effects of reduced accessible surface area of aggregate particles and surface energy on titania particle formation and growth. It is taken into consideration that surface-related growth mechanisms, i.e. surface reaction and condensation, are limited to the fraction of the surface area of primary particles which is exposed to the collision with single molecules. Surface energy data determine the critical particle size with respect to evaporation and values are varied within the published range. This implies to develop a model which considers "surface shielding" and accounts for the formation of stable clusters from a supersaturated vapour due to nucleation and condensation besides considering the generation of monomers due to chemical reaction, growth due to surface reaction, agglomeration and sintering. Taking the accessible surface area into account is found out to be especially important if agglomerates contain a large number of primary particles or if agglomerate structure is rather compact. In this case, precursor consumption and primary particle growth turn out to be significantly retarded. Surface energy data are shown to be decisive with respect to the thermodynamic barrier to the formation of particles, thus to active particle formation and growth mechanisms, besides affecting sintering kinetics. Elevated surface energy data typically retard precursor consumption and favour primary particle growth. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Accessible surface; Aerosol process simulations; Nanoparticles; Surface energy

On the mechanism of Zn4O-acetate precursors ripening to ZnO: How dimerization is promoted by hydroxide incorporation - Segets, Doris; Milek, Theodor; Kirschbaum, Rolf; von Gernler, Marc; Lübbert, Christian; Drewello, Thomas; Peukert, Wolfgang; Zahn, Dirk (Journal of Chemical Physics, 2015)
We report on a combined experimental and molecular modelling study on Zn4O ion clusters stabilized by acetate molecules (OAc). In particular, ab initio calculations of acetate substitution by hydroxide ions are compared with mass spectrometry data. Though quantum calculations in the gas phase indicate strong energetic preference, no experimental evidence of stable Zn4O(OAc)6−x(OH)x clusters in ethanolic solutions could be observed. This apparent contradiction is rationalized by identifying the supportive role of hydroxide ions for the association of (OAc− → OH− substituted) Zn4O(OAc)6 and Zn4O(OAc)5+ clusters. Mass spectrometry and quantum calculations hint at the stability of (Zn4O)2(OAc)12−x(OH)x dimers with x = 1, 2. Therein, the hydroxide ions establish salt-bridges that allow for the formation of additional Zn3 motifs with the OH above the triangle center—a structural motif close to that of the ZnO-crystal. The association of Zn4O(OAc)6 clusters is thus suggested to involve OAc− → OH− substitution as an activation step, quickly followed by dimerization and the subsequent agglomeration of oligomer
Keywords: mechanism; particle; rod; nano; ripening

On the relevance of accounting for the evolution of the fractal dimension in aerosol process simulations - Peukert, Wolfgang; Artelt, Christian; Schmid, Hans-Joachim (Journal of Aerosol Science, 2003)
A population balance model is presented, which tracks particle growth in the gas phase and accounts for simultaneous agglomeration and sintering: Simulations reveal the evolution of the full distribution of a volume equivalent diameter and, amongst others, the evolution of the agglomerate collision diameter, a mean primary particle size and the number of primary particles per agglomerate. Furthermore, assuming fractal behaviour of the growing agglomerate particles—for the first time—a model for the evolution of a mean value of the fractal dimension based on physical and process parameters is proposed and incorporated into the simulation model. PARSIVAL, a commercial solver for integro-differential equations is employed to solve the equations involved. It is based on a generalised finite-element scheme with self-adaptive grid- and order construction. Calculations are performed to validate the model against monodisperse and sectional models published in literature for the exemplary case of Si production. The results are in good agreement if the same simplifying assumptions are made. However, results obtained from the new model for both—isothermal and non-isothermal process conditions—clearly show that it is important to consider the changing fractal dimension in many cases.
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.simula
Keywords: aerosol; agglomeration; simulation

Optical Analysis and Material Characterization of Nanoparticulate Oxides Synthesized via Flame Spray Pyrolysis - Münsterjohann, Bettina; Engel, Sascha; Stanzel, Melanie; Kilian, Daniel; Herre, Patrick; Peukert, Wolfgang; Will, Stefan (2014 MRS (Materials Research Society) Fall Meeting and Exhibit, 2014)

Optical Characterization of a Flame Spray Pyrolysis Process for the Synthesis of Nanoparticulate Oxides - Holfelder, Sandra; Stanzel, Melanie; Peukert, Wolfgang; Will, Stefan (36th International Symposium on Combustion, 2016)

Optical Investigation of a Flame Spray Pyrolysis Process for the Production of Nanoparticulate Oxides - Münsterjohann, Bettina; Holfelder, Sandra; Stanzel, Melanie; Peukert, Wolfgang; Will, Stefan (International Symposium Gas-phase Synthesis of Functional Nanomaterials, 2017)

Optical investigations of the droplet formation, evaporation and particle nucleation during the synthesis of zinc oxide nanoparticles in a Flame Spray Pyrolysis Process - Münsterjohann, Bettina; Labus, Markus; Huber, Franz; Stanzel, Melanie; Peukert, Wolfgang; Will, Stefan (37th International Symposium on Combustion, 2018)

Optimized polybutylene terephthalate powders for selective laser beam melting - Schmidt, Jochen; Sachs, Marius; Fanselow, Stephanie; Zhao, Meng; Romeis, Stefan; Drummer, Dietmar; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemical Engineering Science, 2016)
Additive manufacturing processes like selective laser beam melting of polymers (LBM) are established for production of prototypes and individualized parts. The transfer to serial production currently is hindered by the limited availability of polymer powders with good processability. Within this contribution the effect of powder properties, such as particle size, shape and flowability on the processability in LBM and their influence on device quality is exemplified for polybutylene terephthalate (PBT) materials. A process chain for the production of spherical polymer microparticles has been developed to obtain PBT powder materials. The process chain consists of three steps: first, polymer microparticles are produced by wet grinding. Second, the particle shape is engineered by rounding in a heated downer reactor to improve the flowability of the product. Third, a further improvement of flowability of the still cohesive spherical PBT particles is realized by dry coating with fumed silica. Moreover, properties of the PBT powders obtained along the process chain are thoroughly characterized with respect to structure and crystallinity by infrared spectroscopy, X-ray diffraction and differential scanning calorimetry. The effect of flowability, shape and bulk density on the powders’ processabilities in LBM is assessed by characterization of the quality of thin layers built in a LBM device. It is demonstrated that the device quality is strongly determined by particle properties: powders of good flowability and high bulk density are mandatory to obtain dense devices.
Keywords: Downer reactor; Dry particle coating; Flowability; Poly butylene terephthalate; Selective laser beam melting; Wet grinding

Optimized production of protein crystals: From 1D crystallization slot towards 2D supersaturation B22 diagram - Peukert, Wolfgang; Wanka, Johanna (Chemical Engineering & Technology, 2011)
The second osmotic virial coefficient, B, of protein solutions is a function of the protein interaction potentials and, thus, summarizes many solution parameters leading to crystallization or precipitation of proteins. B of hen egg-white lysozyme and bovine serum albumin was measured by static light scattering under the variation of pH, temperature, and crystallization agents. Comparing B values and precipitate morphology in a systematically analyzed range of solution conditions allows the construction of the so-called crystallization slot. The thermodynamic driving force for crystallization is supersaturation, which is set by the protein concentration and the solubility (related to B). Hence, besides the optimal B range, the protein concentration and, if solubilities are available, the supersaturation leads to a two-dimensional crystallization window where crystal formation is possible. This is shown in a generalized state diagram, where protein morphologies are solely determined as a function of protein concentration or supersaturation and interactions. The second osmotic virial coefficient, B, of protein solutions is a function of the protein interaction potentials. It therefore summarizes many solution parameters leading to crystallization or precipitation of proteins. Values of B were measured for different protein molecules under different solution conditions and were correlated to the results of crystallization experiments. © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Crystallization; Lysozyme; Proteins

Optimum between purification and colloidal stability of ZnO nanoparticles - Marczak, Renata; Segets, Doris; Voigt, Michael; Peukert, Wolfgang (Advanced Powder Technology, 2010)
Crystalline ZnO quantum dots have been synthesized by hydrolysis of zinc acetate dihydrate with lithium hydroxide in ethanolic solution. By varying different parameters of the synthesis process, the size of the ZnO particles can be controlled. Detailed investigation of the ripening of the nanoparticles evidenced that despite of the well-known influence of ageing temperature and time, the presence of the reaction byproduct lithium acetate strongly affects the ripening behaviour. In particular, the particle size can be almost completely arrested by the removal of this byproduct via reversible flocculation of the ZnO nanoparticles using heptane as an antisolvent. A closer analysis of the repeated washing process shows an initial improvement of the colloidal stability of the ZnO nanoparticles during the first purification cycle as it mainly removes the lithium acetate from the suspension and not the stabilizing acetate groups directly bound to the particle surface. With further washing the remaining acetate ligands are unable to maintain the stabilization against agglomeration of the ZnO nanoparticles. Thus, there exists an optimum between purification progress and colloidal stability. These findings are also confirmed by calculations according to the DLVO theory, which show that there exists nearly no primary minimum of small ZnO nanoparticles below 5 nm in the presence of stabilizing acetate ions whereas the decrease in acetate ions bound to the particle surface leads to a more and more pronounced primary minimum. The present work is of particular significance for the preparation of purified colloidal ZnO nanoparticles for studies of their electrical and optical properties with respect to their wide range of potential applications.

Organization of functionalized gold nanoparticles by controlled protein interactions - Kohut, Ananiy; Voronov, Andriy; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2006)
Gold colloidal particles were synthesized and modified by molecular self‐assembly. In addition, the reaction of biotinylated colloids with a tetrameric protein, avidin, was studied by optical absorption spectroscopy and dynamic light scattering. The modification involves the chemisorption of octadecanethiol on the gold, with the further attachment of alkyl biotin and cross‐linking with avidin molecules. The specific interaction of avidin with biotin leads to the controlled cross‐linking of particles. The degree of flocculation was quantified using a semi‐empirical flocculation parameter and its dependence on the biotinylation system was studied. The measured data were in good agreement, showing the possibility of regulating the aggregation rate and size of the aggregates using the experimental time, degree of biotinylation, and avidin concentration. The morphology of the self‐assembled gold monolayers, from the aggregated particles, was imaged by high‐resolution scanning electron microscopy. The structure of the thin particulate film depends on the bulk aggregate size and aggregation rat
Keywords: Bio-recognition; Particle size distribution; Gold aggregates

Organometallic perovskites for optoelectronic applications (Conference Presentation) - Levchuk, Ievgen; Högl, Florian; Brandl, Marco; Osvet, Andres; Herre, Patrick; Hock, Rainer; Schweizer, Peter; Spiecker, Erdmann; Batentschuk, Miroslaw; Brabec, Christoph; Peukert, Wolfgang (SPIE Nanoscience + Engineering, 2016, 2016)
Organometallic halide perovskites CH3NH3BX3 (B= Pb, Sn, Ge; X = I, Br, Cl) have become one of the most promising semiconductors for solar cell applications, reaching power conversion efficiencies beyond 20%. Improving our ability to harness the full potential of organometal halide perovskites requires the development of more reliable synthesis routines of well defined, reproducible and defect free reference systems allowing to study the fundamental photo-physical processes. In this study we present size and band gap engineering for organo-lead perovskites crystallites with various shapes and sizes ranging from the 5 nm regime all the way to 1 cm. Colloidal nano-crystals, micro-crystlline particles as well as single crystals are demonstrated with excellent purity and control in shape and size are demonstrated. The structural, optical and photo-physical properties of these reference materials are investigated and analyzed as function of their size and shape.
Keywords: particle; crystal; organometal; optoelectronics

Origin and use of SolidSim modules using as example the fluidized bed spray granulation, size reduction, and screening - Peukert, Wolfgang; Möhrl, Lothar; Drechsler, Jörg; Schmidt, Eberhard; Nitschke, Dirk; Toneva, Petya Ivanova (Chemie Ingenieur Technik, 2005)
Die Grundbausteine das SimulationssystemsSolidSim bilden sogenannte Units. Aus diesen Units werden im Rahmensystem des Program-mes flexibel komplexe Flieûbilder aufgebaut. So können in Simulationen die stationären Zustände unterschiedlichster Anlagenkonfigurationen unter Berücksichtigung variabler Prozessparameter untersucht werden.
Keywords: Simulation; solidsim; process; granulation; sieving; comminution

Packings of micron-sized spherical particles – Insights from bulk density determination, X-ray microtomography and discrete element simulations - Schmidt, Jochen; Parteli, Eric J.R.; Uhlmann, Norman; Wörlein, Norbert; Wirth, Karl-Ernst; Pöschel, Thorsten; Peukert, Wolfgang (Advanced Powder Technology, 2020)
The quantitative description of packing behaviour of particulate systems under consideration of realistic particle size distributions and material properties poses one challenging problem in powder technology, with impacts on a broad range of technological areas. Here we investigate the packing characteristics of micrometer to millimeter-sized, polydisperse spherical particle systems of glass, zirconia and copper by means of experimental measurements of the bulk density, X-ray microtomography (CT) and numerical simulations of the granular packings using a 3d discrete element method (DEM). The applied DEM method takes realistic material properties into account and considers the experimentally obtained particle size distributions as well as attractive inter-particle forces including adhesion (Johnson, Kendall, Roberts (JKR)) and non-bonded van der Waals (vdW) interactions. Good agreement of the packing densities predicted by DEM and observed in the experiments (bulk density determination & CT) is found. Moreover, we show that a simple mathematical expression for the packing fraction as a function of average particle size of the polydisperse powder system describes well our experimental and simulation results for all investigated materials, with only two fitting parameters. From the DEM simulations, the mean (first) coordination number in the respective polydisperse packing is extracted and discussed with respect to the experimentally obtained direct neighborhood detection from X-ray tomography and in context of previous works. The mean coordination number shows a rather broad variance due to the polydispersity of the samples considered. It also shows a remarkable dependency on the definition of particle contact. Therefore, caution is advised when evaluating coordination numbers with this quantity being highly dependent on the instrumental resolution.
CRIS-Team Scopus Importer:2020-04-24
Keywords: Bulk density; Discrete element method; Packings; X-ray microtomography

Painting by numbers: Nanoparticle-based colorants in the post-empirical age - Klupp Taylor, Robin; Seifrt, Frantiek; Zhuromskyy, Oleksandr; Peschel, Ulf; Leugering, Günter; Peukert, Wolfgang (Advanced Materials, 2011)
The visual appearance of the artificial world is largely governed by films or composites containing particles with at least one dimension smaller than a micron. Over the past century and a half, the optical properties of such materials have been scrutinized and a broad range of colorant products, based mostly on empirical microstructural improvements, developed. With the advent of advanced synthetic approaches capable of tailoring particle shape, size and composition on the nanoscale, the question of what is the optimum particle for a certain optical property can no longer be answered solely by experimentation. Instead, new and improved computational approaches are required to invert the structure-function relationship. This progress report reviews the development in our understanding of this relationship and indicates recent examples of how theoretical design is taking an ever increasingly important role in the search for enhanced or multifunctional colorants. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: colloids; core/shell nanoparticles; designed nanostructures; functional coatings; structure-property relationships

Particle Adhesion Force Distributions on Rough Surfaces - Götzinger, Martin; Peukert, Wolfgang (Langmuir, 2004)
The effect of roughness on adhesion force distribution was studied in the gas phase. Spherical gold particles with diameters between 5 and 20 μm were generated in a flame process and glued onto atomic force microscope (AFM) cantilevers directly after. Nanostructured substrates with defined roughness were produced by a dip-coating process. The geometry of the adhering partners was determined by AFM imaging, and the adhesion force was measured with the AFM. Depending on the roughness of the particles and the substrates, three types of distribution functions can be identified; two of them can be explained with a simple model. The obtained adhesion force distributions not only agree with those experimentally recorded in previous studies of commercially important powders (e.g., alumina, toner, and gold on different substrates) but also agree with distributions reported in the literature.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.adhesi_9

Particle attrition during pneumatic transport - Peukert, Wolfgang; Frye, Lars (Proceedings PARTEC 2004, 2004)
UnivIS-Import:2015-04-16:Pub.2004.tech.ITC.mechve.partic

Particle breakage in the nanometer range - Knieke, Catharina; Peukert, Wolfgang (2008 AIChE Annual Meeting, AIChE 100, 2008)

Particle breakage in the nanometer range - Knieke, Catharina; Peukert, Wolfgang (2008 AIChE Annual Meeting, AIChE 100, 2008)

Particle dispersions in liquid media - Damm, Cornelia; Peukert, Wolfgang (Particle Separation Techniques, 2022)
Particle separation and characterization requires their individualization in dispersions at moderate concentrations. Powders must be properly wetted by the liquid while dispersion requires breaking particle-particle bonds. For aggregates forming solid bridges the bonds in the bridges and within the primary particles can be similar strong. Therefore, dispersion requires considerable stress energy input. Many different devices are available to disperse agglomerates (weak bonds) and aggregates (strong bonds) in the lab and at production scale. Their understanding and design is discussed from a unified perspective. The dispersed particles must be sufficiently stable against coagulation. Colloidal stability can be estimated by the Derjaguin, Landau, Verwey, and Overbeek theory and determined experimentally by analytical centrifugation. Finally, case studies are presented: solvent-mediated size-selective precipitation of quantum dots <10 nm, dispersion of novel 2D materials at moderate energy input and of organic pigments <1 μm, drugs, and particles from gas phase synthesis in high energy mills are discussed.<br

Particle generation in pulsed plasmas - Peukert, Wolfgang; Artelt, Cordula; Rott, Martin; Höschen, Till; Behringer, Kurt; Bolt, Harald (Plasma Devices and Operations, 2008)
A new pulsed coaxial plasma generator has been developed in order to allow particle generation in the quench of a propagating jet to be investigated. The related process provides an extremely transient environment which is characterized by initially high energy and charge densities, steep temperature gradients and short particle residence times. The combinations of high quench rates and high charge densities, which cannot be obtained in conventional reactors such as in flames or quasistationary plasmas, provide in fact a potential for 'freezing' of non-equilibrium phases and for tailoring particle characteristics by means of controlling particle-particle interactions. The pulsed plasma is characterized by determining the energy coupling, the charge density, the expansion behaviour and the evolution of temperature. Particle properties such as the primary particle size and aggregate structure are determined for various process parameters, namely the energy coupling, precursor injection and ambient pressure.
Keywords: Carbon black; Emission spectroscopy; Particle charging; Particle-particle interactions; Plasma quench; Pulsed plasma generator

Particle Lagrangian CFD Simulation and Experimental Characterization of the Rounding of Polymer Particles in a Downer Reactor with Direct Heating - Gómez Bonilla, Juan S.; Unger, Laura; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Processes, 2021)
Polypropylene (PP) powders are rounded at different conditions in a downer reactor with direct heating. The particles are fed through a single central tube, while the preheated sheath gas is fed coaxially surrounding the central aerosol jet. The influence of the process parameters on the quality of the powder product in terms of particle shape and size is analyzed by correlating the experimental results with the flow pattern, residence time distribution of the particles and temperature distribution predicted by computational fluid dynamics (CFD) simulations. An Eulerian–Lagrangian numerical approach is used to capture the effect of the particle size distribution on the particle dynamics and the degree of rounding. The simulation results reveal that inlet effects lead to inhomogeneous particle radial distributions along the total length of the downer. The configuration of particle/gas injection also leads to fast dispersion of the particles in direction of the wall and to particle segregation by size. Broad particle residence time distributions are obtained due to broad particle size distribution of the powders and the particles dispersion towards the wall. Lower mass flow ratios of aerosol to sheath gas are useful to reduce the particle dispersion and produce more homogenous residence time distributions. The particles’ residence time at temperatures above the polymer’s melting onset is determined from the simulations. This time accounts for the effective treatment (rounding) time of the particles. Clear correlations are observed between the numerically determined effective rounding time distributions and the progress of shape modification on the particles determined experimentally.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Downer reactor; Eulerian–Lagrangian CFD; Particle aerodynamics; Particle rounding; Residence time distribution; Rounding time

Particle Properties - a missing link for predictive models in powder processing - Peukert, Wolfgang; Vogel, Lutz; Götzinger, Martin (4th International Conference on Bulk Solids Handling, 2003)
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.partic
Keywords: predictive; modeling; powder

Perikinetic and orthokinetic aggregation kinetics of a nanoscale model dispersion with use in size reduction in agitated ball mills - Peukert, Wolfgang; Sommer, Marc; Wagner, Norman (Chemie Ingenieur Technik, 2005)
Seit kurzem ist es möglich Partikel bis unter ca. 10 nm zu zerkleinern. Die Herausforderun- gen bei der Produktion von Nanopartikeln liegen im Wesentlichen in der Kontrolle von Partikel/Partikel-Wechselwirkungen, die das Verhalten von Suspensionen mit Partikel- gröûen unterhalb von einem Mikrometer maßgeblich beeinflussen. Mit abnehmender Partikelgröûe dominieren die attraktiven van der Waals-Wechselwirkungen, die bei Kollision zu festen Agglomeraten und zu einer Änderung der rheologischen Eigenschaften der Produktsuspension führen können. Aufgrund der Reagglomerationserscheinungen stellt sich nach dem Erreichen einer bestimmten Partikelgröûe ein Gleichgewichtszustand zwischen Agglomeration, Dispergierung und Bruch ein, so dass trotz steigenden spezifischen Ener- gieeintrags kein weiterer Zerkleinerungsfortschritt beobachtet wird. Um ein besseres Verständnis des Agglomerationsvorgangs während des Zerkleinerns zu erhalten, wurden Experimente mit einem gut charakterisierten Modellsystem monodisperser, nanoskaliger Primärpartikel durchgeführt. Der Einfluss der Stabilität der Suspension auf den, Agglomerationsvorgang wurde unter perikinetischen, orthokinetischen sowie unter Mühlenbedingungen untersucht. Die Agglomerationskinetik wurde durch dynamische Lichtstreuexperimente als Funktion von Partikel- und Elektrolytkonzentration gemessen. Weitere Informationen über den Agglomerationsprozess und die Struktur der Agglomerate wurden durch Neutronenkleinwinkelstreuexperimente erhalten. Die Agglomerationsrate ist unter orthokinetischen Bedingungen deutlich höher und die Agglomeratstruktur viel kompakter als unter perikinetischen Bedingungen (s. Abb.). Die Arbeit zeigt auûerdem die Möglichkeit auf, wie die Agglomeratstruktur durch Mahlung in Rührwerkskugelmühlen gezielt eingestellt werden können.
Keywords: Zerkleinerung; comminution; nanoparticle; interaction

Permeation durch vakuumbedampfte Kunststofffolien - Peukert, Wolfgang; Hanika, Markus; Langowski, Horst-Christian (Chemie Ingenieur Technik, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.permea
Keywords: permeation

Phase evolution of Cu2ZnSnS4 (CZTS) nanoparticles from in situ formed binary sulphides under solvothermal conditions - Ahmad, Rameez; Saddiqi, Naeem-ul-Hasan; Wu, Mingjian; Prato, Mirko; Spiecker, Erdmann; Peukert, Wolfgang; Distaso, Monica (CrystEngComm, 2021)
Cu2ZnSn(S,Se)(4) (CZTSSe) are benign and low-cost materials, overcoming the limitations of toxicity and high costs of other semiconductors such as CuInGa(S,Se)(2), cadmium and lead chalcogenides, and Pb-based perovskites widely used in photovoltaic and thermoelectric applications. In order to shed light on the formation mechanism of CZTS nanoparticles using anisole as the solvent, oleylamine as the organic ligand, carbon disulphide as the sulphur source and Zn(NO3)(2)center dot 6H(2)O as the Zn(ii) precursor, we follow the conversion of binary sulphides formed in situ under solvothermal conditions into quaternary phases. Besides a careful microstructural characterization of the as-synthesized materials by X-ray diffraction (XRD), Raman spectroscopy, electron microscopy (TEM and HRTEM) and energy dispersive X-ray (EDX) spectroscopy at micron- and nano-scale, we study the evolution of particle surface properties by X-ray-photoelectron spectroscopy (XPS). The results show that CZTS particles form already during the early stages of the reaction, most probably through a nucleation and growth mechanism. In parallel, a comparably slower growth mechanism is observed that involves recrystallization between the binary phases, without evidence of ternary phase formation.
CRIS-Team WoS Importer:2021-05-28
Keywords: Solar cell; Molecular precursors; Electronic structure; Thin films; Nanocrystals; Reduction; Complexes; Hydrogen; Stannite; Spectra

Phase Transition Behavior and Oriented Aggregation During Precipitation of In(OH)3 and InOOH Nanocrystals - Klaumünzer, Martin; Mackovic, Mirza; Ferstl, Pascal; Voigt, Michael; Spiecker, Erdmann; Meyer, Bernd; Peukert, Wolfgang (Journal of Physical Chemistry C, 2012)
The phase transition behavior and oriented aggregation (OA) during colloidal synthesis of In(OH)3 nanocrystals in water are investigated by TEM, SEM, X-ray diffraction, and density functional theory (DFT) calculations. Besides the cubic In(OH)3 phase, also orthorhombic InOOH is formed in a precipitation route using indium acetate as the In3+ source. Well-developed nano- and microcuboids are observed that consist solely of In(OH)3. In contrast, the InOOH phase remains semicrystalline even for long reaction (refluxing) times. The irregular growth of the InOOH phase is explained by proton transfers from hydroxyl groups to oxygen ions within the InOOH lattice that lead to OH disorder and lattice strain. DFT calculations of the surface energies of ideal and water-saturated low-index InOOH and In(OH)3 surfaces predict that the In(OH)3 phase becomes energetically more favorable than InOOH above a critical crystallite size. This explains why InOOH is formed before the In(OH)3 phase, which is an unusual pathway for a hydrothermal process. Once InOOH has transformed to In(OH)3 by incorporation of water, the crystallites can grow without restriction due to the disappearance of OH-disorder-induced strain. Finally, for the In(OH)3 cuboids a three-step formation process is suggested: In the first step, one-dimensional OA under formation of nanorods occurs. In the second step, parallel bundles are formed from the nanorods. In the third step these bundles merge into cuboids by three-dimensional O

pH effects on the molecular structure of β-lactoglobulin modified air-water interfaces and its impact on foam rheology - Peukert, Wolfgang; Engelhardt, Kathrin; Konnerth, Christoph-Günther; Braunschweig, Björn; Lexis, Meike; Gochev, Georgi; Miller, Reinhardt; Willenbacher, Norbert (Langmuir, 2013)
Macroscopic properties of aqueous β-lactoglobulin (BLG) foams and the molecular properties of BLG modified air-water interfaces as their major structural element were investigated with a unique combination of foam rheology measurements and interfacial sensitive methods such as sum-frequency generation and interfacial dilatational rheology. The molecular structure and protein-protein interactions at the air-water interface can be changed substantially with the solution pH and result in major changes in interfacial dilational and foam rheology. At a pH near the interfacial isoelectric point BLG molecules carry zero net charge and disordered multilayers with the highest interfacial dilatational elasticity are formed at the air-water interface. Increasing or decreasing the pH with respect to the isoelectric point leads to the formation of a BLG monolayer with repulsive electrostatic interactions among the adsorbed molecules which decrease the interfacial dilational elasticity. The latter molecular information does explain the behavior of BLG foams in our rheological studies, where in fact the highest apparent yield stresses and storage moduli are established with foams from electrolyte solutions with a pH close to the isoelectric point of BLG. At this pH the gas bubbles of the foam are stabilized by BLG multilayers with attractive intermolecular interactions at the ubiquitous air-water interfaces, while BLG layers with repulsive interactions decrease the apparent yield stress and storage moduli as stabilization of gas bubbles with a monolayer of BLG is less effective. © 2013 American Chemical Societ
Keywords: interface; surface; multilayer; foam; charge; bubble; stabilization

Photobleaching and stabilization of carbon nanodots produced by solvothermal synthesis. - Peukert, Wolfgang; Wang, Wenshuo; Damm, Cornelia; Walter, Johannes; Nacken, Thomas (Physical Chemistry Chemical Physics, 2015)
In this work we performed a detailed investigation of the photostability of bottom-up produced carbon nanodots (CDs) prepared from citric acid and urea by solvothermal synthesis. Analytical ultracentrifugation (AUC) reveals that the CDs have a hydrodynamic diameter of <1 nm and a very narrow size distribution. In the community it is widely assumed that CDs are photo-stable. In contrast, we found that CDs exposed to UV-irradiation exhibit noteworthy fluorescence degeneration compared to freshly prepared CDs or CDs stored in the dark, indicating that fluorescence bleaching is caused by a photochemical process. We found that fluorescence intensity decay due to exposure to UV-irradiation is accelerated in the presence of oxygen and identified the surface status of CDs as the decisive factor of fluorescence bleaching of CDs. Based on a discussion on the underlying mechanisms we show how to avoid photobleaching of CDs.
Keywords: carbon; nanodots; analytical; centrifugation; size distribution; fluorescence

pH-responsive anodic titanium dioxide nanotubes and nanocylinders for cancer drug delivery - Hasanzadeh Kafshgari, Morteza; Mazare, Anca Valentina; Distaso, Monica; Goldmann, Wolfgang; Peukert, Wolfgang; Fabry, Ben; Schmuki, Patrik (AMER SOC CELL BIOLOGY, 2018)

Physical degradation of proteins in well-defined fluid flows studied within a four-roll apparatus. - Peukert, Wolfgang; Simon, Sonja; Krause, H; Weber, C (Biotechnology and bioengineering, 2011)
In most applications of biotechnology and downstream processing proteins are exposed to fluid stresses in various flow configurations which often lead to the formation of unwanted protein aggregates. In this paper we present physical degradation experiments for proteins under well-defined flow conditions in a four-roll apparatus. The flow field was characterized numerically by computational fluid dynamics (CFD) and experimentally by particle image velocimetry (PIV). The local shear strain rate as well as the local shear and elongation rate was used to characterize the hydrodynamic stress environment acting on the proteins. Lysozyme was used as a model protein and subjected to well-defined fluid stresses in high and low stress environment. By using in situ turbidity measurements during stressing the aggregate formation was monitored directly in the fluid flow. An increase in absorbance at 350 nm was attributed to a higher content of visible particles (>1 µm). In addition to lysozyme, the formation of aggregates was confirmed for two larger proteins (bovine serum albumin and alcohol dehydrogenase). Thus, the presented experimental setup is a helpful tool to monitor flow-induced protein aggregation with high reproducibility. For instance, screening experiments for formulation development of biopharmaceuticals for fill and finish operations can be performed in the lab-scale in a short time-period if the stress distributions in the application are transferred and applied in the four-roll mill.
Keywords: biotechnology; downstream; polymer; simulation; cfd

PMSE 131-Self-assembly of amphiphilic polyesters monitored by Hyper-Rayleigh scattering and adsolubilization study in media differing by polarity - Voronov, Andriy; Martinez Tomalino, Lars-Owe; Kohut, Ananiy; Peukert, Wolfgang (2008)

PMSE 414-Synthesis of metal particles in nanoreactors made from amphiphilic polyesters - Kohut, Ananiy; Voronov, Andriy; Vasylyev, Serhiy; Peukert, Wolfgang (2008)

PMSE 94-Surface activity of new amphiphilic invertible polyesters from poly (ethylene glycol) and aliphatic dicarboxylic acids - Voronov, Andriy; Vasylyev, Serhiy; Kohut, Ananiy; Peukert, Wolfgang (2008)

Polarized light transmission in distorted 2-dimensional slab colloidal plasmonic-photonic crystals - Peukert, Wolfgang; Romanov, Sergey; Belotitskii, Vladimir; Korovin, Alexander; Lobazh, V (7th International Congress on Advanced Electromagnetic Materials in Microwaves and Optics Metamaterials 2013, 2013)
Polarization rotation was induced in 2-dimensional plasmonic-photonic crystal by uniformly distorting the shape of silver semishells. Physical mechanism of this phenomenon was analyzed using co-and cross-polarized transmission spectra. © 2013 IEEE.
Keywords: polarization; plasmon; crystal; transmission; photonic

Polarized Raman scattering and SEM combined full characterization of self-assembled nematic thin films - Srikantharajah, Rubitha; Gerstner, Karin; Romeis, Stefan; Peukert, Wolfgang (Nanoscale, 2016)
Elongated particles are predestined for a fast transfer of optical and electronical signals in a preferred direction, which is mandatory for a quick response in optoelectronic devices. The performance of the material is based on the quality of defect less alignment of the particles. On this account we present an easy non-invasive methodology for characterization of both surface and bulk order. The characterization of bulk order is performed by orientation dependent variation of the polarized Raman scattering signal on large areas by mapping. Scanning electron microscopy and image analysis on the surface complete the characterization. New insights in dip coated nematic structures clearly show the interplay of evaporation induced and shear-induced self-assembly and reveal a comprehensive mechanistic picture for nanorod assembly: the shear force dominated regime orients the particle in direction of withdrawal. At low withdrawal velocity, however, shear forces and evaporation counteract to produce a three-layered film where the top and bottom layers are oriented perpendicular to each other. The middle layer gives a clear evidence for a reorientation by convective flow.

Polyamide 11 nanocomposite feedstocks for powder bed fusion via liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Düsenberg, Björn; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Powder Technology, 2023)
Within this contribution, the incorporation of nanoparticles (SiO2, Al2O3, TiO2) into the matrix of precipitated polyamide particles during thermally induced phase separation (TIPS) is demonstrated. The obtained polymer composite powders are tailored for their application in powder bed fusion (PBF). The flexible process allows to tune and adapt the powder properties to meet specific challenges like narrow particle size distribution, spherical particles, high additive contents and good distribution of the additive within the powder. Thermogravimetric analysis and electron microscopy prove the incorporation of the nano-sized additive into the matrix of the polymer. The influence of the additive material during polymer precipitation on the particle size distribution and shape of the powders is discussed. Thermal properties of the composite powders were assessed by dynamic and isothermal DSC for subsequent Avrami analysis. The observed acceleration of the crystallization kinetics could be attributed to the nucleating effect of the additive. All powders showed an easy-flowing (flow index ffC > 4) behavior. This allowed the deposition of homogeneous powder layers during PBF experiments also at high temperatures. The processability of the composite powders in the PBF process was demonstrated by single layer experiments.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Liquid-liquid phase separation; Nanocomposite; Polyamides; Polymer precipitation; Powder bed fusion; Tailoring bulk properties; Thermal analysis

Polymeric stabilization of fused corundum during nanogrinding in stirred media mills - Eisermann, Claudia; Mallembakam, Madhusudhan Rao; Damm, Cornelia; Peukert, Wolfgang; Breitung-Faes, Sandra; Kwade, Arno (Powder Technology, 2012)
This paper deals with the steric stabilization of fused corundum during milling in ethanol and water. Different molecular weights of DAPRAL, a block copolymer with lyophilic and lyophobic side chains, were used to stabilize the feed material particles during wet grinding. Preliminary studies of the adsorbed amounts of the polymer in different solvents were determined by TGA and by rheology measurements in order to select sufficient amount of polymer to stabilize the suspension. The median particle size of sterically stabilized milled alumina particles was obtained via Dynamic Light Scattering, Ultrasonic Extinction, BET and SEM. In this investigation primary median particle sizes of 60 nm were obtained in ethanol by applying the steric stabilization mechanism. The mechanochemical characterization was carried out on the milled alumina particles and a phase transformation from alumina to aluminum hydroxide in water was observed, irrespective of stabilization mechanisms. However, no phase transformation was observed in ethanol. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Steric stabilization; Corundum dispersion; DLVO theory; Wet grinding; Adsorption mechanism; Mechanochemical effects

Polyurethane/silver-nanocomposites with enhanced silver ion release using multifunctional invertible polyesters - Peukert, Wolfgang; Damm, Cornelia; Triebel, Christian; Vasylyev, Serhiy; Stara, Hana; Özpinar, Celal; Münstedt, Helmut; Hausmann, Sebastian (Journal of Materials Chemistry, 2011)
Nano-silver composites with a thermoplastic polyurethane as the matrix were prepared by two different routes. Using the so-called in situ preparation, silver nanoparticles were obtained by a thermal reduction of silver acetate during melt mixing. In addition, a more sophisticated ex situ preparation method was developed. Here, the silver nanoparticles are synthesized in an invertible polyester resulting in much smaller particle sizes. The particles obtained are surrounded by the polyester cage, which stabilizes them with respect to agglomeration. Hence, an incorporation of those particles into a polymer melt with common techniques like extrusion leads to an even distribution. This is due to the fact that the invertible polyester and the polymer matrix are entirely miscible which was proven with DSC measurements. The silver ion release of the composites prepared was measured with anodic stripping voltammetry. At a constant weight percentage of silver in the polymer, the composite with the ex situ silver nanoparticles exhibits a silver ion release which is about two orders of magnitude higher than the release from the composite with the in situ silver nanoparticles. This observation is explained by the higher specific surface area of the smaller particles and a higher coefficient of diffusion for silver ions. A concentration of only 0.07 wt% silver nanoparticles, prepared with the ex situ method, exhibits a high enough release of silver ions to achieve antimicrobial properties. © 2011 The Royal Society of Chemistry.
Keywords: nanoparticle; polymer; thermal; reduction; ex-situ

Population balance modeling of InP quantum dots: Experimentally enabled global optimization to identify unknown material parameters - Wang, Zhuang; Traore, Nabi; Schikarski, Tobias; Stiegler, Lisa; Drobek, Dominik; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Walter, Johannes; Peukert, Wolfgang; Pflug, Lukas; Segets, Doris (Chemical Engineering Science, 2023)
Despite great progress in the synthetic chemistry of InP QDs, a predictive model to describe their temporal formation is still missing. In this work, we introduce a population balance model incorporating liquid phase reactions, homogeneous nucleation and reaction-limited growth of InP supported with the highly reproducible and reliable experimental data acquired from an automated robotic synthesis platform. A comparison between experimental kinetic data (different initial concentrations and temperatures) and simulations was made. The proposed model describes the temporal evolution of solid concentration, particle diameter and particle size distribution very well. The quantitative agreement between experiments and simulations was only achieved by global optimization to identify unknown and hardly measurable material parameters and kinetic constants such as surface energy, growth rate constants or activation energies. We see this model rendering the first step towards the development of more refined models that enable rigorous optimization and control of the production process for III-V semiconductors.
CRIS-Team Scopus Importer:2023-08-11
Keywords: Automated synthesis; InP; Population balance equation; Simulation

Prallzerkleinerung in Fließbettgegenstrahlmühlen: Vom Einzelkorn zur Mühle - Romeis, Stefan; Köninger, Benedikt; Strobel, Alexander; Wirth, Karl-Ernst; Peukert, Wolfgang (Chemie Ingenieur Technik, 2016)
Keywords: zerkleinerung; prallmühle; partikel

Precipitation of In(OH)3 and InOOH nanocrystals for the use in nanoelectronics: Phase transition behavior and oriented aggregation - Klaumünzer, Martin; Mackovic, Mirza; Ferstl, Pascal; Voigt, Michael; Spiecker, Erdmann; Meyer, Bernd; Peukert, Wolfgang (Nanotechnology 2013: Advanced Materials, CNTs, Particles, Films and Composites - 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
With respect to diverse applications in the wide field of nanoelectronics we characterize a specific phase transition behaviour and oriented aggregation (OA) during wet chemical synthesis of In(OH) nanocrystals as a wide band gap- and precursor material for InO. Contiguous to the cubic In(OH) phase, also orthorhombic InOOH is formed in a precipitation route with indium acetate as the In3+ source. Nano- and microcuboids are observed that consist exclusively of In(OH). The InOOH phase stays semi-crystalline even for long reaction times. On the basis of DFT calculations we find that for small crystallites the InOOH phase is more stable than the In(OH) phase, leading to a size-dependent transition from the InOOH phase to In(OH) above a critical crystallite size.
Keywords: Indium oxohydroxide; Nanocrystals; Oriented aggregation indium hydroxide; Precipitation

Precipitation of nanoparticles: A coupled LIF / PIV, DNS and PBE approach for prediction of the particle size distribution (PSD) - Peukert, Wolfgang; Gradl, Johannes; Schwertfirm, Florian; Schwarzer, Hans-Christoph; Manhart, Michael (2005)
Continuous precipitation is a promising process to generate nanoparticles with tailored properties. One challenge is to predict the PSD by considering all fluid dynamical, physiochemical and thermodynamical process parameters. A CFD-based approach using DNS in combination with Lagrangian Particle Tracking is applied coupled with micromixing and population balance models. The simulated flow field is validated by optical measurement methods (PIV and LIF). Whereas the mean particle size in dependence of the Re-number (over 6 orders of magnitude) can be predicted by a 1D approach, prediction of the complete PSD needs information from the fully resolved 3D fluid flow field.
Keywords: precipitation; continuous; mixing; prediction; simulation

Precipitation of nanoparticles in a T-mixer: Coupling the particle population dynamics with hydrodynamics through direct numerical simulation - Peukert, Wolfgang; Gradl, Johannes; Schwarzer, Hans-Christoph; Schwertfirm, Florian; Manhart, Michael (Chemical Engineering and Processing, 2006)
Mixing is a key parameter to tailor the particle size distribution (PSD) in nanoparticle precipitation. In this study we present two model approaches to simulate the impact of mixing on the PSD, using barium sulfate as exemplary material. In the first model, we combine a Lagrangian micromixing model with the population balance equation. This approach was found successful in predicting the influence of mixing on mean particle sizes but fails to predict the shape and width of the PSD. This is attributed to the neglect of spatial and temporal fluctuations in that model. Therefore, an improved CFD-based approach using direct numerical simulation (DNS) in combination with Lagrangian particle tracking strategy is applied. We found that the full DNS-approach, coupled to the population balance and a derived micromixing model, is capable of predicting the full PSD in nanoparticle precipitation. © 2006 Elsevier B.V. All rights reserved.
Keywords: Direct numeric simulation; Micromixing; Nanoparticle precipitation; Population balance; Supersaturation

Precision fermentation as a route to modify β-lactoglobulin structure through substitution of specific cysteine residues - Brune, Sarah E.; Hoppenreijs, Loes J.G.; Kuehl, Toni; Lautenbach, Vanessa; Walter, Johannes; Peukert, Wolfgang; Schwarz, Karin; Imhof, Diana; Boom, Remko M.; Krull, Rainer; Keppler, Julia K.; Biedendieck, Rebekka (International Dairy Journal, 2023)
Precision fermentation is a promising route to develop recombinant proteins with improved functionality. Protein functionality is highly influenced by protein structure, which can be significantly affected by conformational restraints induced by cysteines. Here, we study the impact of individual cysteines on β-lactoglobulin structure, by stepwise substituting them with alanine. Structural characterisation was performed from secondary to quaternary level. The findings demonstrated that the free Cys121 played no role in the folding and dimerisation of BLG. The β-barrel usually includes one disulphide bond (Cys106–Cys119), which was found to be crucial for its formation. The usually exposed disulphide bond (Cys66–Cys160) played no major role in folding of the β-barrel, but mainly modulated its accessibility and mediated dimerisation. Thereby, cysteine mutations can be used as a tool to modify protein structures. These different structures can now be used to further understand the impact on protein behaviour and their functionalit
Keywords: Amino acids; Recombinant proteins; Sulfur compounds; Cysteine residues; Different structure; Dimerizations; Disulphide bonds; Foldings; Lactoglobulin; Protein functionalities; Proteins structures; Structural characterization; Fermentation

Prediction of adsorption equilibria from physical properties of the pure components - Peukert, Wolfgang; Jung, Holger (Reprints of the 20th European Symposium on Applied Thermodynamics (ESAT 2003), 2003)
The prediction of adsorption energies equilibria is often based on mixed terms influenced by both the adsorptive and the adsorbent. Our aim is to predict adsorption equilibria by using physical properties of the pure components. Based on the concept of equivalent surface properties we introduce models using one or two mean parameters (Hamaker constant, mean partial charge) as well as a model which takes partial charge distributions into account. Density functional theory (DFT) calculations can be used to describe well defined and regular surfaces. However, the structure and topology of heterogeneous surfaces are generally unknown. Thus the combination of DFT-calculations with a continuum solvation model and experimental data allows the prediction of the adsorption equilibrium at infinite dilution. For activated carbon in the gas phase and in water the Henry’s law coefficients obtained by this method cover a range of 7 orders of magnitude. In order to gain a better understanding of the role of heterogeneities, DFT-calculations of model surfaces like functionalized coronenes or fullerenes were performed. A good qualitative agreement with the experimentally determined results was observed.
UnivIS-Import:2015-04-16:Pub.2003.tech.ITC.mechve.predic
Keywords: adsorption; equilibrium; property

Prediction of adsorption equilibria from physical properties of the pure components - Schürer, Gudrun; Peukert, Wolfgang (Adsorption-Journal of the International Adsorption Society, 2005)
The prediction of adsorption energies equilibria is often based on mixed terms influenced by both the adsorptive and the adsorbent. Our aim is to predict adsorption equilibria by using physical properties of the pure components. Based on the concept of equivalent surface properties we introduce models using one or two mean parameters (Hamaker constant, mean partial charge) as well as a model which takes partial charge distributions into account. Density functional theory (DFT) calculations can be used to describe well defined and regular surfaces. However, the structure and topology of heterogeneous surfaces are generally unknown. Thus the combination of DFT-calculations with a continuum solvation model and experimental data allows the prediction of the adsorption equilibrium at infinite dilution. For activated carbon in the gas phase and in water the Henry’s law coefficients obtained by this method cover a range of 7 orders of magnitude. In order to gain a better understanding of the role of heterogeneities, DFT-calculations of model surfaces like functionalized coronenes or fullerenes were performed. A good qualitative agreement with the experimentally determined results was observe
Keywords: Activated carbon; COSMO-RS; Adsorption equilibria prediction; Henry's law coefficient

Prediction of aggregation kinetics based on surface properties of nanoparticles - Peukert, Wolfgang; Schwarzer, Hans-Christoph (Chemical Engineering Science, 2005)
Aggregation of nanoscaled particles is a challenge to be met when controlling or tailoring particle size distributions (PSDs) in many areas including precipitation, dip-coating and milling. Control of aggregation can be achieved for sparingly soluble salts through stabilization by electrostatic repulsive particle-particle interaction. The presented work shows a combined experimental/numerical approach to quantitatively determine the stability using barium sulfate as the model substance. The experimental data is obtained by measuring the temporal evolution of the PSD. A detailed aggregation model is presented based on the population balance equation including the influence of particle-particle interactions via the so-called stability ratio W. Values for this ratio are determined by a parameter estimation strategy from the experimental data and then successfully correlated via the surface charge density to the adsorption of potential-determining ions (H+- and Ba2+-ions in the investigated system). The model is validated and its ability to capture the influence of ionic strength and particle size is tested successfully. Many insights are gained and favorable feed concentrations for the production of nanoparticles through precipitation identified. Thus the presented multi-scale approach relating the aggregation behavior to surface properties is not only well-suited for finding optimal stability but also to determine surface properties of nanoparticles. © 2004 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2005.tech.ITC.mechve.predic
Keywords: Aggregation; Barium sulfate; Ion adsorption; Nanoparticle precipitation; Stabilization; Surface charge density

Prediction of thermodynamic properties from pure compound information: Characterization of fullerenes - Peukert, Wolfgang; Schürer, Gudrun (Applied Surface Science, 2005)
Fullerenes are widely studied not only in material, but also in life science due to their special properties. Their surface properties determine their interaction with the environment and influence adsorption as well as biodistribution. In this work, the surfaces of a series of fullerenes and polyhydroxylated C-fullerenes were investigated using density functional theory (DFT)/conductor-like screening model (COSMO)-calculations. The dependence of the screening charge density from the curvature of a carbon hexagon and its effect on the adsorption behavior was studied. The estimation of thermodynamic properties of multiply functionalized C-molecules gives promising qualitative results using only properties of the pure compounds. © 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; DFT; Fullerenes; Functionalization

Predictive simulation of nanoparticle precipitation based on the population balance equation - Peukert, Wolfgang; Schwarzer, Hans-Christoph; Schwertfirm, Florian; Manhart, Michael; Schmid, Hans-Joachim (Chemical Engineering Science, 2006)
Nanoparticle precipitation is an interesting process to generate particles with tailored properties. In this study we investigate the impact of various process steps such as solid formation, mixing and agglomeration on the resulting particle size distribution (PSD) as representative property using barium sulfate as exemplary material. Besides the experimental investigation, process simulations were carried out by solving the full 1D population balance equation coupled to a model describing the micromixing kinetics based on a finite-element Galerkin h-p-method. This combination of population balance and micromixing model was applied successfully to predict the influence of mixing on mean sizes (good quantitative agreement between experimental data and simulation results are obtained) and gain insights into nanoparticle precipitation: The interfacial energy was identified to be a critical parameter in predicting the particle size, poor mixing results in larger particles and the impact of agglomeration was found to increase with supersaturation due to larger particle numbers. Shear-induced agglomeration was found to be controllable through the residence time in turbulent regions and the intensity of turbulence, necessary for intense mixing but undesired due to agglomeration. By this approach, however, the distribution width is underestimated which is attributed to the large spectrum of mixing histories of fluid elements on their way through the mixer. Therefore, an improved computational fluid dynamics-based approach using direct numerical simulation with a Lagrangian particle tracking strategy is applied in combination with the coupled population balance-micromixing approach. We found that the full DNS-approach, coupled to the population balance and micromixing model is capable of predicting not only the mean sizes but the full PSD in nanoparticle precipitation. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Computational fluid dynamics; Direct numerical simulation; Micromixing; Nanoparticle; Population balance; Precipitation

Predictive simulation of nanoparticles-precipitation in a T-mixer by coupling direct numerical simulation with population balance equations - Peukert, Wolfgang; Gradl, Johannes; et al. (2006 AIChE Spring National Meeting - 5th World Congress on Particle Technology, 2006)
Mixing and consequently fluid dynamics are key parameters to tailor the particle size distribution (PSD) in nanoparticle precipitation. The influence of the operating conditions on the flow and concentration field of the applied mixer is investigated experimentally by PIV and LIF. In this study we present two model approaches to simulate the impact of mixing on the PSD, using barium sulfate as exemplary material, In the first model, a Lagrangian micromixing model is combined with the population balance equation. This approach was found successful in predicting the influence of mixing on mean particle sizes but fails to predict the shape and width of the PSD. This is attributed to the neglect of spatial and temporal fluctuations in that model. Therefore, an improved CFD-based approach using Direct Numerical Simulation (DNS) in combination with Lagrangian Particle Tracking strategy is applied. We found that the DNS-approach including macro and micro mixing, coupled to the population balance is capable of predicting the full PSD in nanoparticle precipitation. Additionally to the resulting PSD this approach delivers 3D-information on all running subprocesses in the mixer, i.e. supersaturation built-up or nucleation, which are visualized for different process variables.
Keywords: Direct numerical simulation; Lagrangian particle tracking; LIF; Mixing; PIV; Population balance equations; Precipitation; Supersaturation

Pressure induced local phase transformation in nanocrystalline tetragonal zirconia microparticles - Schwenger, Jan; Romeis, Stefan; Herre, Patrick; Yokosawa, Tadahiro; Finsel, Maik; Leib, Elisabeth W.; Weller, Horst; Vossmeyer, Tobias; Spiecker, Erdmann; Peukert, Wolfgang (Scripta Materialia, 2019)
Keywords: Focused ion beam (FIB); Martensitic phase transformation; Compression testing; Electron diffraction; Zirconia microparticles

Probing colloidal interfaces by angle-resolved second harmonic light scattering - Schürer, Benedikt; Wunderlich, Sarina; Sauerbeck, Christian; Peschel, Ulf; Peukert, Wolfgang (Physical Review B, 2010)
We report angle-resolved second harmonic light scattering from bare colloidal particles in water. A nonlinear Mie model is used to quantitatively analyze the nonresonant second harmonic (SH) scattering profiles and to determine the elements of the local second-order surface susceptibility. The SH signal is attributed to oriented and electrically polarized water molecules at the charged particle interface. The results show how angle-resolved SH light scattering can be applied to probe not only resonant excited dye molecules but also nonresonant molecules such as water at the interface of colloidal particles.

Probing particle heteroaggregation using analytical centrifugation - Rey, Marcel; Uttinger, Maximilian; Peukert, Wolfgang; Walter, Johannes; Vogel, Nicolas (Soft Matter, 2020)
The controlled aggregation of colloidal particles is not only a widespread natural phenomenon but also serves as a tool to design complex building blocks with tailored shape and functionalities. However, the quantitative characterization of such heteroaggregation processes remains challenging. Here, we demonstrate the use of analytical centrifugation to characterize the heteroaggregation of silica particles and soft microgels bearing similar surface charges. We investigate the attachment as well as the stability of the formed heteroaggregates as a function of particle to microgel surface ratio, microgel size and the influence of temperature. The attachment of microgels onto the colloidal particles induces a change in the sedimentation coefficient, which is used to quantitatively identify the number of attached microgels. We corroborate the shift in sedimentation coefficient by computer simulations of the frictional properties of heteroaggregates via a modified Brownian dynamic algorithm. The comparison between theoretical investigations and experiments suggest that the microgels deform and flatten upon attachment. <

Probing sedimentation non-ideality of particulate systems using analytical centrifugation - Uttinger, Maximilian; Jung, Wieland David Krischan; Dao, Thi Quynh Nhi; Canziani, Herbert; Lübbert, Christian; Vogel, Nicolas; Peukert, Wolfgang; Harting, Jens; Walter, Johannes (Soft Matter, 2021)
Analytical centrifugation is a versatile technique for the quantitative characterization of colloidal systems including colloidal stability. The recent developments in data acquisition and evaluation allow the accurate determination of particle size, shape anisotropy and particle density. High precision analytical centrifugation is in particular suited for the study of particle interactions and concentration-dependent sedimentation coefficients. We present a holistic approach for the quantitative determination of sedimentation non-ideality via analytical centrifugation for polydisperse, plain and amino-functionalized silica particles spanning over one order of magnitude in particle size between 100 nm and 1200 nm. These systems typically behave as neutral hard spheres as predicted by auxiliary lattice Boltzmann simulations. The extent of electrostatic interactions and their impact on sedimentation non-ideality can be quantified by the repulsion range, which is the ratio of the Debye length and the average interparticle distance. Experimental access to the repulsion range is provided through conductivity measurements. With the experimental repulsion range at hand, we estimate the effect of polydispersity on concentration-dependent sedimentation properties through a combination of lattice Boltzmann and Brownian dynamics simulations. Finally, we determine the concentration-dependent sedimentation properties of charge-stabilized, fluorescently-labeled silica particles with a nominal particle size of 30 nm and reduced interparticle distance, hence an elevated repulsion range. Overall, our results demonstrate how the influence of hard-sphere type and electrostatic interactions can be quantified when probing sedimentation non-ideality of particulate systems using analytical centrifugation even for systems exhibiting moderate sample heterogeneity and complex interactions.<br

Process control strategies for the gas phase synthesis of silicon nanoparticles - Gröschel, Michael; Koermer, Richard; Walther, Maximilian; Leugering, Günter; Peukert, Wolfgang (Chemical Engineering Science, 2012)
In this contribution the identification of new reaction conditions for the production of nearly monodisperse silicon nanoparticles via the pyrolysis of monosilane in a hot wall reactor is considered. For this purpose a full finite volume model has been combined with a state-of-the-art trust-region optimisation algorithm for process control. Verified against experimental data, specific process conditions are determined accomplishing a versatile range of prescribed product properties. The main achievement of the optimisation is the possibility to control the different mechanisms in the particle formation process by mainly adjusting the temperature profile. Due to a successful separation of the nucleation and growth process, significantly narrower particle size distributions are obtained. Moreover, the presented optimisation framework establishes rate constants based on measured data.

Process engineering of nanoparticles below 20 nm—a fundamental discussion of characterization, particle formation, stability and post processing - Peukert, Wolfgang; Segets, Doris (Springer International Publishing, 2015)
In the following chapter fundamental aspects that have to be considered during the processing of small nanoparticles will be addressed. We investigated quantum confined manganese doped ZnS, ZnO, PbS and PbSe semiconductor nanoparticles, so-called quantum dots (QDs) and silver noble metal nanorods. All materials were chosen due to their technical relevance for future applications in the emerging fields of solar cells, sensors and diagnostics as well as due to the possibility of their in situ characterization by UV/Vis absorbance spectroscopy. After a brief introduction to the specific prospects and challenges of these materials we will focus on the important processing issues that need to be solved for producing these particles at high quality on a larger scale: (i) the modelling of particle formation including nucleation, growth and ripening based on a mechanistic understanding and on experimentally derived data on solubility and surface energies, (ii) the stabilization of nanoparticles not only against agglomeration but also against shape changes and (iii) classification. The latter is realized by size selective precipitation which allows surprisingly sharp separations (κ= 0.75) of particles with only a few nm in diameter. Although the extremely small particle sizes (feed PSD between 1.5 and 3 nm), classification results were successfully analyzed by well-known concepts from particle technology. Our results are seen to be an essential contribution to colloidal processing. They enable a future optimization of process parameters by a knowledge-based design strategy that can be applied within continuous as well as automatized batch reactor concepts.
Keywords: Classification; Colloidal stability; Nanoparticle handling; Optical properties; Oriented attachment; Ostwald ripening; Particle formation mechanism; Quantum dots; Shape transformation

Process modeling of in situ-adsorption of a bacterial lipase - Peukert, Wolfgang; Militzer, Michael; Wenzig, Edda (Biotechnology and Bioengineering, 2005)
In situ adsorption, known as an in situ-product removal (ISPR) technique for low molecular mass bioproducts, was in this study applied to a bacterial exoenzyme proving that this method is also suitable for the separation of macromolecules like proteins. For this, adsorbent particles were added to growing cultures of Staphylococcus carnosus rec., therefore both production and adsorption occurred simultaneously in shaking flasks, stirred tank, or airlift bioreactor as the chosen types of fermenters. The exoenzyme lipase adsorbed rapidly and, after separating cells and adsorbents, desorbed in a packed bed column. Up to 85% of the produced lipase were recovered, fractions of these had been concentrated up to the factor 20 and purified up to a factor of 40 by the procedure. By using the airlift bioreactor an enhancement of biomass production was observed, but the necessity of the addition of an anti-foam reagent resulted in higher product losses in adsorption as well as in desorption. Production and adsorption kinetics have been modeled and applied to in situ-adsorption. The model was used to perform a parameter study in which the influence of biological and physical parameters as well as process parameters on discontinuous and continuous in situ-adsorption was investigate
Keywords: adsorption; bacterial; enzyme; kinetic; product

Process Routes towards Novel Polybutylene Terephthalate – Polycarbonate Blend Powders for Selective Laser Sintering - Schmidt, Jochen; Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Bück, Andreas; Peukert, Wolfgang (Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium 2019, 2019)

Product engineering of nanoscaled materials - Peukert, Wolfgang; Voronov, Andriy (Particulate Systems in Nano- and Biotechnologies, 2008)

Production and analysis of electrically conductive polymer – Carbon-black composites for powder based Additive Manufacturing - Düsenberg, Björn; Tischer, Florentin; Seidel, Anne Marie; Kopp, Sebastian-Paul; Schmidt, Jochen; Roth, Stephan; Peukert, Wolfgang; Bück, Andreas (Procedia CIRP, 2022)
In laser powder bed fusion, micro-particles are selectively fused by a laser to produce parts, layer-by-layer. While this process offers a high freedom of design, the variety of commercially available materials, especially composites are limited. Conductive polymers blends, are very interesting for many applications, especially as sensors with freely definable shape. First, the amount of carbon-black needed to make the composite electrically conductive has to be determined; this limit is called percolation threshold (PT). The PT depends on many properties, such as particle size and shape of both polymer and carbon-black and will be determined experimentally. In this work, polypropylene is dry mixed with different types of micron sized carbon blacks. The PT and the conductivity is determined by means of impedance spectroscopy. Finally, layers are printed to evaluate the processability of the new composite.<br
Keywords: polypropylene; carbon black; percolation threshold

Production of dispersions with small particle size from commercial indium tin oxide powder for the deposition of highly conductive and transparent films - Mahajeri, Mahdi; Schneider, Andreas; Baum, Marcus; Rechtenwald, T.; Voigt, Michael; Schmidt, Michael; Peukert, Wolfgang (Thin Solid Films, 2012)
Indium tin oxide (ITO) nanoparticle films for applications in printable electronics were prepared by dip-coating. The dispersion conditions (bead size, stabilizer concentration) strongly affect the particle size of the ITO suspensions and consequently determine the surface morphology of the ITO films. Deposition from ethanolic ITO suspensions with an extremely small particle size of 17 nm to 21 nm led to the formation of extremely smooth and spike-free ITO films with a typical root mean square surface roughness of 4.5 nm +/- 0.2 nm and a high optical transparency above 95%. The effect of annealing with forming gas and CO2 laser treatment on the electrical properties of the ITO films was investigated. Annealing with forming gas and CO2 laser treatment led to a temporary increase in the electrical conductivity of the ITO films by up to a factor of 10 and 6, respectively. Specific conductivities of up to 196 S cm(-1) were obtained for our ITO nanoparticle films under optimized conditions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Indium tin oxide; Nanoparticles; Suspension; Conductivity; Laser treatment; Forming gas treatment

Production of filled hydrogels by mechanochemically induced polymerization - Damm, Cornelia; Mallembakam, Madhusudhan Rao; Voronov, Andriy; Peukert, Wolfgang (Journal of Applied Polymer Science, 2011)
Silica nanoparticles functionalized with polyvinylpyrrolidone (PVP) were obtained by the grinding/mechanical activation of quartz or nonfunctionalized silica nanoparticles in a stirred media mill in the presence of 1-vinyl-2-pyrrolidone, as proven by Fourier transform infrared spectroscopy. The polymer layer thickness formed on the silica nanoparticles after 8 h of mechanical activation in the absence of polymerization initiators amounted to about 10 nm, as derived from shear rheology. The silica nanoparticles functionalized with the hydrophilic PVP by mechanochemical polymerization reaction were used as fillers for hydrogels based on poly(hydroxyethyl methacrylate) (polyHEMA). The water absorption, release properties, and mechanical properties of the polyHEMA-silica composites were measured as functions of the filler content and particle size of the filler. PolyHEMA samples containing 20 wt % of the functionalized silica particles exhibited a higher maximum water absorption than the unfilled polymer; this showed that the hydrophilic interface between the filler and the matrix improved the water absorption. The release of methylene blue from the polyHEMA-silica composites was governed by diffusion and was almost unaffected by the silica particles. The values for the storage modulus and loss modulus of the polyHEMA-silica composites increased with growing filler content. For constant filler content, the storage modulus increased with decreasing particle diameter of the filler; this showed that the reinforcing effect increased with the interface between the filler particles and the matrix polymer. © 2010 Wiley Periodicals, Inc.
Keywords: composites; hydrophilic polymers; silicas; swelling

Production of Micron-Sized particles by melt emulsification - Fanselow, Stephanie; Schmidt, Jochen; Wirth, Karl-Ernst; Peukert, Wolfgang (8th International Conference for Conveying and Handling of Particulate Solids, CHoPS 2015, 2015)
Melt emulsification permits the production of spherical particles and is well-known for pharmaceutical applications and in the food industries. To increase the spectrum of applications the feasibility of the process for polymers is presented. In this study the influence of process parameters such as rotor-stator speed, temperature and dispersed phase viscosity on the particle size distribution of paraffin and polyethylene (PE) wax will be discussed. A major challenge is the stabilization of the droplet interface, thus, a new method for the selection of an efficient emulsifier using a high-pressure/high-temperature cell will be presented. Finally, results for higher viscous technical polymers, such as polypropylene (PP) will be presented. PP is a promising candidate for advanced powders to be used in additive manufacturing processes like laser beam melting (LBM) of polymers, i.e. melt emulsification might be a suitable approach to produce new and optimized LBM powder
Keywords: Laser beams; Particle size; Particle size analysis; Polymers; Polypropylenes; Powders; Additive manufacturing process; Dispersed phase; Food industries; Influence of process parameters; Laser beam melting; Micron-sized particles; Pharmaceutical applications; Spherical particle; Emulsification

Production of micron-sized polymer particles for additive manufacturing by melt emulsification - Peukert, Wolfgang; Fanselow, Stephanie; Schmidt, Jochen; Wirth, Karl-Ernst (Proceedings of PPS-31, 2016)
Melt emulsification is an advanced top-down approach that permits to produce spherical particles and thus widens the availability of polymer feed materials for additive manufacturing. In the process the polymer is molten in a continuous phase and droplet breakup is realized in a rotor-stator-device. The stabilization of the newly formed surfaces is quite challenging. Therefore, a new method to identify an appropriate emulsifier by measuring the interfacial tension between the polymer and continuous phase using a high pressure / high temperature cell is presented. The obtained powders are characterized by scanning electron microscopy (SEM) and by a Zimmermann tensile strength tester to determine the powder flowability. The processability of the polymer powders for additive manufacturing is investigated and demonstrated by building single layers by laser beam melting.
Keywords: additive manufacturing; melt emulsification; polymers

Production of PBT/PC multi-material particles via a combination of co-grinding and spray-agglomeration for powder bed fusion - Riedel, Florentin; Düsenberg, Björn; Schmidt, Jochen; Bück, Andreas; Peukert, Wolfgang (Procedia CIRP, 2020)
Polybutylene terephthalate (PBT) – polycarbonate (PC) multi-materials with a PBT mass content of 25% to 75% were produced for the powder bed fusion process by the means of co-grinding and spray agglomeration. The influence of the PC content and the process parameters on the thermal properties of the obtained powders are discussed in detail. Compared to pure PBT powder, the PBT/PC multi-materials crystallize at lower temperatures, which improves the handling during the additive manufacturing proces
Keywords: multi-material particles; polycarbonate; polybutylene terephthalate; comminution; spray agglomeration

Production of PBT/PC particle systems by wet grinding - Schmidt, Jochen; Romeis, Stefan; Peukert, Wolfgang (32nd International Conference of the Polymer Processing Society, PPS 2016, 2017)
Keywords: polycarbonate; polybutylene terephthalate; wet comminution; stirred media mill

Production of polyamide 11 microparticles for Additive Manufacturing by liquid-liquid phase separation and precipitation - Dechet, Maximilian; Goblirsch, Anja; Romeis, Stefan; Zhao, Meng; Lanyi, Franz; Kaschta, Joachim; Schubert, Dirk W.; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Chemical Engineering Science, 2019)
Within this contribution liquid-liquid phase separation (LLPS) and precipitation from ethanol was studied as an approach to produce polyamide 11 (PA11) powders for selective laser sintering (SLS). To this end, the cloud point and solution temperature curve of the PAll-ethanol system was determined experimentally via turbidity measurements. The proper range of system composition and temperature for particle formation was deduced. The dependence of particle characteristics on process parameters (polymer concentration, stirring conditions and temperature regime) during LLPS and precipitation was assessed and the products were characterized with respect to their size and morphology. Furthermore, structural, rheological and thermal characteristics were analyzed and correlated with process parameters. Molecular weight distributions were determined. After removal of fines and dry coating with hydrophobic fumed silica, an optimized PA11 powder with mean particle size of 91 mu m showing good flowability for SLS was obtained. SLS processability of this optimized PA11 powder was demonstrated by building multilayered test specimens in a laser sintering machine. With this contribution, we present a comprehensive workflow for the process development, product characterization and product application of a SLS powder manufactured via precipitation. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-21

Production of polybutylene terephtalate glass composite powders and characterization for processing in selective laser sintering - Schmidt, Jochen; Gomez Bonilla, Juan Sebastian; Sachs, Marius; Lanzl, Lydia; Wudy, Katrin; Wirth, Karl-Ernst; Drummer, Dietmar; Peukert, Wolfgang (26th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference, 2016)

Production of polymer particles below 5 μm by wet grinding - Schmidt, Jochen; Plata Acevedo, Miguel Angel; Tröger, Sulay; Peukert, Wolfgang (Powder Technology, 2012)
Polymeric microparticles that may be used in rapid prototyping processes typically are produced by either polymerization processes or cryogenic grinding in impact mills at liquid nitrogen temperature (− 196 °C) or by dry grinding at solid carbon dioxide temperature (− 78 °C). Within this account an alternative approach for the production of polymer particles is presented. It is shown that wet grinding of polymers in a stirred media mill and organic solvents (ethanol, hexane) at reduced temperatures down to − 80 °C is a suitable method to produce polymer particles of mean diameter smaller than 5 μm with narrow particle size distribution. Results are presented for wet grinding of polystyrene (PS) and polyetheretherketone (PEEK). The influence of the mechanical properties of the polymers under consideration and the influence of the process parameters, namely stress energy, process time and especially temperature and solvent viscosity are addressed. Remarkably, we found in case of PEEK that the mean diameter is one order of magnitude smaller than the zone of plastic deformation estimated from fracture toughness and yield stres
Keywords: Wet grinding; Micro-grinding; Stirred media mill; Polymer; Polystyrene; PEEK

Production of spherical ester wax powders by melt emulsification for Additive Manufacturing - Tischer, Florentin; Düsenberg, Björn; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2022)
Powder bed fusion of polymers with laser beam (PBF-LB/P) involves selectively melting plastic micro particles with a laser and building up the parts layer by layer, which offers great freedom of design. However, the choice of commercially available thermoplast feedstock powders is limited (90% polyamides). In order to extend the range of materials, this contribution presents the production of highly spherical micro particles by melt emulsification followed by spray agglomeration for ester wax. The effect of process parameters during emulsification (energy input, surfactant to polymer ratio) on the particle size distribution is demonstrated in detail for the ester wax system. In order to generate and tune particle sizes to a range suitable for PBF, melt emulsified ester wax dispersions are spray agglomerated. Agglomerated ester wax powders were used for the PBF process to manufacture tensile strength specimens type 5A.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Additive manufacturing; ester wax; Polycaprolactone; Melt emulsification; Polymers; Spray agglomeration

Production of Spherical Micron-Sized Polymer Particles for Additive Manufacturing by Liquid Phase Processes - Dechet, Maximilian; Kloos, Stephanie; Peukert, Wolfgang; Schmidt, Jochen (Proceedings of the Europe/Africa Conference Dresden 2017 Polymer Processing Society PPS, 2019)
CRIS-Team WoS Importer:2019-05-03

Production of spherical semi-crystalline polycarbonate microparticles for Additive Manufacturing by liquid-liquid phase separation - Kloos, Stephanie; Dechet, Maximilian; Peukert, Wolfgang; Schmidt, Jochen (Powder Technology, 2018)
Keywords: Polycarbonate (PC); Polymer microspheres; Additive Manufacturing (AM); Semi-crystalline thermoplast; Thermally induced phase separation (TIPS)

Production of spherical wax and polyolefin microparticles by melt emulsification for additive manufacturing - Fanselow, Stephanie; Emamjomeh, S. Ehsan; Wirth, Karl-Ernst; Schmidt, Jochen; Peukert, Wolfgang (Chemical Engineering Science, 2016)
Keywords: Melt emulsification; Polymer microspheres; Waxes; Polyethylene (PE); Polypropylene (PP); Additive manufacturing

Production of sub-micron particles by wet comminution in stirred media mills - Peukert, Wolfgang; Stenger, Frank; Mende, Stefan; Schwedes, Jörg (Journal of Materials Science, 2004)
A joined research project between the Technical University of Braunschweig and the Technical University of München investigates the possibilities for the production of stable product suspensions in a particle size range smaller than 100 nm. In this paper results for comminution of fused corundum showing the influence of the electrostatic stabilization at different pH-values on the grinding progress and the grinding media wear are presented. Furthermore, by means of experimental results the influence of the grinding media diameter and the stirrer tip speed is discussed. © 2004 Kluwer Academic Publishers.
Keywords: stabilization; comminution; electrostatic; grinding

Production of well dispersible single walled carbon nanotubes via a "floating catalyst"-method - Toni, Franziska; Xing, Haichen; Walter, Johannes; Strauß, Volker; Nacken, Thomas; Damm, Cornelia; Wirth, Karl-Ernst; Guldi, Dirk Michael; Peukert, Wolfgang (Chemical Engineering Science, 2015)
In this paper, we present a unique process chain for the production of single-walled carbon nanotubes (SWCNT) and document the relationship between the process parameters in gas phase production, the dispersibility of SWCNTs in aqueous solutions of sodium cholate and their properties. SWCNTs were prepared by a "floating catalyst" method using a solution of ferrocene in ethanol as precursor. Production rates in the range from 5 to 20. mg/h were achieved by using an optimized riser reactor design, which enables reduction of undesired wall-sticking of the catalyst particles and SWCNTs. Products featuring iron catalyst contents less than 30. wt% were obtained for low precursor concentrations in combination with short residence time in the reactor. Transmission electron microscopy (TEM) and statistical Raman analyses of the products reveal that the SWCNTs exhibit a diameter distribution ranging from 0.5 to 2.0. nm. Processing conditions, including precursor concentration, residence time, etc. were found to have only a slight impact on the mean geometric SWCNT diameter. Sonication based post-processing of the as-prepared SWCNTs in aqueous solutions of sodium cholate leads to an effective individualization of SWCNTs as proven by atomic force microscopy (AFM), 3D fluorescence spectroscopy, and by multi-wavelength analytical ultracentrifugation (AUC). Overall, the dispersibility of the non-purified SWCNTs in a 2. wt% aqueous solution of sodium cholate increases as the ferrocene partial pressure is decreased and, in turn, the catalyst concentration is reduced in the gas phase. Statistical Raman spectroscopy performed with the SWCNTs reveals that more than 75% of the produced carbon species are SWCNTs and that about 2/3 are semiconducting.
Keywords: Analytical ultracentrifugation and Raman spectroscopy; CNTs; Dispersion; Floating catalyst

Progress in Multidimensional Particle Characterization - Frank, Uwe; Uttinger, Maximilian; Wawra, Simon; Lübbert, Christian; Peukert, Wolfgang (KONA Powder and Particle Journal, 2021)
The properties of particle ensembles are defined by a complex multidimensional parameter space, namely particle size, shape, surface, structure, composition and their distributions. Macroscopic product properties are a direct result of these disperse particle properties. Therefore, the comprehensive multidimensional characterization of particle ensembles is a key task in any product design. However, the determination of complex property distributions is major challenge. We provide a broad overview of the current tools for multidimensional particle characterization. First, the mathematical handling of multidimensional (nD) property distribution is outlined as a necessary framework for the correct handling of nD particle size distributions (PSDs). Then, well-established techniques as well as recent developments with the potential to extract nD property distributions are reviewed. Exsitu imaging techniques like electron tomography or Raman spectroscopy with AFM co-localization, for instance, provide a resolution on the level of single particles but are limited in terms of sample statistics. A particular focus lies therefore on methods in the gas and the liquid phase, which provide multidimensional particle properties either directly or by a combination of one-dimensional technique

Progress in the understanding of bulk solids attrition in dilute phase pneumatic conveying - Peukert, Wolfgang; Frye, Lars (Powder Technology, 2004)
To investigate attrition processes in pneumatic conveying, it is distinguished between process parameters, determining the stress conditions (SC) the particles are subjected to during conveying (process function), and material properties, being responsible for the individual reaction of different materials to these stress conditions (material function). For dilute phase conveying, the process function was determined for a pipe bend preceded by a straight pipe by employing computational fluid dynamics (CFD). The influence of the main parameters as obtained by dimensional analysis, namely, Stokes parameter, Froude number, Reynolds number and the ratio of bend radius to pipe diameter, was investigated and discussed. The results showed that the impact conditions were different from what is commonly expected. The impact angles in a pipe bend (r /D=5; D=80 mm) were determined to lie between 5° and 35°. Consequently, the tangential impact velocity components are considerably higher than the normal ones. The experiments carried out to determine the material function revealed that the dominating attrition mechanisms differ between polypropylene (PP) particles on one hand and polymethylmethacrylates (PMMA) and polystyrenes (PS) on the other. By applying dynamic mechanical analysis (DMA), the glass transition temperature of the polymers was identified to be a key factor in the determination of the prevailing attrition mechanism. Based on these findings, a qualitative three-level model of the attrition process, involving stress mode, material-specific attrition mechanisms and basic (microscopic) attrition mechanisms, was developed. © 2004 Published by Elsevier B.V.
Keywords: Attrition mechanisms; Dynamic mechanical analysis (DMA); Material function; Pneumatic conveying; Polymers; Process function

Protein adsorption at the air-water interface studied by surface vibrational spectroscopy - Rumpel, Armin; Engelhardt, Kathrin; Braunschweig, Björn; Peukert, Wolfgang (Engineering Sciences and Fundamentals - Core Programming Topic at the 2011 AIChE Annual Meeting, 2011)

Protein adsorption at the electrified air-water interface: Effects on foam stability - Engelhardt, Kathrin; Peukert, Wolfgang; Braunschweig, Björn (Engineering Sciences and Fundamentals 2013 - Core Programming Area at the 2013 AIChE Annual Meeting: Global Challenges for Engineering a Sustainable Future, 2013)

Protein adsorption at the electrified air-water interface: Implications on foam stability - Braunschweig, Björn; Engelhardt, Kathrin; Rumpel, Armin; Walter, Johannes; Peukert, Wolfgang (2012)

Protein adsorption at the electrified air-water interface: Implications on foam stability - Engelhardt, Kathrin; Rumpel, Armin; Walter, Johannes; Dombrowski, Jannika; Kulozik, Ulrich; Braunschweig, Björn; Peukert, Wolfgang (Langmuir, 2012)
The surface chemistry of ions, water molecules, and proteins as well as their ability to form stable networks in foams can influence and control macroscopic properties such as taste and texture of dairy products considerably. Despite the significant relevance of protein adsorption at liquid interfaces, a molecular level understanding on the arrangement of proteins at interfaces and their interactions has been elusive. Therefore, we have addressed the adsorption of the model protein bovine serum albumin (BSA) at the air-water interface with vibrational sum-frequency generation (SFG) and ellipsometry. SFG provides specific information on the composition and average orientation of molecules at interfaces, while complementary information on the thickness of the adsorbed layer can be obtained with ellipsometry. Adsorption of charged BSA proteins at the water surface leads to an electrified interface, pH dependent charging, and electric field-induced polar ordering of interfacial H 2O and BSA. Varying the bulk pH of protein solutions changes the intensities of the protein related vibrational bands substantially, while dramatic changes in vibrational bands of interfacial H 2O are simultaneously observed. These observations have allowed us to determine the isoelectric point of BSA directly at the electrolyte-air interface for the first time. BSA covered air-water interfaces with a pH near the isoelectric point form an amorphous network of possibly agglomerated BSA proteins. Finally, we provide a direct correlation of the molecular structure of BSA interfaces with foam stability and new information on the link between microscopic properties of BSA at water surfaces and macroscopic properties such as the stability of protein foams. © 2012 American Chemical Society.
Created from Fastlane, Scopus look-up

Pulsed direct flame deposition and thermal annealing of transparent amorphous indium zinc oxide films as active layers in field effect transistors - Kilian, Daniel; Polster, Sebastian; Vogeler, Isabell; Frey, Lothar; Jank, Michael; Peukert, Wolfgang (ACS Applied Materials and Interfaces, 2014)
Indium-zinc oxide (IZO) films were deposited via flame spray pyrolysis (FSP) by pulsewise shooting a Si/SiO2 substrate directly into the combustion area of the flame. Based on UV-vis measurements of thin-films deposited on glass substrates, the optimal deposition parameters with respect to low haze values and film thicknesses of around 100 nm were determined. Thermal annealing of the deposited films at temperatures between 300 and 700 °C was carried out and staggered bottom gate thin-film transistors (TFT) were fabricated. The thin films were investigated by scanning electron microscopy, atomic force microscopy, X-ray diffraction, Fourier transformed infrared spectroscopy, and room-temperature photoluminescence measurements. The outcome of these investigations lead to two major requirements in order to implement a working TFT: (i) organic residues from the deposition process need to be removed and (ii) the net free charge carrier concentration has to be minimized by controlling the trap states in the semiconductor. The optimal annealing temperature was 300 °C as both requirements are fulfilled best in this case. This leads to field effect transistors with a low hysteresis, a saturation mobility of μSat = 0.1 cm2/(V s), a threshold voltage of Vth = -18.9 V, and an Ion/Ioff ratio on the order of 107. Depending on thermal treatment, the defect density changes significantly strongly influencing the transfer characteristics of the device. © 2014 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2014.tech.IE.LEB.pulsed
Keywords: amorphous metal oxides; direct deposition; field-effect transistor; flame spray pyrolysis; indium-zinc oxide; thermal annealing

Pulverschüttungsanalyse für das selektive Laser-Sintern mittels Computertomographie - Zhao, Meng; Greiner, Sandra; Wudy, Katrin; Schmidt, Jochen; Peukert, Wolfgang; Drummer, Dietmar (Proceedings of the 15th Rapid.Tech Conference, 2018)

Purification and structural elucidation of carbon dots by column chromatography - Hinterberger, Vanessa; Damm, Cornelia; Haines, Philipp; Guldi, Dirk Michael; Peukert, Wolfgang (Nanoscale, 2019)
Carbon dots (CDs) are an astonishing class of fluorescent materials with many applications in bioimaging, drug delivery, photovoltaics and photocatalysis due to their outstanding luminescence properties and low toxicity. However, the internal CD structure of bottom-up synthesized CDs is still the subject of considerable debate. Unambiguous analysis of the internal CD composition is hampered by the fact that reaction products usually contain mixtures of several CD fractions as well as molecular intermediate and side products. Therefore, purification and careful separation of the various CD fractions is vital for structural analysis and isolation of pure CDs possessing optimized optical properties. In this study, CD solutions were synthesized from citric acid and cysteine via a one-pot hydrothermal synthesis. A simple column chromatography unit was used to systematically study the influence of the molar precursor ratios and synthesis conditions (temperature, reaction time) on the CD solution composition. By investigating the structural and optical properties of the chromatographically separated fractions, three different fluorescent species could be identified. Freely floating molecular fluorophores left the column first, followed by highly fluorescent CDs with fluorophores bound to the carbon core, finally followed by low-fluorescent carbon particles without fluorophores. We demonstrate that the CD solution composition and the internal structure of the individual fluorescent components can be clarified via chromatographic separation. This information can be further applied to isolate pure CDs with optimized optical properties.
CRIS-Team Scopus Importer:2019-05-09

Quantification of grinding relevant material properties - Peukert, Wolfgang; Vogel, Lutz (World Congress Particle Technology 4, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.quanti
Keywords: grinding; material; property

Quantitative evaluation of delamination of graphite by wet media milling - Damm, Cornelia; Nacken, Thomas; Peukert, Wolfgang (Carbon, 2015)
Surfactant-free Few-Layer-Graphene (FLG) suspensions were prepared by wet media delamination of unmodified isostatic graphite in organic solvents using a shaking plate for fast screening of favorable process parameters and a stirred media mill as a delamination tool. The achieved FLG-concentration was determined by a combination of UV/Vis and Raman spectroscopy. A study of wet delamination for different solvents reveals an analogue behavior as for ultrasound-assisted delaminated samples. In N-methylpyrrolidone as dispersing medium the influence of delamination process parameters on FLG concentration was studied and an optimal set of parameters was found. A comparison between various delamination methods shows that delamination by enhanced shear leads to largest flake structures. The highest value for the FLG production rate (produced mass/time) is obtained in a stirred media mill. The formation of FLG was also proved by measuring the flake thickness by atomic force microscopy (AFM). The FLG percentage derived from AFM agrees well with the results determined by statistical Raman spectroscopic analyses.

Quantitative Evaluation of Fullerene Separation by Liquid Chromatography - Süß, Sebastian; Michaud, Vanessa; Amsharov, Konstantin; Akhmetov, Vladimir; Kaspereit, Malte; Damm, Cornelia; Peukert, Wolfgang (Journal of Physical Chemistry C, 2019)
Although a huge number of facile synthesis methods for nanoparticles (NPs) do exist, the products usually exhibit a distribution in particle size and shape. Thus, a separation step needs to be applied to adjust the particle properties according to the needs of the later application. Chromatography is a potentially scalable separation method which is well-established for separating molecules and promising for classifying NPs by size. Herein, we lay the foundations of particle chromatography by studying the separation of a C-60/C-70 fullerene mixture as well-defined particle probes using a pyrene-functionalized silica stationary phase. C-60 fullerenes are perfect model particles as they are spherical, roughly 1 nm in diameter, interacting via van der Waals interactions only. First, we extract the Henry coefficients for C-60 and C-70 fullerenes from the elution behavior of the fullerene mixture. Using a particle-wall as well as particle-particle model for the van der Waals interaction potential, we determine the Hamaker constant of the stationary phase material from the measured Henry coefficients. Moreover, we investigate the concentration-dependent diffusion and mass transport in the column by quantitative evaluation of the flow rate dependent elution behavior of the fullerenes. Our study shows the huge potential of chromatography for the separation of nanoparticles and demonstrates the strength of physical-chemical concepts for the quantitative analysis and the prediction of nanoparticle classification.
CRIS-Team WoS Importer:2019-07-30

Quantitative evaluation of nanoparticle classification by size-exclusion chromatography - Süß, Sebastian; Metzger, Christoph; Damm, Cornelia; Segets, Doris; Peukert, Wolfgang (Powder Technology, 2018)
Although few attempts for classification of nanoparticles (NPs) in labscale do exist, the transfer to industrial applications is still challenging. One promising separation method, which is already established for biological molecules, is chromatography. Herein, we study the classification of differently sized gold NPs (AuNPs) by size-exclusion chromatography (SEC). First, we investigated the interactions of AuNPs with potential stationary phases in order to identify a suitable material for the chromatographic process where irreversible NP adhesion is excluded. Then, we demonstrate the high reproducibility of our SEC experiments by multiple sample injections that lead to constant peak areas. In particular, we show the size-dependent elution behavior of AuNP mixtures resulting in bimodal elution peaks, where size separation was confirmed by inline measured UV/Vis spectra. Finally, NP classification results by using a fraction collector are characterized by retention time, mass balances and size-dependent separation efficiencies. The adjustment of the particle size distributions (PSDs) is demonstrated by changing the switching time of the fraction collector. Our study evidences the high potential of SEC for preparative and continuous separation of NPs.
Keywords: (Gold) particles; Separation efficiency; Chromatography; Separation

Quantitative evaluation of size selective precipitation of Mn-doped ZnS quantum dots by size distributions calculated from UV/Vis absorbance spectra - Segets, Doris; Komada, So; Butz, Benjamin; Spiecker, Erdmann; Mori, Yasushige; Peukert, Wolfgang (Journal of Nanoparticle Research, 2013)
We demonstrate the quantitative evaluation of the sharp classification of manganese-doped zinc sulfide (ZnS:Mn) quantum dots by size selective precipitation. The particles were characterized by the direct conversion of absorbance spectra to particle size distributions (PSDs) and high-resolution transmission electron micrographs (HRTEM). Gradual addition of a poor solvent (2-propanol) to the aqueous colloid led to the flocculation of larger particles. Though the starting suspension after synthesis had an already narrow PSD between 1.5 and 3.2 nm, different particle size fractions were subsequently isolated by the careful adjustment of the good solvent/poor solvent ratio. Moreover, due to the fact that for the analysis of the classification results the size distributions were available, an in-depth understanding of the quality of the distinct classification steps could be achieved. From the PSDs of the feed, as well as the coarse and the fine fractions with their corresponding yields determined after each classification step, an optimum after the first addition of poor solvent was identified with a maximal separation sharpness κ as high as 0.75. Only by the quantitative evaluation of classification results leading to an in-depth understanding of the relevant driving forces, a future transfer of this lab scale post-processing to larger quantities will be possible.

Quantitative investigation of the fragmentation process and defect density evolution of oxo-functionalized graphene due to ultrasonication and milling - Halbig, Christian Eberhard; Nacken, Thomas; Walter, Johannes; Damm, Cornelia; Eigler, Siegfried; Peukert, Wolfgang (Carbon, 2016)
In the view of technical and medical applications we examined the effect of ultrasonication and ball milling of oxo-functionalized graphene bearing an almost intact carbon lattice (oxo-G) with respect to the lateral flake size reduction and defect formation in the carbon lattice for the first time. The energy input was screened for both methods and quantitative changes in lateral flake size distribution were characterized in solution by analytical ultracentrifugation (AUC) supported by atomic force microscopy (AFM). For the first time, we applied statistical Raman spectroscopy to reliably evaluate the formation of lattice defects with processing time. Surprisingly, the density of lattice defects remains unaffected with energy inputs below a limiting threshold. Furthermore, for both processing techniques, the size reduction scales with the energy input according to a power law function, which is well known for emulsification and mechanical comminution processes. With the results of this study it is possible to precisely predetermine the lateral size of flakes of oxo-G upon sonication or milling processing, preserving the carbon lattice. Understanding this controlled formation of oxo-G flakes enables target oriented technical, medical and electronic applications with tailored properties.
EAM Import::2019-03-13

Quantitative modeling of precipitation processes - Schikarski, Tobias; Avila, Marc; Trzenschiok, Holger; Güldenpfennig, Andreas; Peukert, Wolfgang (Chemical Engineering Journal, 2022)
Precipitation from the liquid phase is a powerful and common unit operation for the continuous, highly reproducible production of nanoparticles. However, a general, predictive and quantitative modeling framework is still missing due to the inherent multiscale nature of the precipitation process and the complex interplay between the relevant sub-processes. We apply direct numerical simulation of the fluid flow coupled with a population balance framework to investigate the precipitation of stabilized ibuprofen nanoparticles in a T-mixer. Our findings suggest that the Damkohler number (the ratio between the mixing time and solid formation time) determines the precipitation outcome. We demonstrate how the primarily unknown solid formation kinetics can be estimated in the simulations with the guidance of experimental input at a single process condition. We subsequently vary the Damkohler number by changing the inflow rates (global mixing time) and the initial ibuprofen concentration. In doing so, excellent agreement between numerical simulations and experiments in the full particle size distribution at different process conditions (from laminar to turbulent flow and different initial ibuprofen concentrations) is obtained using the beforehand estimated solid formation kinetics. Our model opens avenues for the predictive simulation of particle-formation dynamics and is a stepping stone for the tailored, scalable production of nanoparticles.
CRIS-Team WoS Importer:2022-06-17

Rapid Characterization and Parameter Space Exploration of Perovskites Using an Automated Routine - Reinhardt, Elisabeth; Salaheldin, Ahmed M.; Distaso, Monica; Segets, Doris; Peukert, Wolfgang (ACS Combinatorial Science, 2020)
Hybrid, e.g., organic inorganic, perovskites from the type methylammonium lead iodide CH3NH3PbI3 are promising solar cell materials. However, due to the large parameter space spanned by the manifold combinations of divalent metals with organic cations and anions, an efficient approach is needed to rapidly test and categorize new promising materials. Herein, we developed a high throughput approach for the automated synthesis of perovskite layers with different precursor ratios at varying annealing temperatures. The layers were analyzed by optical absorption and photo-luminescence (PL) spectroscopy as well as X-ray diffraction (XRD) and evaluated using two different procedures. The first one is a stepwise exclusion of nonperforming reactant ratios and synthesis conditions by using both spectroscopic techniques, followed by a final validation of the procedure by XRD. In the second procedure, only PL results were consulted in combination with high throughput screening using design of experiments (DoE) to reduce the total number of experiments needed and compared to the manual cascade approach. Noteworthy, by simple PL screening, it was possible to identify the best ratio of perovskite to byproducts and annealing temperature. Thus, only with PL, more detailed results as with the manual protocol were reached, while at the same time the effort for characterization was significantly reduced (by 60% of the experimental time). In conclusion, our approach opens a way toward fast and efficient identification of new promising materials under different reaction and process conditions.
CRIS-Team WoS Importer:2020-01-31

Rapid fabrication and interface structure of highly faceted epitaxial Ni-Au solid solution nanoparticles on sapphire - Herre, Patrick; Will, Johannes; Dierner, Martin; Wang, Dong; Yokosawa, Tadahiro; Zech, Tobias; Wu, Mingjian; Przybilla, Thomas; Romeis, Stefan; Unruh, Tobias; Peukert, Wolfgang; Spiecker, Erdmann (Acta Materialia, 2021)
Supersaturated Ni-Au solid solution particles were synthesized by rapid solid-state dewetting of bilayer thin films deposited onto c-plane sapphire single-crystals. Rapid thermal annealing above the miscibility gap of the Ni-Au system followed by quenching to room temperature resulted in textured and faceted submicron-sized particles as a function of alloying content in the range of 0–28 at% Au. Morphologically, the observed kinetic crystal shapes are confined by close-packed planes; in addition, high-index facets are identified as a function of alloying content by TEM cross-sectioning and equilibrium crystal shape simulations. All samples exhibit a distinct 〈111〉 out-of-plane as well as in-plane texture along densely packed directions. Lattice parameters extracted from independent orthogonal X-ray and electron diffraction techniques prove the formation of a solid solution without tetragonal distortion imposed by the sapphire substrate. At the particle-substrate interface of highly alloyed particles segregation of Au atoms as well as dislocations in stand-off position are found. These observations are in-line with a semi-coherent interface, where Au segregation is triggered by the reduction of the overall strain energy due to: (i) a lower shear modulus on the particle side of the interface, (ii) the shifting of misfit dislocations in stand-off position further away from the stiffer substrate and (iii) a reduction of intrinsic misfit dislocation strain energy on the tensile side. In addition, the mechanical properties of pure and alloyed particles were characterized by in situ compression experiments in the SEM. Typical force-displacement data of defect-free single-crystals were obtained, reaching the theoretical strength of Ni for particles smaller than 400 nm. Alloying changes the mechanical response from an intermittent and discrete plastic flow behavior into a homogeneous deformation regime at large compressive strain.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Solid-state dewetting; Orientation relationship; Interface segregation; Scanning electron microscopy; Compression test

Reactor system for the study of high-temperature short-time sintering of nanoparticles - Peukert, Wolfgang; Kirchhof, Martin; Schmid, Hans-Joachim (Review of Scientific Instruments, 2004)
A high-temperature short residence time flow reactor system has been realized for the investigation of the gas phase sintering kinetics of nanoparticles separated from all other synthesis mechanisms, e.g.. chemical reaction, nucleation, coagulation and condensation. Major components are a hot-wall tubular reactor for the production of unsintered aggregates consisting of spherical primary particles in the size range 10-80 nm and a sintering reactor for the investigation of the sintering kinetics at well-defined temperature and residence time history. Therefore, rapid heating and quenching of the particles at the beginning and at the end of the reaction zone, respectively, is maintained. Main parameters in the sintering reactor are: temperatures up to 1873 K and residence times in the range 8-1000 ms. The reactor conditions are characterized by temperature profile measurements with a newly constructed suction thermocouple probe and by computational fluid dynamics simulations of the residence time distributions. Exemplary results of the sintering of silica nanoparticles obtained by transmission electron microscopy analysis are presented. © 2004 American Institute of Physics.
Keywords: high-temperature; sintering; kinetic; aggregates; nanoparticle; quenching; thermocouple

Real-Time Monitoring of the Nucleation and Growth of ZnO Nanoparticles Using an Optical Hyper-Rayleigh Scattering Method - Segets, Doris; Martinez Tomalino, Lars-Owe; Gradl, Johannes; Peukert, Wolfgang (Journal of Physical Chemistry C, 2009)
Incoherent nonlinear hyper-Rayleigh scattering (HRS) has been applied to monitor the different stages in the synthesis of sub-10 nm ZnO nanoparticles. During time-resolved investigation of the ripening process, we measured an increase in the particle hyperpolarizability, βZnO, with increasing particle size. Millisecond time resolution measurements revealed regions of prevalent nucleation, growth, and ripening. Using the size-dependent hyperpolarizabilities, a new general approach is introduced for the quantitative determination of nucleation, growth, and ripening rates via in situ HRS measurements. The derived solubility also allowed the determination of reasonable values of the ZnO surface energy.

Relation of Nanostructure and Recombination Dynamics in a Low-Temperature Solution-Processed CuInS2 Nanocrystalline Solar Cell - Azimi, Seyed Hamed; Heumüller, Thomas; Gerl, Andreas; Matt, Gebhard; Kubis, Peter; Distaso, Monica; Ahmad, Rameez; Akdas, Tugce; Richter, Moses; Peukert, Wolfgang; Brabec, Christoph (Advanced Energy Materials, 2013)
The understanding and control of nanostructures with regard to transport and recombination mechanisms is of key importance in the optimization of the power conversion efficiency (PCE) of solar cells based on inorganic nanocrystals. Here, the transport properties of solution-processed solar cells are investigated using photo-CELIV (photogenerated charge carrier extraction by linearly increasing voltage) and transient photovoltage techniques; the solar cells are prepared by an in-situ formation of CuInS2 nanocrystals (CIS NCs) at the low temperature of 270 °C. Structural and morphological analyses reveal the presence of a metastable CuIn5S8 phase and a disordered morphology in the CuInS2 nanocrytalline films consisting of polycrystalline grains at the nanoscale range. Consistent with the disordered morphology of the CIS NC thin films, the CIS NC devices are characterized by a low carrier mobility. The carrier density dynamic indicates that the recombination kinetics in these devices follows the dispersive bimolecular recombination model and does not fully behave in a diffusion-controlled manner, as expected by Langevin-type recombination. The mobility–lifetime product of the charge carriers properly explains the performance of the thin (200 nm) CIS NC solar cell with a high fill-factor of 64% and a PCE of over 3.5\
Keywords: nanostructures; power; conversion; nanocrystal

Relationship between Rheological Properties of Concentrated Colloidal Suspensions and the Structure of Dip-drawn Coatings Zusammenhang zwischen rheologischen Eigenschaften konzentrierter kolloidaler Suspensionen und der Struktur tauchgezogener Schichten - Günther, Lydia; Peukert, Wolfgang (Chemie Ingenieur Technik, 2003)

Retention mechanisms of 1.7 nm ZnS quantum dots and sub-20 nm Au nanoparticles in ultrafiltration membranes - Lee, Handol; Segets, Doris; Süß, Sebastian; Peukert, Wolfgang; Chen, Sheng-Chieh; Pui, David Y. H. (Journal of Membrane Science, 2018)
Keywords: Ultrafiltration; Rejection; Membrane categorization; Colloids; Diffusion deposition

Review: Second harmonic generation spectroscopy as a method for in Situ and online characterization of particle surface properties - Peukert, Wolfgang; Schneider, Lars (Particle & Particle Systems Characterization, 2007)
Non-linear optical spectroscopy is a recently established technique used in the investigation of the properties of colloidal interfaces. Since it is an optical method it is non-invasive, can be applied in situ, and can provide real time resolution. Until recently, only a few papers concerning this method have been published, but these all show the great potential and the large field of applications of the technique. This paper gives an overview of the fundamentals of the technique and its possible applications. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: Adsorption; Non-linear optical spectroscopy; Online-measurement; Particle surface characterization; Surface charge

Robust Optimization in Nanoparticle Technology: A Proof of Principle by Quantum Dot Growth in a Residence Time Reactor - Dienstbier, Jana; Aigner, Kevin-Martin; Rolfes, Jan; Peukert, Wolfgang; Segets, Doris; Pflug, Lukas; Liers, Frauke (Computers & Chemical Engineering, 2021)
Knowledge-based determination of the best-possible experimental setups for nanoparticle design is highly challenging. Additionally, such processes are accompanied by noticeable uncertainties. Therefore, protection against these uncertainties is needed. Robust optimization helps determining such best possible processes. The latter guarantees quality requirements regardless of how the uncertainties, e.g. with regard to variations in raw materials, heat and mass transport characteristics, material properties and (growth) rates, manifest within predefined ranges. To approach this huge task, in this paper we exemplarily model a particle synthesis process with seeded growth by population balance equations and study different growth kinetics. We determine the mean residence time maximizing the product mass subject to a guaranteed yield. Additionally, we hedge against uncertain growth rates and derive an algorithmically tractable reformulation for the robustified problem. We evaluate our approach for seeded growth synthesis of zinc oxide quantum dots and demonstrate computationally that a guaranteed yield is met for all growth rates within previously defined regions. The protection against uncertainties only reduces the maximum amount of product that can be obtained by a negligible margin.<br
Keywords: particle design; robust optimization; process optimization; reformulation

Role of Citrate and NaBr at the Surface of Colloidal Gold Nanoparticles during Functionalization - Dinkel, Rebecca; Jakobi, Jurij; Ziefuß, Anna Rosa; Barcikowski, Stephan; Braunschweig, Björn; Peukert, Wolfgang (Journal of Physical Chemistry C, 2018)
A molecular understanding of the ligand shell and the functionalization process is essential for the development of surface-functionalized gold nanoparticles (AuNPs). Obviously, the initial ligand shell from the synthesis plays a crucial role in this process. Here, in situ second-harmonic scattering is applied to study the adsorption of a 3-mercapto-1-propanesulfonate (MPS) at the surface of laser-ablated NaBr- and citrate-stabilized AuNPs with sizes of 5 nm. This systematic comparison is possible due to the fact that laser ablation in micromolar saline water gives access to narrowly distributed colloidal AuNPs without organic stabilizers. The Gibbs free energy of adsorption was determined to be of similar order for both AuNP batches (ca. −40 kJ/mol). The surface concentration of MPS, however, differed strongly and was more than 30% higher for NaBr-stabilized AuNP than for citrate-stabilized AuNP. Compared to planar Au substrates, the surface concentration of MPS on NaBr-AuNP suggests formation of a complete monolayer of MPS and demonstrates the fast functionalization of ligand-free AuNP up to monolayer coverage. On citrate-AuNP, however, an MPS coverage of only two-thirds of a monolayer is observed, which indicates that citrate partially resists functionalization and is mostly exchanged at low-coordinated Au surface sites. High surface coverage, however, is often closely linked to functionality, for example, when avidity effects are exploited during conjugate–receptor interaction
Keywords: Thiols; Metal nanoparticles; Adsorption; Gold; Nanoparticles

Role of Prenucleation Building Units in Determining Metal-Organic Framework MIL-53(Al) Morphology - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Crystal Growth and Design, 2020)
While it is well-known that the particle size of solvothermally synthesized metal-organic frameworks (MOFs) can be controlled by tuning the solvent composition, which affects the solubility of the linker and metal salt educts, the exact relationship between linker solubility, initial chemical coordination steps occurring in solution, and the resulting MOFs' particle size has not yet been investigated. Here, we have studied the solvothermal synthesis of MIL-53(Al) in DMF and water/DMF mixtures with in situ Raman spectroscopy, which reveals the formation of intermediate prenucleation building unit (PNBU) species that consist of one linker molecule and one metal atom and self-assemble in solution to form MIL-53(Al). The concentration of PNBUs in solution prior to particle precipitation is dependent on the synthesis solvent ratio used and influences the MIL-53 particle size. Synthesis in pure DMF results in a high concentration of PNBUs in solution prior to MOF supersaturation and precipitation. This results in a large burst of MOF nucleation and the formation of nanosized MIL-53(Al) particles. Adding water to the DMF solution leads to reduced PNBU accumulation in solution prior to MOF precipitation due to the reduced linker solubility. The reduced accumulation of PNBUs prior to particle precipitation causes reduced nucleation and favors particle growth. The MIL-53(Al) particle size, in contrast, is independent of the MOF phase growth rate, which is highly dependent on the synthesis temperature.
CRIS-Team WoS Importer:2020-06-26

Role of shear and extensional stress on the degradation of proteins during downstream processing - Simon, Sonja; Weber, Carsten; Peukert, Wolfgang (2010 AIChE Annual Meeting, 10AIChE, 2010)
In most applications of biotechnology and downstream processing proteins are stressed in various flow configurations by shear and extensional stress. In this work we present stress experiments of several proteins under well-defined flow conditions. In combination with insitu analytics flow-induced aggregation phenomena and conformational changes can be successfully monitored. In addition to shear and elongation, the contribution of adsorption phenomena to interfaces is investigate
Keywords: Prefil; Syringe; Protein Aggregate; Adsorption phenomena; Aggregation phenomena; Conformational change; Downstream-processing; Extensional stress; Flow condition; Flow configurations; In-situ; Adsorption; Proteins

Rounding of irregular polymer particles in a downer reactor - Sachs, Marius; Schmidt, Jochen; Toni, Franziska; Blümel, Christina; Winzer, Bettina; Peukert, Wolfgang; Wirth, Karl-Ernst (Procedia Engineering 102, 2015)
In the past additive manufacturing processes relying on beam-based methods such as selective laser sintering (SLS) of polymers were almost exclusively applied for the generation of prototypes. In recent years, however, these methods are increasingly applied in the serial production of e.g. special parts to be used in the automotive industry. With this increased relevance in industrial applications, the demands on the powder material increased as well [1]. The so far used polymer materials show weak performance regarding the mechanical stability of processed parts. In consequence, there is a need for fine powders of different polymers showing good powder flowability and high bulk density. Currently, the commercial availability of polymer powders for SLS is very limited and the production processes are still not reliable enough due to poor powder characteristics. Within this contribution a process for the production of spherical polymer micro particles showing good powder flowability is presented [2]. It has been recently shown [3] for different materials that commercially available polymer granules can be ground down to the micron size range by a wet grinding process. Due to the grinding process the produced micron-sized particles are in a chiseled state, which leads to a bad flowability of the powder material. To overcome this problem the single particles are melted in a heated downer reactor and spherical particles are obtained by using the effect of the surface tension [3]. The rounding of ground PS microparticles was performed in a downer reactor with a length of 1,600 mm and a diameter of 25 mm. The reactor temperature was set 100 °C above the melting temperature of the treated material. The laminar flow regime in the downer reactor allows a well-defined residence time of particles and the surrounding gas [4]. The design of the downer reactor allows transferring the polymer particles in the molten state whilst avoiding contact between the single particles and between molten particles and the reactor wall. The mechanism of the rounding process in dependence of particle size, interfacial tension and melt viscosity will be shown within a sintering model [6]. The influence of residence time and overall solids density in the downer reactor on the particle shape and on the flowability of the bulk material is shown. Estimates from the sintering model allow for a reliable reactor design.<br
Keywords: additive manufacturing; particle rounding; downer reactor; polymers

Scalable production of glass flakes via compression in the liquid phase - Esper, Julian Duane; Liu, Lingfeng; Willnauer, Johannes; Strobel, Alexander; Schwenger, Jan; Romeis, Stefan; Peukert, Wolfgang (Advanced Powder Technology, 2020)
A comprehensive study on controlled shape formation with high yield of three commercially relevant SiO2-based amorphous glasses in a stirred media mill is presented. Stressing under well-controlled conditions leads to micron-sized amorphous glass flakes with high aspect ratios. This unique result is quite contrary to the fundamental observation that comminution processes generally result in irregular shaped particles. The influences of glass composition, processing time, stirrer tip speed and grinding media size on the obtained products have been investigated. The size and shape of the obtained glass flakes have been characterized by scanning electron microscopy and atomic force microscopy. The glass flakes exhibit thicknesses as low as 155 nm while the lateral dimensions are well within the micrometer range. Our study shows that particle size reduction occurs within the first hour of grinding. Afterwards plastic deformation of the fragments, which can be accompanied by densification of the glass network, leads to the formation and further thinning of the glass flakes. To demonstrate the quality and applicability of the glass flakes interference pigments were realized by a TiO2 coating via an aqueous titration process. The presented approach offers a simple, convenient and fully scalable top-down method to produce flake-like particles from various silica glasses. The obtained flakes are suitable substrates for further modifications and applications and the process can be transferred to other materials and glasses with tailor-made chemical composition
Keywords: Stirred media mill; Comminution; Liquid phase compression; Particle processing; Glass flakes; Pigments

Scalable production of graphene sheets by mechanical delamination - Knieke, Catharina; Berger, Angela; Voigt, Michael; Klupp Taylor, Robin; Röhrl, Jonas; Peukert, Wolfgang (Carbon, 2010)
Mono- and multilayer graphene sheets have been successfully produced from commercial graphite powder in a wet grinding process under mild milling conditions. The shear forces in the milling chamber lead to a continuous delamination of ultrathin graphene flakes which are dispersed in a liquid medium. To avoid agglomeration of the exfoliated flakes the anionic surfactant sodium dodecyl sulfate was used. By adjusting the process parameters in a way to overcome the weak interlayer forces between the sheets without breaking them leads to the fabrication of thin flakes with high aspect ratios. The presented scalable process allows a high-yield and low-cost production of free-standing graphene sheets for various application
Keywords: monolayer; graphene; graphite; wet; grinding; interlayer; forces; flake; scaleable; sheet

Second Harmonic Generation from metallic and dielectric spherical nanoparticles - Peukert, Wolfgang; Wunderlich, Sarina; Zhuromskyy, Oleksandr; Schürer, Benedikt; Haderlein, Michael; Sauerbeck, Christian; Peschel, Ulf (2012 Conference on Lasers and Electro-Optics (CLEO), 2012)
Due to symmetry-breaking at an interface, Second Harmonic Generation (SHG) is an extremely surface sensitive process. Therefore it is a widely used tool to study surfaces. Applied to colloidal nanoparticles it offers efficient means to monitor growth and molecular adsorption processes in real time and in situ. This makes SHG a preferred method to study the formation of core-shell plasmonic nanoparticles, which recently became quite popular because of their strong and tunable plasmonic resonances.
Keywords: Symmetry; spherical; nanoparticle; second; harmonic; generation; plasmon; Optical; surface; wave; Harmonic analysis; Plasmons; Frequency conversion; Dielectrics

Second Harmonic Light Scattering from Spherical Polyelectrolyte Brushes - Peukert, Wolfgang; Schürer, Benedikt; Hoffmann, Martin; Wunderlich, Sarina; Peschel, Ulf; Harnau, Ludger; Ballauf, Matthias (Journal of Physical Chemistry C, 2011)
Optical second harmonic generation (SHG) was applied to study the shell layer of spherical polyelectrolyte brushes (SPB) as a function of ionic strength. The particles consist of a polystyrene core from which linear chains of a quenched polyelectrolyte are grafted. Compared to all systems studied by SHG previously, the shell layer in this study has a remarkable thickness of ca. 100 nm. Angle-resolved second harmonic (SH) scattering profiles were recorded and compared to simulations with different model geometries using a nonlinear Mie scattering model. The analysis reveals that the second harmonic signal is not generated by the polyelectrolyte molecules, but rather by oriented and polarized water molecules at the inner (polystyrene / polyelectrolyte) and at the outer (polyelectrolyte / solvent) interface of the polyelectrolyte shell. The results demonstrate that angle-resolved SH light scattering provides direct access to the structure of water and the screening of charges at the inner and outer interface of the polyelectrolyte shell. Correspondingly, this work sets the experimental and theoretical basis for the study of the extended interfacial layer of electrosterically stabilized particles by SH light scattering.
Keywords: optical; second; harmonic; generation; particle; polyelectrolyte

Selective and caspase-independent cytotoxicity of bioactive glasses towards giant cell tumor of bone derived neoplastic stromal cells but not to bone marrow derived stromal cells. - Westhauser, Fabian; Arango Ospina, Marcela; Losch, Sarina; Wilkesmann, Sebastian; Lehner, Burkhard; Ali, Muhammad Saad; Peukert, Wolfgang; Boccaccini, Aldo R.; Fellenberg, Jörg (Biomaterials, 2021)
Semi-malignant giant cell tumors of bone (GCTB) are associated with large osteolytic defects and significant bone destructions. Surgical resection remains the standard therapy that is, however, associated with very high recurrence rates. Bioactive glasses (BGs) that are osteogenic but under certain conditions also cytotoxic might be suitable to achieve biological reconstruction with simultaneous reduction of tumor recurrence in GCTB. In this study, a concentration and time dependent cytotoxic effect of five different BG compositions towards neoplastic GCTB cells was identified while bone marrow derived mesenchymal stromal cells were mostly unaffected. Time course and extent of the cytotoxic effect were dependent on the BG composition and were not associated with caspases activation, indicating that apoptotic mechanisms are not involved. Rather, detection of BG-induced disruption of the cell membranes and a rapid drop of intracellular HMG1 (High Mobility Group Box 1 protein) levels suggest a necrotic cell death. Notably, the cytotoxic effects were dependent on a direct contact of cells and BGs and could not be observed using indirect cultivation settings. Our data suggest that BGs might represent promising materials for the treatment of GCTB in order to reduce tumor recurrence with simultaneous enhancement of bone regeneration.
Keywords: Apoptosis; Bioactive glass; Caspases; Cytotoxicity; Giant cell tumor of bone; Mesenchymal stromal cells; Necrosis

Self-alignment of zinc oxide nanorods into a 3D-smectic phase - Schäfer, Stefan; Srikantharajah, Rubitha; Klaumünzer, Martin; Lobaz, Volodymyr; Voigt, Michael; Peukert, Wolfgang (Thin Solid Films, 2014)
We focus on thin films from ZnO nanorod dispersions in order to generate a high lateral order and a dense space filling structure applicable e. g. in printed optoelectronic devices. Highly stable dispersions with a solid content of up to 60 wt.% in ethanol were prepared using trioxadecanoic acid as stabilizer. With the dispersions we prepared thin films on substrates with a 3D-smectic phase in lateral dimension of cm2 and thicknesses from below 100 nm up to 1 μm. We show how the concentration of the initial solid content is influencing the formation of domains in our films and discuss the self-assembly process into ordered structures.

Self-assembled monolayers as corrosion inhibitors; indoor, marine and biologically relevant exposure - Hosseinpour, Saman; Leygraf, Christofer; Gretic, Zana Hajdari; Mioc, Ekatarina Kristan; Curkovic, Helena Otmacic; Bochmann, Sebastian; Bachmann, Julien; Waegner, Victoria; Virtanen, Sannakaisa; Peukert, Wolfgang (Joint European Corrosion Congress 2017, EUROCORR 2017 and 20th International Corrosion Congress and Process Safety Congress 2017, 2017)

Self-Assembled Monolayers Get Their Final Finish via a Quasi-Langmuir-Blodgett Transfer - Meltzer, Christian; Dietrich, Hanno; Zahn, Dirk; Peukert, Wolfgang; Braunschweig, Björn (Langmuir, 2015)
The growth of self-assembled monolayers (SAMs) of octadecylphosphonic acid (ODPA) molecules on α-Al2O3(0001) and subsequent dewetting of the SAMs were studied with a combination of in situ sum-frequency generation (SFG) and molecular dynamics (MD) simulations. Although SAM growth after deposition times >8 h reduces to nearly negligible values, the resultant ODPA SAMs in solution are still not in a well-ordered state with the alkyl chains in all-trans configurations. In fact, in situ SFG spectroscopy revealed a comparatively high concentration of gauche defects of the SAM in the ODPA 2-propanol solution even after a growth time of 16 h. Here, results of the MD simulations strongly suggest that defects can be caused by ODPA molecules which are not attached to the substrate but are incorporated into the SAM layer with the polar headgroup oriented into the 2-propanol solvent. This inverted adsorption geometry of additional ODPA molecules blocks adsorption sites and thus stabilizes the SAM without improving ordering to an extent that all molecules are in the all-trans configuration. While persistent in solution, the observed defects can be healed out when the SAMs are transferred from the solvent to a gas phase. During this process, a quasi-Langmuir-Blodgett transfer of molecules takes place which drives the SAM into a higher conformational state and significantly improves its quality.

Separation of nanoparticles: Filtration and scavenging from waste incineration plants - Förster, Henning; Thajudeen, Thaseem; Funk, Christine; Peukert, Wolfgang (Waste Management, 2016)
Increased amounts of nanoparticles are applied in products of everyday life and despite material recycling efforts, at the end of their life cycle they are fed into waste incineration plants. This raises the question on the fate of nanoparticles during incineration. In terms of environmental impact the key question is how well airborne nanoparticles are removed by separation processes on their way to the bag house filters and by the existing filtration process based on pulse-jet cleanable fibrous filter media. Therefore, we investigate the scavenging and the filtration of metal nanoparticles under typical conditions in waste incineration plants. The scavenging process is investigated by a population balance model while the nanoparticle filtration experiments are realized in a filter test rig. The results show that depending on the particle sizes, in some cases nearly 80% of the nanoparticles are scavenged by fly ash particles before they reach the bag house filter. For the filtration step dust cakes with a pressure drop of 500 Pa or higher are found to be very effective in preventing nanoparticles from penetrating through the filter. Thus, regeneration of the filter must be undertaken with care in order to guarantee highly efficient collection of particles even in the lower nanometre size regime.
Keywords: Filtration efficiency; Nanoparticle scavenging; Population balance modelling; Ultrafine particle emission; Waste incineration

Separation of the influences of material and machine in impact comminuton – Modelling with with population balances - Peukert, Wolfgang; Vogel, Lutz (Developments in Mineral Processing, 2002)
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.separa
Keywords: separation; modeling; simulation

Shape-anisotropic cobalt-germanium-borate glass flakes as novel Li-ion battery anodes - Esper, Julian Duane; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; de Ligny, Dominique; Bachmann, Julien; Peukert, Wolfgang; Romeis, Stefan (Powder Technology, 2020)
Novel CoO-Li2O-B2O3 and CoO-GeO2-Li2O-B2O3 flake-like glass particles for battery applications are produced by an innovative technique: Glasses from melt quenching are processed into micron-sized glass flakes in a stirred media mill. Processing under well-controlled conditions yields flake-like particles with high aspect ratios which are suitable for anodes in Lithium-ion batteries. Electrochemical characterization by cyclic voltammetry, electrochemical impedance spectroscopy, galvanostatic charge/discharge cycles and rate capability measurements indicates that the flakes show superior electrochemical properties compared to the bulk glass counterparts with a stable specific capacity of 620 mAh g−1 after 100 cycles. The majority of charge is stored by Li+ ion diffusion inside the material and impedance spectroscopy shows enhanced lithium ion diffusion capabilities of the flakes. The proposed fabrication process is performed under ambient conditions and is simple, cost-efficient, fully scalable and can be easily transferred to other glass compositions with electrochemically active metal oxide
Keywords: Anode; Particle design; Glasses; Shape-anisotropy; Lithium-ion battery

Shape Transformation Mechanism of Silver Nanorods in Aqueous Solution - Damm, Cornelia; Segets, Doris; Yang, Guang; Vieweg, Benito; Spiecker, Erdmann; Peukert, Wolfgang (Small, 2011)
The spontaneous shape transformation of silver nanorods with an initial length of several hundred nanometers towards spherical particle shapes in aqueous solution is investigated by means of scanning electron microscopy, UV–vis absorption spectroscopy, anodic stripping voltammetry, and high-resolution transmission electron microscopy (HRTEM). The consolidation of the results reveals an increase in the particle number density with time. Moreover, HRTEM image analysis along the cross section of the rods evidences the presence of fivefold twinning defects which extend along the whole rod length. According to the analytical model of Monk et al. this kind of rod structure is only thermodynamically stable if the rod length is below a critical value at a given diameter. The rods investigated in the present work do not fulfill the stability criterion as they exceed the critical length. Thus, the rods decay into smaller “nanobuns” and defective as well as defect-free spheres. A mechanism based on findings from the literature, HRTEM image analysis of former rods, transition states, and the final particle structures is proposed. The defects along the surface are seen as starting points for the dissolution of material, which is reintegrated into the solid phase by homogeneous as well as heterogeneous nucleation and growth.

Shedding light on the effective fluorophore structure of high fluorescence quantum yield carbon nanodots - Wang, Wenshuo; Wang, Bingzhe; Embrechts, Heidemarie; Damm, Cornelia; Cadranel, Alejandro; Strauß, Volker; Distaso, Monica; Hinterberger, Vanessa; Guldi, Dirk Michael; Peukert, Wolfgang (RSC Advances, 2017)
Carbon nanodots (CD) have great potential for imaging and sensing applications, due to their unique luminescence properties in combination with their low toxicity. Although CDs are currently the subject of intensive research activity, the exact structure of their effective fluorophore species has to be clarified because it can depend on the starting materials and reaction conditions. Most importantly, the limited photostability of some CDs presents an impediment to the much-needed breakthroughs required in the field. In this work, the photobleaching of CDs synthesized hydrothermally from citric acid and urea undervarious conditions is studied in detail. By visualizing changes in the absorption and fluorescence properties of CDs over time upon exposure to UV-light by means of in situ spectroscopic probes, we demonstrate a trade-off between high initial quantum yield and photostability. We found that the CDs consist of low-molecular weight fluorophores bound to extgreekp-conjugated domains (carbon core). In the case of CDs synthesized at higher reaction temperatures and/or for longer reaction times, lower initial quantum yields and higher photostability originate from partial conversion of the low-molecular weight fluorophores to extgreekp-conjugated domains during synthesis. Thus, the remaining surface bound fluorophores are bound to larger extgreekp-conjugated domains, which, in turn, enable dissipation of absorbed UV-energy and protection against photochemical damage. Reference experiments were performed with citrazinic acid – a pyridone-based structure – using ultrafast time-resolved spectroscopy, steady-state spectroscopy, and theoretical DFT simulations. We conclude that pyridone-like structures are most likely responsible for both the high quantum yields and the photobleaching of CDs.

Shedding light on the growth of gold nanoshells - Sauerbeck, Christian; Haderlein, Michael; Schürer, Benedikt; Braunschweig, Björn; Peukert, Wolfgang; Klupp Taylor, Robin (ACS nano, 2014)
Nanostructured particles containing noble metals can have highly tunable localized surface plasmon resonances and are therefore of particular interest for numerous applications. Nanoshells comprising a dielectric core and gold or silver shell are a widely researched systems because of the strong dependence of their optical properties on the ratio of core diameter to shell thickness. Although seeded-growth procedures have been developed to produce these particles, the many reported studies show significant variation in the nanoshell morphologies and hence optical properties. In order to establish processes that reproducibly synthesize nanoshells with high optical quality, it is necessary to develop techniques that monitor changes at the core particle surface during shell growth. For that purpose, we have carried out in situ nonlinear second-harmonic scattering (SHS) and linear vis-NIR extinction spectroscopy simultaneously during the seeded growth of gold nanoshells on silica core particles. Our SHS measurements show a striking variation in the nonlinear optical properties of the growing gold nanoshells. In comparison with linear optical measurements and with scanning electron microscopy (SEM) images made of gold nanoshells produced with varying shell completenesses, the SHS signal was observed to reach a peak intensity at a stage prior to shell closure. We attribute this high sensitivity of the SHS signal to the incomplete nanoshell surface morphology to the generation and subsequent degeneration of regions of electric field enhancement at gaps between isolated gold islands, which grow and coalesce. This conclusion is corroborated by finite-difference time-domain simulations of incomplete nanoshells. We suggest that the in situ analytical approach demonstrated here offers significant promise for future activities regarding the in-process optimization of the morphology and optical properties of metal nanoshells and other nanostructured plasmonic particles. © 2014 American Chemical Society.
Keywords: electric field enhancement; in situ vis-NIR spectroscopy; nanostructured particles; plasmonic particles; second-harmonic generation

Simple and Reliable Method for Studying the Adsorption Behavior of Aquivion lonomers on Carbon Black Surfaces - Damm, Cornelia; Thoma, Martin; Hoffmann, Eva-Maria; Sattes, Maria-Melanie; Segets, Doris; Peukert, Wolfgang; Lin, Wei (Langmuir, 2018)
A better understanding of the interactions of carbon black and perfluorinated sulfonic acid (PFSA) ionomer helps to improve the effectiveness of polymer electrolyte membrane fuel cells. We present a simple and fast method for quantitative PFSA ionomer analysis based on suspension density measurements. After validation of the reliability of our method by thermogravimetric analysis and isothermal titration calorimetry (ITC), we investigate the adsorption equilibrium of short-side-chain PFSA ionomers of different equivalent weights (EW) and polarities on carbon black. The measured adsorption isotherms exhibit a plateau in the ionomer surface concentration for ionomer equilibrium concentrations <= 2 g/L. In this concentration range, the adsorption isotherms are described by the Langmuir model, whereby the surface concentrations in the plateau region are between 0.041 and 0.070 g/g. The plateau value of the ionomer surface concentration increases with EW and therefore with decreasing number of side chains with terminal sulfonic acid group per ionomer molecule, while the amount of adsorbed sulfonic acid groups remains constant for all investigated ionomers, resulting in similar zeta-potentials and sedimentation stability of the suspensions. The free energies of adsorption Delta G calculated from the association constants of the adsorption isotherms agree well with Delta G values obtained by isothermal titration calorimetry (ITC) and thus validate the adsorption isotherm measurement method. From the values of adsorption enthalpy Delta H ((-7.3 +/- 0.8) kJ/mol) and entropy Delta S (ca. 100 J/(mol K)), which were extracted from ITC, we conclude that the ionomer adsorption on carbon black is a spontaneous physisorption process.
Keywords: nano; carbon; allotrope; black

Simulating grinding in impact mills - Separation of mill and material function - Peukert, Wolfgang; Vogel, Lutz; Sommer, Marc; Schäfer, Micheal; Grünwald, J (World Congress Particle Technology 4, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.simula

Simulation and Verification of Defect-Dominated Permeation Mechanisms in Multiple Structures of Inorganic and Polymeric Barrier Layers - Hanika, Markus; Langowski, Horst-Christian; Peukert, Wolfgang (Proceedings of the Society of Vacuum Coaters 46th Annual Technical Conference, 2003)
In flexible barrier materials, the required barrier properties are obtained via combinations of polymeric and inorganic layers. In standard configurations like common laminates, the barrier effect is achieved by the combined action of the inorganic layer together with the substrate and an additional polymeric top layer, whereas the inorganic layer alone would be no barrier at all. For higher barrier requirements, more complex systems are tailored, consisting of a sequence of polymeric layers (organic or inorganic-organic hybrid materials) and inorganic barrier layers. Their final functionality is given by the bulk permeability properties of the polymeric layers and their thickness and by the microscopic and macroscopic properties of the inorganic layers. In this paper, the defect structures of the inorganic layers - as assessed via different analytical methods - are used as basis for numerical simulations, for which always a defect dominated permeation mechanism was taken. The complexity of the layer structures is increased stepwise, from the known configurations of one inorganic layer on top of a substrate and one inorganic layer embedded between two different polymers up to a description of one polymeric layer of varying thickness between two inorganic layers and its extension to repeated sequences of this structure. The results demonstrate the importance of the inherent barrier properties of the polymeric interlayers as a scaling factor for the performance of multi layer stacks.<br
Keywords: Permeation barrier coatings; Polymer base coats; Pinholes/porosity; Polymer substrates; moisture permeation; oxygen permeation

Simulation of Moving Nano-Particles with the Lattice Boltzmann Method in 3D - Iglberger, Klaus; Thürey, Nils; Rüde, Ulrich; Peukert, Wolfgang; Schmid, Hans-Joachim (18th Symposium Simulationstechnique ASIM 2005 Proceedings, 2005)
We will present our simulation to predict the behavior of moving nano-particles in a flow using the Lattice Boltzmann method. Targeted applications for this simulation are the pre- diction of particle movement in shear flows for large agglomerates and possible break ups or structural changes within the particles. The focus for the implementation is a stable and correct simulation even for high Reynolds numbers. Therefore, the Lattice Boltzmann Method is extended by complex geometries for an improved particle boundary treatment (4) and the method of momentum exchange for the force interaction between the fluid and the particle (1). The Lattice Boltzmann sim- ulation system is coupled to a rigid-body physics engine to build a two-system simulation (3). We will show results of simulations with static particles, which show consistent drag forces in comparison with the analytical results (2). The influence of the domain and particle radius were investigated. Further results for moving particles agree with real world measurements and, where possible, with the analytical results. Furthermore, an outlook to future work will be given, which will focus on performance improvements by grid refinement and parallelization for large scale simulations. Larger sim- ulations will also oer the possibility to include multi body interactions with agglomerations and potentials.
UnivIS-Import:2015-04-16:Pub.2005.tech.IMMD.lsinfs.simula_87
Keywords: nanoparticle; agglomerate; simulation; lattice; boltzmann

Simulation of structure and mobility of aggregates formed by simultaneous coagulation, sintering and surface growth - Peukert, Wolfgang; Schmid, Hans-Joachim; Al Zaitone, Belal (Journal of Aerosol Science, 2009)
In this work, a new model for the simulation of nanostructured aggregates by simultaneous coagulation, sintering and surface growth is presented. Coagulation is treated as cluster-cluster agglomeration along the line connecting the center of mass of both agglomerates and is implemented using a Monte Carlo algorithm. Sintering is modeled as successive overlapping of spheres which cause reduction in the surface area based on a rate law for surface reduction. Surface growth is modeled as an increase in primary particle diameter, e.g. as a result of surface reactions. The evolved aggregates are analyzed by calculating their fractal dimension, radius of gyration, mobility diameter and mobility shape factor. It is found that the aggregates structure tends to be more compact when introducing the surface growth in shorter time comparing to the coagulation-sintering step only. Fractal dimension and the mobility shape factor of the resulting aggregates are correlated to an effective dimensionless time that combines the characteristic times of these three fundamental mechanisms. It is shown that the mobility diameter in the free molecular regime is not proportional to the radius of gyration. A power law relation that correlates the aggregates projected area and the equivalent number of primary particles is found to be in a very good agreement with estimates published in literature. © 2009 Elsevier Ltd. All rights reserved.
Keywords: Agglomeration; Fractal dimension; Mobility diameter; Nanostructure; Particle formation; Simulation; Sintering

Simulation of the hydrodynamic behaviour of aggregated particles - Peukert, Wolfgang; Binder, Christian; Thürey, Nils; Schmid, Hans-Joachim; Rüde, Ulrich (2006 AIChE Spring National Meeting - 5th World Congress on Particle Technology, 2006)
The drag force on aggregates and partially sintered agglomerates is assessed using different techniques. In the free molecular regime - most relevant for nanoscaled particles in air at ambient or lower pressures - it has been shown that the projected area is very well representing the drag force of aggregates. In the continuum regime however, the projected area is not suitable to get a unique correlation with the drag force. This has been shown by applying two different techniques, namely the Lattice-Boltzmann Method (LBM) and Accelerated Stokesian Dynamics (ASD) to study the drag of agglomerates. Both methods have been compared in terms of accuracy and computational effort. It is shown that they give comparable results if all numerical parameters are controlled carefully. LBM requires a much higher computational effort, however, in contrast to ASD it is able to simulate partially sintered agglomerates as well. The results show that even a very small amount of sintering leads to a significant reduction in the drag force. The variation in drag force for single aggregates at different orientations or for the orientation averaged drag force of different aggregates of the same size is examined and discussed in both regimes.
Keywords: Aggregate structure; Nanoparticles; Physical properties; Simulation

Simulation of the Hydrodynamic Drag of Aggregated Particles - Binder, Christian; Feichtinger, Christian; Schmid, Hans-Joachim; Thürey, Nils; Peukert, Wolfgang; Rüde, Ulrich (Journal of Colloid and Interface Science, 2006)
The drag force on aggregates and partially sintered agglomerates is assessed using the lattice Boltzmann method (LBM) and accelerated Stokesian dynamics (ASD). Both methods have been compared in terms of accuracy and computational effort. It is shown that they give comparable results if all numerical parameters are controlled carefully. LBM requires a much higher computational effort, however, in contrast to ASD it is able to simulate partially sintered agglomerates as well. The results show that even a very small amount of sintering leads to a significant reduction in the drag force. The analysis of the drag force on agglomerates as well as on aggregates shows that there is no simple geometric quantity which is uniquely related to the drag force. Moreover, there is a significant variation in drag force for single aggregates at different orientations or for the orientation averaged drag force of different aggregates of the same size. This is explained by the structural effects which may lead to a variation in the drag force up to ± 20 %. © 2006.
UnivIS-Import:2015-03-09:Pub.2006.tech.IMMD.lsinfs.simula_1
Keywords: Agglomerates; Aggregates; Drag force; Fractal clusters; Lattice Boltzmann method; Simulation; Stokesian dynamics

Simultaneous 3D observation of different kinetic subprocesses for precipitation in a T-mixer - Gradl, Johannes; Peukert, Wolfgang (Chemical Engineering Science, 2009)
A coupled direct numerical simulation (DNS)—population balance equation (PBE)–DLVO approach is presented to calculate the product properties of particles originating from precipitation in a T-mixer. A special focus is given to the coupling of different subprocesses such as mixing, nucleation, growth, stabilization and aggregation for a rapid precipitation process. Based on the predictive computation of the resulting particle size distributions (PSD) full 3D-field information of all transient parameters are accessible, e.g., supersaturations, nucleation rates, particle sizes and stabilities. By interpolating the kinetic data, relevant subprocesses can be visualized and studied separately in the mixer. The resulting PSDs are predicted for different conditions where aggregation can be neglected. For unstable conditions aggregation and transient stabilization effects are determined by the DLVO theory. The size of the particles, their surface potential and the ionic strength of the solution vary extensively during the solid formation process. The dynamic evolution of the particle stability leads to a better description of the PSD based on the DNS–PBE–DLVO approach for unstable conditions and allows to develop strategies how to better stabilize particles. This approach is verified for barium sulphate precipitation but can be transferred to any other ionic system for which the relevant material specific data are known.

Simultaneous Analysis of Hydrodynamic and Optical Properties Using Analytical Ultracentrifugation Equipped with Multiwavelength Detection - Peukert, Wolfgang; Walter, Johannes; Lin, Wei; Segets, Doris; Sherwood, Peter; Stafford, Walter (Analytical Chemistry, 2015)
Analytical ultracentrifugation (AUC) has proven to be a powerful tool for the study of particle size distributions, particle shapes, and interactions with high accuracy and unrevealed resolution. In this work we show how the analysis of sedimentation velocity data from the AUC equipped with a multiwavelength detector (MWL) can be used to gain an even deeper understanding of colloidal and macromolecular mixtures. New data evaluation routines have been integrated in the software SEDANAL to allow for the handling of MWL data. This opens up a variety of new possibilities because spectroscopic information becomes available for individual components in mixtures at the same time using MWL-AUC. For systems of known optical properties information on the hydrodynamic properties of the individual components in a mixture becomes accessible. For the first time, the determination of individual extinction spectra of components in mixtures is demonstrated via MWL evaluation of sedimentation velocity data. In our paper we first provide the informational background for the data analysis and expose the accessible parameters of our methodology. We further demonstrate the data evaluation by means of simulated data. Finally, we give two examples which are highly relevant in the field of nanotechnology using colored silica and gold nanoparticles of different size and extinction properties.
Keywords: analytical; ultracentrifugation; sedimentation; colloid; macromolecular; simulation

Simultaneous Identification of Spectral Properties and Sizes of Multiple Particles in Solution with Subnanometer Resolution - Peukert, Wolfgang; Karabudak, Engin; Brookes, Emre; Lesnyak, Vladimir; Gaponik, Nikolai; Eychmüller, Alexander; Walter, Johannes; Segets, Doris; Wohlleben, Wendel; Demeler, Borries; Cölfen, Helmut (Angewandte Chemie-International Edition, 2016)
We report an unsurpassed solution characterization technique based on analytical ultracentrifugation, which demonstrates exceptional potential for resolving particle sizes in solution with sub-nm resolution. We achieve this improvement in resolution by simultaneously measuring UV/Vis spectra while hydrodynamically separating individual components in the mixture. By equipping an analytical ultracentrifuge with a novel multi-wavelength detector, we are adding a new spectral discovery dimension to traditional hydrodynamic characterization, and amplify the information obtained by orders of magnitude. We demonstrate the power of this technique by characterizing unpurified CdTe nanoparticle samples, avoiding tedious and often impossible purification and fractionation of nanoparticles into apparently monodisperse fractions. With this approach, we have for the first time identified the pure spectral properties and band-gap positions of discrete species present in the CdTe mixture.
Keywords: analytical methods; colloids; nanoparticles

Single-Molecule Pycnometry and Shape Analysis of Ions in the Gas Phase - Lübbert, Christian; Supper, Malvina; Kaspereit, Malte; Walter, Johannes; Peukert, Wolfgang (Analytical Chemistry, 2023)
The analysis of ions and clusters by mobility-classified mass spectrometry provides information on the mobility of analytes in the drift gas and the analyte mass. Mass equivalent and mobility equivalent diameters of globular analytes, such as ions, poly(ethylene glycol) (PEG), and ionic liquid nanodroplets, can be correlated with good accuracy by the Stokes-Millikan mobility model. A prerequisite to such an analysis is, however, the assumption of a globular analyte shape, which then allows determination of material density for globular ions. We show that the analyte density can be evaluated with high precision, independent of any assumptions on the analyte shape, by careful analysis of analyte-PEG-cluster ions following the concept of classical pycnometry. In particular, the analyte is entrapped in a globular PEG-analyte droplet. Based on the now independently derived mobility diameter and volume equivalent diameter, it is possible to attribute two parameters, size and shape, to the analyte molecule. We demonstrate the approach for lysozyme, cyano-cobalamin (vitamin B12), and glucose, which cover two orders of magnitude in analyte mass (180···14 300 Da). The derived densities for these analytes are highly accurate, i.e., they deviate less than 1% from literature values. Our method can be applied to newly synthesized molecules, supramolecular assemblies, isolated biomolecules, and molecular clusters, where only minor amounts of materials are available. The obtained shape parameters of lysozyme and cyano-cobalamin agree well with the expected molecular shapes. Data evaluation relies only on locations of the species in the mass-mobility plane and is in principle independent of any mobility theory. Our approach is thus robust with respect to experimental uncertainties and produces identical results irrespective of the type of mobility classification and drift ga
Keywords: Enzymes; Ionic liquids; Mass spectrometry; Molecules; Polyethylene glycols; Synthesis (chemical); Analytes; Classifieds; Drift gas; Gas-phases; Liquid nanodroplets; Mobility equivalent diameter; Poly(ethylene glycol)(PEG); Pycnometry; Shape-analysis; Single molecule; Ions

Single-step aerosol synthesis of oxygen-deficient blue titania - Domaschke, Maximilian; Strunz, Lea; Peukert, Wolfgang (Chemical Engineering Science, 2019)
We present a novel approach for the single-step, continuous aerosol synthesis of blue, oxygen-deficient titania in a hot-wall reactor operated under reducing conditions by adding hydrogen. The precursor titanium(IV) tetraisopropoxide is evaporated in a bubbler and consecutively carried into the reactor by a nitrogen stream where it undergoes thermal decomposition. According to X-ray diffraction analysis, several reduced titania states, among them the Magneli phases Ti4O7 and Ti5O9, are formed via the intermediates anatase and rutile. By slight modifications in the reactor setup both nanoparticles in the size range from 20 to 50 nm with high surface area and well-defined spherical submicron particles of 100 to 160 nm diameter can be produced. In particular, crystallographically phase-pure Ti4O7 is formed at high reactor temperatures. The presented synthesis process is scalable and poses an attractive alternative for the multi-step synthesis of oxygen deficient titania nanoparticles that is currently done via batch-wise annealing. Such nanoparticles are attractive material in the field of photocatalysis. They can be used for both water splitting to produce hydrogen and the decomposition of organic pollutants. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-07-02

Singlet Fission for Photovoltaics with 130 % Injection Efficiency - Kunzmann, Andreas; Gruber, Marco; Casillas Pacheco, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2018)
A novel pentacene dimer (P2) and a structurally analogous monomer (P1) were synthesized for use in n-type dye-sensitized solar cells. In P2, the triplet excited states formed by the rapid, spin-allowed process singlet fission were expected to enable carrier multiplication in comparison to the slow, spin-forbidden intersystem crossing seen in P1. A meta-positioning of the two pentacenes and the carboxylate anchor were chosen in P2 to balance the intramolecular dynamics of singlet fission and electron injection. Electron injection from energetically low-lying triplet excited states of pentacene units necessitated the intrinsic and extrinsic lowering of the Fermi level of the semiconductor. Indium-zinc oxide in the presence of Li+ was found to be the optimum choice for the photoelectrodes. Efficient electron injection from the triplet excited states of P1 and P2 was found, with a carrier multiplication of nearly 130 %.
Keywords: pentacene sensitizers; singlet fission; dye-sensitized solar cells; transient absorption spectroscopy

Singulettspaltung für Photovoltaikanwendungen mit Injektionseffizienzen von bis zu 130 % - Kunzmann, Andreas; Gruber, Marco; Casillas, Ruben; Zirzlmeier, Johannes; Stanzel, Melanie; Peukert, Wolfgang; Tykwinski, Rik R.; Guldi, Dirk Michael (Angewandte Chemie, 2018)

Sintering kinetics and mechanism of vitreous nanoparticles - Kirchhof, Martin; Förster, Henning; Schmid, Hans-Joachim; Peukert, Wolfgang (Journal of Aerosol Science, 2012)
The sintering of vitreous nanoparticle doublets is investigated numerically by a volume of fluid method coupled to Hamaker summation and experimentally by a high-temperature sintering flow reactor as well as by doublet shape analysis in the transmission electron microscope. In particular, the characteristic differences between nanoparticulate and bulk sintering are studied. The sintering mechanism of vitreous nanoparticles is determined to be viscous flow with interparticle van der Waals interactions acting as additional driving force. The early stages of the nanoparticle sintering kinetics are inversely proportional to the square of the particle size, instead of an indirect proportionality to the first order of the particle size for the entire bulk process. The transition between nanoparticulate and bulk sintering is localised to primary particle diameters of approx. 200-300nm. © 2011 Elsevier Ltd.
Keywords: Nanoparticles; Silica; Sintering; Van Der Waals interactions; Viscous flow

SiO2–GeO2 Glass–Ceramic Flakes as an Anode Material for High-Performance Lithium-Ion Batteries - Esper, Julian Duane; Maußner, Felix; Romeis, Stefan; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; Bachmann, Julien; Peukert, Wolfgang (Energy Technology, 2022)
The preparation of a flake-like glass–ceramic anode material comprised of SiO2 and GeO2 for Li-ion batteries (LIBs) is demonstrated. The precursor glass material is prepared via a traditional melt quenching technique. Flake-like glass particles are obtained by compression in the liquid phase via ball milling. A subsequent heat treatment induces crystallization of GexSiyO6 domains inside the vitreous SiO2–GeO2 matrix. This novel glass-ceramic material is applied as an anode material for LIBs and shows a stable reversible capacity of 520 mAh g−1 at 0.2 C combined with good capacity retention of 87% after 100 cycles. This cycling stability can be attributed to the synergistic effects of having nanocrystalline domains embedded in the glass matrix: The open glass network can withstand the volume change and stress caused by the lithium insertion during cycling, while the nanocrystals act as active sites for the electrochemical conversion and alloying reactions. The glass–ceramic anode material exhibits superior electrochemical properties compared to its pure glass counterparts.
CRIS-Team Scopus Importer:2022-06-10
Keywords: anodes; flake-like particles; glass ceramics; lithium-ion batteries; shape-anisotropy; thermal annealing

Size and shape engineering of ZnO nanoparticles - Klupp Taylor, Robin; Voigt, Michael; Segets, Doris; Peukert, Wolfgang; Marczak, Renata (2008 AIChE Annual Meeting, 2008)
The investigation of ZnO nanoparticles is of great interest due to the wide range of potential applications for this material. Despite this, a thorough understanding of the optical, electronic and structural properties of ZnO nanoparticles with respect to their synthesis is still lacking. We tackled this problem by synthesizing ZnO nanoparticles with nanocrystal, nanorod and self-assembled aggregate form using ambient and hydrothermal wet chemical processes. Dynamic light scattering, absorption and emission spectroscopies, thermogravimetric analysis, X-ray powder diffraction, Fourier infrared spectroscopy as well as transmission and scanning electron microscopies were employed to characterize and compare the nanoparticles composition, their shape, size and crystallinity. By varying different parameters of the synthesis processes like precursors and their concentrations, solvent used, surfactant, temperature, and reaction time we were able to control the size and shape of the particles. In particular we noted the tendency of ZnO nanocrystals to self-assemble into dense structures which preserve the anisotropic crystal structure. Using surface-mediating polymers such as PVP, this self-organisation could be modified so as to produce nanostructures with a tunable porosity, with great potential for application.
Keywords: ZnO; nanoparticle; nanostructure; growth; crystal; self-assembly

Size effects in the elastic deformation behavior of metallic nanoparticles - Armstrong, Patrick; Peukert, Wolfgang (Journal of Nanoparticle Research, 2012)
In this work, the results of a series of molecular statics simulations to investigate the size dependence of the elastic properties of metallic nanoparticles are presented. The per-atom stiffness tensor was calculated from the derivative of the used embedded atom method potentials and, from it, lower order elastic parameters, such as the Young's modulus or the Poisson ratio. The Young's modulus decayed up to 30 % relative to the bulk values for 2.5 nm small particles, whereas the Poisson ratio showed an increase with decreasing particle size for most materials. Particles with a diameter of 30 nm approached the continuum values to around 1 %, marking the transition to continuum theory. The size-dependent Young's modulus and several other material properties can be described by a simple algebraic function of the number of atoms per particle. By plotting the radial distribution of the local Young's modulus within particles of different size, it is shown that only the outermost 2-3 atomic layers are responsible for the size-dependent change of elastic properties. Within these layers, the average atomic stiffness was found to decay linearly and independent of the particle siz
Keywords: Size effect; Elasticity; Molecular statics; Nanoparticles; Young's modulus

Size exclusion chromatography (SEC) - Peukert, Wolfgang; Kaspereit, Malte; Hofe, Thorsten; Gromotka, Lukas (Particle Separation Techniques, 2022)
Size exclusion chromatography (SEC) is a liquid phase chromatographic technique for separating molecules, proteins, macromolecules, and nanoparticles (below 100 nm) solely according to their hydrodynamic volume in solution. Classification depends on the size- and shape-dependent exclusion of components in the pores of the stationary phase material, that is, larger and less mobile components leave the column first. Ideally, the separation is purely driven by entropy, the absence of strong enthalpic interactions encompasses mild operating conditions. SEC is a standard method in polymer science and technology for the characterization of molecular weight distributions. SEC is also well established for preparative applications, for example, for the separation of proteins from aggregates in biotechnology. The size-dependent classification of nanoparticles is a promising new field of application.<br

Size specific energy (SSE) - Energy required to generate minus 75 micron material - Ballantyne, Grant; Peukert, Wolfgang; Powell, Malcolm (International Journal of Mineral Processing, 2015)
This paper explores the relationship between energy and the generation of minus 75 micron material. Rittinger's law of comminution states that the energy input is proportional to the generation of new surface area. An accurate and consistent measurement of surface area, applicable across multiple size ranges, is required to apply this practically. The amount of new - 75 μm material generated has previously been proposed as a proxy for surface area. This has been demonstrated to some extent on a range of different laboratory equipment, but not in a manner suited to equipment-independent ore characterisation. To this end the JK Rotary Breakage Tester (JKRBT) and Schönert breakage device have been used to measure the progressive production of fines from cumulative single impacts starting with 37.5 mm particles down to 250 μm. As per expectation, the generation of - 75 μm material was found to be proportional to the specific energy, but there was a secondary influence of size. A model was developed to describe the breakage and it was found that the standard t relationship could be used to effectively calculate the size specific energy. Measuring the intrinsic competence of an ore in this way can then be used to assess the energy efficiency of full-scale mills in relation to a lab scale test. It is envisaged that this relationship also has the potential to be used in the design of new comminution circuits. The methodology and the results from its application are presented for discussion and revie
Keywords: Benchmarking; Comminution; Efficiency; Energy

Smart silver nanoparticles from nanoreactors made by invertible polyesters - Kohut, Ananiy; Voronov, Andriy; Peukert, Wolfgang (2, 2007)
We developed a simple way to prepare smart silver nanoparticles that are well dispersible in both polar and nonpolar media. The synthesis was performed using solutions of an invertible amphiphilic polyester made via a polycondensation reaction of sebacic acid and poly(ethylene glycol). Reduction, formation of silver nanoparticles, and their stabilization occur in the polyester micellar domains (nanoreactors) that are formed in the reaction medium. Comparison of XRD experimental data shows that microphase separation of polyester units resulting in subsequent large range ordering occurs by change of the polyester concentration. The shape and size of the domains depend on the polyester concentration and the ratio between the lipophilic and hydrophilic constituents in the macromolecule as well as on solvent (reaction medium) polarit
Keywords: Smart nanoparticles; Polymeric nanoreactors

Solvent effects of zinc sulfide quantum dots classified by size selective precipitation - Mori, Y.; Yamamoto, K.; Segets, Doris; Peukert, Wolfgang; Tuchiya, K. (22nd International Congress of Chemical and Process Engineering (CHISA 2016) and 19th Conference on Process Integration, Modelling and Optimisation for Energy Saving and Pollution Reduction (PRES 2016), 2016)

Spatially resolved flame zone classification of a flame spray nanoparticle synthesis process by combining different optical techniques - Kilian, Daniel; Engel, Sascha; Borsdorf, B.; Gao, Yi; Kögler, Andreas; Kobler, S.; Seeger, Thomas; Will, Stefan; Leipertz, Alfred; Peukert, Wolfgang (Journal of Aerosol Science, 2014)
Flame spray synthesis of silica nanoparticles is characterized by a set of complementary optical techniques. By means of laser-sheet based Mie scattering imaging, 2D-chemiluminescence imaging and coherent anti-Stokes Raman spectroscopy (CARS) local information on spatial droplet distribution, combustion zone, nucleation zone and temperature in the flame could be obtained. In addition, the outcomes from optical metrology are validated by thermophoretic sampling at different flame heights and the synthesized powders were analyzed by N2 gas sorption. By comparing these results the flame can be quantitatively classified into three distinct zones: (i) the droplet zone where precursor atomization and evaporation take place, (ii) the nucleation zone indicated by SiO*/Si* radicals as a preliminary species before SiO2 particle formation and (iii) the sintering zone characterized by the highest temperatures in flame. In addition the spatial spreading of the nucleation zone as a function of precursor concentration is investigated. Theoretical calculations and experimental results show an extended nucleation regime for the lowest precursor concentration compared to higher concentrations. Although this study is performed with hexamethyldisiloxane (HMDS) precursor to synthesize silica nanoparticles as a model system, dimensionless analysis shows that the results, concerning the spray formation, can be transferred to the synthesis of other materials as well.

Special Issue of Core-to-Core Young Researchers Meeting 2008 Preface - Peukert, Wolfgang; Higashitani, Ko; Marczak, Renata (Advanced Powder Technology, 2010)

Specific effects of Ca2+ ions and molecular structure of β-lactoglobulin interfacial layers that drive macroscopic foam stability - Braunschweig, Björn; Schulze-Zachau, Felix; Nagel, Eva; Engelhardt, Kathrin; Stoyanov, Stefan; Gochev, Georgi; Khristov, Khr.; Mileva, Elena; Exerowa, Dotchi; Miller, Reinhard; Peukert, Wolfgang (Soft Matter, 2016)
β-Lactoglobulin (BLG) adsorption layers at air–water interfaces were studied in situ with vibrational sum-frequency generation (SFG), tensiometry, surface dilatational rheology and ellipsometry as a function of bulk Ca2+ concentration. The relation between the interfacial molecular structure of adsorbed BLG and the interactions with the supporting electrolyte is additionally addressed on higher length scales along the foam hierarchy – from the ubiquitous air–water interface through thin foam films to macroscopic foam. For concentrations <1 mM, a strong decrease in SFG intensity from O–H stretching bands and a slight increase in layer thickness and surface pressure are observed. A further increase in Ca2+ concentrations above 1 mM causes an apparent change in the polarity of aromatic C–H stretching vibrations from interfacial BLG which we associate to a charge reversal at the interface. Foam film measurements show formation of common black films at Ca2+ concentrations above 1 mM due to considerable decrease of the stabilizing electrostatic disjoining pressure. These observations also correlate with a minimum in macroscopic foam stability. For concentrations >30 mM Ca2+, micrographs of foam films show clear signatures of aggregates which tend to increase the stability of foam films. Here, the interfacial layers have a higher surface dilatational elasticity. In fact, macroscopic foams formed from BLG dilutions with high Ca2+ concentrations where aggregates and interfacial layers with higher elasticity are found, showed the highest stability with much smaller bubble size

Specific Properties of Nanoparticles - Peukert, Wolfgang; Walter, Johannes (Powder Technology Handbook, Fourth Edition, 2019)

Spectra library: An assumption-free in situ method to access the kinetics of catechols binding to colloidal ZnO quantum dots - Lin, Wei; Haderlein, Michael; Walter, Johannes; Peukert, Wolfgang; Segets, Doris (Angewandte Chemie International Edition, 2016)
Assumption-free and in situ resolving of the kinetics of ligand binding to colloidal nanoparticles (NPs) with high time resolution is still a challenge in NP research. A unique concept of using spectra library and stopped-flow together with a "search best-match" Matlab algorithm to access the kinetics of ligand binding in colloidal systems is reported. Instead of deconvoluting superimposed spectra using assumptions, species absorbance contributions (ligand@ZnO NPs and ligand in solution) are obtained by offline experiments. Therefrom, a library of well-defined targets with known ligand distribution between particle surface and solution is created. Finally, the evolution of bound ligand is derived by comparing in situ spectra recorded by stopped-flow and the library spectra with the algorithm. Our concept is a widely applicable strategy for kinetic studies of ligand adsorption to colloidal NPs and a big step towards deep understanding of surface functionalization kinetics. Well-established libraries of target spectra that are derived by means of careful offline analysis and identification of equilibrium data within larger kinetic datasets can be used for any particle-ligand system. Kinetics of ligand binding to nanoparticles can be derived free of assumption, in situ, and with high time resolution.
Keywords: colloids; kinetics; ligand exchange; nanoparticles; surface analysis

Spectroscopy of Electrified Interfaces with Broadband Sum Frequency Generation: From Electrocatalysis to Protein Foams - Braunschweig, Björn; Mukherjee, Prabuddha; Kutz, Robert; Rumpel, Armin; Engelhardt, Kathrin; Peukert, Wolfgang; Dlott, Dana; Wieckowski, Andrzej (Vibrational Spectroscopy at Electrified Interfaces, 2013)
This chapter focuses on the application of vibrational sum frequency generation (SFG) spectroscopy to study the molecular structure of electrode‐electrolyte and electrified liquid‐gas interfaces. Vibrational SFG is inherently interface specific because a second‐order process such as SFG is not allowed in the bulk of materials with inversion symmetry. The development of direct ethanol fuel cells demands an in‐depth understanding of ethanol's electrooxidation reactions. With recent advances in the practical design of alkaline fuel cells, a thorough understanding of the ethanol electrooxidation mechanism in alkaline media is now more important than ever. The chapter provides novel insights into this mechanism by examining new data on surface‐adsorbed reaction intermediates at fuel cell relevant conditions. Foams are materials of particular importance since they have a broad range of applications such as metal foams for light‐weight structures, polymer foams for thermal insulation, as well as in textured food product
Keywords: Electrooxidation reactions; Ethanol fuel cells; Electrified interfaces; Electrocatalysis; Vibrational sum frequency generation (SFG); Protein foams; Spectroscopy

Spherical Polybutylene Terephtalate (PBT)-Polycarbonate (PC) Blend Particles by Mechanical Alloying and Thermal Rounding - Dechet, Maximilian; Gomez Bonilla, Juan Sebastian; Lanzl, Lydia; Drummer, Dietmar; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2018)
In this study, the feasibility of co-grinding and the subsequent thermal rounding to produce spherical polymer blend particles for selective laser sintering (SLS) is demonstrated for polybutylene terephthalate (PBT) and polycarbonate (PC). The polymers are jointly comminuted in a planetary ball mill, and the obtained product particles are rounded in a heated downer reactor. The size distribution of PBT-PC composite particles is characterized with laser diffraction particle sizing, while the shape and morphology are investigated via scanning electron microscopy (SEM). A thorough investigation and characterization of the polymer intermixing in single particles is achieved via staining techniques and Raman microscopy. Furthermore, polarized light microscopy on thin film cuts enables the visualization of polymer mixing inside the particles. Trans-esterification between PBT and PC during the process steps is investigated via vibrational spectroscopy and differential scanning calorimetry (DSC). In this way, a new process route for the production of novel polymer blend particle systems for SLS is developed and carefully analyzed.
Keywords: polybutylene terephthalate (PBT); polycarbonate (PC); polymer blend particles; spheroidization; additive manufacturing; Raman microscopy; SEM staining; trans-esterification

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Stabilization mechanism of ZnO quantum dots - Peukert, Wolfgang; Marczak, Renata; Schäfer, Stefan; Segets, Doris (Nanotechnology 2010: Advanced Materials, CNTs, Particles, Films and Composites - 2010 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2010, 2010)
The current work addresses the understanding of the stabilization of small ZnO quantum dots in ethanolic suspension. Thereby different degrees of purification were investigated. The results revealed that not only the well-known ζ-potential as a representative for the surface charge determines the colloidal stability but also the surface coverage of acetate groups bound to the particle surface. Those acetate groups act as molecular spacers between the nanoparticles and prevent agglomeration. Regarding DLVO-calculations using a core-shell model, not only the height of the maximum but also the depth of the primary minimum has to be considered to see if a colloidal suspension is stable or not.
Keywords: Core-shell model; Purification; Quantum dot; Stability; ZnO

Stabilization of carbon black particles with Cetyltrimethylammoniumbromide in aqueous media - Eisermann, Claudia; Damm, Cornelia; Winzer, Bettina; Peukert, Wolfgang (Powder Technology, 2014)
The stabilization mechanism of aqueous carbon black suspensions by Cetyltrimethylammoniumbromide (CTAB) is studied in this paper. The adsorption of the surfactant CTAB on the carbon black particles was investigated on dried samples by thermogravimetric analyses (TGA), nitrogen adsorption and attenuated total reflection Fourier transformation infrared spectroscopy (ATR-FTIR) as well as in suspension by zeta potential measurements and atomic force microscopy. The particles are stabilized by an adsorbed CTAB monolayer as can be concluded from the results of TGA and of AFM investigations using a liquid cell. Extended DLVO calculations including the steric contribution of CTAB reveal that carbon particles with an adsorbed monolayer of CTAB exhibit sufficient colloidal stability. This result is in qualitative agreement with the experimental results. © 2013 Elsevier B.V.
Keywords: Carbon black; CTAB adsorption; Dispersion; DLVO calculations; Electrosteric stabilization

Structural dependent drag force and orientation prediction for small fractal aggregates - Binder, Christian; Hartig, Martin Andreas Johannes; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2009)
Aggregates settle in viscous fluids in specific directions depending on their morphology. We investigated the settling behavior of fractal aggregates with D = 1.85 in fluids using the Accelerated Stokesian Dynamics method. The results have been compared with experimental data. A simple equation is proposed which gives the drag force in dependence on the radius of gyration r, the projection area A and the aggregate orientation during settling. This equation reproduces the data from ASD within ± 10 % for Re <1. Additionally, a new algorithm has been developed which allows a prediction of the orientation of such fractal aggregates provided that they have time enough to orient in the fluid. Moreover, the drag force acting on them can be predicted in a narrow range (maximum error 15%). This algorithm allows a very fast evaluation of the orienting behavior with small deviations. © 2008 Elsevier Inc. All rights reserved.
Keywords: Aggregate behavior; Drag force; Fractal aggregates; Hydrodynamics; Stokesian Dynamics

Structural factors controlling size reduction of graphene oxide in liquid processing - Nacken, Thomas; Halbig, Christian E.; Wawra, Simon; Damm, Cornelia; Romeis, Stefan; Walter, Johannes; Tehrani, Mohammad J.; Hu, Yichen; Ishii, Yoshitaka; Eigler, Siegfried; Peukert, Wolfgang (Carbon, 2017)
Graphene oxide materials can be prepared in manifold synthesis approaches and allow for further post-functionalization to adopt the properties of the desired application. Small sized sheets with lateral dimensions on the 100 nm scale are e.g. beneficial for cell applications. Breakage of sheets by liquid phase processing is an ideal way to generate such nano-sized sheets. However, until now it is unknown how functionalization influences the breakage behavior. We have chosen single layered oxo-functionalized graphene (oxo-G) derivatives with lattice defects < 1% to evaluate their size reduction rate upon ultrasonication of flakes with respect to the type and degree of functionalization of the graphene sheets. Lateral dimensions of the processed sheets were quantitatively determined in solution by analytical ultracentrifugation. The highest size reduction rate is observed for pristine oxo-G, which bears the highest degree of functionalization of around 60% and the negatively charged organosulfate group. Partial hydrolysis of organosulfate, or conversion of surface-functional groups to hydroxyl-groups in majority or partial defunctionalization lead to size-reduction rates which are up to 25% lower in comparison with the initial oxo-G. Moreover, the size reduction rate can be correlated in first approximation also with UV–vis spectroscopy.

Structural influence on the drag of fractal aggregates - Peukert, Wolfgang; Binder, Christian (The 2007 Annual Meeting Salt Lake City, UT, 2007)
Aggregates typically formed in aerosol processes have a fractal dimension of Df=1.85. These aggregates suspended in a fluid flow have a behavior dependent on their structure, very different from the behaivor of a volume equivalent sphere in a fluid. The drag is considerably changing with increasing particle number and the settling behavior changes too, especially when the aggregates have enough time to relax into a quasi-equilibrium state and follow the streamlines. Simulation of the settling of such aggregates consisting of equally sized spheres generated by a Monte Carlo method using diffusion limited cluster-cluster aggregation has been performed on the basis of the Stokesian Dynamics method developed by Bossis and Brady, yielding approximations of the drag force in dependency on the aggregate number and the projected area. The dependency of the settling velocity and the drag on the structure of random aggregates will be shown by correlations with parameters characterizing the morphology of each aggregate.
Keywords: monte; carlo; stokesian; simulation; drag; settling; particle; aerosol; aggregate

Structure and adsorption behavior of high hydrostatic pressure-treated β-lactoglobulin - Kieserling, Helena; Giefer, Patrick; Uttinger, Maximilian; Lautenbach, Vanessa; Nguyen, Thu; Sevenich, Robert; Lübbert, Christian; Rauh, Cornelia; Peukert, Wolfgang; Fritsching, Udo; Drusch, Stephan; Maria Wagemans, Anja (Journal of Colloid and Interface Science, 2021)
Hypothesis: High hydrostatic pressure treatment causes structural changes in interfacial-active β-lactoglobulin (β-lg). We hypothesized that the pressure-induced structural changes affect the intra- and intermolecular interactions which determine the interfacial activity of β-lg. The conducted experimental and numerical investigations could contribute to the mechanistic understanding of the adsorption behavior of proteins in food-related emulsions. Experiments: We treated β-lg in water at pH 7 with high hydrostatic pressures up to 600 MPa for 10 min at 20 °C. The secondary structure was characterized with Fourier-transform infrared spectroscopy (FTIR) and circular dichroism (CD), the surface hydrophobicity and charge with fluorescence-spectroscopy and ζ-potential, and the quaternary structure with membrane-osmometry, analytical ultracentrifugation (AUC) and mass spectrometry (MS). Experimental analyses were supported through molecular dynamic (MD) simulations. The adsorption behavior was investigated with pendant drop analysis. Findings: MD simulation revealed a pressure-induced molten globule state of β-lg, confirmed by an unfolding of β-sheets with FTIR, a stabilization of α-helices with CD and loss in tertiary structure induced by an increase in surface hydrophobicity. Membrane-osmometry, AUC and MS indicated the formation of non-covalently linked dimers that migrated slower through the water phase, adsorbed more quickly due to hydrophobic interactions with the oil, and lowered the interfacial tension more strongly than reference β-lg.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Adsorption rate; High pressure processing; Lag time; Molecular dynamic simulation; Oil/water-interface; Pendant drop; Protein structure analysis

Structure and dynamics of interfacial peptides and proteins from vibrational sum-frequency generation spectroscopy - Hosseinpour, Saman; Roeters, Steven; Bonn, Mihscha; Peukert, Wolfgang; Woutersen, Sander; Weidner, Tobias (Chemical Reviews, 2020)
Proteins at interfaces play an important role in cell biology, immunology, bioengineering, and biomimetic material design. Many biological processes are based on interfacial protein action, ranging from cellular communication to immune responses and the protein-driven mineralization of bone. Despite the importance of interfacial proteins, comparatively little is known about their structure. The standard methods for studying crystalline or solution-phase proteins (X-ray diffraction and NMR) are not well suited for studying proteins at interfaces, and for these proteins, we still lack a corresponding technique that can provide the same level of structural resolutions. This is not surprising in view of the challenges involved in probing the structure of proteins within monomolecular films assembled at a very thin interface in situ. Vibrational sum-frequency generation (SFG) spectroscopy has the potential to overcome this ‘resolution gap’ and investigate the structure and dynamics of proteins at interfaces at the molecular level and with sub-picosecond time resolution. While SFG studies were initially limited to simple model peptides, the past decade has seen a dramatic advancement of experimental techniques and data analysis methods, which has made it possible to also study interfacial proteins and their folding, binding, orientation, hydration, and dynamics. In this review, we first explain the principles of protein SFG and the experimental and theoretical methods to measure and analyze protein SFG spectra. Then we give an extensive overview of the interfacial proteins studied thus far with SFG. We highlight representative examples to demonstrate recent advances in probing the structure of proteins at the interfaces of liquids, membranes, minerals, and synthetic materials.<br
Keywords: Biomimetic materials; Biomimetics; Bone; Cytology; Dynamics; Interferometry; Membranes; Nuclear magnetic resonance spectroscopy; PeptidesSurface chemistry; Biological process; Data analysis methods; Experimental techniques; Molecular levels; Structure and dynamics; Synthetic materialsTheoretical methods; Vibrational sum-frequency generations; Interfaces (materials); Liquid-Air Interface; Vibrational Spectrum; Heterodyne

Structuring of surfaces with the aid of polymer stamping structures - Peukert, Wolfgang; Winzer, Bettina (Chemie Ingenieur Technik, 2006)
Oberflächen, die hinsichtlich der Benetzungseigenschaften über Microcontact-Printing vorstrukturiert sind, können in weiteren Experimenten zur geordneten Anlagerung von verschiedensten kolloidalen Partikeln eingesetzt werden. Bei entsprechender Wahl der Stabilitätsbedingungen in der Lösung, der Partikelkonzentration und der Trocknungsbedingungen des Films erhält man geordnete Strukturen von Mikro- und Nanopartikeln auf lokal scharf abgegrenzten Oberflächenbereichen.
Keywords: oberfläche; nanostruktur; benetzung; microcontact; trocknung

Study of amphiphilic polyester micelles by hyper-rayleigh scattering: Invertibility and phase transfer - Peukert, Wolfgang; Martinez Tomalino, Lars-Owe; Voronov, Andriy; Kohut, Ananiy (Journal of Physical Chemistry B, 2008)
For the first time, hyper-Rayleigh scattering (HRS) of invertible polymeric micellar structures has been measured. HRS measurements on amphophilic invertible polyesters with alternating hydrophilic and hydrophobic fragments were carried out in solvents of differing polarity. The observed strong variation of the HRS signals is attributed to the switching behavior of the polyester micelles in the different solvents. The hyperpolarizabilities and the size of the micelles increased with decreasing polarity of the solvent. Observing the dynamics of the solubilization of an insoluble dye (malachite green) by the invertible polyester in toluene confirmed the possibility to reveal conformational changes in polyester macromolecules by HRS. In contrast to UV measurements which showed a continuous increase in absorbance and indicated overall solubilization of the dye, the HRS signals decreased after approaching a maximum value. The decrease of the HRS signals is attributed to the change of dye molecules' orientation within the micelles due to the change of polymeric conformation in toluene. The results have shown that HRS is sensitive to reorientation and ordering of the macromolecules and might become a powerful tool for studying polymer micellar structures as well as phase transfer processes at the nanoscale. © 2008 American Chemical Society.
Keywords: rayleigh; scattering; polymer; structure; polarizability; hydrophilic; hydrophobic

Study of particle synthesis in a low pressure plasma reactor using time resolved laser induced annealing technique (TIRE-LII) - Peukert, Wolfgang; Leipertz, Alfred; Sommer, Roland; Artelt, Christian (Chemie Ingenieur Technik, 2005)
Bei der Partikelsynthese in gepulsten, d. h. äußerst kurzzeitigen Plasmen stellt die Steuerung von Produkteigenschaften mit Hilfe von Prozessparametern einen sehr wichtigen Aspekt dar. Um deren Einfluss bei der Rußsynthese unter Niederdruck auf die Bildungs und Wachstumskinetik besser verstehen und kontrollieren zu können, ist es notwendig, charakteristische Teilcheneigenschaften wie die Primärpartikelgröûe online und in situ zu bestimmen. Eine hierfür geeignete Messmethode stellt prinzipiell die zeitaufgelöste laserinduzierte Glühtechnik (TIRE-LII) dar, deren Anwendbarkeit zur Ruûcharakterisierung an groûtechnischen Produktionsreaktoren unter Atmosphärendruck bereits in den vergangenen Jahren erfolgreich aufgezeigt werden konnte [1]. Bei der laserinduzierten Glühtechnik werden die Teilchen durch einen hochenergetischen Laserpuls bis auf annähernd Sublimationstemperatur aufgeheizt, anschlieûend werden deren spektral und zeitlich aufgelöste Temperatur- bzw. Signalverläufe analysiert. Unter Atmosphärendruck stellt dabei die Wärmeleitung an das umgebende Gas den dominierenden Energieabgabemechanismus zu späteren Zeitpunkten nach dem Laserpuls dar. Deshalb kühlen die Teilchen aufgrund ihrer spezifischen Oberfläche unterschiedlich schnell ab, was sich direkt im Signalverlauf widerspiegelt. Um die Messtechnik zur Bestimmung der Partikelgröûe auch unter Niederdruck einzusetzen, ist eine Modifizierung und experimentelle Validierung des zugrunde liegenden LII-Modells für freie Molekülbewegung notwendig. Bei der experimentellen Realisierung wurde als Anregungsquelle ein gepulster Nd:YAG-Laser eingesetzt und die dadurch induzierte  Inkandeszenz mittels entsprechender Detektionsoptik und schnellem Photomultiplier punktuell erfasst. Zur Analyse der Partikelbildung wurden Untersuchungen für verschiedene Plasmaleistungen, Precursorkonzentrationen und Umgebungsdrücke durchgeführt. Auûerdem konnte der Einfluss von unterschiedlichen Inertgasen bei Unterdruck betrachtet werden.
Keywords: Laser; Glühtechnik; Pplasma; Partikel; Niederdruck

Supported liquid metals - A new class of robust dehydrogenation catalysts - Taccardi, Nicola; Grabau, Mathias; Debuschewltz, Jonas; Distaso, Monica; Brandl, Marco; Hock, Rainer; Maier, Florian; Papp, Christian; Erhard, Jannis; Neiß, Christian; Peukert, Wolfgang; Görling, Andreas; et al. (12th Natural Gas Conversion Symposium 2019, 2019)
CRIS-Team Scopus Importer:2019-12-10

Surface activity of new invertible amphiphilic polyesters based on poly(ethylene glycol) and aliphatic dicarboxylic acids - Voronov, Andriy; Vasylyev, Serhiy; Kohut, Ananiy; Peukert, Wolfgang (Journal of Colloid and Interface Science, 2008)
The surface active properties of aqueous solutions of invertible amphiphilic alternated polyesters differing by hydrophilic-lipophilic balance (HLB) and molecular weight have been determined over the wide concentration range. The polyesters are based on poly(ethylene glycol) (PEG) of two molecular weights and aliphatic dicarboxylic acids (decanedioic and dodecanedioic). The surface activity of the polyesters and their ability to form micellar assemblies (which was recently shown for organic solvents) has been confirmed in water. The central role of the balance of hydrophilic to hydrophobic groups ratio in the formation of polymeric arrangements having hydrophobic pockets and external hydrophilic shell has been shown. The effect of molecular weight has been found considerable as well. Two changes in slope have been observed for the more hydrophobic polyesters in the surface tension vs log concentration curve. The change at low concentration is believed to originate from the formation of polyester assemblies with a hydrophobic interior and hydrophilic exterior due to the interaction of hydrophobic fragments and macromolecular flexibility. The higher concentration region exhibits behavior consistent with a cmc, which was confirmed by additional dye solubilization experiments. Molecular structure of the polyester micelles is determined by the solubilization of a solvatochromic dye. The experiment confirmed that micellization of polyesters is accompanied by the association of more hydrophobic (aliphatic) constituents forming the micelle interior. The hydrophilic fragments (ethylene oxide groups) are involved in the formation of micelle exterior. © 2008 Elsevier Inc. All rights reserve
Keywords: Assemblies with a hydrophobic interior and hydrophilic exterior; Hydrophobic effect; Invertible amphiphilic polyesters

Surface Charging and Interfacial Water Structure of Amphoteric Colloidal Particles - Peukert, Wolfgang; Braunschweig, Björn; Sauerbeck, Christian (Journal of Physical Chemistry C, 2014)
Colloidal stability and adsorption processes at particle surfaces are controlled by the generation of surface charge and the molecular structure of the resulting electrical double layers. We have applied second-harmonic light scattering (SHS) to address doublelayer charging and the orientation of water molecules at surfaces of amphoteric particles in unprecedented detail. For that purpose we have performed the first SHS experiments of neat polystyrene particles with a mixture of sulfate (R−O−SO3-) and amino (R-NH2) functional groups. Changing the pH has a dramatic effect on the surface potential which can be tuned from positive to negative values and has allowed us to record changes in SHS signal while the isoelectric point of the particles is being crossed. The SHS signal is a function of two contributions which are directly related to the first molecular layer, its orientation, and to a second electric field induced contribution of the unidirectional field within the interfacial electric double layer. Through additional charge screening experiments we measured the surface charge density for positively as well as for negatively charged particle surfaces and confirmed the isoelectric point, where an increase in ionic strength had little effect on the SHS intensity. Furthermore, we have determined the net orientation of water molecules directly adsorbed to the particle surface from pH-dependent changes in the relative phase of the two SHS contributions.
Keywords: colloid; adsorption; particle; surface; charge; electric; ionic; strength; double; layer

Surface functionalization and electronic interactions of ZnO nanorods with a porphyrin derivative - Klaumünzer, Martin; Kahnt, Axel; Burger, Alexandra; Mackovic, Mirza; Muenzel, Corinna; Srikantharajah, Rubitha; Spiecker, Erdmann; Hirsch, Andreas; Peukert, Wolfgang; Guldi, Dirk Michael (ACS Applied Materials and Interfaces, 2014)
To optimize electron transfer and optoelectronic properties in nanoparticulate thin films for electronics we show the surface functionalization of ZnO nanorods by means of replacing surface active 2-[2-(2-methoxyethoxy) ethoxy]acetic acid (TODA) by a redoxactive organic component, that is, 5,10,15,20-(phenoxyacetat)-porphyrin bearing four carboxylic acids as possible ZnO anchors. Microscopy-transmission electron microscopy-And spectroscopy-optical spectroscopy-verifies the successful and homogenous integration of the porphyrin onto the surface of ZnO nanorods, a process that is facilitated by the four anchoring groups. Photophysical investigations based on emission and absorption spectroscopy prompt to distinct electronic interactions between ZnO nanorods and the porphyrins. Consequently, we performed further photophysical studies flanked by pulse radiolysis assays to corroborate the nature of the electronic interactions. © 2014 American Chemical Society.

Surface functionalization of ZnO nanorods with C60 derivatives carrying phosphonic acid functionalities - Voigt, Michael; Klaumünzer, Martin; Ebel, Alexander; Werner, Fabian; Yang, Guang; Marczak, Renata; Spiecker, Erdmann; Guldi, Dirk Michael; Hirsch, Andreas; Peukert, Wolfgang (Journal of Physical Chemistry C, 2011)
ZnO with its wide band gap (3.37 eV) emerged as a promising semiconductor material for applications in the fields of printable and flexible electronics such as field effect transistors, etc. The fact that contacts at particle/particle interfaces exert a limiting impact on device performances motivates research on aligning the electronic levels at particle/particle interfaces. To this end, we focus in the present study on the surface functionalization of ZnO nanorods by a series of C derivatives. The latter share in common (i) a phosphonic acid as an anchor to ZnO, (ii) an alkyl chain as a flexible spacer, and (iii) a C as the headgroup. To shed light onto the electronic interactions between ZnO and C, we vary the alkyl chain length from n = 3 to n = 18. HRTEM and EELS prove the successful surface functionalization. Fundamental to this work are steady state absorption and photoluminescence measurements, which confirm the presence of appreciable electronic couplings between ZnO nanorods and C. Especially the photoluminescence measurements are important since they provide strong support for the dependence between spacer length and strength of electronic communication. In particular, a blue-shift of the ZnO free exciton emission band amounting to as much as 50 meV is observed with a decrease in spacer length. Furthermore, time-resolved absorption measurements corroborate ultrafast charge injection - facilitated by strong coupling - from the photoexcited ZnO nanorods to C. © 2011 American Chemical Society.
Keywords: Functionalization; Oxides; Reaction products; Organophosphorus compounds; Nanorods

Surface Modification of ZnO Nanorods with Hamilton Receptors - Hirsch, Andreas; Peukert, Wolfgang; Zeininger, Lukas; Klaumünzer, Martin (International Journal of Molecular Sciences, 2015)
A new prototype of a Hamilton receptor suitable for the functionalization of inorganic nanoparticles was synthesized and characterized. The hydrogen bonding receptor was coupled to a catechol moiety, which served as anchor group for the functionalization of metal oxides, in particular zinc oxide. Synthesized zinc oxide nanorods [ZnO] were used for surface functionalization. The wet-chemical functionalization procedure towards monolayer-grafted particles [ZnO-HR] is described and a detailed characterization study is presented. In addition, the detection of specific cyanurate molecules is demonstrated. The hybrid structures [ZnO-HR-CA] were stable towards agglomeration and exhibited enhanced dispersability in apolar solvents. This observation, in combination with several spectroscopic experiments gave evidence of the highly directional supramolecular recognition at the surface of nanoparticles.
Keywords: nanorod; functional; particle; ZnO; zinc; oxide; monolayer; stabilization

Suspension- and powder-based derivation of Hansen dispersibility parameters for zinc oxide quantum dots - Süß, Sebastian; Lin, Wei; Getmanenko, Olga; Pflug, Lukas; Sobisch, Titus; Peukert, Wolfgang; Lerche, Dietmar; Segets, Doris (Particuology, 2019)
For most particle-based applications, formulation in the liquid phase is a decisive step, and thus, particle interactions and stability in liquid media are of major importance. The concept of Hansen solubility parameters (HSP) was initially invented to describe the interactions of (polymer) molecules and their solubility in different liquids and is increasingly being used in particle technology to describe dispersibility. Because dispersions are not thermodynamically stable, the term Hansen dispersibility parameters (HDP) is used instead of HSP (Süß, Sobisch, Peukert, Lerche, & Segets, 2018). Herein, we extend a previously developed standardized and non-subjective method for determination of Hansen parameters based on analytical centrifugation to the important class of quantum materials. As a technically relevant model system, zinc oxide quantum dots (QDs) were used to transfer our methodology to nanoparticles (NPs) with sizes below 10 nm. The results obtained using the standard procedure starting from a dried powder were compared with those obtained through redispersion from the wet sediment produced during the typical washing procedure of QDs, and drying was observed to play an important role. In conclusion, our study reveals the high potential of HDP for quantifying the interfacial properties of NPs as well as their link to dispersibility.
CRIS-Team Scopus Importer:2019-05-09
Keywords: Colloidal stability; Functionalization; Hansen solubility parameter; Quantum material; Semiconductor nanoparticles

Synergy of Catechol-Functionalized Zinc Oxide Nanorods and Porphyrins in Layer-by-Layer Assemblies - Burger, Alexandra; Kunzmann, Andreas; Costa, Ruben Dario; Srikantharajah, Rubitha; Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas (Chemistry - A European Journal, 2018)
Catechol-functionalized, positively charged ZnO nanorods (NRs) and anionic porphyrins were integrated into layer-by-layer (LbL) assemblies. In general, this study focuses on the impact that different porphyrins, varying in size and number of negative charges, exert on the LbL architecture in terms of morphology and spectroscopy. In particular, through a combination of analytical methods, including UV/Vis spectroscopy, SEM, and profilometry, valuable insights into LbL assembly formation were gathered. A key feature was the surface coverage in the resulting films. Denser films and surface coverages were realized when highly negatively charged and sterically demanding porphyrins were employed. As a complement to basic characterization, the LbL assembled films were used to fabricate proof-of-concept solar cells.
Keywords: porphyrins; solar energy conversion; layer-by-layer assemblies; layered compounds; thin films; ZnO nanorods

Synthesis and characterization of manganese containing mesoporous bioactive glass nanoparticles for biomedical applications - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Burkovski, Andreas; Schmidt, Jochen; Shahid, Ameen; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2018)
Mesoporous bioactive glass (BG) nanoparticles based in the system: SiO2–P2O5-CaO-MnO were synthesized via a modified Stöber process at various concentrations of Mn (0-7 mol%). The synthesized manganese-doped BG nanoparticles were characterized in terms of morphology, composition, in vitro bioactivity and antibacterial activity. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis confirmed that the particles had spherical morphology (mean particle size: 110 nm) with disordered mesoporous structure. Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn, Ca, Si and P in the synthesized Mn-doped BG particles. Moreover, X-ray diffraction (XRD) analysis has shown that Mn has been incorporated into the amorphous silica network (bioactive glass). More over, it was found that manganese-doped BG particles form apatite crystals upon being immersed in simulated body fluid (SBF). Inductively coupled plasma atomic emission spectroscopy (ICP-OES) measurements confirmed that Mn is released in a sustained mannerBacillus subtilis , Pseudomonas aeruginosaaeruginosa Staphylococcus aureus . The multifunctional BG nanoparticles for bone tissue engineering. The results indicate that the incorporation of Mn into the bioactive glass network is effective. and <br

Synthesis and characterization of manganese containing mesoporous bioactive glass nanoparticles for biomedical applications - Nawaz, Qaisar; Ur Rehman, Muhammad Atiq; Burkovski, Andreas; Schmidt, Jochen; Beltran, Ana M.; Shahid, Ameen; Alber, Nina K.; Peukert, Wolfgang; Boccaccini, Aldo R. (Journal of Materials Science: Materials in Medicine, 2018)
Mesoporous bioactive glass (BG) nanoparticles based in the system: SiO2-P2O5-CaO-MnO were synthesized via a modified Stober process at various concentrations of Mn (0-7 mol %). The synthesized manganese-doped BG nanoparticles were characterized in terms of morphology, composition, in vitro bioactivity and antibacterial activity. Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and Brunauer-Emmett-Teller (BET) analysis confirmed that the particles had spherical morphology (mean particle size: 110 nm) with disordered mesoporous structure. Energy dispersive X-ray spectroscopy (EDX) confirmed the presence of Mn, Ca, Si and P in the synthesized Mn-doped BG particles. Moreover, X-ray diffraction (XRD) analysis showed that Mn has been incorporated in the amorphous silica network (bioactive glass). Moreover, it was found that manganese-doped BG particles form apatite crystals upon immersion in simulated body fluid (SBF). Inductively coupled plasma atomic emission spectroscopy (ICP-OES) measurements confirmed that Mn is released in a sustained manner, which provided antibacterial effect against Bacillus subtilis, Pseudomonas aeruginosa and Staphylococcus aureus. The results indicate that the incorporation of Mn in the bioactive glass network is an effective strategy to develop novel multifunctional BG nanoparticles for bone tissue engineering.

Synthesis and characterization of zinc oxide nanoparticles for dye-sensitized solar cells - Peukert, Wolfgang; Guldi, Dirk Michael; Hirsch, Andreas; Werner, Fabian; Gnichwitz, Jan-Frederik; Marczak, Renata (2008 AIChE Annual Meeting, AIChE 100, 2008)
Stable ZnO nanoparticles suitable for further derivatization of their surface were synthesized in the liquid phase from homogeneous ethanolic solutions of the precursors, lithium hydroxide and zinc acetate. The particle growth was monitored by in situ absorption spectroscopy and dynamic light scattering (DLS). It was found that the growth of the particles was governed by temperature as well as the presence of the reaction by-product lithium acetate during the ripening process. In particular, the reaction could be almost completely arrested by removal of this by-product. The "washing" consisted of repeated precipitation of the ZnO particles by addition of alkanes such as heptane, removal of the supernatant, and redispersion in ethanol. The ZnO nanoparticles, before and after "washing", were characterized by absorption spectroscopy, DLS, thermogravimetric analysis (TGA), X-ray powder diffraction (XRD) and high resolution transmission electron microscopy (HRTEM). The functionalization of the ZnO nanoparticles with photoactive organic compounds, i.e., 5-(N-(3,4-dihydroxyphenethyl)-2-phenoxyacetamide)-10, 15, 20-(p-tert-butyl-triphenyl)-porphyrinato-zinc and 5-(3,4-dihydroxy-N- phenylbenzamide)-10,15,20-tris(4-tertbutylphenyl)-porphyrinato-zinc, was examined. Mesoporous films of the ZnO nanoparticles suitable for use as electrodes in dye-sensitized solar cells (DSSCs) were prepared by the doctor blade technique. Following sintering the films were sensitized by the dye molecules mentioned above. The morphology of the films was characterized by using scanning electron microscopy (SEM). The current generated during photoelectrochemical measurements of these films was ascribed to an efficient photoinduced electron transfer from the photoexcited porphyrin to the ZnO moiety.
Keywords: functionalization; ZnO; nanoparticle; growth; light; scattering; solar; call

Synthesis of amphiphilic silver nanoparticles in nanoreactors from invertible polyester - Voronov, Andriy; Kohut, Ananiy; Peukert, Wolfgang (Langmuir, 2007)
A silver complex is transformed into amphiphilic nanoparticles at room temperature using nanoreactors formed from an amphiphilic polyester. It takes a few minutes to form silver nanocolloids with a narrow particle size distribution. Developed silver forms a stable dispersion in both polar and nonpolar media. The amphiphilic polyester acts as a reducing and stabilizing agent simultaneously. The size of the synthesized amphiphilic silver nanoparticles depends on the concentration of the invertible polyester and solvent polarity. © 2007 American Chemical Society.

Synthesis of Goethite α-FeOOH Particles by Air Oxidation of Ferrous Hydroxide Fe(OH)2 Suspensions: Insight on the Formation Mechanism - Klupp Taylor, Robin; Encina, Ezequiel Roberto; Distaso, Monica; Taylor, Robin N. Klupp; Peukert, Wolfgang (Crystal Growth & Design, 2015)
Iron oxide and iron oxyhydroxide particles, particularly, the goethite extgreeka-FeOOH phase, are environmentally friendly materials and are used in various technological applications as adsorbents, precursors of Fe powders for magnetic recording media, and pigments. In this work, the formation process of extgreeka-FeOOH by air oxidation of Fe(OH)2 suspensions has been studied. The effects of the air flow rate, as well as of the reactant concentration ratio, R (=[(OH)-]/[Fe(II)]), on the reaction product were analyzed. It has been found that the morphology and the size of the extgreeka-FeOOH particles can be modified by means of the air flow rate. Furthermore, by performing a detailed microscopic analysis of the morphology of the initial, intermediate, and final reaction products, we have obtained evidence of epitaxial growth of extgreeka-FeOOH on the Fe(OH)2 substrate. It is suggested that the similarity between the anion arrangements in both phases facilitates this process. Based on these results, a pathway for the formation of extgreeka-FeOOH in highly alkaline medium is proposed in which the size and shape of the initial Fe(OH)2 particles plays a significant role in the formation the extgreeka-FeOOH particles obtained upon completion of the oxidation process.
EAM Import::2019-03-12
Keywords: Oxidation reactions; Atmospheric chemistry; Suspensions; Anions; Oxidation

Synthesis of In2Se3 and Cu2-xSe Micro- and Nanoparticles with Microwave-Assisted Solvothermal and Aqueous Redox Reactions for the Preparation and Stabilization of Printable Precursors for a CuInSe2 Solar Cell Absorber Layer - Schuster, Matthias; Distaso, Monica; Möckel, Stefan; Künecke, Ulrike; Peukert, Wolfgang; Wellmann, Peter (2015)
Micro- and nanoparticles were synthesized and stabilized in order to process a copper indium diselenide (CISe) solar cell absorber layer. A microwave assisted solvothermal reaction for In2Se3 particles was performed, finding that smaller particles could be obtained in shorter times and at lower temperatures than with a conventional autoclave based solvothermal synthesis. In a second route In2Se3 and Cu2-xSe nanoparticles have been synthesized via aqueous redox reactions and been Zeta potential-stabilized to acquire a nanoparticulate ink. This ink was drop cast in ambient atmosphere and annealed in N-2-atmosphere leading to the formation of CISe at lower temperatures than with state-of-the-art processing routes. (C) 2015 Published by Elsevier Ltd.
Keywords: In2Se3; Cu2-xSe; nanoparticles; microwave; Zeta potential; low temperature; CuInSe2; solar cell

Synthesis of In2Se3 and Cu2-xSe Micro- and Nanoparticles with Microwave-Assisted Solvothermal and Aqueous Redox Reactions for the Preparation and Stabilization of Printable Precursors for a CuInSe2 Solar Cell Absorber Layer - Schuster, Matthias; Distaso, Monica; Möckel, Stefan; Künecke, Ulrike; Peukert, Wolfgang; Wellmann, Peter (Energy Procedia, 2015)
Micro- and nanoparticles were synthesized and stabilized in order to process a copper indium diselenide (CISe) solar cell absorber layer. A microwave assisted solvothermal reaction for In2Se3 particles was performed, finding that smaller particles could be obtained in shorter times and at lower temperatures than with a conventional autoclave based solvothermal synthesis. In a second route In2Se3 and Cu2-xSe nanoparticles have been synthesized via aqueous redox reactions and been Zeta potential-stabilized to acquire a nanoparticulate ink. This ink was drop cast in ambient atmosphere and annealed in N2 -atmosphere leading to the formation of CISe at lower temperatures than with state-of-the-art processing route
Keywords: In2Se3; Cu2-xSe; nanoparticles; microwave; Zeta potential; low temperature; CuInSe2; solar cell

Synthesis of silicon nanoparticles with a narrow size distribution: A theoretical study - Peukert, Wolfgang; Körmer, Richard; Menz, William; Shekar, Shraddha; Brownbridge, George; Mosbach, Sebastian; Kraft, Markus (Journal of Aerosol Science, 2012)
This work presents a study of the processes involved in synthesis of narrowly distributed silicon nanoparticles from the thermal decomposition of silane. Two models are proposed, one which simultaneously solves the kinetic mechanism of Swihart & Girshick (1999, Journal of Physical Chemistry B 103, 64–76) while adjusting the sintering parameters; and another which adjusts the kinetic and surface growth mechanisms while neglecting coagulation and sintering. The models are applied to simulate the centreline of the hot-wall reactor and process conditions of Körmer et al. (2010, Journal of Aerosol Science 41, 998–1007). Both models are shown to give good agreement with experimental PSDs at a range of process conditions. However, it is reported that an unphysical sintering process is obtained when attempting to use Swihart & Girshick’s kinetic mechanism, while solving for the sintering parameters. The model with adjusted gas-phase and surface growth processes gives better quantitative and qualitative agreement with experimental results. It is therefore recommended that further study into the kinetic and heterogeneous growth mechanisms be conducted in order to better understand the fundamental processes occurring in this hot-wall reactor.
Keywords: synthesis; nanoparticle; thermal; decomposition; sintering; coagulation

Synthesis of silver nanoparticles in melts of amphiphilic polyesters - Vasylyev, Serhiy; Damm, Cornelia; Segets, Doris; Hanisch, Mathias; Taccardi, Nicola; Wasserscheid, Peter; Peukert, Wolfgang (Nanotechnology, 2013)
The current work presents a one-step procedure for the synthesis of amphiphilic silver nanoparticles suitable for production of silver-filled polymeric materials. This solvent free synthesis via reduction of Tollens' reagent as silver precursor in melts of amphiphilic polyesters consisting of hydrophilic poly(ethylene glycol) blocks and hydrophobic alkyl chains allows the production of silver nanoparticles without any by-product formation. This makes them especially interesting for the production of medical devices with antimicrobial properties. In this article the influences of the chain length of the hydrophobic block in the amphiphilic polyesters and the process temperature on the particle size distribution (PSD) and the stability of the particles against agglomeration are discussed. According to the results of spectroscopic and viscosimetric investigations the silver precursor is reduced to elemental silver nanoparticles by a single electron transfer process from the poly(ethylene glycol) chain to the silver ion.

Synthesis of stable and surface functionalized nanoparticles in an amphiphilic block copolymer melt - Klaumünzer, Martin; Distaso, Monica; Hübner, Jakob; Kryschi, Carola; Peukert, Wolfgang; Wolfrum, Christian (Technical Proceedings of the 2013 NSTI Nanotechnology Conference and Expo, NSTI-Nanotech 2013, 2013)
We report on an ultrafast and simple one pot synthesis of noble metal nanoparticles and semiconducting metaloxide nanoparticles with aminoblockcopolymer O,O'-Bis (2-aminopropyl) polypropylene glycol- block-polyethylene glycol- block- polypropylene glycols. No additional organic or anorganic solvents are used during synthesis. For demonstrating the universal application of the amino block copolymer for multiple nanoparticle formation we present exemplary syntheses and their characterizations for the following precursor metal compounds: HAuCl, AgNO and Zn(Ac) .
Keywords: synthesis; particle; functionalization

Tailored modification of flow behavior and processability of polypropylene powders in SLS by fluidized bed coating with in-situ plasma produced silica nanoparticles - Gomez Bonilla, Juan Sebastian; Trzenschiok, Holger; Lanyi, Franz; Schubert, Dirk W.; Bück, Andreas; Schmidt, Jochen; Peukert, Wolfgang (30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019, 2019)
The processability of selective laser sintering (SLS) powders and the characteristics of the generated parts depend amongst others on the flowability. To increase the flowability, SLS powders are usually functionalized with flowing agents. Flowing agents are typically applied by dry particle coating. The optimization of the process parameters necessary to achieve a homogenous coating avoiding segregation is still empirical. In this contribution, an alternative process to particle dry coating is presented. This process integrates the synthesis of silica nanoparticles via plasma enhanced chemical vapor deposition (PECVD) and coating of polymer host particles in a fluidized bed in a single process. The influence of the treatment time on the packing density and flow behavior of the powders is investigated. Test specimen are produced to assess the influence of the treatment on the processability of the powders and the mechanical properties of the produced parts. © Solid Freeform Fabrication 2019: Proceedings of the 30th Annual International Solid Freeform Fabrication Symposium - An Additive Manufacturing Conference, SFF 2019. All rights reserve
Keywords: Additives; Coatings; Compressive strength; Fluidized bed process; Laser heating; Nanoparticles; Plasma CVD; Plasma enhanced chemical vapor deposition; Polypropylenes; Powders; Selective laser sintering; Silica; Silica nanoparticles; Sintering; Synthesis (chemical); Alternative process; Dry-particle coating; Fluidized bed coating; Homogenous coatings; Packing density; Process parameters; Selective laser sintering (SLS); Fluidized beds

Tailoring particle size through nanoparticle precipitation - Peukert, Wolfgang; Schwarzer, Hans-Christoph (Chemical Engineering Communications, 2004)
Precipitation of nanoscaled particles and the size-determining precipitation parameters are investigated experimentally as well as numerically using barium sulfate as a reference substance. The objective of this work is to successfully understand and predict precipitation kinetics. Optimization and tailoring of product properties to specific needs would then be possible without the need of extensive experimentation and its costs. Special attention is paid to the influences of mixing as well as stabilization on the formed PSID. To simulate particle formation the population balance equation, including the terms for nucleation, growth, and agglomeration, is coupled with an specially developed extended version for equi-volumetric mixing of the Engulfment-Deformation-Diffusion-model of micromixing of Baldyga and Bourne (1999). The proposed predictive model for nanoparticle precipitation is explained in detail and simulation results are presented, discussed, and compared to experimental results. © Taylor and Francis Inc.
UnivIS-Import:2015-03-09:Pub.2004.tech.ITC.mechve.tailor
Keywords: Barium sulfate; Micromixing; Nanoparticle; Particle size distribution; Population balance; Precipitation

Tailoring the Reaction Pathway for Control of Size and Composition of Silver-Gold Alloy Nanoparticles - Traore, Nabi; Berthold, Michelle; Hartmann, Lukas; Schmul, Patricia; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Peukert, Wolfgang (Journal of Physical Chemistry C, 2024)
In this work, we independently tune both the particle size and the chemical composition of bimetallic silver−gold alloy nanoparticles (NPs) by carefully controlling the reaction pathway. NP synthesis involves control of the supersaturation profile in time and space. For the reaction-controlled case, this supersaturation profile is determined by a network of reactions leading to the buildup of the monomer concentration. Using a variety of characterization tools, we show how the process conditions influence the coupled reactions in the complex formation mechanism of Ag−Au alloy NPs. Applying a simple mass balance allows for the independent control of size and chemical composition of these NPs, yielding particles with constant composition and varying size in the range of 20 to 40 nm. A series of constant sizes and varying chemical compositions in the range of 10% to 100% molar gold content is also possible. Our new methodology shows an example of how reaction networks can be tailored to achieve targeted NP properties and paves the way for better control in the synthesis of multicomponent NPs.<br

Targeted color design of silver-gold alloy nanoparticles - Traore, Nabi; Spruck, Christina; Uihlein, Andrian; Pflug, Lukas; Peukert, Wolfgang (Nanoscale Advances, 2023)
This research article focuses on the targeted color design of silver-gold alloy nanoparticles (NPs), employing a multivariate optimization approach. NP synthesis involves interconnected process parameters, making independent variation challenging. Data-based property-process relationships are established to optimize optical properties effectively. We define a color target, employ a green chemical co-reduction method at room temperature and optimize process parameters accordingly. The CIEL*a*b* color space (Commission Internationale de l'Éclairage - International Commission on Illumination) and Euclidean distances facilitate accurate color matching to establish the property-process relationship. Concurrently, theoretical Mie calculations explore the structure-property relationship across particle sizes, concentrations, and molar gold contents. The theoretically optimal structure agrees very well with experimental particle structures at the property-process relationship's optimum. The data-driven property-process relationship provides valuable insights into the formation mechanism of a complex particle system, sheds light on the role of relevant process parameters and allows to evaluate the practically available property space. Model validation beyond the original grid demonstrates its robustness, yielding colors close to the target. Additionally, Design of Experiments (DoE) methods reduce experimental work by threefold with slight accuracy trade-offs. Our novel methodology for targeted color design demonstrates how data-based methods can be utilized alongside structure-property relationships to unravel property-process relationships in the design of complex nanoparticle systems and paves the way for future developments in targeted property design.
CRIS-Team Scopus Importer:2023-12-22

Temperature influence on the triboelectric powder charging during dry coating of polypropylene with nanosilica particles - Düsenberg, Björn; Tischer, Florentin; Valayne, Erika; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Powder Technology, 2022)
The influence of process temperature on the triboelectric charge during dry coating of cohesive polymer powders is investigated. The purpose of heating is to decrease the surface moisture of the powder, which results in an increase of electrical charge of the powder. The effect of the hydrophilicity of the SiO2 guest particles on the quality of the dry coating of PP host particles was investigated with respect to the integral charge of the dry coated powder. Furthermore, the flowability, crystallization behavior and degree of coverage (DOC) were investigated to determine the influence of the increased charge on these topics. Increased process temperature increases the electrical charge of the powder, which leads to a higher DOC with guest particles and, thus, drastically improved flowability compared to dry coating at ambient temperature. Furthermore, changes in the crystallization behavior of polypropylene are observed, due to more nuclei.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Crystallization; Dry coating; Flowability; Mixing; Polymer; Thermal treatment; Triboelectricity

TEM preparation method for site- and orientation-specific sectioning of individual anisotropic nanoparticles based on shadow-FIB geometry - Vieweg, Benito; Butz, Benjamin; Peukert, Wolfgang; Klupp Taylor, Robin; Spiecker, Erdmann (Ultramicroscopy, 2012)
For the comprehensive characterization of nanoparticles cross-sectional investigation on the atomic scale by analytical and high-resolution transmission electron microscopy (TEM) is indispensable. Cross-sectioning is especially important for anisotropic nanoparticles to gain information on structure and chemistry along all important projections. We present a focused ion beam (FIB) method for site- and orientation-specific cross-sectioning of arbitrary nanoparticles that are dispersed on a substrate. By adopting a shadow geometry originally developed for thin sensitive films' protection of the specimen by a platinum layer is avoided. This enables simultaneous observation (from the front side) by the electron beam and ion-beam sectioning (from the back side of the supporting substrate) of individually selected particles with excellent accuracy on the nanometer scale. The feasibility and general applicability of the method is demonstrated by site-specific sectioning and cross-section HRTEM investigation of two types of anisotropic nanostructures: silver nanorods with five-fold twin structure and Janus-type silver patchy particles. © 2011 Elsevier B.V.
Keywords: FIB; High-resolution transmission electron microscopy; Nanoparticles; Nanorods; Patchy particles; TEM preparation

The effect of mixing on silver particle morphology in flow synthesis - Yang, Tao; Segets, Doris; Thajudeen, Thaseem; Han, Yongsheng; Peukert, Wolfgang (Chemical Engineering Science, 2018)
Keywords: Anisotropic silver particles; Dendrites; Analytical centrifugation; Mixing time; Plates

The effects of post-processing on the surface and the optical properties of copper indium sulfide quantum dots - Akdas, Tugce; Distaso, Monica; Kuhri, Susanne; Winter, Benjamin; Birajdar, Balaji; Spiecker, Erdmann; Guldi, Dirk Michael; Peukert, Wolfgang (Advances in Colloid and Interface Science, 2015)
In the current contribution we report on investigations regarding the surface of CuInS2 quantum dots and on different strategies to control the amount of surface ligands in a post-processing step. In particular, the reactivity of the organic components, that is, 1-dodecanthiol and 1-octadecene as ligand and solvent, respectively, during nanocrystal formation was studied. A new method to remove residuals from the reaction mixture and to detach excess organics from the surface of the nanocrystals is reported. Our new method, which is based on the utilization of acids, is compared with standard purification procedures by means of thermogravimetric analysis (TGA) with particular focus on its efficiency to remove organics. As a complement, the surface chemistry is analyzed by nuclear magnetic resonance spectroscopy (NMR) to shed light on the nature of the organic components still present after purification. Further analysis of the product by inductively coupled plasma optical emission spectroscopy (ICP-OES) is performed to verify the influence of the new purification method on surface composition and properties. Moreover, steady state and time resolved spectroscopies give insights into excitonic behavior as well as recombination processes. Finally, the new method is optimized for the purification of CuInS2-ZnS nanocrystals, which show enhanced optical properties.

The flow field in the mill - a key factor for the prediction of the comminution result - Epple, Philipp; Breuer, Michael; Peukert, Wolfgang; Toneva, Petya Ivanova; Wirth, Karl-Ernst (AIChE Annual Meeting, Conference Proceedings, 2006)
Measurements of the mean and time dependent velocity profile were obtained for the first time in an air classifier mill using particle image velocimetry (PIV). Detailed measurements in the vicinity of the impact elements and in the region of the internal classifier are presented. Different pin geometries have been studied at various circumferential velocities of the grinding disk and the classifier. Regions with high turbulence have been observed for all investigated pin geometries at the flow off side of the impact element. The classifier velocity doesn't influence the velocity profiles near the impact elements in main flow direction. The velocity profile on the front sight of the impact element, where the comminution process takes place, is constant with time and preserves a characteristic form with varying operational conditions. The one phase flow field in the complete mill geometry has been modelled by CFX.
UnivIS-Import:2015-04-16:Pub.2006.tech.ITC.stmmec.theflo
Keywords: Air classifier mill; CFX; Flow investigations; PIV; Turbulence modeling

The influence of dispersing and stabilizing of indium tin oxide nanoparticles upon the characteristic properties of thin films - Peukert, Wolfgang; Reindl, Armin; Mahajeri, Mahdi; Hanft, J (Thin Solid Films, 2009)
Stable suspensions of indium tin oxide nanoparticles were prepared by dispersing for 1 h in ethanol and stabilizing with 2-[2-(2-Methoxyethoxy)ethoxy]acetic acid. Particle size, morphology, and structure were characterized by a combination of dynamic light scattering, high resolution transmission electron microscopy, and X-ray diffraction. Spin coating of the stable suspensions resulted in densely packed films with a high transparency. Dispersing times exceeding 1 h led to a significant "overdispersing" effect, i.e. an increasing aggregate size of the suspensions was observed. Zeta-potential, pH, and X-ray photoelectron spectroscopy measurements were conducted to achieve a detailed understanding of the effect of "overdispersing". With an increasing time of dispersion, i.e. with a decreasing stability of the suspensions, the thin films fabricated by spin coating displayed an increasing pore size distribution and surface roughness. In addition a strong decrease in transmittance and in conductivity was observed. © 2008 Elsevier B.V. All rights reserved.
Keywords: Conductivity; Dispersion; Indium tin oxide; ITO; Morphology; Nanoparticles; Stability; Thin films; Transmittance

The influence of particle charge and roughness on particle-substrate adhesion - Peukert, Wolfgang; Zhou, Hongben; Götzinger, Martin (Powder Technology, 2003)
In the electrophotographic process, charged toner particles are transferred from the bulk to the photoreceptor drum and from there to the paper. In high performance printing systems, more than 1000 pages/min are printed, equivalent to the transfer of more than 10 particles/min. The key to understand and to improve the printing system is particle-particle and particle-substrate interactions, respectively. We study the adhesion forces by means of atomic force microscopy (AFM) measurements complemented by centrifugal detachment measurements in an ultracentrifuge. The interpretation of AFM measurements requires careful calibration of the used cantilevers together with a sound statistical analysis. Particle charges have been determined from force-displacement curves. Silicon wafers, polished and PVD-coated aluminum substrates with tailored roughness are chosen as model materials. Spherical, smooth polystyrene and specially prepared alumina particles as well as rugged toner particles of irregular shape are investigated. We proceed from well-defined model systems (flat smooth substrate interacting with spherical particles) to technical systems where rugged particles adhere to rough substrates. The adhesion forces consist of electrostatic and of non-electrostatic (e.g. van der Waals forces) components. We show how the influence of electrostatic forces relative to the van der Waals forces can be controlled. © 2003 Elsevier B.V. All rights reserved.
Keywords: Adhesion; AFM; Electrostatic force; Toner

The influence of suspension properties on the grinding behavior of alumina particles in the submicron size range in stirred media mills - Peukert, Wolfgang; Stenger, Frank; Mende, Stefan; Schwedes, Jörg (Powder Technology, 2005)
The paper shows the possibility to produce alumina nanoparticles in a stirred media mill by an appropriate adjustment of the suspension properties and the milling parameters. Besides a high electrostatic suspension stability that can be realised for metal oxides by means of pH value adjustment small grinding beads favour the production of alumina particles with a median particle size of around 10 nm. In addition to size reduction mechanochemical changes and the formation of alumina hydroxide are detected during wet grinding of alumina. This is analysed by means of X-ray diffraction analysis (XRD), thermogravimetry (TG) and dynamic scanning calorimetry (DSC) measurement and a quantitatively good agreement between the three methods could be obtained. Further, it is proved that the hydroxide produced dissolves at pH values lower than 5 thus influencing the grinding process under these conditions.
Keywords: Mechanochemical effects; Nanosized alumina; Stirred media mill; Suspension properties

The low Reynolds number turbulent flow and mixing in a confined impinging jet reactor - Schwertfirm, Florian; Gradl, Johannes; Schwarzer, Hans-Christoph; Peukert, Wolfgang; Manhart, Michael (International Journal of Heat and Fluid Flow, 2007)
Turbulent mixing takes an important role in chemical engineering, especially when the chemical reaction is fast compared to the mixing time. In this context a detailed knowledge of the flow field, the distribution of turbulent kinetic energy (TKE) and its dissipation rate is important, as these quantities are used for many mixing models. For this reason we conduct a direct numerical simulation (DNS) of a confined impinging jet reactor (CUR) at Re = 500 and Sc = 1. The data is compared with particle image velocimetry (PIV) measurements and the basic flow features match between simulation and experiment. The DNS data is analysed and it is shown that the flow is dominated by a stable vortex in the main mixing duct. High intensities of turbulent kinetic energy and dissipation are found in the impingement zone which decrease rapidly towards the exit of the CUR. In the whole CIJR the turbulence is not in equilibrium. The strong mixing in the impingement zone leads to a rapid development of a monomodal PDF. Due to the special properties of the flow field, a bimodal PDF is generated in cross-sections downstream the impingement zone, that slowly relaxes under relaminarising conditions. The time required for meso-mixing is dominating the overall mixing performance.
Keywords: direct numerical simulation; confined impinging jet reactor; particle image velocimetry; opposing jets; turbulent mixing

The mass transfer at Taylor cones - Lübbert, Christian; Peukert, Wolfgang (Journal of Aerosol Science, 2018)

The morphology of integrated self-assembled monolayers and their impact on devices – A computational and experimental approach - Novak, Michael; Jäger, Christof; Rumpel, Armin; Kropp, Henning; Peukert, Wolfgang; Clark, Timothy; Halik, Marcus (Organic Electronics, 2010)
We report on a combined experimental and computational study on self-assembled monolayers (SAMs). The dielectric properties of SAMs based on n-alkyl phosphonic acids in large area thin film devices (organic field-effect transistors with good hole mobilities up to 0.3 cm² V−1 s−1 at −1 V and capacitors) depend on their chain length, but not consistently to theoretical pictures of tunneling through saturated n-alkanes. An unexpected saturation of current density with increasing chain length was obtained in devices, what impact on the leakage current in transistors and current density in capacitors. This is attributed to different self-assembled monolayer morphology ranging from an amorphous state for short alkyl chains to a quasi-crystalline state for longer alkyl chains. Molecular dynamics (MD) simulations provide a deeper insight into the nature of the three-dimensional intermolecular interactions and support the proposed SAM morphology. The change in morphology leads to a reduced effective SAM thickness in devices, which could be described by a Simmons approach quantitatively. The morphological aspect of self-assembled molecules is of enormous importance beyond the applications of SAMs in low-voltage, high mobility organic transistors because of it’s relevance for the hole field of molecular scale electronics. It demonstrates that even small changes in the molecular design can change the molecular interactions and monolayer assembly.

Theoretical and experimental investigations on sintering kinetics of silica nanoparticles - Peukert, Wolfgang; Schmid, Hans-Joachim; Kirchhof, Martin; Förster, Henning (2006 AIChE Spring National Meeting - 5th World Congress on Particle Technology, 2006)
The sintering kinetics of single silica nanoparticle contacts in the gas phase is investigated experimentally and theoretically. Experiments are conducted in a high-temperature short-time flow reactor allowing for precise control of temperature and residence time. Sintering experiments have been conducted for temperatures up to 1600 °C and residence times down to 5 ms. Results show significantly shorter sintering times than predicted by macroscopic sintering models. For vitreous materials such as silica the predominant sintering mechanism is supposed to be viscous flow. Therefore, three dimensional simulations of the sintering process have been conducted by solving the free surface viscous flow process using a volume-of-fluid (VOF) method. Additionally, van der Waals interactions have been considered as momentum source. The results suggest that molecular van der Waals interactions have great influence on the sintering kinetics of nanoparticles which is insufficiently described by macroscopic models.
Keywords: Silica; Sintering; Viscous flow; Volume-of-fluid method (VOF)

The relevance of interactions in nanoparticulate systems - Peukert, Wolfgang (World Congress Particle Technology 4, 2002)
In the field of Particle Technology, processes cannot yet be designed from basic molecular understanding. Nanotechnology, however, begins to bridge this gap between molecules and particles and may thus open up new ways not only for the production and handling of particulate matter but also for the engineered design of advanced material properties. The visions and applications in nanoparticle technology cover a broad range, for instance quantum dots in information technology, refractory particles for advanced ceramics, highly active substances in pharmacy, catalysts or micro- and mesoporous adsorbents, to name only a few applications. Starting from the concept of product engineering, we investigate the basic preconditions for tailoring nanoparticulate properties, i.e. the control of the particle interactions. This concept is then applied to particulate thin film formation as an example of structure formation. The structure of dip-coated samples, defined as the order of particles within the layer, was found to vary with the pH and the ion concentration adjusted in the sol bath. It was observed that the surface roughness scanned by an atomic force microscope increased with increasing electrolyte concentration. The structural evolution of the particulate network was studied by measuring the viscosity as a function of shear rate and solid concentration. Finally, the influence of coating structures on the transmission properties was determined. Especially in the case of LaCl3 a strong dependence was observed. The results explicitly confirm a correlation between microscopic structure and macroscopic propertie
UnivIS-Import:2015-04-16:Pub.2002.tech.ITC.mechve.therel_5
Keywords: nanotechnology; particle; interaction

The relevance of particle interactions in nanoparticulate systems - Application to particulate thin films - Günther, Lydia; Peukert, Wolfgang (Particle & Particle Systems Characterization, 2002)
In the field of Particle Technology, processes cannot yet be designed from basic molecular understanding. Nanotechnology, however, begins to bridge this gap between molecules and particles and may thus open up new ways not only for the production and handling of particulate matter but also for the engineered design of advanced material properties. The visions and applications in nanoparticle technology cover a broad range, for instance quantum dots in information technology, refractory particles for advanced ceramics, highly active substances in pharmacy, catalysts or micro- and mesoporous adsorbents, to name only a few applications. Starting from the concept of product engineering, we investigate the basic preconditions for tailoring nanoparticulate properties, i.e. the control of the particle interactions. This concept is then applied to particulate thin film formation as an example of structure formation. The structure of dip-coated samples, defined as the order of particles within the layer, was found to vary with the pH and the ion concentration adjusted in the sol bath. It was observed that the surface roughness scanned by an atomic force microscope increased with increasing electrolyte concentration. The structural evolution of the particulate network was studied by measuring the viscosity as a function of shear rate and solid concentration. Finally, the influence of coating structures on the transmission properties was determined. Especially in the case of LaCl3 a strong dependence was observed. The results explicitly confirm a correlation between microscopic structure and macroscopic properties.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.therel

Thermal rounding of micron-sized polymer particles in a downer reactor: direct vs indirect heating - Gomez Bonilla, Juan Sebastian; Dechet, Maximilian; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Rapid Prototyping Journal, 2020)
Purpose: The purpose of this paper is to investigate the effect of different heating approaches during thermal rounding of polymer powders on powder bulk properties such as particle size, shape and flowability, as well as on the yield of process. Design/methodology/approach: This study focuses on the rounding of commercial high-density polyethylene polymer particles in two different downer reactor designs using heated walls (indirect heating) and preheated carrier gas (direct heating). Powder bulk properties of the product obtained from both designs are characterized and compared. Findings: Particle rounding with direct heating leads to a considerable increase in process yield and a reduction in powder agglomeration compared to the design with indirect heating. This subsequently leads to higher powder flowability. In terms of shape, indirect heating yields not only particles with higher sphericity but also entails substantial agglomeration of the rounded particles. Originality/value: Shape modification via thermal rounding is the decisive step for the success of a top-down process chain for selective laser sintering powders with excellent flowability, starting with polymer particles from comminution. This report provides new information on the influence of the heating mode (direct/indirect) on the performance of the rounding process and particle properties.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Crystallinity; Particle shape; Particle size; Polymers; Powder flowability; Selective laser sintering; Shape modification; Thermal rounding

The role of particle interactions on suspension rheology - Application to submicron grinding in stirred ball mills - Stenger, Frank; Peukert, Wolfgang (Chemical Engineering & Technology, 2003)
UnivIS-Import:2015-03-09:Pub.2003.tech.ITC.mechve.therol

The significance of the second osmotic virial coefficients for protein crystallization Die Bedeutung des zweiten osmotischen Virialkoeffizienten für die Proteinkristallisation - Wanka, Johanna; Peukert, Wolfgang (Chemie Ingenieur Technik, 2006)
Die Kristallisation der Proteine bietet eine gute und quantitative Möglichkeit zu ihrer Ab- trennung und Aufreinigung. Wichtigster und zeitaufwändigster Schritt der Kristallisation ist das Auffinden geeigneter Kristallisationsbedingungen meist über ein groß angelegtes Screening. Als prädiktiver Parameter für die Proteinkristallisation zur Reduzierung der not- wendigen Experimente wurde der zweite osmotische Virialkoeffizient B22 erkannt. Der Zu- sammenhang zwischen B22 und den Präzipitateigenschaften wurde bisher nur qualitativ hergestellt, es ist deshalb Thema dieser Untersuchungen, ihn zu quantifizieren.<br
Keywords: Kristallisation; Proteine; Prozessoptimierung

The Stokes–Einstein–Sutherland Equation at the Nanoscale Revisited - Baer, Andreas; Wawra, Simon; Bielmeier, Kristina; Uttinger, Maximilian; Smith, David M.; Peukert, Wolfgang; Walter, Johannes; Smith, Alexander Kingsbury (Small, 2023)
The Stokes–Einstein–Sutherland (SES) equation is at the foundation of statistical physics, relating a particle's diffusion coefficient and size with the fluid viscosity, temperature, and the boundary condition for the particle-solvent interface. It is assumed that it relies on the separation of scales between the particle and the solvent, hence it is expected to break down for diffusive transport on the molecular scale. This assumption is however challenged by a number of experimental studies showing a remarkably small, if any, violation, while simulations systematically report the opposite. To understand these discrepancies, analytical ultracentrifugation experiments are combined with molecular simulations, both performed at unprecedented accuracies, to study the transport of buckminsterfullerene C60 in toluene at infinite dilution. This system is demonstrated to clearly violate the conditions of slow momentum relaxation. Yet, through a linear response to a constant force, the SES equation can be recovered in the long time limit with no more than 4% uncertainty both in experiments and in simulations. This nonetheless requires partial slip on the particle interface, extracted consistently from all the data. These results, thus, resolve a long-standing discussion on the validity and limits of the SES equation at the molecular scale.
CRIS-Team Scopus Importer:2023-10-20
Keywords: analytical ultracentrifugation; boundary condition; Green–Kubo formalism; molecular dynamics; Stokes–Einstein–Sutherland equation

Three-dimensional and quantitative reconstruction of non-accessible internal porosity in hematite nanoreactors using 360 degrees electron tomography - Distaso, Monica; Apeleo Zubiri, Benjamin; Mohtasebi, Amirmasoud; Inayat, Alexandra; Dudak, Michal; Koci, Petr; Butz, Benjamin; Klupp Taylor, Robin; Schwieger, Wilhelm; Spiecker, Erdmann; Peukert, Wolfgang (Microporous and Mesoporous Materials, 2017)
In the current paper, mesocrystals are used as effective precursors to design nanoreactors with different kinds of enclosed porosity. The thermal treatment of hematite mesocrystalline nanoparticles is investigated as a post-processing tool for the engineering of internal organization of hierarchical structures. The porosity of starting materials and of particles thermally treated at different temperatures is investigated by transmission electron microscopy, nitrogen sorption and 360 degrees electron tomography. Virtual Capillary Condensation and Maximum Sphere Inscription are used as independent approaches for the quantitative assessment of internal porosity. The combination of experimental evidences and simulations provides a deep understanding of the internal topology of nanoreactors upon thermal treatment of mesocrystalline particles. This new design strategy may pave the way for exploring the use of the post treated mesocrystals as carriers to encapsulate materials for optoelectronic applications. (C) 2017 Elsevier Inc. All rights reserve
Keywords: Mesocrystals; Inorganic hollow nanoparticles; Compartmentalization; Encapsulation

Three-dimensional simulation of viscous-flow agglomerate sintering - Peukert, Wolfgang; Kirchhof, Martin; Schmid, Hans-Joachim (Physical Review E, 2009)
The viscous-flow sintering of different agglomerate particle morphologies is studied by three-dimensional computer simulations based on the concept of fractional volume of fluid. For a fundamental understanding of particle sintering characteristics, the neck growth kinetics in agglomerate chains and in doublets consisting of differently sized primary particles is investigated. Results show that different sintering contacts in agglomerates even during the first stages are not completely independent from each other, even though differences are small. The neck growth kinetics of differently sized primary particles is determined by the smaller one up to a size difference by a factor of approximately 2, whereas for larger size differences, the kinetics becomes faster. In particular, the agglomerate sintering kinetics is investigated for particle chains of different lengths and for different particle morphologies each having ten primary particles and nine initial sintering contacts. For agglomerate chains, the kinetics approximately can be normalized by using the radius of the fully coalesced sphere. In general, different agglomerate morphologies show equal kinetics during the first sintering stages, whereas during advanced stages, compact morphologies show significantly faster sintering progress than more open morphologies. Hence, the overall kinetics cannot be described by simply using constant morphology correction factors such as fractal dimension or mean coordination number which are used in common sintering models. However, for the first stages of viscous-flow agglomerate sintering, which are the most important for many particle processes, a sintering equation is presented. Although we use agglomerates consisting of spherical primary particles, our methodology can be applied to other aggregate geometries as well. © 2009 The American Physical Society.
Keywords: sintering; agglomerate; simulation; kinetic; model

Top-down processing of submicron 45S5 Bioglass® for enhanced in vitro bioactivity and biocompatibility - Romeis, Stefan; Hoppe, Alexander; Detsch, Rainer; Boccaccini, Aldo R.; Schmidt, Jochen; Peukert, Wolfgang (Procedia Engineering, 2015)
45S5 Bioglass® (45S5BG - 45 wt.% SiO, 24.5 wt.% CaO, 24.5 wt.% NaO and 6 wt.% PO glass forming system) is a frequently applied type A bioactive material, forming an inherent bond to bone and soft tissue. Recent studies for nanometer sized bioactive glasses (nBG) have indicated their great potential for several biomedical applications. It is recognized that cost-efficient processing routes are required for the development of submicron bioactive glasses, given the advantages associated with the nanoscale. In this study, the potential of top-down processing of 45S5BG by wet comminution in a stirred media mill is investigated and the key importance of the used solvents is revealed: whereas bioactive submicron particles can be produced in organic solvents, as shown exemplarily for n-pentanol, bioactivity is lost after processing in water. Analysis of the elemental constituents in the solid phase by ICP-OES indicates enhanced dissolution during processing in water, i.e. The glass composition is changing during processing. In n-pentanol the overall composition and structure is maintained and only the formation of surface carbonates is observed; flake-like particles are obtained. As a marker for bioactivity in vitro hydroxycarbonate apatite formation as determined by FTIR is used; biocompatibility is addressed by in vitro incubation with osteoblast like MG-63 cells. All-together, we propose wet comminution under controlled conditions as an appropriate technique to produce submicrometer bioactive glass particles with enhanced bioactivit
Keywords: in vitro bioactivity and biocompatibility; solvent influence; submicron 45S5 Bioglass®; top-down

Top-down processing of submicron 45S5 Bioglass (R) for enhanced in vitro bioactivity and biocompatibility - Romeis, Stefan; Hoppe, Alexander; Detsch, Rainer; Boccaccini, Aldo R.; Schmidt, Jochen; Peukert, Wolfgang (2015)
45S5 Bioglass (R) (45S5BG - 45 wt.% SiO2, 24.5 wt.% CaO, 24.5 wt.% Na2O and 6 wt.% P2O5 glass forming system) is a frequently applied type A bioactive material, forming an inherent bond to bone and soft tissue. Recent studies for nanometer sized bioactive glasses (nBG) have indicated their great potential for several biomedical applications. It is recognized that cost-efficient processing routes are required for the development of submicron bioactive glasses, given the advantages associated with the nanoscale. In this study, the potential of top-down processing of 45S5BG by wet comminution in a stirred media mill is investigated and the key importance of the used solvents is revealed: whereas bioactive submicron particles can be produced in organic solvents, as shown exemplarily for n-pentanol, bioactivity is lost after processing in water. Analysis of the elemental constituents in the solid phase by ICP-OES indicates enhanced dissolution during processing in water, i.e. the glass composition is changing during processing. In n-pentanol the overall composition and structure is maintained and only the formation of surface carbonates is observed; flake-like particles are obtained. As a marker for bioactivity in vitro hydroxycarbonate apatite formation as determined by FTIR is used; biocompatibility is addressed by in vitro incubation with osteoblast like MG-63 cells. All-together, we propose wet comminution under controlled conditions as an appropriate technique to produce submicrometer bioactive glass particles with enhanced bioactivity. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: submicron 45S5 Bioglass (R); top-down; solvent influence; in vitro bioactivity and biocompatibility

Towards a generally applicable methodology for the characterization of particle properties relevant to processing in powder bed fusion of polymers – from single particle to bulk solid behavior - Hesse, Nicolas; Winzer, Bettina; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2021)
The majority of additively manufactured plastic parts built with powder bed fusion (PBF) processes are made of polyamide 12. Since only a fraction of powder ends up in the components built, part cake material and overflow powder has to be re-used for economic and ecologic reasons, even though its material properties are altered by thermo-mechanical stress during processing. Changes in bulk solid properties play a key role for the stability of the PBF process and the quality of manufactured parts. However, there is still no generally accepted method for the evaluation of used powders with respect to their processability and a lack of understanding of underlying bulk material mechanics. The aim of this study, exemplified for polyamide 12, is to assess widely applicable, standardized and process-adapted characterization methods in additive manufacturing and to shed light on the underlying phenomena causing the changes in flowability and packing properties of used powders.<br
Keywords: Powder bed fusion; Powder characterization; Powder flowability; Powder aging; Polyamide 12

Towards recombinantly produced milk proteins: Physicochemical and emulsifying properties of engineered whey protein beta-lactoglobulin variants - Keppler, Julia K.; Heyse, Anja; Scheidler, Eva; Uttinger, Maximilian; Fitzner, Laura; Jandt, Uwe; Heyn, Timon R.; Lautenbach, Vanessa; Loch, Joanna I.; Lohr, Jonas; Kieserling, Helena; Günther, Gabriele; et al. (Food Hydrocolloids, 2021)
CRIS-Team Scopus Importer:2020-08-07

Transfer of fracture mechanical concepts to bulk solids attrition in pneumatic conveying - Peukert, Wolfgang; Frye, Lars (International Journal of Mineral Processing, 2004)
In the present project, attrition in pneumatic conveying—as in fracture mechanics and comminution—is regarded as a result of a process function (stress conditions) and a material function (influence of material properties). The first part of the paper describes the results of the determination of the stress conditions, where special emphasis is put on the numerical simulation of dilute-phase conveying. In the second part, results of single-particle tests are discussed. They simulate the two basic stress modes: impact and friction. The results show that the attrition behavior of the polymers tested changes between both stress modes. It is currently evaluated which material properties are suitable to describe this experimentally observed behavio
Keywords: Fracture mechanics: Computational fluid dynamics; Solid degradation; Pneumatic transport

Transfer of Individual Micro- and Nanoparticles for High-Precision 3D Analysis Using 360° Electron Tomography - Przybilla, Thomas; Apeleo Zubiri, Benjamin; Maria Beltran, Ana; Butz, Benjamin; Machoke, Albert; Inayat, Alexandra; Distaso, Monica; Peukert, Wolfgang; Schwieger, Wilhelm; Spiecker, Erdmann (Small Methods, 2017)
A versatile approach is demonstrated, providing a general routine for an extensive and advanced 3D characterization of individually selected micro- and nanoparticles, enabling the combination of complementary and scale-bridging techniques. Quintessential to the method is the transfer of individual particles onto tailored tips using a conventional scanning electron microscope equipped with a suitable micromanipulator. The method enables a damage- and contamination-free preparation of freestanding particles. This is of significant importance for applications addressing the measurement of structural, physical, and chemical properties of specifically selected particles, such as 360° electron tomography, atom probe tomography, nano X-ray tomography, or optical near-field measurements. In this context, the method is demonstrated for 360° electron tomography of micro-/macroporous zeolite particles with sizes in the micrometer range and mesoporous alpha-hematite nanoparticles exhibiting sizes of 50–100 nm, including detailed pre- and post-characterization on the nanoscal
Keywords: 360 degrees electron tomography; dual-beam SEM/FIB; micromanipulation; pick and place; sample preparation

Translational and Rotational Diffusion Coefficients of Gold Nanorods Dispersed in Mixtures of Water and Glycerol by Polarized Dynamic Light Scattering - Bioucas, Francisco; Damm, Cornelia; Peukert, Wolfgang; Rausch, Michael Heinrich; Koller, Thomas Manfred; Giraudet, Cédric; Fröba, Andreas Paul (Journal of Physical Chemistry B, 2019)
Polarized dynamic light scattering (DLS) gives access to orientation-averaged translational and rotational diffusion coefficients of anisotropic particles dispersed in fluids in a single experiment. As the combination of both diffusivities contains information on the morphology of the particles, their simultaneous and accurate measurement for the same sample and thermodynamic state is beneficial for particle characterization. For nontransparent model suspensions of gold nanorods in water and water-glycerol mixtures, a scattering geometry in reflection direction was realized, which minimizes multiple scattering and allows using low laser powers to avoid laser heating. Furthermore, a heterodyne detection scheme was guaranteed by superimposing much stronger reference light to the scattered light. This ensures an unambiguous data evaluation and reduces the uncertainties for the rotational and the translational diffusivity, where the latter is accessible with smaller uncertainty. For the water-based suspensions, both diffusivities agree well with the stick hydrodynamic theory for rods and show an Andrade-type behavior in the studied temperature range from 271 to 323 K. The measured results for both diffusivities, particularly for the rotational diffusivity, indicate a breakdown of the stick boundary conditions for dynamic viscosities larger than 4 mPa·s.
CRIS-Team Scopus Importer:2019-11-08

Transmission electron microscopy and time resolved optical spectroscopy study of the electronic and structural interactions of ZnO nanorods with bovine serum albumin - Klaumünzer, Martin; Weichsel, Ulrike; Mackovic, Mirza; Spiecker, Erdmann; Peukert, Wolfgang; Kryschi, Carola; Spiecker, Erdmann; Mackovic, Mirza (Journal of Physical Chemistry B, 2013)
The adsorption behavior and electronic interactions of bovine serum albumin (BSA) with ZnO nanorod surfaces were investigated using high-resolution transmission electron microscopy as well as stationary and time-resolved optical spectroscopy techniques. Transmission electron microscopy shows that ZnO nanorod surfaces are surrounded by a homogeneous amorphous BSA film with thicknesses between ∼2.5 and 5.0 nm. The electronic structure and adsorption geometry of BSA were examined using high-angle annular dark field scanning transmission electron microscopy combined with electron energy loss spectroscopy. The adsorption process was observed to result into an unfolded conformation of BSA becoming predominantly bound in the side-on orientation at the ZnO surface. This adsorption mode of the BSA molecules allows for a strong interaction with surface states of the ZnO nanorods. This is obvious from its efficient quenching of the defect-center photoluminescence of ZnO. Complementary information of electronic interactions across the ZnO nanorod interface was obtained from femtosecond transient absorption spectroscopy experiments. The rise dynamics of the measured transients revealed altered hole trapping dynamics and, thus, indicated to heterogeneous charge transfer as emerging from adsorbed BSA molecules to defect centers of the ZnO interface. © 2013 American Chemical Society.

Treatment of polymer powders by combining an atmospheric plasma jet and a fluidized bed reactor - Sachs, Marius; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
Keywords: Atmospheric pressure plasma; Fluidized bed reactor; Additive manufacturing; Polymers; Secondary gas injection

Tunable conduction type of solution-processed germanium nanoparticle based field effect transistors and their inverter integration - Peukert, Wolfgang; Meric, Zeynep; Mehringer, Christian; Jank, Michael; Frey, Lothar; Karpstein, Nicolas (Physical Chemistry Chemical Physics, 2015)
In this work we demonstrate the fabrication of germanium nanoparticle (NP) based electronics. The whole process chain from the nanoparticle production up to the point of inverter integration is covered. Ge NPs with a mean diameter of 33 nm and a geometric standard deviation of 1.19 are synthesized in the gas phase by thermal decomposition of GeH4 precursor in a seeded growth process. Dispersions of these particles in ethanol are employed to fabricate thin particulate films (60 to 120 nm in thickness) on substrates with a pre-patterned interdigitated aluminum electrode structure. The effect of temperature treatment, polymethyl methacrylate encapsulation and alumina coating by plasma-assisted atomic layer deposition (employing various temperatures) on the performance of these layers as thin film transistors (TFTs) is investigated. This coating combined with thermal annealing delivers ambipolar TFTs which show an Ion/Ioff ratio in the range of 102. We report fabrication of n-type, p-type or ambipolar Ge NP TFTs at maximum temperatures of 450 °C. For the first time, a circuit using two ambipolar TFTs is demonstrated to function as a NOT gate with an inverter gain of up to 4 which can be operated at room temperature in ambient ai
Keywords: nanoparticle; electronic; thermal; decomposition; growth; particulate; film

Tuning the Molecular Order of C60 Functionalized Phosphonic Acid Monolayers - Rumpel, Armin; Novak, Michael; Walter, Johannes; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (Langmuir, 2011)
Mixed self-assembled monolayers (SAM) of alkyl phosphonic acids and C60 functionalized octadecyl phosphonic acids (C60C18–PA) are deposited on alumina substrates from solution and are shown to form wellordered structures with an insulating layer of alkyl chains and a semiconducting layer that comprises mainly C60. Such an ordered structure is a necessity for the application of SAMs in organic transistors but is difficult to obtain since C60C18–PA without additional support do self-assemble in dense packaging but not in a well-ordered fashion. To avoid disordering of the SAM and to gain a better control of the interfacial properties we have investigated the stabilizing effects of fluorinated dodecyl phosphonic acids (FC12–PA) on the C60C18–PA monolayer. Vibrational sum-frequency (SFG) spectroscopy, ellipsometry, X-ray photoelectron spectroscopy, and electrical measurements were applied to study the mixed monolayers. Here, we make use of the differently labeled PA to determine surface coverages and molecular properties of the two species independently. Adsorption of FC12–PA gives rise to vibrational bands at 1344 cm-1 and 1376 cm-1 in SFG spectra, while a pronounced vibrational band centered at 1465 cm-1 is attributable to C60 vibrations. The coexistence of the bands is indicative for the presence of a mixed monolayer that is composed of both molecular species. Furthermore, a pronounced maximum in SFG intensity of the C60 band is observed for SAMs, which are deposited from solutions with  75% C60C18–PA and  25% FC12–PA. The intensity maximum originates from successful stabilization of C60 modified C60C18–PA by FC12–PA and a significantly improved molecular order. Conclusions from SFG spectra are corroborated by electric measurements that show best performance at these concentrations. Our results provide new information on the morphology and composition of C60 modified SAMs and establish a route to fabricate well-defined layers for molecular scale organic electronics.
Keywords: Thickness; Nonlinear optics; Layers; Monolayers

Tuning the molecular order of C-60 functionalized phosphonic acids - Rumpel, Armin; Novak, Michael; Walter, Johannes; Braunschweig, Björn; Halik, Marcus; Peukert, Wolfgang (2012)

Tuning the Properties of CZTS Films by Controlling the Process Parameters in Cost-Effective Non-vacuum Technique - Abdelhaleem, Soraya; Hassanien, A.E.; Ahmad, Rameez; Schuster, Matthias; Ashour, A.H.; Distaso, Monica; Peukert, Wolfgang; Wellmann, Peter (Journal of Electronic Materials, 2018)
Highly dispersive Cu2ZnSnS4 (CZTS) nanoparticles were successfully synthesized by a simple solvothermal route. A low cost, non-vacuum method was used to deposit CZTS nanoparticle ink on glass substrates by a doctor blade process followed by selenization in a tube furnace to form Cu2ZnSn (S,Se)4 (CZTSSe) layers. Different selenization conditions and particle concentrations were considered in order to improve the crystallinity and surface morphology; the annealing temperature was varied between 400C and 550C and the annealing time was varied between 5 min and 20 min in a seleniumnitrogen atmosphere. The influence of annealing conditions on structural, compositional, optical and electrical properties of CZTSSe thin films was studied. An improvement in the structural and surface morphology was observed with increasing of annealing temperature (up to 500C). An enhancement in the crystallinity and surface morphology were observed for thin films annealed for 10–15 min. Absorption study revealed that the band gap energy of as-deposited CZTS thin film was approximately 1.43 eV, while for CZTSSe thin films it ranged from 1.15 eV to 1.34 eV at different annealing temperatures, and from 1.33 eV to 1.38 eV for different annealing times.<br
Keywords: CZTSSe; selenization; solvothermal; thin films; doctor blade; resistivity

Tuning the size and the optical properties of ZnO mesocrystals synthesized under solvothermal conditions - Distaso, Monica; Segets, Doris; Wernet, Ruth; Peukert, Wolfgang; Klupp Taylor, Robin (Nanoscale, 2012)
Mesocrystals are a promising class of nanomaterials enabling new optical and mechanical properties due to their three dimensional organization of primary crystallites sharing a common crystallographic orientation. In the present article, the influence of process parameters such as temperature profile and stirring on the primary and secondary size of ZnO mesocrystals synthesized under solvothermal conditions has been investigated. In general, small but noticeable lattice strain is introduced to the particles during the synthesis process. Additionally, with increasing mass transport the fusion of primary crystallites due to coarsening is enhanced. A closer analysis revealed an influence of the polymer chain length on the final particle structure throughout different hierarchical levels. Based on our findings a reaction mechanism with nucleation and growth taking place embedded in poly-N-vinylpyrrolidone (PVP), followed by a polymer-mediated step of oriented aggregation and subsequent coarsening is proposed. In consequence, the careful control throughout all hierarchical levels of particle synthesis allows fine-tuning of the optical properties of ZnO mesocrystals which show a high UV absorption and minimal scattering in the visible region. © 2012 The Royal Society of Chemistry.

Unified Design Strategies for Particulate Products - Peukert, Wolfgang; Segets, Doris; Pflug, Lukas; Leugering, Günter (Academic Press Inc., 2015)
Unit operations and product design are the two most important pillars of chemical engineering. Product design is the formation, formulation, handling, manufacturing, and characterization of complex multiphase products with specific properties and is thus at the core of mesoscale science and engineering. The applications define the required product properties which cover both classical fields of process technology in the chemical industry as well as new emerging fields of electronics, energy and environmental technologies, life sciences, materials science and engineering, nanotechnology, and photonic technologies highlighting the broad relevance of mesoscale science. Unifying principles of product design are proposed which are widely applicable to many different kinds of products including solid, liquid, and even gaseous particles. Results from the Erlangen Cluster of Excellence "Engineering of Advanced Materials" show that the joint venture of chemical engineering with materials science in concert with the basic sciences opens new prospects for all involved disciplines. In particular, chemical and biochemical engineering expands through particle technologies also in physics-related fields of technology such as electronics, photonics, or 3D printing. Rigorous mathematical optimization methods based on predictive models for products, structures, and processes catalyze new possibilities for true design of particulate products which is at the core of mesoscale science and technolog
Keywords: Bottom up; Hierarchical systems; Multiscale; Optimization; Product design; Structure formation; Top down; Unifying principles

Unraveling Complexity: A Strategy for the Characterization of Anisotropic Core Multishell Nanoparticles - Lin, Wei; Greve, Christoph; Härtner, Sebastian; Götz, Klaus; Walter, Johannes; Wu, Mingjian; Rechberger, Stefanie; Spiecker, Erdmann; Busch, Sebastian; Schmutzler, Tilo; Avadhut, Yamini; Hartmann, Martin; et al. (Particle & Particle Systems Characterization, 2020)
In this work, a widely applicable routine to characterize the core, surface, stability, and optical properties of CdSe/CdS/ZnS core–shell–shell nanorods after multiple growth steps is established. First, size, shape, and shell thickness of the nanorods are characterized by transmission electron microscopy (TEM), analytical ultracentrifugation (AUC), and small angle X-ray/neutron scattering (SAXS/SANS). In the next step, Fourier-transform infrared (FT-IR) spectroscopy, thermogravimetric analysis (TGA), and SANS measurements are applied to determine the surface species of nanorods. Then, the colloidal stability of the nanorods is investigated by UV–vis spectroscopy and dynamic light scattering (DLS) after different washing cycles. Finally, photoluminescence quantum yield (PLQY) of the nanorods during washing and sample storage is determined. With this highly complementary routine for particle characterization, the core, surface, stability, and optical properties of nanorods after multiple growth steps are resolved. The results demonstrate the importance of the developed toolbox to characterize such highly complex, anisotropic nanorods for a technical environment. This is of major importance for the handling of colloidal quantum materials and their quality control in industrial applications.
CRIS-Team Scopus Importer:2020-09-11
Keywords: anisotropic; characterization; core multishell; nanoparticles

Use of COSMO-RS for the prediction of adsorption equilibria - Peukert, Wolfgang; Mehler, Carsten; Klamt, Andreas (Aiche Journal, 2002)
The novel method COSMO-RS for the calculation of thermodynamic partition equilibria based on quantum chemical calculations is applied for the first time to the correlation and prediction of adsorption equilibria. In the limit of small adsorbate concentrations, very good predictions have been achieved for adsorption equilibria of activated carbon for both the phase and the aqueous phase.
UnivIS-Import:2015-03-09:Pub.2002.tech.ITC.mechve.useofc
Keywords: thermodynamic; simulation; equilibrium

Using carbon nanodots as inexpensive and environmentally friendly sensitizers in mesoscopic solar cells - Margraf, Johannes; Lodermeyer, Fabian; Strauß, Volker; Haines, Philipp; Walter, Johannes; Peukert, Wolfgang; Costa, Ruben Dario; Clark, Timothy; Guldi, Dirk Michael (Nanoscale Horizons, 2016)
We discuss the use of carbon nanodots (CNDs) as sensitizers in mesoscopic solar cells. The CNDs are synthesized using a one-step, bottom-up microwave approach with citric acid, urea, and formic acid as precursors in aqueous media. Their light-harvesting capabilities can be tuned by adjusting the synthetic parameters. Comprehensive spectroscopic and theoretical studies allow us to rationalize the nature of their absorption features. Promising power conversion efficiencies ( extgreekh) of 0.24% can be achieved from these cheap and eco-friendly sensitizers by optimizing the solar-cell assembly process. Interestingly, we found that extending the light absorption towards longer wavelengths does not necessarily improve the performance of the solar cells, since the longer-wavelength absorption features hardly contribute to the cells' photo-action spectra, so that the overall power conversion efficiency is actually worse. The origin of the lower performance is corroborated in transient absorption spectroscopy and photovoltage decay measurements. Our work points, on one hand, to the limits of as-synthesized CNDs as photosensitizers and, on the other hand, to possible improvements.

Versatile strategy for homogeneous drying patterns of dispersed particles - Rey, Marcel; Walter, Johannes; Harrer, Johannes; Perez, Carmen Morcillo; Chiera, Salvatore; Nair, Sharanya; Ickler, Maret; Fuchs, Alesa; Michaud, Mark; Uttinger, Maximilian; Schofield, Andrew B.; Thijssen, Job H. J.; et al. (Nature Communications, 2022)
After spilling coffee, a tell-tale stain is left by the drying droplet. This universal phenomenon, known as the coffee ring effect, is observed independent of the dispersed material. However, for many technological processes such as coating techniques and ink-jet printing a uniform particle deposition is required and the coffee ring effect is a major drawback. Here, we present a simple and versatile strategy to achieve homogeneous drying patterns using surface-modified particle dispersions. High-molecular weight surface-active polymers that physisorb onto the particle surfaces provide enhanced steric stabilization and prevent accumulation and pinning at the droplet edge. In addition, in the absence of free polymer in the dispersion, the surface modification strongly enhances the particle adsorption to the air/liquid interface, where they experience a thermal Marangoni backflow towards the apex of the drop, leading to uniform particle deposition after drying. The method is independent of particle shape and applicable to a variety of commercial pigment particles and different dispersion media, demonstrating the practicality of this work for everyday processes.
CRIS-Team WoS Importer:2022-06-10

Vibrational sum-frequency generation at protein modified air–water interfaces: Effects of molecular structure and surface charging - Engelhardt, Kathrin; Peukert, Wolfgang; Braunschweig, Björn (Current Opinion in Colloid & Interface Science, 2014)
Protein and surfactant modified air–water interfaces are an important model system for colloid science as many applications for example aqueous foams in food products rely on our knowledge and ability to tune molecular structures at these interfaces. That is because interfaces are a fundamental building block in the hierarchical structure of foam, where in fact the molecular level can determine properties on larger length scales. For that reason it is of great importance to increase our ability to study air–water interfaces with molecular level probes and to obtain not only information on coverage but also direct information on interfacial composition, molecular order, orientations as well as information on the charged state of an interface. Vibrational sum-frequency generation (SFG) is a powerful tool that can help to address these issues and is inherently surface sensitive. In this contribution we will review recent developments in the use of SFG for studies of biomolecules at aqueous interfaces and discuss current issues with the interpretation of SFG spectra from electrified interfaces. In order to guide interpretations from interface spectroscopy we invoke the use of complementary methods such as ellipsometry and zetapotential measurements of bulk molecules.
Keywords: Surfactants; Interface spectroscopy; Foam; Sum-frequency generation; Proteins

Well-separated water-soluble carbon dots via gradient chromatography - Michaud, Vanessa; Pracht, Jonas; Schilfarth, Fabian; Damm, Cornelia; Platzer, Benedikt; Haines, Philipp; Harreiß, Christina; Guldi, Dirk Michael; Spiecker, Erdmann; Peukert, Wolfgang (Nanoscale, 2021)
Carbon dots (CDs) are strongly fluorescent advanced materials that are promising for applications in bio-imaging, sensors or luminescent displays. One of the most-widely used class of CDs is synthesized via an aqueous, bottom-up technique starting from citric acid (CA) and an amino-precursor. Very high fluorescence quantum yields (QY) are reported for the resulting CDs. The as-synthesized raw suspensions, however, are crude mixtures of many components: bare carbon cores, carbon cores functionalized with fluorophores, freely floating molecular fluorophores, and several other by-products. In this study, we synthesized CDs from CA and amino acid cysteine (Cys) hydrothermally and demonstrate a complete separation of all components by means of two step gradient chromatography. In the first step, the separation was carried out on a normal-pressure preparative silica-gel column to get sufficient amounts of material to investigate structure and optical properties of the collected fractions. This preparative gradient elution method enabled us to separate moderately-fluorescent CDs from freely floating molecular fluorophores, polymeric fluorophores and CDs with built-in fluorophores. Here, we evidenced that amorphous CDs co-exist with crystalline CDs in one and the same suspension and showed that the amount of crystalline CDs increases with the synthesis temperature. In the second step, we turned to high performance liquid chromatography (HPLC) to further improve and optimize the efficiency of purification and automate it. Via HPLC, we were able to well-separate of up to six components. Within this work, we laid the foundation for CD purification with the highest possible purity for aqueous, bottom-up synthesized CDs and quantified the true quantum yield of CDs.
Keywords: Graphene quantum dots; Photoluminescence mechanism; Polymer dots; Citric-acid; Nanodots; Fluorescence; Yield; Nitrogen; Light; Reduction

Wet milling of H-ZSM-5 zeolite and its effects on direct oxidation of benzene to phenol - Gopalakrishnan, Saiprasath; Yada, S.; Münch, Jörg; Selvam, Thangaraj; Schwieger, Wilhelm; Sommer, Marc; Peukert, Wolfgang (Applied Catalysis A-General, 2007)
The direct oxidation of benzene to phenol with NO over ZSM-5 catalysts suffers from the problem of rapid catalyst deactivation mainly due to the secondary transformation of phenol into heavier hydrocarbon compounds leading to the catalyst coking. In order to investigate the deactivation behavior of the ZSM-5 catalysts during this reaction, a comparative study was performed over ZSM-5 catalysts having different crystal sizes. The original catalyst was milled to two different periods of time to obtain catalysts having various crystal sizes. The original and the milled catalysts were tested for the benzene to phenol reaction to get an insight into the effect of crystal size on the catalyst deactivation. There was a decrease in catalyst deactivation with a decrease in crystal size. An indirect dependence of catalyst deactivation with total acidity was observed. © 2007 Elsevier B.V. All rights reserved.
Keywords: Benzene oxidation; Crystal size; Microreactor; Nitrous oxide; Phenol; ZSM-5

Wet nanomilling of naproxen using a novel stabilization mechanism via zirconium complexation - Maar, Scott; Damm, Cornelia; Peukert, Wolfgang (Advanced Powder Technology, 2022)
Using a novel electrostatic stabilization mechanism that utilizes complexation of Zr(IV) species by carboxylic acid groups at the particle surface, the true grinding limit of monocrystalline naproxen nanoparticles was identified at 30 nm under an optimized naproxen/Zr(IV)-salt formulation. In a stirred media mill, we studied the influence of stress energy and number of stress events by varying the milling bead diameter. Small milling beads provide a compromise between sufficiently high stress energy and stress number and are beneficial for nanomilling of naproxen in terms of grinding kinetics. It is shown that the product particle size can be controlled by adjusting the colloidal stability via the Zr(IV) concentration. Regardless of formulation properties, particle fracture propagates along the grain boundaries as revealed by crystallite size analysis. Investigations of the solvent phase and the particle geometry reveal that mechanical stress leads to enhanced solubility of the drug, which in return promotes recrystallization and thus particle growth. The solubility can be reduced by lowering the process temperature and stabilizer concentration. In contrast to inorganic nanoparticles, which are almost free of lattice imperfections at the true grinding limit, we find a clear indication of lattice strain in the stressed naproxen nanoparticles. Since the nanoparticle yield is still limited to 40% due to particle ripening, fast removal of the nanoparticles from the mill must be a further next step to be solved in nanoparticle processing.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Colloidal stability; Grinding limit; Naproxen; Solubility; Stirred media ball mill

Wet nanomilling of naproxen using a novel stabilization mechanism via zirconium complexation - Maar, Scott; Damm, Cornelia; Peukert, Wolfgang (Advanced Powder Technology, 2022)
Using a novel electrostatic stabilization mechanism that utilizes complexation of Zr(IV) species by car-boxylic acid groups at the particle surface, the true grinding limit of monocrystalline naproxen nanopar-ticles was identified at 30 nm under an optimized naproxen/Zr(IV)-salt formulation. In a stirred media mill, we studied the influence of stress energy and number of stress events by varying the milling bead diameter. Small milling beads provide a compromise between sufficiently high stress energy and stress number and are beneficial for nanomilling of naproxen in terms of grinding kinetics. It is shown that the product particle size can be controlled by adjusting the colloidal stability via the Zr(IV) concentration. Regardless of formulation properties, particle fracture propagates along the grain boundaries as revealed by crystallite size analysis. Investigations of the solvent phase and the particle geometry reveal that mechanical stress leads to enhanced solubility of the drug, which in return promotes recrystallization and thus particle growth. The solubility can be reduced by lowering the process temperature and stabi-lizer concentration. In contrast to inorganic nanoparticles, which are almost free of lattice imperfections at the true grinding limit, we find a clear indication of lattice strain in the stressed naproxen nanoparti-cles. Since the nanoparticle yield is still limited to 40% due to particle ripening, fast removal of the nanoparticles from the mill must be a further next step to be solved in nanoparticle processing.
Keywords: Grinding limit; Colloidal stability; Stirred media ball mill; Solubility; Naproxen

Whey protein (amyloid)-aggregates in oil-water systems: The process-related comminution effect - Heyn, Timon R.; Uttinger, Maximilian; Kwade, Arno; Peukert, Wolfgang; Keppler, Julia K.; Schwarz, Karin (Journal of Food Engineering, 2021)
Whey protein fibrils are excellent emulsifiers. However, the emulsification process significantly alters the size of the aggregates and thus their functionality. It is not yet known how strongly the disperse phase (oil) contributes to the size change. Furthermore, it is unknown whether the aggregate morphologies (semi-flexible amyloid-, and flexible amyloid-like aggregates) differ in their size reduction during emulsification. Therefore, both types of aggregates were processed under different stress levels and in the presence and absence of an oil phase by rotor-stator dispersion, ultrasonication and high-pressure homogenisation. The size reduction exponent for each aggregate type was determined by atomic force microscopy, analytical ultracentrifugation and dynamic light scattering. Semi-flexible fibrils decreased in length by rotor-stator shear from 6200 to a minimum of 190 nm, but sonication resulted in even greater shortening (150 - 84 nm) and is comparable to high pressure homogenisation (283 - 111 nm). Worm-like flexible aggregates are only affected by sonication (98 - 46 nm). The addition of oil resulted in a further reduced aggregate length with lower energy input for all aggregates. Overall, these results provide new insights about the emulsion processing behaviour of different amyloid aggregates, which should be taken into account when preparing emulsions
Keywords: Length reduction; Processing; Emulsification; Fibrils; Rotor-stator shear; Beta-lactoglobulin; Amyloid aggregates

You get what you screen for: a benchmark analysis of leaf branch compost cutinase variants for polyethylene terephthalate (PET) degradation - Fritzsche, Stefanie; Tischer, Florentin; Peukert, Wolfgang; Castiglione, Kathrin (Reaction Chemistry & Engineering, 2023)
Enzymatic recycling of polyethylene terephthalate (PET) is an innovative and environmentally friendly way to promote a circular plastics economy and reduce the use of petroleum-based plastic monomers. Despite, or rather because of the large number of natural and engineered enzymes discovered in recent years, there are substantial difficulties in comparing PET degradation rates between studies. The present study therefore gathered knowledge about potential pitfalls and the question of how benchmarking for enzymatic PET degradation should be performed. Since there is no progress to establish a well-defined standard substrate as well as uniform reaction conditions for comparative studies of PET hydrolases, we propose to carry a well-characterized enzyme as a reference in all studies. In this way, variants of the leaf branch compost cutinase (LCC) were benchmarked in miniaturized stirred tank reactors. Different mutants with amino acid exchanges inspired by natural or engineered PET hydrolases were compared. The best enzyme resulted from a combination of mutations contained in the ICCG variant of the LCC and the so-called DuraPETase. The product release rate of the resulting variant ICCG(DAQI) was 27% higher than the reference enzyme ICCG. Although the relative performance of the different enzymes seemed to be independent of the PET material used (bottles, textile fibres), the absolute degradation rates were strongly influenced by the substrate properties. In particular, compared to bottle PET, post-industrial textile fibres were efficiently degraded releasing 40 mg terephthalic acid per hour and mg(enzyme), resulting in complete degradation within less than 24 hours.
CRIS-Team WoS Importer:2023-06-02

Zeolite-Coated Porous Arrays: A Novel Strategy for Enzyme Encapsulation - Marthala, Venkata; Friedrich, Mona; Zhou, Zhou; Distaso, Monica; Reuß, Stephanie; Al-Thabaiti, Shaeel A.; Peukert, Wolfgang; Schwieger, Wilhelm; Hartmann, Martin (Advanced Functional Materials, 2015)
Zeolite Beta-coated stainless steel supports with gradient porosity are employed as filter-panels for lipase encapsulation. Enzyme encapsulation on the stainless steel porous discs is achieved via vacuum infiltration. Subsequently, two lipase-encapsulated zeolite Beta-coated stainless steel discs are attached using an adhesive. The zeolite Beta layer on the stainless steel discs largely prevents lipase leaching in comparison to the stainless steel discs without a zeolite layer. The activity of the lipase-encapsulated, attached zeolite Beta-coated stainless steel porous discs depends on the thickness of the zeolite Beta layer. It is shown that the biocatalytic performance of the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈0.7–1 μm is better than the lipase-encapsulated, attached zeolite Beta-coated stainless steel supports with a zeolite Beta layer thickness of ≈2–3 μm in the lipase-catalyzed transesterification of vinyl propionate with 1-butanol using n-hexane as solvent.

ZnO superstructures via oriented aggregation initiated in a block copolymer melt - Klaumünzer, Martin; Distaso, Monica; Hübner, Jakob; Mackovic, Mirza; Spiecker, Erdmann; Kryschi, Carola; Peukert, Wolfgang (Crystengcomm, 2014)
A fast and simple one pot synthesis of ZnO nano- and microparticles initiated and driven by an amino block copolymer O,O′-bis(2-aminopropyl) polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol (Jeffamine®) is reported. The specific building mechanism of ZnO mesocrystals is investigated in detail using electron microscopy and diffraction methods. Mesocrystals with a complex superstructure are formed as a result of a consecutive and oriented multiple stage aggregation process: first a 0D → 1D aggregation process is observed, then a 1D → 3D aggregation process occurs in which secondary particles form cones and multiple cone symmetries. Dots, rods, cones, and multiple cones have been isolated within a time resolved study which clearly supports the growth model. To control the morphology of the product particles, the influence of relevant synthesis parameters including stirring and sonication of the intermediate were investigated. Extensive surface characterization of the resulting mesocrystals is presented using infrared and photoluminescence spectroscopies as well as thermogravimetric analysis. Even after multiple washing steps, the particles exhibit a Jeffamine® coated surface that allows for easy dispersion in both polar and nonpolar solvents. The obtained mesocrystals efficiently scatter in the whole range of visible light. © 2014 The Royal Society of Chemistry.